Health effects of late-career unemployment - Maren W Voss; Lori Wadsworth; Wendy Church Birmingham; Merryman, M. Beth; Crabtree, Lisa; Subasic, Kathy; Hung, Man (Journal of Aging and Health, 2020)
Objective: Job loss has a demonstrated negative impact on physical and mental health. Involuntary retirement has also been linked to poorer physical and mental health outcomes. This study examined whether late-career unemployment is related to involuntary retirement and health declines postretirement. Method: Analysis was conducted using the 2000-2012 U.S. Health and Retirement Study (HRS) survey data with unemployment months regressed with demographic and baseline health measures on physical and mental health. Results: Individuals with late-career unemployment reported more involuntary retirement timing (47.0%) compared with those reporting no unemployment (27.9%). Late-career unemployment had no significant effect on self-reported physical health (β =.003, p =.84), but was significantly associated with lower levels of mental health (β =.039; p <.01). Conclusion: Self-reports of late-career unemployment are not associated with physical health in retirement, but unemployment is associated with involuntary retirement timing and mental health declines in retirement. Unemployment late in the working career should be addressed as a public mental health concern.
Keywords: Job loss; Retirement Planning and Satisfaction; Unemployment

The Affordable Care Act as retiree health insurance: implications for retirement and Social Security claiming - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Journal of Pension Economics and Finance, 2019)
This paper investigates the effects of the Affordable Care Act (ACA) on retirement. The first part of the paper is a difference-in-difference analysis of changes in retirement (and retirement expectations) before and after adoption of the ACA. We find no statistically significant evidence that ACA increased the propensity to retire or changed retirement expectations. The second part of the analysis is based on a structural retirement model. For those age 50 at the time ACA was introduced, the overall reduction in full-time work over the age span 54–65 is simulated to be about 0.1 percentage points. Data are from the Health and Retirement Study.
Keywords: Affordable Care Act; Pensions; Policy; Retirement Planning and Satisfaction; Social Security

Asset Depletion, Chronic Financial Stress, and Mortgage Trouble Among Older Female Homeowners. - Amy Castro Baker; West, Stacia; Wood, Anna (Gerontologist, 2019)
Background and Objectives: The Great Recession disproportionately impacted older adults and women of color, suggesting that women may be entering retirement without adequate assets. However, the current literature lacks a detailed account of women's experiences of mortgage trouble and foreclosure, as well as a longitudinal view of how these experiences impacted their overall financial assets. Research Design and Methods: Grounded in cumulative inequality theory, this mixed methods study employed a QUAL→quan approach to gather qualitative data from a sample of 21 older adult women regarding their experiences of mortgage trouble. Quantitative longitudinal data was gathered for a subsample of the Early Baby Boomer Cohort using the Health and Retirement Study. Results: Qualitative findings indicated women approaching retirement experienced chronic underemployment, wage stagnation, and financial volatility as contributors to asset depletion and eventual mortgage default or foreclosure. Quantitative results indicated asset depletion both during and post-Recession was considerably more pronounced among older adult women of color compared to older adult White men. Discussion and Implications: These findings suggest that a lifetime of financial disadvantage coupled with macroeconomic instability situates older adult women, particularly women of color, in a financially vulnerable position for retirement. The ways in which 2017 attacks on the Consumer Financial Protection Bureau, Dodd-Frank, and the Fiduciary rule carry potential to further destabilize this population are also discussed.
Keywords: Chronic stress; Financial Health; Mortgages; Retirement Planning and Satisfaction; Wealth Inequality; Women and Minorities

Does the Health of Adult Child Caregivers Vary by Employment Status in the United States? - Noreen M Kohl; Krysia N Mossakowski; Ivan I Sanidad; Omar T. Bird; Lawrence H Nitz (Journal of Aging and Health, 2019)
OBJECTIVE: This study investigates whether the health effects of informal caregiving for aging parents vary by employment status in the United States. Two opposing hypotheses are tested: dual role strain and role enhancement. METHOD: Using national longitudinal data from the U.S. Health and Retirement Study, multivariate regression models predicted self-rated health and mental health among older adult children caregiving for their parents (2009-2012) and noncaregivers. RESULTS: A statistically significant interaction was found between caregiving duration and employment, indicating that employed caregivers had significantly worse health than retired caregivers. Caregiving duration also predicted significantly higher levels of depressive symptoms. DISCUSSION: Our results support the dual role strain hypothesis and suggest that caregiving for a parent up to 4 years is enough to predict significantly worse health among older adult Baby Boomers, especially those in the labor force. The broader implications for public health and workplace policies are discussed.
Keywords: Adult children; Caregiving; Employment and Labor Force; Retirement Planning and Satisfaction

Even ‘top earners’ still might not be prepared for retirement - Nova, Annie (CNBC, 2019)
Keywords: News; Retirement Planning and Satisfaction

From Snapshots to Movies: The Association Between Retirement Sequences and Aging Trajectories in Limitations to Perform Activities of Daily Living. - Azar, Ariel; Ursula M. Staudinger; Slachevsky, Andrea; Madero-Cabib, Ignacio; Calvo, Esteban (Journal of Aging and Health, 2019)
OBJECTIVE: This study analyzes the dynamic association between retirement sequences and activities of daily living (ADLs) trajectories between ages 60 and 70. METHOD: Retirement sequences previously established for 7,880 older Americans from the Health and Retirement Study were used in hierarchical linear and propensity score full matching models, analyzing their association with ADL trajectories. RESULTS: Sequences of partial retirement from full- or part-time jobs showed higher baseline and slower decline in ADL than sequences characterized by early labor force disengagement. DISCUSSION: The conventional model in which people completely retire from a full-time job at normative ages and the widely promoted new conventional model of late retirement are both associated with better functioning than early labor force disengagement. But unconventional models, where older adults keep partially engaged with the labor force are also significantly associated with better functioning. These findings call attention to more research on potential avenues to simultaneously promote productive engagement and health later in life.
Keywords: Activities of Daily Living; Disabilities; Policy; Retirement Planning and Satisfaction

Gender differences in the effect of social resources and social status on the retirement satisfaction and health of retirees. - Wang, Yihan; Matz-Costa, Christina (Journal of Gerontological Social Work, 2019)
This study explores the effect of positive and negative social support, social reciprocity, and subjective social status on the retirement satisfaction and health of retirees and gender differences therein. Using cross-sectional data from the 2010 and 2012 waves of the Health and Retirement Study (HRS), we found that social support seems to matter more for the retirement satisfaction and health of women, while social reciprocity matters more for the health of men and subjective social status for the retirement satisfaction of men. Implications for the development of social programs and policies over the life course are discussed.<
Keywords: Gender Differences; Retirement Planning and Satisfaction; Social Support

His and Her Retirement: Effects of Gender and Familial Caregiving Profiles on Retirement Timing. - Rachel R Stoiko; Strough, JoNell (International journal of aging & human development, 2019)
Objectives: Retirement timing has been linked to a host of outcomes for individuals, families, and societies. The present study predicted retirement timing using profiles of preretirement family caregiving and gender. Method: Using longitudinal data from the Health and Retirement Study, cluster analysis was used to create profiles of preretirement family caregiving (operationalized as time and financial transfers to aging parents and adult children). These profiles, as well as gender, were used to predict later retirement timing. Result:s Four distinct preretirement caregiving profiles were evident. All profiles retired, on average, earlier than their full eligibility for Social Security benefits. A main effect of caregiving profile, but not gender, was evident. The Eldercare profile, which was characterized by high levels of time and financial transfers to aging parents, retired the earliest. There was not a significant interaction between caregiving profile and gender. Discussion: When men enacted female-typical caregiving roles, their retirement timing resembled women's. Eldercare, in particular, was associated with earlier retirement timing. Implications for individual retirement decision-making and policy are discussed.
Keywords: Caregiving; Gender Differences; Retirement Planning and Satisfaction; Women and Minorities

How will retirement saving change by 2050? Prospects for the millennial generation - William G. Gale; Gelfond, Hilary; Fichtner, Jason (Brookings Working Paper Series, 2019)
In “How Will Retirement Saving Change by 2050? Prospects for the Millennial Generation” William G. Gale, Hilary Gelfond, and Jason Fichtner consider prospects for retirement saving for members of the millennial generation, who will be between ages 54 and 69 in 2050. Adequacy of retirement saving preparation among current and near-retirees is marked by significant heterogeneity, a characteristic that will likely hold for Millennials as well. In preparing for retirement, Millennials will have several advantages relative to previous generations, such as more education, longer working lives, and more flexible work arrangements, but also several disadvantages, including having to take more responsibility for their own retirement plans and marrying and bearing children at later ages. The millennial generation contains a significantly higher percentage of minorities than previous generations. The authors find that minority households have tended to accumulate less wealth than whites in the past, even after controlling for income, education, and marital status, and the difference appears to be growing over time for black households relative to whites. Whether these trends persist is central to understanding how the Millennials will fare in retirement.
Keywords: Future; Millenials; Public Policy; Retirement Planning and Satisfaction

Peak performance: Use early career wage gains to supercharge retirement savings - Weston, Liz (NerdWallet, 2019)
Keywords: Financial Health; News; Retirement Planning and Satisfaction

Pension plan heterogeneity and retirement behavior - Bairoliya, Neha (European Economic Review, 2019)
This paper examines the role of Social Security policy changes and the shift in pension plans — from annuity based retirement plans like Defined Benefit to account based plans like Defined Contribution — in explaining the recent increase in labor force participation of older workers. A structural retirement model of consumption, savings, Social Security, health insurance and pension plan heterogeneity is estimated using data from the Health and Retirement Study. The model captures key differences in pension wealth evolution across Defined Benefit and Defined Contribution pension plans and accounts for differences in out-of pocket medical spending across different health insurance groups. As a result, it produces variation in labor supply, both across different pension plan groups and health insurance types at older ages, as observed in the data. After controlling for any changes in the population age distribution and health insurance plans over time, model simulations indicate that changes in pension plan composition can explain 30.5 percent of the increase in labor force participation of the age group 65 to 69. Changes in Social Security normal retirement age and earnings test can each explain 19 and 45% of the increase in labor supply respectively for this age group.
Keywords: Employment and Labor Force; Pensions; Retirement Planning and Satisfaction; Social Security

Pension Plan Types and Financial Literacy in Later Life. - Li, Yang; Jeffrey A Burr; Edward Alan Miller (Gerontologist, 2019)
Background and Objectives: The ongoing shift from defined benefit (DB) to defined contribution (DC) pension plans means that middle-aged and older adults are increasingly being called upon to manage their own fiscal security in retirement. Yet, half of older Americans are financially illiterate, lacking the knowledge and skills to manage financial resources. This study investigates whether pension plan types are associated with varying levels of financial literacy among older Americans. Research Design and Methods: Cross-sectional analyses of the 2010 Health and Retirement Study (HRS) (n = 1,281) using logistic and linear regression models were employed to investigate the association between different pension plans and multiple indicators of financial literacy. The potential moderating effect of gender was also examined. Results: Respondents with DC plans, with or without additional DB plans, were more likely to correctly answer various financial literacy questions, in comparison with respondents with DB plans only. Men with both DC and DB plans scored significantly higher on the financial literacy index than women with both types of plans, relative to respondents with DB plans only. Discussion and Implications: Middle-aged and older adults, who are incentivized by participation in DC plans to manage financial resources and decide where to invest pension funds, tend to self-educate to improve financial knowledge and skills, thereby resulting in greater financial literacy. This finding suggests that traditional financial education programs may not be the only means of achieving financial literacy. Further consideration should be given to providing older adults with continued, long-term exposure to financial decision-making opportunities.
Keywords: Financial literacy; Pensions; Retirement Planning and Satisfaction

Personality and Saving Behavior Among Older Adults - Asebedo, Sarah D.; Wilmarth, Melissa J.; Martin C. Seay; Archuleta, Kristy; Brase, Gary L.; Maurice MacDonald (Journal of Consumer Affairs, 2019)
This study investigates how psychological characteristics influence saving behavior within a sample of 1,380 U.S. preretirees aged 50–70 from the Health and Retirement Study (HRS). Using the 3M Model of Motivation and Personality as a theoretical basis, structural equation model results revealed that financial self‐efficacy (FSE) directly explains saving behavior and is central to understanding the link between other psychological characteristics and the saving behavior of older adults. Through higher FSE, increased positive affect and reduced negative affect indirectly supported saving behavior. Moreover, the results revealed personality traits indirectly explained saving behavior. Conscientiousness and extroversion indirectly supported saving behavior; whereas openness to experience and neuroticism indirectly undermined saving behavior. This study connects broad personality traits with saving behavior, which provides information about how older adults' psychological composition is related to their saving practices.
Keywords: Finances; Personality; Retirement Planning and Satisfaction; Saving

Promoting middle-class retirement security: The importance of accounting for inequality in resources, burdens, and risks - Melissa Favreault (Budget Committee, United States of Representatives, 2019)
Keywords: Inequality; Retirement Planning and Satisfaction; Testimony

Retirees say, "We're doing okay." Experts refuse to listen. - Andrew G. Biggs (Forbes, 2019)
Keywords: Demographics; News; Retirement Planning and Satisfaction

Retirement choices by state and local public sector employees: The role of eligibility and financial incentives - Papke, Leslie E. (Journal of Pension Economics and Finance, 2019)
I analyze the effects of state public pension parameters on the retirement of public employees. Using a panel data set of public sector workers from 12 waves of the Health and Retirement Study, I model the probability of retirement as a function of pension wealth at early and normal retirement eligibility and Social Security coverage in the public sector job. I find that becoming eligible for early retirement, or receiving an early-out offer, significantly increases the probability of retiring. I do not find any effect of retirement wealth levels. These findings suggest that state legislative action to affect retirement decisions and reduce future pension costs would be most effective operating through plan eligibility rules and early-out incentives. © Cambridge University Press 2019.
Keywords: Finances; Public Health; Retirement Planning and Satisfaction

Retirement, Leisure Activity Engagement, and Cognition Among Older Adults in the United States. - Yura Lee; Lawrence A Palinkas (Journal of Aging and Health, 2019)
OBJECTIVE: Retirement is a salient later-life transition that may influence cognition. Leisure activities can help individuals better adjust to life after significant life transitions. This study examined the role of leisure activity engagement in the relationship between retirement and cognition. METHOD: A path analysis ( N = 2,827) was conducted using three waves of the Health and Retirement Study (2004, 2006, 2008) and its supplementary Consumption and Activities Mail Survey, to test the association between retirement (categorized as remained working, transitioned to retirement, remained retired) and cognition (memory, working memory, attention, and processing speed) via leisure (mental, physical, social, household) activity engagement. RESULTS: Older adults who remained retired showed significantly lower cognition than those who remained working. Moreover, this negative association between retirement and cognition was attenuated by greater engagement mental activities. DISCUSSION: Interventions that encourage mental activities among retired individuals are strongly suggested to help maintain cognitive function.
Keywords: Cognitive Ability; Leisure activities; Retirement Planning and Satisfaction

This job challenge should scare older workers - Kelli B. Grant (CNBC, 2019)
Keywords: Job loss; News; Retirement Planning and Satisfaction

Time discounting and economic decision-making in the older population - Huffman, David; Maurer, Raimond; Olivia S. Mitchell (The Journal of the Economics of Ageing, 2019)
This paper examines heterogeneity in time discounting among a representative sample of elderly Americans, as well as its role in explaining key economic behaviors at older ages. We show how older Americans evaluate simple (hypothetical) inter-temporal choices in which payments today are compared with payments in the future. Using the indicators derived from this measure, we then demonstrate that differences in discounting patterns are associated with characteristics of particular importance in elderly populations. For example, cognitive deficits are associated with greater impatience, whereas bequest motives are associated with less impatience. We then relate our discounting measure to key economic outcomes and find that impatience is associated with lower wealth, fewer investments in health, and less planning for end of life care.
Keywords: Decision making; Retirement Planning and Satisfaction; Self-control

Why everyone should save like they’re going to retire early - Hester, Tanja (MarketWatch, 2019)
Keywords: Future; Retirement Planning and Satisfaction; Savings

Why Working Till Whenever Is a Risky Retirement Strategy - Mark Miller (The New York Times, 2019)
Keywords: Health Shocks; Retirement Planning and Satisfaction; Wealth Shocks

Working to 70 is not an easy fix to the retirement crisis - Gail MarksJarvis (Reuters, 2019)
Keywords: News; Retirement Planning and Satisfaction

4 Big Benefits of a Roth IRA - Rita Williams (The Motley Fool, 2018)
Keywords: News; Retirement Planning and Satisfaction; Roth IRA

4 Reasons to Work Longer - Koenig, Rebecca (U.S. News and World Report, 2018)
Keywords: News; Retirement Planning and Satisfaction

Accounting for Social Security Claiming Behavior - Svetlana Pashchenko; Ponpoje Porapakkarm (Center for Retirement Research at Boston College Working Paper Series, 2018)
The paper examines why most individuals claim Social Security benefits before the full retirement age. Early claiming results in a substantial reduction in pension income, yet many people claim as early as possible, age 62, or soon thereafter. Since delaying claiming is equivalent to purchasing additional annuity income, this behavior is consistent with the so-called annuity puzzle. We provide a quantitative analysis of claiming decisions (or equivalently, of the demand for the Social Security annuity). Our tool is a structural lifecycle model calibrated to match many important features of the data.
Keywords: Annuitization; Decision making; Retirement Planning and Satisfaction; Social Security

Activities Matter: Personality and Resource Determinants of Activities and their Effect on Mental and Physical Well-being and Retirement Expectations - Beier, Margaret E.; Torres, W. Jackeline; Gilberto, Jacqueline M. (Work, Aging and Retirement, 2018)
Remaining active throughout the lifespan is central to healthy aging. The current study tests a model derived from investment and resource theories that examines the extent to which activities mediate the relationship between individual differences in personality and resources on mental and physical well-being and retirement expectations. A subsample (N = 400; 58% women) of participants from the nationally representative Health and Retirement Study (HRS) was used. Self-reported activities were grouped into 4 broad categories: productive, physical, social, and leisure. Activity variety, operationalized as the number of different activity categories in which a person reported participating over a specified period of time, was also examined. Correlations and path analysis results suggest small but significant effects between personality traits and activity participation, and more consistent effects of personality for predicting activity variety. Personality was also significantly correlated with well-being and retirement expectations as was activity variety. There was limited evidence, however, that activity variety mediated the relationship between personality and resources and mental and physical well-being and retirement expectations as would be predicted by investment theory.
Keywords: Activities of Daily Living; Health Conditions and Status; Personality; Psychosocial; Retirement Planning and Satisfaction; Well-being

Are retirees spending too little? - Eisenberg, Richard (#RetireWell, 2018)
Keywords: News; Op-ed; Retirement Planning and Satisfaction

The Associations between Falls, Fall Injuries and Labor Market Outcomes among U.S. Workers 65 Years and Older. - Kenneth A Scott; Gwenith G Fisher; Barón, Anna E; Tompa, Emile; Stallones, Lorann; DiGuiseppi, Carolyn (Journal of Occupational and Environmental Medicine, 2018)
OBJECTIVE: To examine whether falls are associated with the subsequent ability to work among workers 65 years and older. METHODS: This longitudinal cohort study followed older workers enrolled in the Health and Retirement Study. Outcomes included time to health-related work limitation and to labor force exit. RESULTS: After adjustment multiple falls with or without a medically-treated injury were associated with time to limitation (HR = 1.77, 95% CI: 1.30-2.40; HR = 1.48, 95% CI: 1.26-1.73, respectively). Adjustment mitigated a crude relationship between falls and time to exit. Significant interactions suggest the relationship between falls and labor force exit depends on age, race and job demands. CONCLUSIONS: Falls, both non-injurious and injurious, are associated with subsequent health-related work limitation among workers 65 and older. Fall prevention activities would benefit workers who want or need to keep working past age 65.
Keywords: Employment and Labor Force; Falls; Retirement Planning and Satisfaction

Is Bridge Job Activity Overstated? - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Work, Aging and Retirement, 2018)
Considerable prior research has shown that most older Americans with career employment transition to bridge jobs before exiting the labor force. One criticism of this research is that bridge job activity may be overstated because the definition of a bridge job in the existing literature does not require a change in occupation. For some, the "bridge job" may just be another in a series of job changes, and not a prelude to retirement. This article investigates the extent to which bridge jobs involve a change in occupation or a switch to part-time status, both of which may signal the start of a retirement transition, as opposed to continued career employment, albeit with a different employer. We utilize the Health and Retirement Study (HRS), a nationally representative longitudinal dataset of older Americans that began in 1992. Among HRS respondents who were on a full-time career job at the time of the first interview and who changed jobs in subsequent waves, 48% of the men and 39% of the women also changed their (two-digit) occupation at the time of their first transition. Further, when hours worked is also considered, about 3 quarters of men and women experienced a change in occupation and/or a switch from full-time to part-time status. We conclude that most career workers who changed jobs later in life did in fact do so as part of a retirement transition. Ignoring these subtleties does result in an overestimate of bridge job activity, but only a modest one.
Keywords: Bridge employment; Employment and Labor Force; Gender Differences; Retirement Planning and Satisfaction

The Changing Face of Debt and Financial Fragility at Older Ages - Annamaria Lusardi; Olivia S. Mitchell; Oggero, Noemi (AEA Papers and Proceedings, 2018)
We investigate changes in older individuals' financial fragility as they stand on the verge of retirement. Using data from the Health and Retirement Study (HRS), we compare how debt has changed for successive cohorts of people age 56-61. Our analysis shows that recent older Americans close to retirement hold more debt, and hence face greater financial insecurity, than earlier generations. This is primarily due to having bought more expensive homes with smaller down payments. We discuss possible policy implications.
Keywords: Debt; Finances; Financial security; Homeownership; Retirement Planning and Satisfaction

The co-development of perceived support and the Big Five in middle and older adulthood - Patrick L Hill; Sara J Weston (International Journal of Behavioral Development, 2018)
The current study examined whether relationships also influence personality trait development during middle and older adulthood, focusing on the individual's perception of support from the relationship partner. Using data from the Health and Retirement Study (n = 20,422; mean age = 65.9 years), we examined the longitudinal relationships between Big Five personality trait levels and perceived support from children, family, friends, and spouses. Results found that participants who reported more positive social support and lower negative support also tended to score higher on conscientiousness, extraversion, agreeableness, and openness to experience, but lower on neuroticism. Moreover, changes in positive support across relationship partners coincided with trait changes over time, in the form of more positive support was associated with seemingly adaptive changes on the Big Five. Findings are discussed with respect to identifying social influences on personality development in adulthood.
Keywords: Personality; Retirement Planning and Satisfaction; Self-reported health; Social Support

Cognitive Ability, Personality, and Pathways to Retirement: An Exploratory Study - Péter Hudomiet; Andrew M Parker; Susann Rohwedder (Work, Aging and Retirement, 2018)
This article describes an exploratory study that investigates the extent to which two sets of psychological factors, fluid cognitive ability and personality traits, predict late-in-life work and retirement outcomes. Using longitudinal data from the Health and Retirement Study, we first provide a detailed characterization of within-subject work-to-retirement pathways, spanning 14 years of data for each individual, and identify the most frequent pathway classes. We found that only 37% of workers followed the "standard" pattern of retiring completely from a full-time job. We then examined how cognitive ability and personality traits predict these work-to-retirement pathways. We found that individuals with better cognitive ability work longer, both in full- and in part-time jobs, and extraversion is a strong predictor of working longer, mainly in part-time jobs. These results are robust to the inclusion of many covariates, including demographics, health, socioeconomic status, and labor market variables. Although the observed patterns match individuals' retirement expectations to some extent, there also seems to be evidence of some surprise. Practical implications and suggestions for future research are discussed.
Keywords: Bridge employment; Cognition & Reasoning; Personality; Retirement Planning and Satisfaction

Column: For U.S. retirees, rising interest rates a double-edged sword - Mark Miller (Reuters, 2018)
Keywords: Finances; News; Retirement Planning and Satisfaction

A comparison of subjective and objective job demands and fit with personal resources as predictors of retirement timing in a national U.S. Sample - Amanda Sonnega; Helppie-McFall, Brooke; Péter Hudomiet; Robert J. Willis; Gwenith G Fisher (Work, Aging and Retirement, 2018)
Population aging and attendant pressures on public budgets have spurred considerable interest in understanding factors that influence retirement timing. A range of sociodemographic and economic characteristics predict both earlier and later retirement. Less is known about the role of job characteristics on the work choices of older workers. Researchers are increasingly using the subjective ratings of job characteristics available in the Health and Retirement Study in conjunction with more objective measures of job characteristics from the Occupational Information Network (O*NET) database. Employing a theoretically-informed model of job demands-personal resources fit, we constructed mismatch measures between resources and job demands (both subjectively and objectively assessed) in physical, emotional, and cognitive domains. When we matched comparable measures across the 2 data sources in the domains of physical, emotional, and cognitive job demands, we found that both sources of information held predictive power in relation to retirement timing. Physical and emotional but not cognitive mismatch were associated with earlier retirement. We discuss theoretical and practical implications of these findings and directions for future research.
Keywords: Comparisons; Job stressors; Retirement Planning and Satisfaction

Could an Early Retirement Help You Live Longer? - Maryalene LaPonsie (U.S. News & World Report, 2018)
Keywords: Depressive symptoms; Longevity; Optimism; Retirement Planning and Satisfaction

The Distribution of Time in Retirement: Evidence From the Health and Retirement Survey - Teresa Ghilarducci; Anthony Webb (Work, Aging and Retirement, 2018)
This is the first study to investigate the distribution of retirement time. We apply hot-deck imputation to Health and Retirement Study data to construct a synthetic sample of people who lived natural human life spans to measure their duration of time between withdrawing from the labor force and death. Men are more likely than women to die without retiring and Blacks and women with low educational attainment have shorter retirements and spend larger shares of their retirement time needing assistance with one or more activities of daily living (ADLs). We also find defined benefit pensions offset the negative impact of male low socioeconomic status how much time is spent in retirement needing assistance with ADLs impaired. Some groups with shorter than average life spans cannot entirely compensate by retiring early. In the United States, access to retirement time is unequally distributed and may become more unequal as pension wealth and longevity inequalities increase.
Keywords: Retirement Planning and Satisfaction; Time Use

Does retirement improve health and life satisfaction? - Gorry, Aspen; Gorry, Devon; Sita Nataraj Slavov (Health Economics, 2018)
We utilize panel data from the Health and Retirement Study to investigate the impact of retirement on physical and mental health, life satisfaction, and health care utilization. Because poor health can induce retirement, we instrument for retirement using eligibility for Social Security and employer-sponsored pensions and coverage by the Social Security earnings test. We find strong evidence that retirement improves reported health, mental health, and life satisfaction. In addition, we find evidence of improvements in functional limitations in the long run. Although the impact on life satisfaction occurs within the first 4 years of retirement, many of the improvements in health show up four or more years later, consistent with the view that health is a stock that evolves slowly. We find no evidence that the health improvements are driven by increased health care utilization. In fact, results suggest decreased utilization in some categories.
Keywords: Life Satisfaction; Optimism; Retirement Planning and Satisfaction

Economic downturns, retirement and long-term cognitive function among older Americans. - Hessel, Philipp; Carlos J Riumallo-Herl; Anja K Leist; Lisa F Berkman; Mauricio Avendano (Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 2018)
Objective: Workers approaching retirement may be particularly vulnerable to economic downturns. This study assesses whether exposure to economic downturns around retirement age leads to poorer cognitive function in later life. Method: Longitudinal data for 13,577 individuals in the Health and Retirement Study were linked to unemployment rates in state of residence. Random- and fixed-effect models were used to examine whether downturns at 55-64 years of age were associated with cognitive functioning levels and decline at ≥65 years, measured by the Wechsler Adult Intelligence Scale-Revised. Results: Longer exposure to downturns at 55-64 years of age was associated with lower levels of cognitive function at ≥65 years. Compared to individuals experiencing only up to 1 year in a downturn at 55-64 years of age, individuals experiencing two downturns at these ages had 0.09 point (95% Confidence Interval [CI, -0.17, -0.02]) lower cognitive functioning scores at ≥65 years (3 years: b = -0.17, 95%CI [-0.29, -0.06]; 4 years: b = -0.14, 95%CI [-0.25, -0.02]; ≥5 years: b = -0.22, 95%CI [-0.38, -0.06]). Downturns at 55-64 years of age were not associated with rates of cognitive decline. Discussion: Exposure to downturns around retirement is associated with a long-lasting decline in cognitive function in later life. Policies mitigating the impact of downturns on older workers may help to maintain cognitive function in later life.
Keywords: Cognitive Ability; Economic Downturn; Retirement Planning and Satisfaction

Effect of health on retirement of older Americans: a competing risks study - Basu Roy, Subhasree (Journal of Labor Research, 2018)
Keywords: Health Shocks; Retirement Planning and Satisfaction

Exploring the Consequences of Discrimination and Health for Retirement by Race and Ethnicity: Results from the Health and Retirement Study - Guillermo Ernest Gonzales; Lee, Yeonjung; Padula, William V.; Jung, Lindsey Subin (Center for Retirement Research at Boston College Working Paper Series, 2018)
This paper examines the association of structural discriminatory risk factors and health with retirement age. It uses data from the Health and Retirement Study (HRS). Critical components of the analysis include ordinary least squares regressions to evaluate associations of discrimination (major lifetime discrimination, neighborhood disadvantage, work discrimination and everyday discrimination) and health with retirement age, while controlling for time, cohort, race, ethnicity, gender, marital status, education, health insurance, income and wealth. Interaction effects explore differences by discrimination and health. Individuals’ ages 51+, employed full-time, part-time, or unemployed were drawn from the HRS Leave-Behind Questionnaire in 2006. Approximately half of the sample retired during the observation period 2008-2014. Key limitations are that valid and reliable measures of discrimination were queried only twice during an 8-year period, limiting our understanding of the timing of events as they relate to health and economic outcomes.
Keywords: Discrimination; Racial/ethnic differences; Retirement Planning and Satisfaction

Exploring the Rise of Mortgage Borrowing among Older Americans - Collins, J. Michael; Hembre, Erik; Urban, Carly (Center for Retirement Research at Boston College Working Paper Series, 2018)
This paper documents and examines the rise in mortgage usage among older Americans over the past 30 years. It uses data from a variety of sources including the Health and Retirement Study, Decennial Census, American Community Survey, Survey of Consumer Finances, and the American Housing Survey. We begin by documenting the large increase in mortgage usage among older Americans across age and income distributions. We then use regression analysis to test for causes of the mortgage increase and subgroup heterogeneity, in particular focusing on changing health, bequest motives, and tax policy incentives. This paper found that: Americans over age 60 are more than three times as likely to have mortgage debt in 2015 compared to 1980, a 24-percentage point increase. This is a consistent increase across the income distribution.Increases to homeownership account for some of the rise in mortgages, but this has increased by only 9 percentage points among Americans over age 60 between 1980 and 2015.Younger age groups have had much smaller increases, and sometimes decreases, in mortgage usage and homeownership over the same time period.Changes in household characteristics, such as education, urbanization, race, income, and marriage rates explain only a small portion of the increase in mortgage rates. Households with below-median assets, and those without pensions, account for a greater share of the rise in older households’ mortgage borrowing. Changes in subjective health and bequest motives explain little of the rise in mortgage rates. Variation in the mortgage interest deduction explains part of the differential increase in mortgage usage by age. The policy implications of the paper are: Policymakers should be aware that the beneficiaries of mortgage and homeownership subsidies, such as the mortgage interest deduction, have changed substantially over the past 30 years.Increased mortgage usage has coincided with less total debt among seniors relative to younger cohorts and has not resulted in increased delinquency. This may indicate that the negative aspects of increased mortgage usage are limited. Further investigation into the causes and consequences of mortgage usage is needed in considering appropriate policy responses.
Keywords: Financial Health; Homeownership; Mortgages; Retirement Planning and Satisfaction

The financial feasibility of delaying Social Security: evidence from administrative tax data - Gopi Shah Goda; Ramnath, Shanthi; John B. Shoven; Sita Nataraj Slavov (Journal of Pension Economics and Finance, 2018)
Despite the large and growing returns to deferring Social Security benefits, most individuals claim Social Security before the full retirement age. In this paper, we use a panel of administrative tax data on individuals likely to financially benefit from delaying Social Security claiming to explore the relationship between Social Security claiming and distributions from tax-advantaged retirement savings accounts. We find that the majority of our sample claim Social Security prior to taking distributions from Individual Retirement Accounts (IRAs). We also find that a third of our sample have IRA balances equivalent to at least two additional years of Social Security benefits, and a quarter have IRA balances equivalent to at least 4 years of Social Security benefits. We complement our analysis with data from the Health and Retirement Study and find that these percentages are considerably higher when other financial assets are taken into account. Copyright © Cambridge University Press 2017 This is a work of the U.S. Government and is not subject to copyright protection in the United States.
Keywords: Retirement Planning and Satisfaction; Social Security; Social Security linkage

Household Time Use Among Older Couples: Evidence and Implications for Labor Supply Parameters - Rogerson, Richard; Wallenius, Johanna (NBER Working Paper Series, 2018)
Using the Consumption Activities Mail Survey (CAMS) module in the HRS we document how time allocations change for individuals within a household when one or more members transitions from full time work to not working. Our basic finding is that the ratio of home production to leisure time is approximately constant for both family members. We then build a model of household labor supply to understand the implications of this finding for preferences and the home production function. We conclude that this fact suggests a relatively large elasticity of substitution between the leisure of the two members. For commonly used preference specifications, this also implies a large (i.e., greater than one) intertemporal elasticity of substitution for leisure.
Keywords: Couples; Employment and Labor Force; Retirement Planning and Satisfaction; Transitions

How much income do retirees actually have? Evaluating the evidence from five national datasets. - Anqi Chen; Alicia H. Munnell; Geoffrey T. Sanzenbacher (Center for Retirement Research at Boston College Working Paper Series, 2018)
Recent research by Bee and Mitchell (2017) has refocused attention on the fact that the Current Population Survey (CPS) underestimates retirement income. In the wake of this study, some observers have questioned whether other surveys more frequently used by retirement researchers also understate retirement income and, if so, whether prior research suggesting that many households are unprepared for retirement is accurate. This paper addresses both questions by examining retirement income data from the CPS and four other surveys: 1) the Survey of Consumer Finances (SCF); 2) the Health and Retirement Study (HRS); 3) the Panel Survey of Income Dynamics (PSID); and 4) the Survey of Income and Program Participation (SIPP). The paper compares the income measures from each survey to administrative data from tax and Social Security records, both in aggregate and across the income distribution. It then uses a common measure of retirement income adequacy, the replacement rate, to assess overall household preparedness for retirement.
Keywords: Finances; Income; Retirement Planning and Satisfaction

How Secure Is Employment at Older Ages? - Richard W. Johnson; Gosselin, Peter (Research Report, 2018)
Tracking older adults in the Health and Retirement Study from 1992 to 2016, we find that about one-half of full-time, full-year workers ages 51 to 54 experience an employer-related involuntary job separation after age 50 that substantially reduces earnings for years or leads to long-term unemployment. The steady earnings that many people count on in their 50s and 60s to build their retirement savings and ensure some financial security in later life often vanishes, upending retirement expectations and creating economic hardship. This problem will likely intensify as more people realize they must work longer to enjoy a comfortable retirement.
Keywords: Ageism; Discrimination; Employment and Labor Force; Retirement Planning and Satisfaction

How We Measured Involuntary Job Losses Among Older Workers - Gosselin, Peter (ProPublica, 2018)
Keywords: Ageism; Employment and Labor Force; Retirement Planning and Satisfaction; Survey Methodology

If You’re Over 50, Chances Are the Decision to Leave a Job Won’t be Yours - Gosselin, Peter (ProPublica, 2018)
Keywords: Ageism; Employment and Labor Force; News; Retirement Planning and Satisfaction

Impact of Divorce on Retirement Security - Hung, Angela; Knapp, David (Working Papers, 2018)
In this paper, we consider the implications of divorce on retirement security. We introduce a theory that highlights how specialization within a divorcing household and timing of divorce relative to planned timing of retirement savings can have a negative impact on retirement security. Using panel data from the Health and Retirement Study (HRS), we evaluate differences in accumulated total and liquid retirement wealth at retirement ages. We replicate past findings that find a negative relationship between ever-divorced individuals and asset accumulation, particularly for women. We find that the negative relationship in our sample between wealth and divorce without remarriage is worse for women who divorce in their 30s than for women who divorce in their 50s whereas for men the relationship is worse for men who divorce in their 50s compared to men who divorce in their 30s. Using the household nature of our data, we compare assets of households before a separation leading to a divorce to those of each individual after that separation. We find evidence of swapping and liquidation of retirement and housing assets: 51 percent of separating households with liquid pre-separation retirement assets will have at least one household member with zero liquid retirement assets after separation. Finally, we develop a methodology to evaluate whether near-retirement divorce impacts retirement decumulation. We conduct a differences-indifferences matching analysis that assigns individuals who eventually divorce within the HRS to similar, but non-divorcing, individuals at first interview. This analysis controls for observed differences between the average divorcee and the average continuously married person, as well as permanent unobserved differences. We find that separated women are more likely to delay Social Security retirement benefit claiming until age 65 or 66, but otherwise we find no significant evidence that divorce is associated with differential decumulation of liquid retirement assets.
Keywords: Divorce; Marriage; Retirement Planning and Satisfaction; Savings

In Debt and Approaching Retirement: Claim Social Security or Work Longer? - Barbara A Butrica; Nadia S. Karamcheva (AEA Papers and Proceedings, 2018)
Over the past couple of decades, older Americans have become considerably more leveraged. This paper considers whether household debt affects the timing of retirement and Social Security benefit claiming. Using data from the Health and Retirement Study, we find that older adults with debt are more likely to work and less likely to receive Social Security benefits than those who are debt-free. Indebted adults are also more likely to delay fully retiring from the labor force and claiming their benefits. Among the sources of debt, mortgages have a stronger impact on older adults' behavior than do other sources of debt.
Keywords: Debt; Retirement Planning and Satisfaction; Social Security

Jobs for the Heartland: Place-Based Policies in 21st Century America - Austin, Benjamin; Edward L Glaeser; Summers, Lawrence (NBER Working Paper Series, 2018)
The economic convergence of American regions has greatly slowed, and rates of long-term non-employment have even been diverging. Simultaneously, the rate of non-employment for working age men has nearly tripled over the last 50 years, generating a terrible social problem that is disproportionately centered in the eastern parts of the American heartland. Should more permanent economic divisions across space lead American economists to rethink their traditional skepticism about place-based policies? We document that increases in labor demand appear to have greater impacts on employment in areas where not working has been historically high, suggesting that subsidizing employment in such places could particularly reduce the not working rate. Pro-employment policies, such as a ramped up Earned Income Tax Credit, that are targeted towards regions with more elastic employment responses, however financed, could plausibly reduce suffering and materially improve economic performance.
Keywords: Economics; Employment and Labor Force; Retirement Planning and Satisfaction

Many Americans Try Retirement, Then Change Their Minds - Paula Span (The New York Times, 2018)
Keywords: Bridge employment; News; Purpose in life; Retirement Planning and Satisfaction

The Mental Health Benefits of Acquiring a Home in Older Age: A Fixed-Effects Analysis of Older Americans - Courtin, Emilie; Jennifer B Dowd; Mauricio Avendano (American Journal of Epidemiology, 2018)
Homeownership is consistently associated with better mental health, but whether becoming a homeowner in later in life has positive psychological benefits has not been examined. We assessed whether acquiring a home after 50 is associated with depression in a representative sample of older Americans. We used individual fixed-effects models based on data from 20,524 respondents aged ≥50 from the Health and Retirement Study and interviewed biannually between 1993 and 2010. Depressive symptoms were measured using the 8-item Centre for Epidemiologic Studies Depression scale. Controlling for confounders, becoming a homeowner in later life predicted a decline in depressive symptoms in the same year (β = -0.0768, 95% CI [confidence interval]: -0.152, -0.007). The association remained significant after two years (β = -0.0556, 95% CI: -0.134 to -0.001) but weakened afterwards. Buying a home for reasons associated with positive characteristics of the new house or neighborhood drove this association (β = -0.426, 95% CI: -0.786, -0.066), while acquiring a home for reasons associated with characteristics of the previous home or neighbourhood, the desire to be closer to relatives, downsizing or upsizing did not predict mental health improvements. Findings suggest that there are small but significant benefits for mental health associated with acquiring a home in older age.
Keywords: Consumption and Savings; Housing; Mental Health; Retirement Planning and Satisfaction

The minimum wage and incentives for full-time work under the Social Security retirement earnings test - Gary V. Engelhardt (Center for Retirement Research at Boston College Working Paper Series, 2018)
This paper examined how the earnings test affects the hours and employment of men who claim early benefits. It uses 1982-2016 data from the Current Population Survey and 1992-2014 data from the Health and Retirement Study. Critical components of the analysis include the idea that for any fixed earnings-test threshold amount, an increase in the hourly wage at which a beneficiary can work reduces the number of hours needed annually to hit the threshold. This feature of the test and substantial state-by-calendar year variation from increases in the minimum wage, which lower the threshold level of hours at which the earnings test binds, are used to identify the impact of the test on labor supply on the intensive and extensive margins for men who claim early.
Keywords: Gender Differences; Policy; Retirement Planning and Satisfaction; Social Security

The myth of outliving your retirement savings - Gail MarksJarvis (Reuters, 2018)
Keywords: Financial Health; Retirement Planning and Satisfaction

The Myth of Steady Retirement Spending, and Why Reality May Cost Less - Peter Finch (The New York Times, 2018)
Keywords: Finances; News; Retirement Planning and Satisfaction

A new model for interdependent durations - Bo E. Honoré; Áureo de Paula (Quantitative Economics, 2018)
This paper introduces a bivariate version of the generalized accelerated failure time model. It allows for simultaneity in the econometric sense that the two realized outcomes depend structurally on each other. Another feature of the proposed model is that it will generate equal durations with positive probability. Our approach takes a stylized economic model that leads to a univariate generalized accelerated failure time model as a starting point. In this model, agents decide when to transition from an initial state to a new one, and the covariates influence the difference in the utility flow in the two states. We introduce simultaneity by allowing the utility flow to depend on the status of the other person. The econometric model is then completed by assuming that the observed outcome is the Nash bargaining solution in that simple economic model. The advantage of this approach is that it includes independent realizations from the generalized accelerated failure time model as a special case, and deviations from this special case can be given an economic interpretation. We established identification under assumptions that are similar to those in the literature on nonparametric estimation of duration models. We illustrate the model by studying the joint retirement decisions in married couples using the Health and Retirement Study. In that example, it seems reasonable to allow for the possibility that each partner's optimal retirement time depends on the retirement time of the spouse. Moreover, the data suggest that the wife and the husband retire at the same time for a nonnegligible fraction of couples. The main empirical finding is that the simultaneity is economically important. In our preferred specification, the indirect utility associated with being retired increases by approximately 5% when one's spouse retires.
Keywords: Couples; Retirement Planning and Satisfaction

Now More Of Us Can Count On More Time Dodging The Dementia Bullet - Judith Graham (The Washington Post, 2018)
Keywords: Cognitive Ability; News; Retirement Planning and Satisfaction

Parental retirement timing: the role of unanticipated events in the lives of adult children - Miller, Marina; Tamborini, Christopher R.; Reznik, Gayle L. (Journal of Population Economics, 2018)
Although anecdotal evidence of older parents postponing retirement to financially support their grown children is common, the empirical evidence is scarce. In this paper, we use data from the 1992 to 2010 waves of the Health and Retirement Study to identify a broad set of pivotal events in the lives of adult children. First, we determine whether these events affect subsequent financial transfers from parents to children over multiple years. Next, we determine whether those events that result in subsequent transfers also shift parental retirement expectations. Finally, we quantify the impact of the unexpected children’s events on retirement realizations, moving beyond the correlational analyses in prior literature. Our findings show that a child’s move out of a parental home decreases both expectations and realizations of working after age 65. The magnitude of this effect is similar to that of an own health shock experienced during pre-retirement years.
Keywords: Adult children; Parents; Retirement Planning and Satisfaction; Wealth Shocks

Reconstructing retirement: Work and welfare in the UK and USA - Lain, David (Policy Press, 2018)
In the United Kingdom, retirement programs are being reconstructed to follow the American practice of abolishing mandatory retirement and increasing state pension ages. This timely book compares prospects for work and retirement at age sixty five-plus in both the United States and the United Kingdom. After exploring the shifting logic behind both nations’ policies—policies that increase both the need and opportunities to work past age sixty five—David Lain presents an original comparative statistical analysis on the wide range of factors influencing employment at this age, from the ability to move between jobs in order to remain employed to changing employment trends. He then proposes a series of policies to address these factors across the life-course and promote security and autonomy for older people. Pathways to employment after sixty five are complex, and pressures to work at this age are likely to result in very unequal outcomes. This book will play a vital role in creating a more positive, more equitable future for late careers and retirement.
Keywords: Bridge employment; Cross-National; Pensions; Retirement Planning and Satisfaction

Retirees can be too frugal with their spending - Vernon, Steve (CBS Moneywatch, 2018)
Keywords: Financial Health; Retirement Planning and Satisfaction; Spending

Retirement and depressive symptoms: A 10-year cross-lagged analysis. - Dikla Segel-Karpas; Liat Ayalon; Margie E Lachman (Psychiatry Research, 2018)
The effect of retirement on depressive symptoms remains a subject of scientific inquiry, given the fact that previous studies have found mixed results. Moreover, the possible effect of depressive symptoms on the propensity to retire remains relatively understudied. Given the sheer number of retirees, and the significance of depressive symptoms for individuals' well-being and ability to work, as well as for societies at large, we used a large longitudinal dataset to examine the reciprocal effects of retirement on depressive symptoms, and of depressive symptoms on the propensity to retire. Using six waves of the Health and Retirement Study (HRS) data collected over a period of 10 years (N = 6584), we tested cross-lagged models of the reciprocal relationships between retirement and depressive symptoms. The analysis revealed that retirement results in increased depressive symptoms, and that depressive symptoms increase the likelihood of retirement. No sex differences in the lagged associations were found. We conclude that depressive symptoms are a risk factor for retirement, and practitioners should try and identify older workers suffering from depression prior to the retirement transition. Similarly, as retirement increases depressive symptoms, the transition should be treated as an important and sometimes risky milestone, where adequate preparation is required.
Keywords: Depressive symptoms; Retirement Planning and Satisfaction

Retirement Reversals and Health Insurance - Joshua Congdon-Hohman (Public Finance Review, 2018)
This article uses the longitudinal aspect of the Health and Retirement Study to explore the characteristics associated with reversals in retirement (referred to here as “unretirement”). Through the use of survival-time analysis with time-variant covariates, this article shows that health insurance status and its source are significant predictors of unretirement decisions. The relationship is important, as the potential impacts of the Affordable Care Act (ACA) are considered. The analysis finds that insurance is equally as predictive of retirement reversals as other financial explanations such as pensions and wealth at retirement. The analysis also shows that health insurance sources play a particularly predictive role for early retirees and those who were previously open to the idea of working in retirement. Rough estimates suggest that the ACA might reduce the number of reversals by between two and four percentage points, which would translate to 80,000 and 170,000 retirees annually.
Keywords: Medicare/Medicaid/Health Insurance; Policy; Retirement Planning and Satisfaction

Retirement sequences of older Americans: Moderately destandardized and highly stratified across gender, class, and race. - Calvo, Esteban; Madero-Cabib, Ignacio; Ursula M. Staudinger (Gerontologist, 2018)
Purpose of the Study: A destandardization of labor-force patterns revolving around retirement has been observed in recent literature. It is unclear, however, to which degree and of which kind. This study looked at sequences rather than individual statuses or transitions and argued that differentiating older Americans' retirement sequences by type, order, and timing and considering gender, class, and race differences yields a less destandardized picture. Design and Methods: Sequence analysis was employed to analyze panel data from the Health and Retirement Study (HRS) for 7,881 individuals observed 6 consecutive times between ages 60-61 and 70-71. Results: As expected, types of retirement sequences were identified that cannot be subsumed under the conventional model of complete retirement from full-time employment around age 65. However, these retirement sequences were not entirely destandardized, as some irreversibility and age-grading persisted. Further, the degree of destandardization varied along gender, class, and race. Unconventional sequences were archetypal for middle-level educated individuals and Blacks. Also, sequences for women and individuals with lower education showed more unemployment and part-time jobs, and less age-grading. Implications: A sequence-analytic approach that models group differences uncovers misjudgments about the degree of destandardization of retirement sequences. When a continuous process is represented as individual transitions, the overall pattern of retirement sequences gets lost and appears destandardized. These patterns get further complicated by differences in social structures by gender, class, and race in ways that seem to reproduce advantages that men, more highly educated individuals, and Whites enjoy in numerous areas over the life course.
Keywords: Gender Differences; Racial/ethnic differences; Retirement Planning and Satisfaction; Women and Minorities

The Return to Work and Women’s Employment Decisions - Nicole Maestas (NBER Working Paper Series, 2018)
It is well documented that individuals in couples tend to retire around the same time. But because women tend to marry older men, this means many married women retire at younger ages than their husbands. This fact is somewhat at odds with lifecycle theory that suggests women might otherwise retire at later ages than men because they have longer life expectancies, and often have had shorter careers on account of childrearing. As a result, the opportunity cost of retirement-in terms of foregone potential earnings and accruals to Social Security wealth-may be larger for married women than for their husbands. Using the Health and Retirement Study (HRS), I find evidence that the returns to additional work beyond mid-life are greater for married women than for married men. The potential gain in Social Security wealth alone is enough to place married women on nearly equal footing with married men in terms of Social Security wealth at age 70.
Keywords: Bridge employment; Employment and Labor Force; Retirement Planning and Satisfaction; Women and Minorities

The role of health in retirement - Alan L Gustman; Thomas L. Steinmeier (Emerald Publishing Limited, 2018)
A dynamic model of the evolution of health for those over the age of 50 is embedded in a structural, econometric model of retirement and saving. Effects of smoking, obesity, alcohol consumption, depression, and other proclivities on medical conditions are analyzed, including hypertension, diabetes, cancer, lung disease, heart problems, stroke, psychiatric problems, and arthritis. Compared to a population in good health, the current health of the population reduces retirement age by about one year. Including detailed health dynamics in a retirement model does not influence estimates of the marginal effects of economic incentives on retirement.
Keywords: Health Conditions and Status; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Rosy assumptions on retirement timing invite rude financial surprise - Mark Miller (Reuters, 2018)
Keywords: Finances; News; Retirement Planning and Satisfaction

Spending Patterns in Retirement: Retirees are Slow to Exhaust their Assets (Fast Facts, 2018)
The analysis examines spending patterns of retirees with low pre-retirement non-housing assets (less than $200,000), moderate pre-retirement non-housing assets (between $200,000 and $500,000), and substantial preretirement non-housing assets (at least $500,000).
Keywords: Retirement Planning and Satisfaction; Spending; Wealth management

There's More Than One Way To Retire - Coombes, Andrea (Forbes, 2018)
Keywords: News; Personality; Retirement Planning and Satisfaction

Too poor to retire? Housing prices and retirement - Zhao, Bo (Review of Economic Dynamics, 2018)
The near-retirement households among all working-age groups in the United States experienced larger drops in consumption and greater increases in labor force participation during the financial crisis of 2007–2009. Also, the retirement probability for near-retirement homeowners (but not for renters) decreases more in those areas where housing prices also decline more. This paper argues that the wealth effect of housing prices on retirement can account for those issues. It creates an incomplete-market life-cycle partial-equilibrium model with risky housing assets and endogenous retirement and verifies that the joint response of retirement and non-durable consumption implied by the structural model is consistent with the empirical findings using data from the Health and Retirement Study 1992–2012. It then shows that, after an unexpected 28 percent housing price decline, near-retirement homeowners ages 55–64 will reduce their non-durable consumption by 4.6 percent and increase their labor force participation by 1 percentage point immediately and delay their retirement by 2.8 months in the long run. The model also quantifies endogenous retirement as self-insurance for elderly homeowners against housing price risk.
Keywords: Housing; Retirement Planning and Satisfaction; Socioeconomic factors

Transitions From Career Employment Among Public- and Private-Sector Workers - Joseph F. Quinn; Kevin E. Cahill; Michael D. Giandrea (NBER Working Paper Series, 2018)
Do the retirement patterns of public-sector workers differ from those in the private sector? Most private-sector workers today face a do-it-yourself retirement income landscape characterized by an exposure to market forces through defined-contribution pension plans and private saving, and the risk of financial insecurity later in life. Public-sector workers, in contrast, are typically covered by defined-benefit pension plans that both encourage retirement at relatively young ages and offer financial security at older ages. As a result, the consequences of private- and public-sector workers’ retirement decisions could differ in important ways. For workers generally, and for private-sector workers in particular, a focus among researchers and policymakers has been the importance of continued work later in life for improving financial security at older ages. Such concerns might be of less consequence for public-sector workers due to the prevalence of defined-benefit pensions. Public-sector workers’ departures from the labor force might also differ from those in the private sector, all else equal, because of the age-specific incentives within their defined-benefit plans. Despite these important differences, the private-public distinction has received relatively little attention in the retirement literature. Our paper examines how private- and public-sector workers transition from career employment to complete labor force withdrawal, with a focus on the role of bridge employment, phased retirement, and re-entry. We identify the prevalence and determinants of each pathway to retirement using longitudinal data on four cohorts of private- and public-sector career older workers from the Health and Retirement Study (HRS). Our findings suggest that the prevalence of work after leaving career employment among public-sector workers resembles that of private-sector workers, although with a higher prevalence of part-time bridge employment, a result that has important implications for public policy as the pace of societal aging accelerates.
Keywords: Employment and Labor Force; Private vs public sector; Retirement Planning and Satisfaction

Why do 37% of older workers retire earlier than planned? - Alicia H. Munnell (Marketwatch, 2018)
Keywords: Employment and Labor Force; News; Retirement Planning and Satisfaction

Why is retirement often more costly for married women than for married men? - Hicks, Maureen Soyars (Monthly Labor Review, 2018)
Keywords: Gender Differences; Marriage; Retirement Planning and Satisfaction

Why Women Should Keep Working After Their Husbands Retire - Leubsdorf, Ben (The Wall Street Journal, 2018)
Keywords: News; Retirement Planning and Satisfaction; Women and Minorities

Would Greater Awareness of Social Security Survivor Benefits Affect Claiming Decisions? - Belbase, Anek; Quinby, Laura D. (Center for Retirement Research at Boston College Working Paper Series, 2018)
Most Americans enter retirement as married couples, and one spouse, typically the wife, outlives the other. Many widows lack the income needed to maintain the standard of living they had when their husbands were alive. Widows would generally have more adequate incomes if their husbands, who are typically the higher earner in the couple, delayed claiming Social Security. This project uses the Health and Retirement Study (HRS) to test the extent to which husbands consider their wives’ well-being as widows when making claiming decisions. It then uses an online experiment to determine whether raising a husband’s awareness of the risks that his widow faces, and how delayed claiming can reduce those risks, affect his claiming behavior.
Keywords: Bereavement; Retirement Planning and Satisfaction; Social Security

Yes, it's true: Older people depend on Social Security - Alicia H. Munnell (Marketwatch, 2018)
Keywords: News; Retirement Planning and Satisfaction; Social Security

Access to Long-Term Care After a Wealth Shock: Evidence from the Housing Bubble and Burst - Costa-Font, Joan; Richard G Frank; Swartz, Katherine (NBER Working Paper Series, 2017)
Home equity is the primary self-funding mechanism for long term services and supports (LTSS). Using data from the relevant waves of the Health and Retirement Study (1996-2010), we exploit the exogenous variation in the form of wealth shocks resulting from the value of housing assets, to examine the effect of wealth on use of home health, unpaid help and nursing home care by older adults. We find a significant increase in the use of paid home health care and unpaid informal care but no effect on nursing home care access. We conduct a placebo test on individuals who do not own property; their use of LTSS was not affected by the housing wealth changes. The findings suggest that a wealth shock exerts a positive and significant effect on the uptake of home health and some effect on unpaid care but no significant effect on nursing home care.
Keywords: Long-term Care; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction; Wealth Shocks

Accounting for the process of disablement and longitudinal outcomes among the near elderly and elderly - Rupp, Kalman; Irena Dushi (Research on Aging, 2017)
Using a new disability measure applicable to both the near elderly and elderly population, we track respondents aged 51–61 in 1992 from the Health and Retirement Study and account for their status over 20 years. We demonstrate that to screen in as disabled and to screen out as nondisabled require different analytic strategies and use multiple indicators to establish three groups: disabled, nondisabled, and a residual category with ambiguous status. We use work-disability and Supplemental Security Income/Disability Insurance (SSI/DI) receipt for testing distributional outcomes and assessing face validity of our disability measure. Selective attrition due to death and institutionalization is substantial over 20 years. Persistent disability is the dominant adverse outcome of initial disability shock. Overtime exits due to death become progressively more important; 44% disabled at baseline are dead by Wave 11 compared to 21% for nondisabled. Disability status at baseline is associated with financial insecurity persisting to Wave 11 among survivors. © 2016, © The Author(s) 2016.
Keywords: Disabilities; Financial security; Longitudinal data; Older Adults; Retirement Planning and Satisfaction

Baby boomers in the United States: Factors associated with working longer and delaying retirement. - Xiuwen S Dong; Wang, Xuanwen; Ringen, Knut; Sokas, Rosemary (American Journal of Industrial Medicine, 2017)
OBJECTIVES: This study estimated the self-reported probability of working full-time past age 62 (P62) or age 65 (P65) among four cohorts of Americans born between 1931 and 1959. METHODS: Data from the Health and Retirement Study (HRS) were analyzed. Respondents in four age cohorts were selected for comparison. Multivariable linear regression models were used to assess cohort differences in P62 and P65 while adjusting for covariates. RESULTS: P62 and P65 increased among boomers despite worsened self-rated health compared to the two preceding cohorts, with 37% and 80% increases among mid-boomers in construction trades. Cohort differences in P62 and P65 remained after controlling for covariates. Changes in pensions, income inequity, and education were significantly associated with work expectations, but SSA policy was not. CONCLUSIONS: Baby boomers expect to work longer than their predecessors. Efforts to improve work quality and availability for older workers are urgently needed, particularly in physically demanding occupations. Am. J. Ind. Med. 60:315-328, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: Baby Boomers; Delaying retirement; Health Conditions and Status; Older Adults; Retirement Planning and Satisfaction

The best investment for retirement? Try marital counseling and a home miles away from your kids - Ian McGugan (The Globe and Mail, 2017)
Keywords: Counseling; Investing; Marriage; News; Older Adults; Retirement Planning and Satisfaction

Beyond the individual: The interdependence of advance directive completion by older married adults. - Catheryn S Koss (Journal of the American Geriatric Society, 2017)
OBJECTIVES: To determine how individual and spousal demographic and health factors are associated with advance directive (AD) completion by married older adults. DESIGN: Dyadic structural equation modeling using the Actor-Partner Interdependence Model. SETTING: The 2004 to 2012 waves of the Health and Retirement Study. PARTICIPANTS: Community-dwelling heterosexual married couples aged 65 and older (N = 2,243). MEASUREMENTS: Structural equation modeling with a probit link function was used to estimate associations between men's and women's age, education, health status, prior hospitalization or outpatient surgery in the past 10 years, regular health care provider, and household net assets and their own and their spouses' probabilities of having an AD. RESULTS: Individual and spousal ages were each positively associated with AD completion for men and women. Those with higher education were more likely to possess ADs. Women's probabilities of having ADs were also positively associated with husbands' education. Men whose wives' were in poor health were less likely to have ADs. Men who were hospitalized or underwent outpatient surgery were more likely to have ADs, as were their wives. Women who had regular sources of health care were more likely to have completed ADs. CONCLUSION: AD completion by older married adults is associated with both individual and spousal factors. How spouses influence one another's advance care planning differs by gender. Future research should account for the dyadic nature of advance care planning, as should public education efforts and interventions promoting AD completion.
Keywords: Advance directives; Retirement Planning and Satisfaction

Characteristics of Second-career Occupations: A Review and Synthesis - McFall, Brooke Helppie; Amanda Sonnega (Michigan Retirement Research Center Working Papers, 2017)
This study is a literature review of research related to the characteristics of second careers undertaken after mid-life. There is a significant lack of literature directly on this topic, so we draw substantially from the literatures about retirement, bridge jobs, encore jobs, and unretirement. First, we provide a working definition of second careers after mid-life. We then provide a brief background of the existing theoretical research related to this topic, which is also in need of updating and synthesis. We find evidence that second careers may already be common, but likely are undertaken by less than half of older workers. For older workers in general, job flexibility and lower stress seem to be particularly prized job characteristics that they seem willing to trade off against earnings, benefits, and prestige. However, individual fit is also likely to be particularly important in learning about second careers. We also find useful information in studies of specific early-retiring occupations and destination second careers. Based on the existing general, late-life labor supply literature and specific occupation literature, we propose new directions for research. An important take-away is that data limitations have been a roadblock; however, forthcoming resources may help open up this area of research.
Keywords: Bridge employment; Employment and Labor Force; Retirement Planning and Satisfaction

Cognitive decline: The importance of awareness and advance planning - Renee Kwok; Daniel Kern (Journal of Financial Planning, 2017)
For an aging population, cognitive decline is an unnerving challenge on numerous levels. Expected longevity has jumped more than 10% since 2000, according to the Society of Actuaries. The average 65-year-old man can be expected to live into his mid-80s, one-fourth live past age 90, and 10% live past 95. The average 65-year-old-woman has an even longer life expectancy. Affluent individuals have actuarial life expectancies beyond the averages and often have complex financial considerations requiring high levels of cognitive function. Although increased life spans bring great benefits, the potential for cognitive decline is an important consideration for financial advisers. Dementia is defined as the loss of cognitive and mental functions severe enough to impair a person's daily functioning, and estimates indicate that nearly 15% of Americans over age 70 suffer from some form of dementia. Cognitive decline can jeopardize hard-earned financial security at a time in which clear-headed decision-making may be most important.
Keywords: Cognitive Ability; Retirement Planning and Satisfaction

Cohort Differences in Joint Retirement: Evidence from the Health and Retirement Study - Bhatt, Vipul (Journal of Labor Research, 2017)
The dramatic rise and sustained participation of recent cohorts of women in the labor force has coincided with their increased attachment to the labor market. In this paper we use twelve waves of the Health and Retirement Study (1992-2014) and investigate how married couples belonging to more recent birth cohorts compare with their predecessors in terms of coordinating their retirement decisions. Using a multinomial logit model we estimate the labor force dynamics of dual-earner married couples and find that couples with wives belonging to more recent birth cohorts are less likely to jointly exit the labor force. Further, this declining cohort trend in joint retirement can only partially be explained by commonly observed socio-economic, employment, and health related factors that affect retirement decisions, suggesting an important role for cohort changes in preferences and social norms such as preference for work and attitudes toward gender roles.
Keywords: Couples; Gender Differences; Retirement Planning and Satisfaction; Women and Minorities

Consumption behavior, annuity income and mortality risk of retirees - Kutlu-Koc, Vesile; Alessie, Rob J.M.; Kalwij, Adriaan ((Netherlands) Economist, 2017)
Previous empirical studies have found that individuals do not draw down their assets after retirement which is at odds with the predictions of a simple life cycle model without uncertainty. Hurd (Econometrica 57(4):779–813, 1989; Mortality risk and consumption by couples, 1999) explains such saving behavior of retired singles and couples by adding lifetime uncertainty to the simple life cycle model. We tested whether predictions about consumption during retirement of this extended life cycle model hold for a sample of older Americans. We used data from the Health and Retirement Study supplemented with data from the Consumption and Activities Mail Survey. In line with theory we found that, on average, total consumption is greater than their annuity income after retirement and that this difference increases with the level of initial wealth. For older singles but not for couples our results suggest that, as predicted by the extended theoretical model of Hurd, the on average negative consumption growth decreases with higher mortality rates.
Keywords: Annuitization; Consumption and Savings; Mortality; Retirement Planning and Satisfaction

Debt and Financial Vulnerability on the Verge of Retirement - Annamaria Lusardi; Olivia S. Mitchell; Oggero, Noemi (NBER Working Paper Series, 2017)
We analyze older individuals’ debt and financial vulnerability using data from the Health and Retirement Study (HRS) and the National Financial Capability Study (NFCS). Specifically, in the HRS we examine three different cohorts (individuals age 56-61) in 1992, 2004, and 2010 to evaluate cross-cohort changes in debt over time. We also use two waves of the NFCS (2012 and 2015) to gain additional insights into debt management and older individuals’ capacity to shield themselves against shocks. We show that recent cohorts have taken on more debt and face more financial insecurity, mostly due to having purchased more expensive homes with smaller down payments.
Keywords: Consumption and Savings; Debt; Retirement Planning and Satisfaction

Diabetes and labor market exits: Evidence from the Health & Retirement Study (HRS) - Chatterji, Pinka; Heesoo Joo; Kajal Chatterji Lahiri (The Journal of the Economics of Ageing, 2017)
The objective of this paper is to estimate the effect of diabetes on labor market exit using longitudinal data from the 1992-2010 Health and Retirement Study (HRS). We estimate a discrete time hazard model to test whether diabetes affects the hazard of leaving employment among individuals who were working for pay at the age of 55-56. Using a probit model, we also estimate the effect of having undiagnosed or poorly controlled diabetes on the probability of labor market exit two years later. Our results indicate that diabetes is associated with an increased hazard of exiting the labor market for males, but not for females. This effect for males persists when we include controls for onset of other health conditions, two of which are documented complications of diabetes (stroke and heart conditions). We also find that diagnosed diabetes with medication use, regardless of whether or not it is under control, is associated with large negative effects on the likelihood of employment two years later. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Chronic disease; Diabetes; Employment and Labor Force; Retirement Planning and Satisfaction

Drawing down retirement wealth: Interactions between Social Security wealth and private retirement savings - Philip Armour; Hung, Angela (Working Paper Series, 2017)
Keywords: Consumption and Savings; Retirement Planning and Satisfaction; Social Security

The effects of leisure-time physical activity for optimism, life satisfaction, psychological well-being, and positive affect among older adults with loneliness - Kim, Junhyoung; Lee, Sunwoo; Sanghee Chun; Areum Han; Jinmoo Heo (Annals of Leisure Research, 2017)
The purpose of this study was to examine the effects of leisure-time physical activity (LTPA) involvement among older adults suffering from loneliness. Using data released from the Health and Retirement Study in 2008, this study investigated how participation in LTPA leads to well-being such as optimism, life satisfaction, psychological well-being, and positive affect among older adults with loneliness. Results indicated that the LTPA involvement was a significant predictor of optimism, life satisfaction, positive affect, and psychological well-being for older adults with a high level of loneliness. The interesting findings of this study were that LTPA enhanced positive emotions for older adults with loneliness and that positive emotions are one of the important factors in protecting individuals from illnesses.
Keywords: Optimism; Retirement Planning and Satisfaction; Well-being

Effects of Pre-Retirement Personality, Health and Job Lock on Post-Retirement Subjective Well-being. - Lindsay H Ryan; Nicky J Newton; Preet K. Chauhan; William J. Chopik (Translational Issues in Psychological Science, 2017)
Retirement can be difficult, and experiences vary greatly. Although health, financial status, and family responsibilities have been associated with retirement adjustment, individual psychosocial characteristics may also play a role. Moreover, relatively little is known about the impact of perceived 'job lock'-the belief that retirement is impossible due to financial or health constraints-and its relationship with later retirement adjustment. The current study addresses these limitations in the literature by examining the retirement transition over four years in a large sample of U.S. adults, with a particular focus on the ways in which personality may affect this transition. Data collected at baseline (2008/2010) and again four years later (2012/2014) included the Big Five personality traits, pre-retirement job lock, self-rated health, and multiple indicators of post-retirement well-being, such as global and experienced well-being (anchored within activities in a single day). Participants were drawn from the Health and Retirement Study (= 716;= 61.9 at baseline). Results indicated that experienced positive affect was the only post-retirement well-being outcome with a significant association with job lock, although only for those with low conscientiousness. Findings also suggest that pre-retirement personality and subjective health play an important role for post-retirement well-being. Thus, the current study highlights the importance for researchers and practitioners to consider both pre-retirement personality and health when evaluating individuals' management of the retirement transition.
Keywords: Health Conditions and Status; Personality; Positive beliefs; Retirement Planning and Satisfaction; Self-reported health; Well-being

Effects of working part-time and full-time on physical and mental health in old age - Tunga Kantarcı (NETSPAR Academic Series, 2017)
An increasing number of studies are analyzing the effect of retirement on health. When analyzing the effect of retirement against work activity, these studies do not distinguish between part-time and full-time work activity. We study how the amount of work hours affects the health conditions in old age. To avoid the potential bias that deteriorating health can cause employees to work fewer hours, retirement eligibility ages are used as instruments for part-time or full-time work decisions. We find that self-perceived health, self-rated memory and body mass index respond to working part-time much more than they respond to working full-time. This suggests that the effect of the number of hours worked on health in old age is not linear.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Examining bridge employment from a self-employment perspective—evidence from the Health and Retirement Study - von Bonsdorff, Monika E.; Zhan, Yujie; Song, Yifan; Wang, Mo (Work, Aging and Retirement, 2017)
This study examines bridge employment decision-making from a self-employment perspective using 3 prominent retirement theories, the life course perspective, continuity theory and role theory. Focusing on self-employment extends the current theoretical understanding of bridge employment and offers interesting implications for retirement policy-making. Specifically, using longitudinal data from the Health and Retirement Study (n = 2,080), we conducted multinomial regression analysis to examine who were more/less likely to fully retire, enter bridge employment in the wage-and-salary form, or enter bridge employment in the self-employment form. Furthermore, we examined the role of pre-retirement self-employment status, to provide us with more information on the very much understudied retirement process of entrepreneurs and self-employed workforce. Our findings indicated that self-employment can be considered as an independent form of bridge employment, apart from bridge employment in wage-and-salary jobs. Furthermore, the decision to enter different forms of bridge employment, including self-employment, may stem from a variety of antecedents. Practical implications of this study are also discussed.
Keywords: Bridge employment; Retirement Planning and Satisfaction; Self-employment

Harvard researchers say this mental shift will help you live a longer, healthier life - Zameena Mejia (CNBC, 2017)
Keywords: Depressive symptoms; News; Optimism; Purpose in life; Retirement Planning and Satisfaction

Health and Retirement Study: A Longitudinal Data Resource for Psychologists - Amanda Sonnega; Jacqui Smith (Encyclopedia of Geropsychology, 2017)
This encyclopedia brings together key established and emerging research findings in geropsychology. It is a comprehensive coverage of the entire breadth of the field, giving readers access to all major subareas and illustrating their interconnections with other disciplines. Entries delve deep into key areas of geropsychology such as perception, cognition, clinical, organizational, health, social, experimental and neuropsychology. In addition to that, the encyclopedia covers related disciplines such as neuroscience, social science, population health, public policy issues pertaining to retirement, epidemiology and demography and medicine. Paying careful attention to research internationally, it cites English and non-English empirical literature from around the globe. This encyclopedia is relevant to a wide audience that include researchers, clinicians, students, policy makers and nongovernmental agencies.
Keywords: Psychosocial; Retirement Planning and Satisfaction; Well-being

Health, Health Insurance, and Retirement: A Survey - Eric French; John Bailey Jones (Working Paper Series, 2017)
The degree to which retirement decisions are driven by health is a key concern for both academics and policymakers. In this paper we survey the economic literature on the health-retirement link in developed countries. We describe the mechanisms through which health affects labor supply and discuss how they interact with public pensions and public health insurance. The historical evidence suggests that health is not the primary source of variation in retirement across countries and over time. Furthermore, declining health with age can only explain a small share of the decline in employment near retirement age. Health considerations nonetheless play an important role, especially in explaining cross-sectional variation in employment and other outcomes within countries. We review the mechanisms through which health affects retirement and discuss recent empirical analyses.
Keywords: Disabilities; Health Conditions and Status; Medicare/Medicaid/Health Insurance; Older Adults; Retirement Planning and Satisfaction

Health Of Americans Who Must Work Longer To Reach Social Security Retirement Age - Choi, Hwajung; Robert F. Schoeni (Health Affairs, 2017)
To receive full Social Security benefits, Americans born after 1937 must claim those benefits at an older age than earlier birth cohorts. Additionally, proposals to improve the fiscal position of Social Security typically include increasing the age at which workers can receive full benefits. Birth cohorts required to work longer are in worse health at ages 49–60, based on multiple measures of morbidity, than cohorts who could retire earlier.
Keywords: Retirement Planning and Satisfaction; Social Security; Working Longer

Health Status, Health Shocks, and Asset Adequacy Over Retirement Years. - Geoffrey L Wallace; Haveman, Robert; Barbara Wolfe (Research on Aging, 2017)
This article uses data on a sample of retirees drawn from the Health and Retirement Study (HRS) to examine changes in health over the retirement years and to estimate the effects of health changes in retirement on wealth. Using the framework of item response theory, we develop a novel measure of health that makes use of multiple indicators of physical health that are available in the HRS. We find that large negative shocks to the health of male retirees and their spouses are frequent in retirement and that when such shocks do occur, recovery to the preshock level of health is rare. Using a dynamic panel data model, we then estimate short- and long-run effects of changes in health on wealth. While our estimated short-run effects are modest, long-run estimates of the impact of health shocks on wealth are large, ranging from a 12% to 20% reduction in wealth by the 10th year, following a permanent one standard deviation decrease in health.
Keywords: Health Conditions and Status; Health Shocks; Older Adults; Retirement Planning and Satisfaction

His way, her way: Retirement timing among dual-earner couples - Jonathan Jackson (Advances in Life Course Research, 2017)
This article examines how the retirement timing of husbands and wives has evolved in the face of women's rising economic resources. Using 11 waves of data from the Health and Retirement Study, I trace individuals into retirement, examining how spousal employment characteristics may facilitate or hinder one's own ability to retire and if such spousal influences have changed across cohorts. Results from event history models indicate that the retirement trajectories have changed for the leading baby boom cohort, as evidence implies they are delaying retirement longer than previous cohorts. Despite women's rising labor force attachment, the findings do not generally support the notion that wives are influencing their husbands' retirement timing more or that the influence of husbands on wives' retirement timing has declined across cohorts.
Keywords: Employment and Labor Force; Gender Differences; Marriage; Retirement Planning and Satisfaction

Hispanics' retirement transitions and differences by nativity. - Mudrazija, Stipica; Richard W. Johnson; Wang, Claire Xiaozhi (Journal of Aging and Health, 2017)
OBJECTIVE: This study examines differences in retirement decisions between older Hispanics and non-Hispanics, with a special focus on the role of nativity. METHODS: We use 1998-2012 waves of the Health and Retirement Study. We estimate survival models of retirement and compare retirement transitions for U.S.-born Hispanics, foreign-born Hispanics, non-Hispanic Whites, and non-Hispanic Blacks. RESULTS: Foreign-born Hispanics retire significantly later than other racial and ethnic groups. Controlling for personal characteristics, their risk of retirement is 39% lower compared with non-Hispanic Whites. Retirement transitions do not differ significantly between U.S.-born Hispanics and non-Hispanic Whites. DISCUSSION: Difference in retirement timing between U.S.- and foreign-born Hispanics may partly be due to lower incomes and wealth accumulation of foreign-born Hispanics. Workforce development initiatives, policy initiatives promoting retirement savings, and Social Security reforms could improve future retirement security for older Hispanics, and make retirement a viable option for more foreign-born Hispanics.
Keywords: Hispanics; Racial/ethnic differences; Retirement Planning and Satisfaction

Homeownership, Social Insurance, and Old-Age Security in the United States and Europe - Mudrazija, Stipica; Barbara A Butrica (Working Papers, 2017)
Relatively few Americans have accumulated substantial savings outside of their employer-sponsored retirement plans, yet most own their homes. The traditional view of the retirement income system as a three-legged stool supported by Social Security, private pensions, and savings may be better viewed as being supported by Social Security, pensions, and homeownership. Country-specific economic, social, and political developments throughout modern history mean that homeownership rates and the relative importance of homeownership for old-age security vary widely across developed countries. Many countries, however, are increasingly promoting homeownership as an effective way of building assets, a de facto self-insurance mechanism for old-age security, and a substitute for various social transfers. This paper uses data from the Health and Retirement Study (HRS) in the United States and the Survey of Health, Ageing, and Retirement in Europe (SHARE) to better understand the role of homeownership in retirement before and after the Great Recession for the United States and nine Western European countries: Austria, Belgium, Denmark, France, Germany, Italy, the Netherlands, Spain, and Sweden. It begins by comparing trends in homeownership rates among older adults and the key characteristics of housing-related policies and regulations that potentially impact home acquisition. It then examines home equity trends, the prevalence and burden of housing debt, and the relative importance of housing as a source of retirement wealth. Next it provides an overview of equity release options and estimates how much older households could increase their incomes by fully monetizing their housing equity. Finally, the paper discusses the prospects for and limits of home equity release and asset-based welfare policies. The paper found that: Most older adults are homeowners, and homeownership rates generally increased between 2006 and 2012; however, there is substantial variation across countries.Housing-related policies in the Netherlands, Sweden, and Denmark provide comparatively high levels of support to both homeowners and non-homeowners, while those in Italy and Spain provide little support to either group. In contrast, housing policies in the United States provide some of the highest levels of support for homeowners and lowest levels of support for non-homeowners.Older American homeowners have substantial housing wealth, but compared with their European peers, housing represents a somewhat smaller part of their net total wealth.While the prevalence of housing debt among older adults is somewhat lower in the United States than in the Netherlands, Denmark, and Sweden, among older homeowners with housing debt, Americans have the highest loan-to-value ratios and the highest proportion of homeowners whose homes may be at risk of going underwater.If the housing equity of older Americans were completely monetized, median household income would increase by over a third – more than in countries like Sweden and Denmark, but well below countries like Spain and Italy. Across all countries in this study, tapping into housing equity could substantially reduce the share of older adults with household incomes below 50 percent of the median – the threshold for relative poverty.However, even after annuitizing housing wealth, the share of poor older Americans would remain as high as, or higher than, the share of poor older Europeans before accounting for annuitized housing wealth.Despite the potentially large impact of monetizing home equity on household incomes and the economic security of older Americans and Europeans, there remain impediments to tapping into home equity that may explain its low use. Objective obstacles include the high costs of withdrawing housing equity, uncertainty about life expectancy and the amount of financial resources required to support retirement, the adverse impact on eligibility for social benefits, and the concentration of housing wealth among (upper) middle- and higher-income individuals who are less likely to need additional resources in old age. Subjective obstacles include an aversion toward assuming additional debt in old age, different (often emotional) attitudes to housing compared with other types of wealth, bequest motives, and a lack of trust in financial institutions. The policy implications of the findings are: Home equity has a potentially important yet limited role in supporting old-age security. Even if objective obstacles related to the design and pricing of home equity release products were fully addressed, subjective reasons for avoiding home equity withdrawal and compositional differences in the concentration of housing wealth would still limit the scope of asset-based welfare.These limitations notwithstanding, using home equity to supplement retirement incomes and improve retirement security remains a potentially attractive option for a substantial number of older adults who have built housing wealth over their life course, but may either have insufficient retirement incomes or face unexpected and expensive life events (e.g. long-term care needs).What remains more uncertain and difficult to predict, though, are the long-run prospects for using home equity to support old-age security since younger generations of Americans and Europeans may find it more difficult to build home equity than their parents’ generation.
Keywords: Debt; Europe; Homeownership; Retirement Planning and Satisfaction; SHARE

Household Retirement Saving: The Location of Savings Between Spouses - Carman, Katherine; Hung, Angela (RAND Corporation, 2017)
Retirement planning is often a joint household decision-making process, and therefore the household is often the more appropriate unit of analysis. However, retirement savings in tax advantaged accounts are held in the name of one individual. While spouses have rights to these assets in the case of divorce and in most cases of death, the separation of accounts in name may cause couples to treat their accounts as separate, with each spouse making decisions separately. In order to optimize retirement planning, couples should consider the entire household portfolio together, accounting for the characteristics of the retirement accounts, the age of the spouses, and income differences between spouses. With separate accounts, one spouse may not be aware of the contributions or assets accumulated in the other spouse's accounts. This may lead to sub-optimal decision-making, as individuals in a couple may not fully optimize across all available retirement accounts. Little is known about how households divide retirement contributions and assets between spouses. In this project, we investigate how households locate contributions across tax deferred savings accounts that are nominally held in one spouse's name and how these decisions may impact accumulated assets. In particular we first document who within a couple nominally holds retirement assets. Using data from the Health and Retirement Study and Survey of Consumer Finances, we find that household retirement assets and contributions are more likely to be located in accounts held in the husband's name or the primary earner's name. In our regression analysis, we find that the location of contributions is largely driven by the distribution of earnings within couples.
Keywords: Consumption and Savings; Marriage; Retirement Planning and Satisfaction

Housing, Mortgages, and Retirement - Mayer, Christopher (2017)
Keywords: Housing; Retirement Planning and Satisfaction

How Couples Approach Portfolio Allocation - Fessenden, Helen; Lazaryan, Nika; Neelakantan, Urvi (Federal Reserve Bank of Richmond, 2017)
The classical theory of household portfolio allocation finds that the share of household wealth invested in risky assets is independent of the level of household wealth. However, this prediction is at odds with empirical observations. This Economic Brief presents findings that reconcile the two. A model in which a household's portfolio allocation reflects the preferences of both spouses, adjusted for the bargaining power of each spouse, predicts that the wealthier a household becomes, the greater the share of its wealth will be invested in risky assets.
Keywords: Decision making; Marriage; Older Adults; Retirement Planning and Satisfaction; Risk Aversion

How Debt Is Threatening Retirement Dreams (Forbes, 2017)
Keywords: Debt; News; Retirement Planning and Satisfaction; Socioeconomic factors

How the growing gap in life expectancy may affect retirement benefits and reforms - Auerbach, Alan; Kerwin K. Charles; Courtney Coile; William G. Gale; Dana P Goldman; Lee, Ronald; Lucas, Charles; Orszag, Peter R.; Sheiner, Louise; Tysinger, Bryan; Weil, David; Wolfers, Justin; et al. (The Geneva Papers on Risk and Insurance - Issues and Practice, 2017)
Keywords: Life Expectancy; Mortality; Retirement Planning and Satisfaction; Social Security

The impact of health and education on future labour force participation among individuals aged 55–74 in the United States of America: the MacArthur Foundation Research Network on an Aging Society - David Rehkopf; Nancy E Adler; John W Rowe (Ageing and Society, 2017)
Chronic disease, mobility limitations and low physical functioning are determinants of an earlier age of retirement. Therefore, long-term population trends in these factors may have an impact on the proportion of individuals near traditional retirement age who continue to work. Our objective is to develop a projection model that accounts for trends in these factors in order to estimate the proportion of the population aged 55–74 with the capacity to participate in the labour force. We used logistic regression models to quantify how chronic disease, mobility and functional status predict labour force participation among individuals aged 55–59. Next, we obtained estimates of the population prevalence of each of these predictors for the years 2010–2050. We then used estimated coefficients from the logistic regression models to predict the age-specific probability of capacity for work up to the age of 74. We find that population capacity for work depends on trends in disability and on level of education. Future population capacity for work depends on trends in functional limitations primarily in the population with lower levels of education. Changes in functional limitations, changes in the environment, technology and social policy targeted towards individuals with lower levels of education could result in mitigation of future decreasing capacity for work in the population near retirement age.
Keywords: Education; Employment and Labor Force; Population Health; Retirement Planning and Satisfaction

The Impact of Retirement on Health Behaviours - Larlee, Caroline (Department of Economics, 2017)
The objective of the analysis is to identify the causal effects of being retired for at least one year on health behaviours. To estimate the effect of retirement, biannual data from the 2004 to 2014 Health and Retirement Study (HRS) is used. The endogeneity of retirement is acknowledged in our model by using an instrumental variable approach with the social security eligibility ages of 62 and 65 as instruments. Additionally, the longitudinal nature of the data gives us the ability to estimate an individual Fixed Effect (FE) model to control for unobservable time-invariant individual heterogeneity. The retirement parameter estimates of the FE-2SLS model show that being retired for at least one year is associated with a 26 percentage point increase in the likelihood of meeting the physical activity guidelines and a 17 percentage point increase in the likelihood of getting a flu shot, but a 9 percentage point decrease in the likelihood of getting a cholesterol blood test. Thus retirement is associated with some improvement in health behaviours.
Keywords: Health Behavior; Health Conditions and Status; Retirement Planning and Satisfaction

Improving the system of financing long-term services and supports for older Americans - Mark J. Warshawsky; Marchand, Ross A. (The Journal of Retirement, 2017)
Medicaid currently pays for most of the long-term services and supports (LTSS) provided older Americans. With an aging population, these costs will increase rapidly. Contrary to a widely held view, current Medicaid eligibility rules allow covered households to own significant housing and retirement assets. The authors present new information about the weak efforts of states in asset recovery and discuss the extensive asset holdings, especially in housing and retirement assets, of retired households. Given that Medicaid crowds out the purchase of private long-term care insurance, liberal eligibility rules and uneven enforcement must increase the costs of governments and discourage better-off households from covering LTSS exposure through private insurance and assets. They conclude with targeted recommendations to reform Medicaid and improve the LTSS financing system, following up on proposals made by certain members of the 2013 federal Commission on Long-Term Care.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Incentivizing older people to delay social security claiming - Maurer, Raimond; Olivia S. Mitchell (SAFE Policy Letter Series, 2017)
Given rising life expectations around the world, it seems that old-age pension benefits will need to be cut and pension contributions boosted in many nations. Yet our research on old-age system reforms does not require raising mandatory retirement ages or contributions. Instead, we offer ways to enhance incentives for people to work longer and delay retirement. There are good reasons to incentivize older people to work longer and delay retirement. These include rising longevity, the shrinking workforce, and emerging evidence indicating that working longer can be associated with better mental and physical health for many people. Nevertheless, old age Social Security systems in many nations find that people tend to claim benefits early, usually leading to reduced benefits.In the United States, for instance, a majority of Americans claim their Social Security benefits at the earlier feasible age, namely 62, even though their monthly benefits would be 75% higher if they waited until age 70. To test whether this is the result of people underweighting the economic value of higher lifetime benefit streams, we examine whether people would claim later and work longer if they were rewarded with a lump sum instead of a higher lifetime benefit stream for deferring. Two arguments have been offered to explain early claiming. One is that workers claim early to avoid potentially “forfeiting” their deferred benefits should they die too soon (Brown et al., 2016). A second explanation is that many people underweight the economic value of lifetime benefit streams (Brown et al., 2017). This latter rationale motivates the present study.
Keywords: Retirement Planning and Satisfaction; Social Security

Intertemporal Poverty among Older Americans - Bayaz Ozturk, Gulgun; Macdonald, Sean P. (Journal of Poverty, 2017)
This study uses aggregate intertemporal poverty indices proposed by Gradin, Del Rio, and Canto (2012) to measure poverty among older American households of different races from 2001 through 2009 employing data from the Health and Retirement Study. The findings indicate that the incidence of intertemporal poverty is higher among Black and Hispanic households and that it is also more intense and of longer duration. In our investigation of anti-poverty effects of the Supplemental Nutrition Assistance Program, we find that the program has a significant impact in reducing intensity and inequality of poverty among poor populations. However, it does not significantly alter the incidence of intertemporal poverty.
Keywords: Finances; Poverty; Racial/ethnic differences; Retirement Planning and Satisfaction

Late Career Job Loss and Retirement Behavior of Couples - Lee, Ajin (Research on Aging, 2017)
This article argues that wealth uncertainty influences when couples choose to retire. Using data from the Health and Retirement Study, I show that wives delay retirement when their husbands retire following a job loss. This effect is stronger when husbands are the primary earners, and couples are relatively poorer. This provides evidence of intra-household insurance that mitigates the impact of an unexpected earnings shock. I find that wives tend to delay retirement only until they become eligible for social security. This suggests that social security benefits can relax households’ budget constraints and allow wives to join their husbands in retirement
Keywords: Couples; Employment and Labor Force; Job loss; Marriage; Older Adults; Retirement Planning and Satisfaction

Later-life employment trajectories and health - McDonough, Peggy; Worts, Diana; Corna, Laurie M.; McMunn, Anne; Sacker, Amanda (Advances in Life Course Research, 2017)
Background: Despite the recent policy push to keep older adults in the labour force, we know almost nothing about the potential health consequences of working longer. Drawing on a life course approach that considers stability and change in employment patterns, this study examines the relationship between long-term labour market involvement in later life and self-rated health. Methods: Our data are from the Health and Retirement Study (1992-2012) for the cohort born 1931-1941 (N = 6522). We used optimal matching analysis to map employment trajectories from ages 52-69, and then logistic regression to examine associations between these trajectories and self-rated health in the early 70s, net of socio-demographics, household resources and prior health. Findings: Women prevail in groups characterized by a weak(er) attachment to the labour market and men, in groups signifying a strong(er) attachment. Men who downshifted from full-time to part-time work around age 65 were the least likely to report poor health in their early 70s.Women had the best health if they remained employed, either full-time or part-time. However, unlike men, they appeared to benefit most in health terms when part-time hours were part of a longer-term pattern. Conclusion: While our study findings show that continuing to work in later life may be positively associated with health, they also suggest the need for flexible employment policies that foster opportunities to work part-time.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Longitudinal Determinants of End-of-Life Wealth Inequality - James M. Poterba; Steven F Venti; David A Wise (NBER Working Paper Series, 2017)
This paper examines inequality in end-of-life wealth and the factors that contribute to individuals reaching this life stage with few financial resources. It analyzes repeated cross-sections of the Health and Retirement Study, as well as a small longitudinal sample of individuals observed both at age 65 and shortly before death. Most of those who die with little wealth had little wealth at retirement. There is strong persistence over time in the bottom tail of the wealth distribution, but the probability of having low wealth increases slowly with age after age 65. Those with low lifetime earnings are much more likely to report low wealth at retirement, and to die with little wealth, than their higher-earning contemporaries. The onset of a major medical condition and the loss of a spouse increase in the probability of falling into the low wealth category at advanced ages, although these factors appear to contribute to wealth decline for only a small fraction of those who had modest wealth at age 65 but low wealth at the time of death.
Keywords: Income inequality; Inequality; Retirement Planning and Satisfaction

Mental retirement and health selection: Analyses from the U.S. Health and Retirement Study. - Sean A. P. Clouston; Denier, Nicole (Social Science & Medicine, 2017)
BACKGROUND: Research has recently suggested that retirement may decrease cognitive engagement, resulting in cognitive aging. Few studies have systematically documented whether or how selectivity into retirement shapes the relationship between retirement and cognitive aging. METHODS: We draw on data from the Health and Retirement Study (1998-2012) to examine the relationship between cognition and retirement for 18,575 labor force participants. Longitudinal regression discontinuity modeling was used to examine performance and decline in episodic memory. Models differentiated three forms of selection bias: indirect and direct selection as well as reverse causation. To further interrogate the disuse hypothesis, we adjust for confounding from health and socioeconomic sources. RESULTS: Results revealed that individuals who retired over the course of the panel were substantially different in terms of health, wealth and cognition when compared to those who remained employed. However, accounting for observed selection biases, significant associations were found linking longer retirement with more rapid cognitive decline. DISCUSSION: This study examined respondents who were in the labor force at baseline and transitioned into retirement. Analyses suggested that those who retired over the course of the panel had worse overall functioning, but also experienced more rapid declines after retirement that increased the rate of aging by two-fold, resulting in yearly losses of 3.7% (95% CI = [3.5, 4.0]) of one standard deviation in functioning attributable to retirement. Results are supportive of the view that retirement is associated with more rapid cognitive aging.
Keywords: Cognitive Ability; Memory; Older Adults; Retirement Planning and Satisfaction

More Women in Their 60s and 70s Are Having ‘Way Too Much Fun’ to Retire - Claire Cain Miller (The New York Times, 2017)
Keywords: News; Older Adults; Retirement Planning and Satisfaction; Women and Minorities

The Most Amazing Retirement Chart You'll Ever See - Brian Stoffel (The Motley Fool, 2017)
Keywords: Happiness; Retirement Planning and Satisfaction

Multiple Chronic Conditions, Resilience, and Workforce Transitions in Later Life: A Socio-Ecological Model. - Kendra Jason; Dawn C Carr; Tiffany R Washington; Tandrea S Hilliard; Chivon A Mingo (The Gerontologist, 2017)
Purpose of the Study: Despite the growing prevalence of multiple chronic conditions (MCC), a problem that disproportionally affects older adults, few studies have examined the impact of MCC status on changes in workforce participation in later life. Recent research suggests that resilience, the ability to recover from adversity, may buffer the negative impact of chronic disease. Guided by an adapted socio-ecological risk and resilience conceptual model, this study examined the buffering effect of resilience on the relationship between individual and contextual risks, including MCC, and workforce transitions (i.e., leaving the workforce, working fewer hours, working the same hours, or working more hours). Design and Methods: Using the Health and Retirement Study, this study pooled a sample of 4,861 older workers aged 51 and older with 2 consecutive biannual waves of data. Nonnested multinomial logistic regression analysis was applied. Results: MCC are related to higher risk of transitioning out of the workforce. Resilience buffered the negative effects of MCC on workforce engagement and remained independently associated with increased probability of working the same or more hours compared with leaving work. Implications: MCC are associated with movement out of the paid workforce in later life. Despite the challenges MCC impose on older workers, having higher levels of resilience may provide the psychological resources needed to sustain work engagement in the face of new deficits. These findings suggest that identifying ways to bolster resilience may enhance the longevity of productive workforce engagement.
Keywords: Comorbidity; Resilience; Retirement Planning and Satisfaction

Optimal financial knowledge and wealth inequality - Annamaria Lusardi; Pierre-Carl Michaud; Olivia S. Mitchell (The Journal of Political Economy, 2017)
We show that financial knowledge is a key determinant of wealth inequality in a stochastic lifecycle model with endogenous financial knowledge accumulation, where financial knowledge enables individuals to better allocate lifetime resources in a world of uncertainty and imperfect insurance. Moreover, because of how the U.S. social insurance system works, better-educated individuals have most to gain from investing in financial knowledge. Our parsimonious specification generates substantial wealth inequality relative to a one-asset saving model and one where returns on wealth depend on portfolio composition alone. We estimate that 30-40 percent of retirement wealth inequality is accounted for by financial knowledge.
Keywords: Financial literacy; Retirement Planning and Satisfaction; Wealth

Pathways to retirement through self-employment - Ramnath, Shanthi; John B. Shoven; Sita Nataraj Slavov (NBER Working Paper Series, 2017)
Keywords: Bridge employment; Retirement Planning and Satisfaction; Self-employment

Phased retirement programs, although uncommon, provide flexibility for workers and employers - United States Government Accountability Office (Reports & Testimonies, 2017)
Participation of older workers in the labor market has increased in the last decade, according to GAO analysis. Further, most individuals ages 61 to 66 who were still working maintained a full-time work schedule. However, although about a quarter of workers in this age group had planned to reduce hours as they transitioned to retirement, fewer than 15 percent subsequently reported being partly retired or gradually retiring from their career jobs. While no nationally representative data on the prevalence of phased retirement exist, GAO's review of studies and interviews with retirement experts indicate that formal phased retirement programs are relatively uncommon. Of those that are offered, they are more common among employers with larger or technical and professional workforces, such as education, consulting, and high-tech, according to studies GAO reviewed (see table). Nine of 16 experts GAO interviewed explained that industries with skilled workers or with labor shortages are motivated to offer phased retirement because their workers are hard to replace.
Keywords: Bridge employment; Government; Phased retirement; Retirement Planning and Satisfaction

Phased retirement programs still rare, GAO finds - Bradford, Hazel (Online, 2017)
Keywords: Bridge employment; GAO; News; Retirement Planning and Satisfaction

Planning for retirement? The importance of time preferences - Robert Clark; Hammond, Robert; Khalaf, Christelle; Morrill, Melinda (NBER Working Paper Series, 2017)
Ensuring retirement income security is a priority for individuals, employers, and policymakers. Using merged administrative and survey data for public sector workers in North Carolina, we explore how workers’ characteristics and preferences are associated with planning and saving for retirement. We then assess the “quality” of a retirement plan and whether retirement behavior is consistent with these plans. The findings indicate that the way that individuals discount future consumption is associated with the extent of their retirement planning and preparedness. We find that individuals who engage in retirement planning are better prepared to meet their retirement goals upon leaving their career jobs.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

Relating Older Workers' Injuries to the Mismatch Between Physical Ability and Job Demands. - Laura A Fraade-Blanar; Jeanne M Sears; Kwun Chuen G. Chan; Hilaire J Thompson; Paul K Crane; Beth E. Ebel (Journal of Occupational and Environmental Medicine, 2017)
OBJECTIVE: We examined the association between job demand and occupational injury among older workers. METHODS: Participants were workers aged 50+ enrolled in the Health and Retirement Study, 2010 to 2014. Participants reported physical ability within three domains: physical effort, stooping/kneeling/crouching, and lifting. To measure subjective job demand, participants rated their job's demands within domains. We generated objective job demand measures through the Occupational Information Network (ONET). Using Poisson regression, we modeled the association between physical ability, job demand, and self-reported occupational injury. A second model explored interaction between job demand and physical ability. RESULTS: The injury rate was 22/1000 worker-years. Higher job demand was associated with increased injury risk. Within high job demands, lower physical ability was associated with increased injury risk. CONCLUSIONS: Older workers whose physical abilities do not meet job demands face increased injury risk.
Keywords: Disabilities; Employment and Labor Force; Health Shocks; Job loss; Older Adults; Retirement Planning and Satisfaction

Rethinking a common assumption about retirement spending - Vernon, Steve (Moneywatch, 2017)
Keywords: Finances; News; Retirement Planning and Satisfaction; Spending

Retirement Income and Expenses - Brannon, Ike (Regulation, 2017)
Keywords: Finances; Retirement Planning and Satisfaction

Retiring (Again and Again) in America - Hymowitz, Carol (Bloomberg Businessweek, 2017)
Keywords: Bridge employment; Employment and Labor Force; Retirement Planning and Satisfaction

Retiring early could kill you - Pesce, Nicole Lyn (Moneyish, 2017)
Keywords: Mortality; Retirement Planning and Satisfaction

Social Security and Total Replacement Rates in Disability and Retirement - Khan, Mashfiqur R.; Matthew S. Rutledge; Geoffrey T. Sanzenbacher (Working Papers, 2017)
Social Security provides higher replacement rates to disability insurance beneficiaries than retired beneficiaries. This fact reflects two factors: 1) Disability Insurance (SSDI) beneficiaries have lower career earnings, and Social Security benefits are progressive; and 2) SSDI benefits are not reduced for claiming early. This project uses the 1992-2010 waves of the Health and Retirement Study (HRS) linked to Social Security Administration earnings records to decompose the differences between the Social Security replacement rates for retired worker and SSDI beneficiaries into these two factors. The project also examines how the total replacement rate – which accounts for other sources of income in addition to Social Security – differs between retirees and SSDI beneficiaries to capture the difference in overall retirement security between the two groups. The results indicate that about half of the 10-percentage-point advantage in Social Security replacement rates for SSDI beneficiaries is due to the actuarial adjustment applied to retirement benefits, implying that career earnings are not that different between retired workers and SSDI beneficiaries. But total replacement rates are substantially lower for SSDI beneficiaries, which indicates that, despite Social Security’s vital role in providing a reliable income source, SSDI beneficiaries have much lower post-career well-being than retired workers.
Keywords: Consumption and Savings; Disabilities; Retirement Planning and Satisfaction; Social Security

Spending in retirement…or not? - Wolfe, Bruce; Brazier, Robert (Savings & Investing, 2017)
Something unexpected has been the shared experience for our most recent generation of retirees. The vast majority haven't been spending their retirement savings—leaving nest eggs mostly untouched and living on ready sources of income instead. However, future retirees may be less fortunate.
Keywords: Financial Health; Retirement Planning and Satisfaction; Spending

Is There Really a Retirement-Savings Crisis? - Anne Tergesen (The Wall Street Journal, 2017)
Keywords: News; Retirement Planning and Satisfaction

To What Extent is Gradual Retirement a Product of Financial Necessity? - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Work, Aging and Retirement, 2017)
Changes in the retirement income landscape over the past 30 years have left older Americans more exposed to market forces than prior generations, and more reliant on earnings to ensure their financial stability at older ages. These earnings come from a variety of nontraditional paths to retirement. Most older Americans reduce hours in career employment, change employers later in life, reenter the labor force after an initial retirement, or follow some combination of these 3 paths. The many pathways to retirement are undoubtedly the product of a flexible labor market and may be good news on balance; however, for some these job changes may reflect hardship, as vulnerable populations seek whatever employment they can find to prevent falling into poverty at older ages. We assess the magnitude of this segment of older workers using data from the Health and Retirement Study (HRS), a large, nationally-representative longitudinal survey of older Americans that began in 1992. We find that bridge job prevalence among those with little or no financial assets resembles that of individuals in the middle of the wealth distribution, implying that financial insecurity does not appear to be a main driver of gradual retirement transitions among career workers. Bridge employment among those with little or no financial assets is, however, more likely to consist of full-time wage-and-salary work. With the prospect of increased financial insecurity among older Americans, this analysis suggests that gradual retirements consisting of short-term, full-time wage-and-salary employment may become more prevalent in the years ahead.
Keywords: Bridge employment; Financial literacy; Older Adults; Retirement Planning and Satisfaction

Work, health and the commodification of life's time: reframing work–life balance and the promise of a long life - Biggs, Simon; McGann, Michael; Dina Bowman; Helen Kimberley (Ageing and Society, 2017)
How to respond to an ageing society has become an increasingly important question, for employers, workers and policy makers. Here we critically engage with that debate, arguing that future approaches to the relationship between work and age should take into account multiple influences on older worker behaviour, including the combination of economic, lifecourse and personal priorities. We consider the international consensus that has emerged about the primacy of work as the solution to what to do with a long life. We then address the uncertain nature of work as it affects older workers, and discuss the commodification of time in relation to a productivist approach to demographic ageing and the attitudes of older workers themselves. A tension is noted between pressures for continuity and discontinuity within the adult lifecourse which is often eclipsed within a policy discourse that tends to focus on continuity as a route to social legitimacy. Thinking about life-time as a meta-narrative, a tension between existential life priorities and commodification, may help to explain the ease with which ‘live longer–work longer’ policies both dominate and obscure the potential of a long life. Finally, we examine the implications for work–life balance and suggest this needs to be radically re-thought when addressing the purpose of a longer working life and the promise of a long life in general.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Work-life balance

The Affordable Care Act as Retiree Health Insurance: Implications for Retirement and Social Security Claiming - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (NBER Working Paper Series, 2016)
Using data from the Health and Retirement Study, we examine the effects of the Affordable Care Act (ACA) on retirement. We first calculate retirements (and in related analyses changes in expected ages of retirement and/or Social Security claiming) between 2010, before ACA, and 2014, after ACA, for those with health insurance at work but not in retirement. This group experienced the sharpest change in retirement incentives from ACA. We then compare retirement measures for those with health insurance at work but not in retirement with retirement measures for two other groups, those who, before ACA, had employer provided health insurance both at work and in retirement, and those who had no health insurance either at work or in retirement. To complete a difference-in-difference analysis, we make the same calculations for members of an older cohort over the same age span. We find no evidence that ACA increases the propensity to retire or changes the retirement expectations of those who, before ACA, had coverage when working but not when retired.
Keywords: Affordable Care Act; Health Insurance; Older Adults; Retirement Planning and Satisfaction; Social Security

The Aggregate Implications of Gender and Marriage - Borella, Margherita; Mariacristina De Nardi; Yang, Fang (NBER Working Paper Series, 2016)
Wages and life expectancy, as well as labor market outcomes, savings, and consumption, differ by gender and marital status. In this paper we compare the aggregate implications of two dynamic structural models. The first model is a standard, quantitative, life-cycle economy, in which people are only heterogenous by age and realized earnings shocks, and is calibrated using data on men, as typically done. The second model is one in which people are also heterogeneous by gender, marital status, wages, and life expectancy, and is calibrated using data for married and single men and women. We show that the standard life-cycle economy misses important aspects of aggregate savings, labor supply, earnings, and consumption. In contrast, the model with richer heterogeneity by gender, marital status, wage, and life expectancy matches the observed data well. We also show that the effects of changing life expectancy and the gender wage gap depend on marital status and gender, and that it is essential to not only model couples, but also the labor supply response of both men and women in a couple.
Keywords: Gender Differences; Marriage; Older Adults; Retirement Planning and Satisfaction; Women and Minorities

Are Retirees Falling Short? Reconciling the Conflicting Evidence - Alicia H. Munnell; Matthew S. Rutledge; Anthony Webb (Reimagining Pensions: The Next 40 Years, 2016)
This paper examines conflicting assessments of whether people will have adequate retirement income to maintain their pre-retirement standard of living. The studies that it examines use data from the Survey of Consumer Finances (SCF), the Health and Retirement Study (HRS), and the HRS supplement Consumption and Activities Mail Survey (CAMS). Critical components of the analysis are behavioral assumptions about household consumption patterns when children leave home and when households retire. A key limitation is that the behavioral assumptions in the different studies are based on incomplete knowledge of actual household behavior.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Changing generations: The importance of understanding long-term care options - Bracken, Krista (Health Care Administration, 2016)
The act of retiring, and retirement itself, is different for each individual, especially for those from different generations. Generational differences, along with economic and health status, can affect how an individual may plan for retirement or whether they plan at all. Though this topic is timely it has yet to be approached from an all-encompassing perspective. Various types of retirement planning were reviewed in this capstone. Literature reviewed from 1992 to 2014 revealed that generational differences impact how individuals plan—or do not plan—for retirement as well as what services they seek. Literature obtained through Utica Online Library and Google Scholar yielded the most significant information when examining retirement in conjunction with the trends in generational differences. Researchers also focused on individuals’ knowledge of and preparation for the retirement process. Future research to provide long-term healthcare planning options to individuals reaching the age of retirement was also discussed.
Keywords: Long-term Care; Nursing homes; Older Adults; Retirement Planning and Satisfaction

Cognitive Ability and Post-Retirement Asset Decumulation - Chris Browning; Huston, Sandra; Michael S. Finke (Journal of Family and Economic Issues, 2016)
Post-retirement asset decumulation decisions are complex and may be affected by cognitive abilities. Estimating uncertainties such as life expectancy and medical costs, and incorporating them effectively into decumulation decisions may be especially difficult as retirees face age-related changes in cognition. This may result in rates of decumulation that are contradictory to the goals that motivated accumulation, leading to potentially large utility losses. We investigated the relevance of cognitive ability to asset decumulation decisions within our sample. We found that cognitive ability was a significant predictor of the rate of asset decumulation, and that those with lower levels of cognitive ability were decumulating at a significantly lower rate. We also showed that the level of cognitive ability influenced the effects of expected longevity, market returns, and medical costs. While the estimates for these factors were consistent between those with high and low cognitive ability, there were significant differences in how the estimates were incorporated into the asset decumulation decisions of the two groups.
Keywords: Cognitive Ability; Consumption and Savings; Retirement Planning and Satisfaction

Disability Insurance Incentives and the Retirement Decision: Evidence from the United States - Courtney Coile (Social Security Programs and Retirement Around the World: Disability INsurance Programs and Retirement, 2016)
Public programs that benefit older individuals, such as Social Security and Medicare, may be changed in the future in ways that reflect an expectation of longer work lives. But do older Americans have the health capacity to work longer? This paper explores this question by asking how much older individuals could work if they worked as much as those with the same mortality rate in the past or as much as their younger counterparts in similar health. Using both methods, we estimate that there is significant additional capacity to work at older ages. We also explore whether there are differences in health capacity across education groups and whether health has improved more over time for the highly educated, using education quartiles to surmount the challenge of changing levels of education over time.
Keywords: Employment and Labor Force; Insurance; Older Adults; Public Policy; Retirement Planning and Satisfaction

Does retirement mean more physical activity? A longitudinal study - Feng, Xiaoqi; Croteau, Karen; Kolt, Gregory S.; Astell-Burt, Thomas (BMC Public Health, 2016)
Background: Evidence on physical activity (PA) and transitions out of full-time employment in middle-to-older age is mainly cross-sectional and focused upon retirement. The purpose was to examine trajectories in PA before and after transitions out of full-time employment. Methods: Data were obtained for 5,754 people in full-time employment aged 50-75 from the US Health and Retirement Survey. Logistic regression was used to examine trajectories in twice-weekly participation in light, moderate and vigorous PA among those transitioning to part-time work, semi-retirement, full retirement, or economic inactivity due to disability, in comparison to those remaining in full-time employment. Results: Twice weekly participation in vigorous and light physical activity changed little for those who remained in full-time employment, while moderate physical activity decreased between baseline and follow-up (OR 0.95, 95 % CI 0.91, 0.99). Differences in physical activity according to transitional categories at follow-up were evident. Baseline differences in physical activity across all intensities were greatest among participants transitioning from full-time to part-time employment compared to those who remained in full-time employment throughout the study period (vigorous OR 1.41 95 % CI 1.23, 1.61; moderate OR 1.28 95 % CI 1.12, 1.46; light OR 1.29 95 % CI 1.12, 1.49). Those transitioning to unemployment were already among the least physically active at baseline, irrespective of intensity (albeit, with 95 % CIs spanning unity). Those transitioning to full-time retirement were also among the least active (e.g. vigorous OR 0.71 95 % CI 0.61, 0.81; moderate OR 0.80 95 % CI 0.71, 0.90). Declines in physical activity were reported for those transitioning to economic inactivity due to a disability (vigorous OR 0.29 95 % CI 0.14, 0.64; moderate OR 0.56 95 % CI 0.33, 0.95; light OR 0.34 95 % CI 0.19, 0.63). Physical activity increased regardless of intensity among participants transitioning to semi-retirement (p > 0.05) and full retirement (e.g. vigorous OR 1.28 95 % CI 1.09, 1. 51; moderate OR 1.24 95 % CI 1.07, 1.43). Light physical activity increased for those transitioning to unemployment (OR 1.40 95 % CI 1.02, 1.93), though less change was evident in moderate or vigorous physical activity. Conclusions: The amount and intensity of PA varies by the type of transition out of full-time employment among people in middle-to-older age.
Keywords: Aging; Health Conditions and Status; Older Adults; Physical activity; Retirement Planning and Satisfaction

Does the Option of Continued Work Later in Life Result in a More Optimistic View of Retirement? - Kevin E. Cahill; Smeaton, Deborah; Principi, Andrea; Socci, Marco; Santini, Sara (Work Retirement and Wellbeing Working Paper, 2016)
This paper explores the link between work options and individuals’ views about retirement and overall well-being. Data for this paper come from 133 qualitative interviews of older individuals in the United States, United Kingdom, and Italy that were conducted in 2014 and from the Health and Retirement Study (HRS). Results from the qualitative interviews reveal that respondents in the US, relative to those in the UK and Italy, reported both a higher frequency of expecting to work in retirement and a more positive outlook for their retirement years. An examination of interview transcripts suggested a bifurcation among those who planned to work in retirement between: 1) those who viewed work as a contingency plan, for whom the outlook was generally positive; and 2) those who viewed work as a necessity for financial reasons, for whom the outlook was generally negative. This explanation was partly supported using data from the HRS. In both a descriptive and multivariate context, career wage-and-salary male respondents who reported some chance of working past age 65 had better retirement experiences and better mental health outcomes compared with those who expected to work past age 65 with certainty, while among women differences were not statistically significant. The findings from this paper suggest that optimism about retirement is related to the optionality of work in the years ahead.
Keywords: Bridge employment; Optimism; Retirement Planning and Satisfaction

The effect of job loss on health: Evidence from biomarkers - Pierre-Carl Michaud; Eileen M. Crimmins; Michael D Hurd (Labour Economics, 2016)
We estimate the effect of job loss on objective measures of physiological dysregulation using biomarker measures collected by the Health and Retirement Study in 2006 and 2008 and longitudinal self-reports of work status. We distinguish between group or individual layoffs, and business closures. Workers who are laid off from their job have lower health as measured by biomarker, whereas workers laid off in the context of a business closure do not. Estimates matching respondents wave-by-wave on self-reported health conditions and subjective job loss expectations prior to job loss, suggest strong effects of layoffs on biomarkers, in particular for glycosylated hemoglobin (HbA1c). A layoff could increase annual mortality rates by 10.3%, consistent with other evidence of the effect of group layoffs on mortality.
Keywords: Biomarkers; Health Shocks; Job loss; Older Adults; Retirement Planning and Satisfaction

Essays in Household Finance - Briggs, Joseph S. (Economics, 2016)
In this dissertation I examine the causes of household financial decision making. The first two chapters use administrative data in Sweden to study how wealth effects financial risk taking. In the third chapter I study the interaction between saving and health in the Health and Retirement Study (HRS). The first two chapters use an administrative data set of Swedish lottery players that were randomly assigned 500M USD to estimate the causal effect of wealth on various measures of financial risk taking. From 1999-2007 the Swedish tax authorities collected detailed records of asset holdings for the entire Swedish population to implement a tax on pre-existing wealth. During this same period, I have gained access to records of over 300K lottery winners that won prizes in three distinct lottery subsamples. By linking these two data sets, I have developed an ideal laboratory to estimate the causal effect of wealth on outcomes. The first chapter of this dissertation estimates the causal effect of wealth on stock market participation. A $150,000 windfall gain increases stock ownership probability among pre-lottery non-participants by 12 percentage points, while pre-lottery stock holders are unaffected. The effect is immediate, seemingly permanent and heterogeneous in intuitive ways. Standard lifecycle models predict wealth effects far too large to match our causal estimates under common calibrations. Additional analyses suggest a limited role for explanations such as procrastination or real-estate investment. Overall, results suggest that "nonstandard" beliefs or preferences contribute to the nonparticipation of households across many demographic groups. In the second chapter of this dissertation I estimate the causal effect of wealth on the share of risky assets in a household's financial portfolio. We find that $150,000 causes a 9 percentage point decrease in the average household portfolio's equity share in their financial portfolio. The effect is immediate, not explained by passive investing, and negative in all subsamples considered. A decrease in risk taking could indicate increasing relative risk aversion. However, we show that a dynamic model with realistic income profile can replicate the estimated decrease in portfolio risk, and that caution should be used when inferring risk preference from portfolio shares. In the third chapter of this dissertation I explore the role of health on retirement savings. Using the HRS, I estimate preferences for wealth when older individuals are in poor health. I find a high marginal value of wealth in the poor health state, and show that it is an important channel that encourages saving late in life.
Keywords: Finances; Income; Older Adults; Retirement Planning and Satisfaction; Savings

Essays in the economics of long-term care utilization. - Hurdelbrink, Jonathan R. (Economics, 2016)
This research examines three factors – macroeconomic conditions, the Deficit Reduction Act of 2005, and inter-vivos transfers – that influence both the availability of long-term care services and the use of these services. The first essay explores how changes in the macroeconomy, specifically the 2007-2009 “Great Recession,” affect the utilization of paid and unpaid long-term care services. It is theoretically unclear how long-term care use should be affected by such downturns, as an individual’s health status, wealth, insurance coverage and access to care are all likely to change during a significant downturn such as the “Great Recession.” Using data from the 1998-2012 waves of the Health and Retirement Study, a survey that follows Americans over the age of 50 as they begin to transition into retirement, we estimate the effects of changes in the unemployment rate at both the national and county levels on long-term care use. We find consistent evidence that overall care use declines significantly during downturns, with additional results suggesting that these results may be driven by reductions in individual wealth and improvements in individual health status. The second essay examines how the implementation of the Deficit Reduction Act of 2005, a policy that imposed stricter regulations about how individuals could “spend down” their assets to become Medicaid eligible, impacts both asset transfers and long-term care use among the elderly. Using data from the 1998-2010 waves of the Health and Retirement Study, I estimate the effects of this policy using a difference-in-difference framework. Overall, individuals seem to substitute from making inter-vivos transfers to holding assets in trusts in response to the enactment of the Deficit Reduction Act. With regard to care use, individuals seem to substitute from in-home long-term care to more visits to both doctors and adult day care facilities following the DRA, an effect primarily driven by the wealthiest and youngest individuals. The third essay investigates the relationship between parent-to-child inter-vivos asset transfers and future informal care provision by that child. Using data from the 1998 – 2010 waves of the Health and Retirement Study, I am able to use the timing of the transfers and the care use to describe this relationship. The results suggest that the receipt of an inter-vivos transfer during the previous two years is strongly positively correlated with that child’s likelihood of providing care during the previous month. In addition, I confirm a previous finding in the literature that child’s gender, relationship to the parent and geographical proximity to the parent all significantly influence the child’s decision to provide care.
Keywords: Economics; Inter Vivos Transfers; Older Adults; Retirement Planning and Satisfaction

Falls, Fall Injuries and the Aging Workforce - Kenneth A Scott (Epidemiology, 2016)
Health is a resource that enables an individual to act more freely within the labor market. A person in good health can initiate and maintain gainful employment, even in a physically or cognitively demanding occupation. Poor health can limit an individual’s functional abilities and job prospects, or the ability to work altogether. As individuals age, the likelihood of poor health increases as various health conditions and health events become more common. By informing which health conditions are likely to have significant economic consequences as the US population ages, epidemiologic research can help guide prevention strategies to reduce the economic burden of poor health and to maintain older adults’ quality of life through retirement. Falls and fall injuries become more common as people age. This is true for falls that occur in the workplace as well as falls that occur outside of work. Falls already have a significant effect on the economy – a trend that will likely increase as the workforce ages. The projected lifetime costs of fall injuries occurring during 2010 in the US was over $152.9 billion. Falls also are a useful window through which researchers can see how work and health interact to influence retirement decisions. Like some other public health issues, such as heart attacks and strokes, falls have a dual nature. Falls are, on the one hand, discrete events and, on the other, indicators of ongoing changes in health and social status. An individual’s labor force participation could, theoretically, be influenced by an injury subsequent to a fall, health changes that preceded and caused the fall or both. The dissertation research presented below is comprised of three research studies that explore how work and health, specifically the experience of falls, might influence older workers’ retirement decisions. The introductory chapter will begin by describing the epidemiology of falls and fall injuries. We present the unadjusted US rates of falls analyzed by age and other factors. We highlight epidemiologic research that has described fall injuries in the workplace and we compare the patterns of fall injuries to other types of occupational injuries, again focusing on age-related patterns. After summarizing the descriptive epidemiology, we highlight analytic research studies that have identified individual-level and environmental risk factors for fall injuries. The consequences of fall injuries are then described, including the types of injuries commonly caused by falls, as well as their effects on disability and retirement. Finally, we present several conceptual models that tie together research on falls and research on work disability. After the introductory chapter, each paper of the dissertation is presented as a chapter. The first paper examines the patterns of same-level fall injuries in US workplaces, exploring whether the relationship between age and fall injury incidence varies by industry. The second paper tests whether, among US workers 65 and older, falls - injurious and non-injurious – are associated with a shorter time to first report of a health-related limitation in the work they can perform. The third paper then examines whether falling is associated with a shorter time to labor force exit among US workers 65 and older. A concluding section compares the findings from each study in relation to the research and broader context covered in the introductory chapter.
Keywords: Falls; Health Shocks; Older Adults; Retirement Planning and Satisfaction

The Great Recession, Housing Wealth, and the Retirement Decisions of Older Workers - Jan I Ondrich; Falevich, Alexander (Public Finance Review, 2016)
To determine how asset values of older workers affect their future retirement decisions, it is important to take into account how asset values change over asset cycles. This study uses Health and Retirement Study data from waves 1992 through 2010 together with restricted Social Security Administration data on respondents occupation to estimate models of the age at first self-reported retirement for the subsample of married males. The model covariates include demographic variables, workplace variables, nonhousing financial wealth, and housing equity. The proportional hazard estimates are, for the most part, significant and of the correct sign. The estimated models suggest that declines in housing wealth during the Great Recession lowered retirement probabilities of married males by as much as 14 percent to 17 percent. This delay was offset in cases where the household had defined benefit or contribution pensions.
Keywords: Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Housing Wealth and Retirement Timing - Martin P. Farnham; Purvi Sevak (Cesifo Economic Studies, 2016)
Labor-supply effects of changes in house value are potentially important but empirically neglected. Using the panel Health and Retirement Study merged to local house prices from the Federal Housing Finance Agency, we estimate the effect of house-price changes on actual and planned retirement timing. While we find no effect of house-price changes on the annual probability of retiring, we find that people respond to rising house prices by revising down their expected retirement age. We estimate that a 10 real increase in house value reduces expected retirement age by about 4 months. Our findings suggest that movements in the housing market may have important labor supply implications, especially in areas experiencing steep price declines.
Keywords: Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

How Family Status and Social Security Claiming Options Shape Optimal Life Cycle Portfolios - Hubener, Andreas; Maurer, Raimond; Olivia S. Mitchell (Review of Financial Studies, 2016)
We show how optimal household decisions regarding work, retirement, saving, portfolio allocations, and life insurance are shaped by the complex financial options embedded in U.S. Social Security rules and uncertain family transitions. Our life cycle model predicts sharp consumption drops on retirement, an age-62 peak in claiming rates, and earlier claiming by wives versus husbands and single women. Moreover, life insurance is mainly purchased on men's lives. Our model, which takes Social Security rules seriously, generates wealth and retirement outcomes that are more consistent with the data, in contrast to earlier and less realistic models
Keywords: Gender Differences; Older Adults; Retirement Planning and Satisfaction; Social Security

How medical marijuana could help boomers get the most out of retirement - Christopher Ingraham (The Washington Post, 2016)
Keywords: Baby Boomers; Cannabis; Older Adults; Prescription Medication; Retirement Planning and Satisfaction

The Impact of Retirement on Smoking Behavior - Padmaja Ayyagari (Eastern Economic Journal, 2016)
We use data from the Health and Retirement Study to examine the relationship between retirement and smoking decisions. Retirement might affect smoking behavior through a change in the opportunity cost of time, job-related factors or income. To estimate the causal effect of retirement on smoking habits, we exploit eligibility for Social Security benefits at age 62 to account for the endogeneity of retirement. We find suggestive evidence that retirement increases the probability of smoking among ever smokers, but this effect is sensitive to the econometric specification used. We also find evidence of heterogeneity in the impact of retirement.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Interdependence between the Social and Material Convoy: Links between Volunteering, Widowhood, and Housing Transitions - Shen, Huei-Wern; Tam E Perry (Social Work Research, 2016)
Relocation in older adulthood may occur due to triggering events, such as widowhood. Guided by Kahn and Antonucci s convoy model, this study explores the influence of volunteering on decision to relocate following the death of a spouse. Using three waves of data from the Health and Retirement Study (2006, 2008, and 2010), 5,146 community-dwelling married older individuals who were 65 years or older in 2008 were included. Findings from two multinomial logistic regression models showed that widows and widowers who were not volunteering in 2008 were more likely to move out of area in 2010 than their married counterparts, whereas the relationship between widowhood and relocation was not detected among those involved in volunteering. This article emphasizes the interdependency of social relationships and residences, a fundamental of one s material convoy, for older adults. Volunteering experiences may not only affect instrumental and emotional support after the loss of a key anchor in one s social convoy, but may also facilitate a widowed older adult to age in place rather than relocate.
Keywords: Other; Retirement Planning and Satisfaction

Issue Brief: Occupation, Cognitive Decline and Retirement - McFall, Brooke Helppie; Amanda Sonnega (MRDRC Issue Briefs, 2016)
Little is known about occupational differences in age-related cognitive decline. This information is an important starting point for understanding the potential role that cognitive decline may play in workforce departure and whether, as with physical health declines, cognitive decline influences rates of Social Security disability insurance claims or claims before the full retirement age. This issue brief uses longitudinal data on cognitive functioning in the Health and Retirement Study to describe differences in rates of age-related cognitive decline across broad occupational categories and to relate these to different work transitions at common retirement ages. Findings support prior research showing that cognitive decline may lead to earlier than planned retirement, and appear to be consistent with research showing that workers may shift to less cognitively demanding jobs as a result of cognitive decline.
Keywords: Cognitive Ability; Employment and Labor Force; Retirement Planning and Satisfaction

Labor Force Participation and Retirement - Noronha, Gilberto (Economics, 2016)
This dissertation contains two different papers on retirement. The two studies share two objectives. The first one is to understand retirement better, and to think about how retirement decisions are related to other decisions that people make during their lives, including decisions about labor supply, savings, and consumption. The second objective is to think about why Americans are retiring later (the labor force participation of older U.S. residents has been going up in the past 25 years, reverting a previous trend towards earlier retirement). The first chapter studies how marriage can affect retirement decisions. In particular, it shows that, when there is some complementarity in couples’ preferences regarding leisure, the increasing labor force participation of older women can help to explain the recent increase in retirement ages of married men. The second chapter studies how different private pension plans can have different effects on retirement. More specifically, it investigates whether the shift from defined benefit to defined contribution pension plans can help to explain recent retirement trends in the United States.
Keywords: Employment and Labor Force; Financial literacy; Marriage; Older Adults; Retirement Planning and Satisfaction

Leaving Big Money on the Table: Arbitrage Opportunities in Delaying Social Security - Bronshtein, Gila; Jason S Scott; John B. Shoven; Sita Nataraj Slavov (NBER Working Paper Series, 2016)
Recent research has documented that delaying the commencement of Social Security benefits increases the expected present value of retirement income for most people. Despite this research, the vast majority of individuals claim Social Security at or before full retirement age. Claiming Social Security early is not necessarily a mistake, as delaying Social Security commencement requires forgoing current income in exchange for future income. The decision to claim early could therefore rationally be driven by liquidity constraints, mortality concerns, bequest motives, a high time discount rate, or a variety of other preference related factors. However, for some individuals, delaying Social Security offers a significant arbitrage opportunity because they can defer Social Security and have higher income in all future years. Arbitrage exists for most primary earners who either purchase a retail-priced annuity or opt for a defined benefit annuity when a lump sum payout is offered, while forgoing the opportunity to defer Social Security. These individuals are essentially buying an expensive annuity when a cheaper one is available, and their decision to claim Social Security early is almost certainly a mistake. The magnitude of the mistake can reach up to approximately $250,000.
Keywords: Older Adults; Retirement Planning and Satisfaction; Social Security

Mechanisms of the Effect of Involuntary Retirement on Older Adults Self-Rated Health and Mental Health - Min-Kyoung Rhee; Michàlle E. Mor Barak; William T Gallo (Journal of Gerontological Social Work, 2016)
This study examined mechanisms of the effect of involuntary retirement on self-rated health and mental health among adults aged 50 or older. Using two waves of the Health and Retirement Study (2006 and 2010), we selected a sample of 1,195 individuals working for pay at baseline who responded to a lifestyle questionnaire in both waves. Regression-based path analyses were conducted to test the mediating effects of financial control, positive and negative family relationships, and social integration on the relationship between involuntary retirement and self-rated health and mental health. Results of mediation analyses indicated that transition to involuntary retirement was directly negatively associated with subsequent self-rated health and indirectly negatively associated with mental health via perception of less financial control. Voluntary retirement was indirectly positively associated with both self-rated and mental health via perception of more financial control. No significant direct or indirect effects of retirement were found when retirement was measured with an aggregate measure without specifying its voluntariness. Findings emphasize the importance of specifying the voluntariness of retirement and recognizing the heterogeneity in the mechanisms of involuntary and voluntary retirement.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

The Mental and Physical Health Consequences of Changes in Private Insurance Before and After Early Retirement - Ben Lennox Kail (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2016)
Objectives. This study evaluated the impact of private insurance coverage on the symptoms of depression, activities of daily living (ADLs), and instrumental activities of daily living (IADLs) in the years leading up to Medicare eligibility focusing on the transition from full-time work to early full retirement.Method. The Health and Retirement Study was used to (a) estimate 2-stage selection equations of (i) the transition to retirement and (ii) current insurance status, and (b) the impact of insurance coverage on health, net of endogeneity associated retirement and insurance coverage.Results. Employment-based insurance coverage was generally associated with better health. Moreover, being without employment-based insurance was particularly problematic during the transition to retirement. Non-group insurance only moderated the association between losing employment-based insurance and IADLs.Discussion. Results indicated that private insurance coverage is an important contextual factor for the health of early retirees. Those who maintain steady coverage tend to fare the best in retirement. This highlights the dynamic nature of changes in health in later life.
Keywords: Health Conditions and Status; Insurance; Retirement Planning and Satisfaction

The New Lifecycle of Women’s Employment: Disappearing Humps, Sagging Middles, Expanding Tops - Goldin, Claudia; Mitchell, Joshua (NBER Working Paper Series, 2016)
A new lifecycle of women's employment emerged with cohorts born in the 1950s. For prior cohorts, lifecycle employment had a hump shape; it increased from the twenties to the forties, hit a peak and then declined starting in the fifties. The new lifecycle of employment is initially high and flat, there is a dip in the middle and a phasing out that is more prolonged than for previous cohorts. The hump is gone, the middle is a bit sagging and the top has greatly expanded. We explore the increase in cumulative work experience for women from the 1930s to the 1970s birth cohorts using the SIPP and the HRS. We investigate the changing labor force impact of a birth event across cohorts and by education and also the impact of taking leave or quitting. We find greatly increased labor force experience across cohorts, far less time out after a birth and greater labor force recovery for those who take paid or unpaid leave. Increased employment of women in their older ages is related to more continuous work experience across the lifecycle.
Keywords: Employment and Labor Force; Lifecycles; Older Adults; Retirement Planning and Satisfaction; Women and Minorities

A new model for interdependent durations with an application to joint retirement - Bo E. Honoré; Áureo de Paula (London, Centre for Microdata Methods and Practice, 2016)
This paper introduces a bivariate version of the generalized accelerated failure time model. It allows for simultaneity in the econometric sense that the two realized outcomes depend structurally on each other. Another feature of the proposed model is that it will generate equal durations with positive probability. The motivating example is retirement decisions by married couples. In that example it seems reasonable to allow for the possibility that each partner's optimal retirement time depends on the retirement time of the spouse. Moreover, the data suggest that the wife and the husband retire at the same time for a nonnegligible fraction of couples. Our approach takes as a starting point a stylized economic model that leads to a univariate generalized accelerated failure time model. The covariates of that generalized accelerated failure time model act as utility-flow shifters in the economic model. We introduce simultaneity by allowing the utility flow in retirement to depend on the retirement status of the spouse. The econometric model is then completed by assuming that the observed outcome is the Nash bargaining solution in that simple economic model. The advantage of this approach is that it includes independent realizations from the generalized accelerated failure time model as a special case, and deviations from this special case can be given an economic interpretation. We illustrate the model by studying the joint retirement decisions in married couples using the Health and Retirement Study. We provide a discussion of relevant identifying variation and estimate our model using indirect inference. The main empirical finding is that the simultaneity seems economically important. In our preferred specification the indirect utility associated with being retired increases by approximately 5 when one's spouse retires. The estimated model also predicts that the marginal effect of a change in the husbands' pension plan on wives' retirement dates is about 3.3 of the direct effect on the husbands'.
Keywords: Adult children; Methodology; Pensions; Retirement Planning and Satisfaction

Older Peoples’ Willingness to Delay Social Security Claiming - Maurer, Raimond; Olivia S. Mitchell (NBER Working Paper Series, 2016)
We have designed and fielded an experimental module in the 2014 HRS which seeks to measure older persons' willingness to voluntarily defer claiming of Social Security benefits. In addition, we evaluate the stated willingness of older individuals to work longer, depending on the Social Security incentives offered to delay claiming their benefits. Our project extends previous work by analyzing the results from our HRS module and comparing findings from other data sources which included very much smaller samples of older persons. We show that half of the respondents would delay claiming if no work requirement were in place under the status quo, and only slightly fewer, 46%, with a work requirement. We also asked respondents how large a lump sum they would need with or without a work requirement. In the former case, the average amount needed to induce delayed claiming was about $60,400, while when part-time work was required, the average was $66,700. This implies a low utility value of leisure foregone of only $6,300, or under 20% of average household income.
Keywords: Employment and Labor Force; Health Shocks; Older Adults; Retirement Planning and Satisfaction; Social Security

Older Women’s Labor Market Attachment, Retirement Planning, and Household Debt - Annamaria Lusardi; Olivia S. Mitchell (NBER Working Paper Series, 2016)
The goal of this paper is to ascertain whether older women’s current and anticipated future labor force patterns have changed over time, and if so, to evaluate the factors associated with longer work lives and plans to continue work at older ages. Using data from both the Health and Retirement Study (HRS) and the National Financial Capability Study (NFCS), we show that older women’s current and intended future labor force attachment patterns are changing over time. Specifically, compared to our 1992 HRS baseline, more recent cohorts of women in their 50’s and 60s’s are more likely to plan to work longer. When we explore the reasons for delayed retirement among older women, factors include education, more marital disruption, and fewer children than prior cohorts. But household finances also play a key role, in that older women today have more debt than previously and are more financially fragile than in the past. The NFCS data show that factors associated with retirement planning include having more education and greater financial literacy. Those who report excessive amounts of debt and are financially fragile are the least financially literate, had more dependent children, and experienced income shocks. Thus shocks do play a role in older women’s debt status, but it is not enough to have resources: people also need the capacity to manage those resources if they are to stay out of debt as they head into retirement.
Keywords: Older Adults; Retirement Planning and Satisfaction; Women and Minorities

Predicting End-of-Career Transitions for Baby Boomers Nearing Retirement Age - Boveda, Ingrid; Metz, A. J. (The Career Development Quarterly, 2016)
Retirement has traditionally been conceptualized as a point‐in‐time decision to physically and psychologically withdraw from the workforce on reaching a certain age. However, the expectations of older workers demonstrate a new retirement paradigm, with many more retirement trajectories. The purpose of this study was to examine actual career decisions being made by older workers and to understand sociodemographic factors that might differentiate their career trajectories. Data from the Health and Retirement Study (Juster & Suzman, 1995) were analyzed using multinomial logistic regression to compare 4 retirement trajectories (i.e., no retirement, full retirement, bridge employment, and encore career). Gender, age, education, marital status, health, and wealth differentially predicted the odds of pursuing each of the 4 retirement decisions. Career practitioners may use these results to help baby boomers make retirement decisions and provide them with appropriate education, guidance, and resources. Additional research is needed to examine other factors salient to each of the retirement trajectories. (PsycINFO Database Record (c) 2016 APA, all rights reserved). (journal abstract)
Keywords: Baby Boomers; Bridge employment; Older Adults; Retirement Planning and Satisfaction

The relationship between retirement decisions and health care expenditures in the United States - Boyacioglu, Serife Nur (Public Policy and Policy Management, 2016)
A substantial literature analyzes the relationship in the U.S. between retirement decisions and health outcomes; however, the relationship between health care costs and retirement has not yet been adequately studied. This paper investigates the association between retirement choices and health care expenditures using data from the U.S. Health and Retirement Study. My analysis shows that retirement status is not predictive of healthcare expenditures. However, I find statistically significant evidence that the overall relationship between healthcare expenditures and retirement status is masked by the fact that this relationship is negative for women but positive for men.
Keywords: Decision making; Income; Medicare/Medicaid/Health Insurance; Older Adults; Retirement Planning and Satisfaction

Retirement Patterns and Their Relationship to Volunteering - Tang, Fengyan (Nonprofit and Voluntary Sector Quarterly, 2016)
This study examines the relationships of volunteering behaviors with work retirement patterns and transition among middle-aged and older Americans using the Health and Retirement Study data (1998-2008). Latent class analysis was used to identify retirement status and cluster respondents into five latent classes: the not-retired, partial retiree, full retiree, non-worker (e.g., homemakers), and the transitioned (i.e., the newly retired from paid work). Generalized linear mixed models showed those experiencing work retirement transitions were significantly more involved in volunteering than the not-retired. Partial retirees and full retirees were more likely to start volunteering, and full retirees were also more likely to end volunteering than the not-retired over the 10-year observation period. Volunteer organizations are advised to recruit older adults who have time available and social connections with the workforce and to target the newly retired who are likely to increase their volunteer time during the transition process.
Keywords: Adult children; Employment and Labor Force; Retirement Planning and Satisfaction

Retirement Timing: A Review and Recommendations for Future Research - Gwenith G Fisher; Chaffee, Dorey S.; Amanda Sonnega (Work, Aging and Retirement, 2016)
Although there have been many reviews of the retirement literature in recent years, the issue of retirement timing has received less attention, neglecting some large and important issues. Further, a significant number of empirical articles about retirement timing have been published across multiple disciplines since these review articles were written. The purpose of our study is to review and integrate prior research regarding retirement timing. We define retirement timing as the age or relative point at which workers exit from their position or career path (e.g., early, on time, and later). We propose a model to serve as an organizing framework for understanding retirement timing. Our model includes antecedents and consequences that are each grouped in terms of individual, family, work, and sociocultural factors related to the timing of the retirement process. We identify and discuss key factors that serve to moderate the relation between retirement timing and consequences. Finally, we identify gaps in the current literature and provide recommendations for future research.
Keywords: Future; Older Adults; Retirement Planning and Satisfaction

Social Security and Retirement Programs Around the World: The Capacity to Work at Older Ages - Introduction and Summary - Courtney Coile; Kevin Milligan; David A Wise (Cambridge, MA: National Bureau of Economic Research, 2016)
This is the introduction and summary to the seventh phase of an ongoing project on Social Security Programs and Retirement Around the World. The project compares the experiences of a dozen developed countries and uses differences in their retirement program provisions to explore the effect of SS on retirement and related questions. The first three phases of this project document that: 1) incentives for retirement from SS are strongly correlated with labor force participation rates across countries; 2) within countries, workers with stronger incentives to delay retirement are more likely to do so; and 3) changes to SS could have substantial effects on labor force participation and government finances. The fourth volume explores whether higher employment among older persons might increase youth unemployment and finds no link between the two. The fifth and sixth volumes focus on the disability insurance (DI) program, finding that changes in DI participation are more closely linked to DI reforms than to changes in health and that reducing access to DI would raise labor supply. This seventh phase of the project explores whether older people are healthy enough to work longer. We use two main methods to estimate the health capacity to work, asking how much older individuals today could work if they worked as much as those with the same mortality rate in the past or as younger individuals in similar health. Both methods suggest there is significant additional health capacity to work at older ages.
Keywords: Disabilities; Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction; Social Security

Social Supports as Enabling Factors in Nursing Home Admissions: Rural, Suburban, and Urban Differences - Cohen, Adrienne; Jennifer R. Bulanda (Journal of Applied Gerontology, 2016)
This study investigates differences in social support and nursing home admission by rurality of residence. We use discrete-time event history models with longitudinal data from seven waves (1998-2010) of the Health and Retirement Study to prospectively examine the risk of spending 30 or more days in a nursing home (n = 5,913). Results show that elders with a health problem who live in rural areas of the South or Midwest have approximately 2 times higher odds of nursing home entry than elders living in urban areas in the Northeast. Rural elders report somewhat higher social support than non-rural elders, and controlling for these forms of social support does not explain the higher risk of a nursing home stay for Southerners and Midwesterners living in rural areas. Results suggest that social support has a similar association with nursing home entry for rural, suburban, and urban elders.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Temporal Market Subordination of Near Term Baby Boomer Retirees: The Effects of Asset Price Volatility on Health and Retirement Satisfaction - Mark Combs (Planning, Policy, and Design, 2016)
The United States is facing a socioeconomic crisis as the Baby Boomer generation reaches retirement age without adequate savings. This problem is not unique to the U.S., as many other large countries in the developed world, particularly in Western Europe, have recognized future budgetary constraints they will face created by an elderly population that will rise dramatically from 2010 to 2030 (Rechel et al., 2013). In terms of retirement preparedness research and U.S. savings policy, the Baby Boomer generation is interesting for three reasons. One, Baby Boomers are members of a large demographic cohort represented by approximately 78 million people born in the United States between 1946 through 1964 (approximately 25 percent of the U.S. population). Two, a large percentage of the cohort can be identified by the type of retirement plan they have: defined benefit, defined contribution, or no plan at all. And finally, because Baby Boomer retirement outcomes became increasingly subordinate to the performance of financial markets throughout their lifecycle, the efficacy of their retirement in terms of satisfaction and solvency provides policy makers evidence of the deleterious effects of financialization. The concept of financialization is based on evidence that during the latter half of the 20th century financial markets and financial institutions became increasingly integral to the overall economy as the United States transitioned away from manufacturing and other types of industrial production. One of the primary examples of financialization was a change in the type of retirement plan offered by corporations to their employees. Defined benefit pension plans were common when first wave Baby Boomers entered the work force in the early 1970s - a retirement benefit managed by a corporate employer that guarantees a fixed monthly payment in retirement for the balance of the employee’s life. However, when late stage Boomers entered the work force in the early 1990s, defined benefit plans were being replaced by defined contribution pension plans, the success of which was dependent on stock market performance, and characterized by a transfer of responsibility for plan management and solvency to the individual - thereby removing pension liabilities from corporate balance sheets. Defined contribution plans were promoted as superior alternatives to defined benefit plans, supported by the fact that as Boomers aged, stocks, bonds, real estate, and other risk-based assets appreciated at historic levels. The growth in these types of assets engendered a growing variety of financial products that were designed to ensure an adequately funded retirement experience. However, as the first wave of Boomers reached retirement age in 2011, 75 percent had less than $30,000 and were faced with the prospect of an underfunded retirement. The aggregate state of Baby Boomer retirement preparedness helps to illustrate a clear incongruence when one considers the appreciation of various asset types throughout their lifecycle, the growth of wealth building products available to Boomers, and the aggregate level of wealth they achieved as a cohort. It was also clear as Boomers reached retirement age in 2011 that the odds of experiencing a satisfactory retirement outcome had become increasingly subordinate in a temporal context to the appreciation of housing prices and other asset classes. The notion of increasing subordination is supported by the dramatic increase in asset price volatility experienced by first wave Boomers in 2011 during an economic crisis that wiped out in a single year 22 percent of accumulated U.S. wealth - an unprecedented level of wealth destruction that left nearly 66 percent of Boomers unprepared for retirement. Whereas the wealth destruction created by the financial crisis is well documented, the longer-term effects of asset price volatility on health and retirement satisfaction remains unexplored in the literature. Moreover, the financial crisis demonstrated that retirement outcomes can be subordinate to market performance in a temporal sense as well – indicating that when an individual retires is just as important as how much wealth has been accumulated. It seems counterintuitive that so many Boomers would be unprepared for retirement when one considers the extent to which various assets appreciated during the Baby Boomer lifecycle, and the historically high level of home ownership that Boomers achieved. This dichotomy creates a central organizing question that informs the present study: how does retirement unpreparedness and market volatility impact the health and retirement satisfaction of Boomers? This dissertation seeks to demonstrate the interaction effects between various periods of asset price volatility, the use of various types of financial products (including home equity loans), increasing levels of market subordination, and post-retirement satisfaction and health status. These interaction effects will be examined primarily by dividing Boomers into a three saver group typology: (1) those with a defined contribution pension plan, or IRA, that are dependent on asset price appreciation for retirement capital requirements, (2) those with a defined benefit pension plan that generates guaranteed monthly retirement income and do not rely on market performance for retirement income, and (3) those without a retirement plan. The present study is based on a custom dataset comprised of multiple explanatory variables derived from the Health and Retirement Survey Database (hereafter, HRS), and historical price data for various types of assets. The HRS (Health and Retirement Study) is sponsored by the National Institute on Aging (grant number NIA U01AG009740) and is conducted by the University of Michigan. This analysis (a) examines a portion of the research literature that compares the retirement preparedness of Boomers nearing retirement age with earlier same-aged cohorts at various times, and during different types of market conditions; (b) identifies the effects of growing market subordination on retirement outcomes and health; (c) estimates the impact of these effects on composite measures that reflect retirement satisfaction, mental health, and physical health; and (d), identifies individual level characteristics that may inhibit or promote vulnerability. The findings from this research will inform policymakers seeking to improve the retirement outcomes of individuals at varying SES levels. It will also provide evidence of the impact of financialization and finance culture on health and retirement satisfaction. Some of the key findings of this study were: (1) a statistically significant increase of negative mental sentiment, and a decrease in retirement satisfaction in male HRS respondents after periods of market volatility, (2) the demonstration of reduced negative mental sentiment and higher levels of retirement satisfaction exhibited by retired individuals with monthly pension income, versus those individuals without monthly pension income, and (3) the demonstration of variation between SES groups in terms of their ability to recover lost capital after periods of market volatility.
Keywords: Baby Boomers; Retirement Planning and Satisfaction; Wealth

Three essays in life-cycle labor supply and human capital formation - Han, Joseph (Economics, 2016)
This dissertation consists of three independent essays on earnings dynamics, educational production function, and retirement. Each chapter explains labor supply and human capital formation from a life-cycle perspective. In the first chapter, I investigate how two different kinds of uncertainty jointly affect young workers' decisions. This paper introduces the possibility of multidimensional learning about worker ability and job match quality into a model of work decisions. This mechanism has a unique prediction, negative sorting into job mobility that fades away over time, which is verified in the NLSY79 data if the AFQT score carries over some information unused by workers and employers. I estimate the structural model, which also has flexible skill accumulation, by indirect inference. From simulation results on earnings dynamics, I find that the contribution of job shopping to average earnings growth is higher than previous estimates; also, individual heterogeneity in earnings growth is mostly explained by the process of resolving uncertainties. In the second chapter, which is joint work with Keunkwan Ryu, we estimate the effects of high school class size on college entrance exam scores, using Korean administrative data. For the identification, we exploit quasi-experimental variation in class size arising from distinct institutional settings in Korea: especially, students are separately educated by major from grade 11 with different class sizes between majors. By using multi-level differencing and instrumental variable techniques, we find the effects of high school class size reduction on the test scores are positive but small. In the third chapter, I examine the effects of life expectancy on retirement and related decisions. I construct a structural model which has a realistic description of complicated dynamic incentives facing the elderly, including Social Security. Furthermore, individual heterogeneity in survival beliefs are flexibly modeled, directly using subjective survival probabilities in the Health and Retirement Study (HRS) data. The estimated model suggests that many people in the data believed their wealth was over-annuitized; they would have chosen to work and save less if their average life expectancy had increased. This result partially explains the early retirement puzzle in the last century.
Keywords: Annuitization; Employment and Labor Force; Life Expectancy; Older Adults; Retirement Planning and Satisfaction

Time to Burn (Calories)? The Impact of Retirement on Physical Activity among Mature Americans - Fabrice Kämpfen; Jürgen Maurer (Journal of Health Economics, 2016)
Physical activity is crucial for maintaining and improving health, especially at advanced ages. While retirement increases the amount of time available for physical activity, there is only limited evidence regarding the causal effect of retirement on recommended levels of physical activity. Addressing this gap in the literature, we use data from the U.S. Health and Retirement Study to estimate the causal impact of retirement on meeting the federal government's 2008 Physical Activity Guidelines for Americans. Using official early and normal retirement ages as instruments for retirement, our causal IV analyses suggest significant positive effects of retirement on meeting the Guidelines. These effects are robust with regard to the treatment of unobserved individual-specific heterogeneity, the measurement of guideline compliance, the definition of retirement and respondents health insurance status. We also show that the effects of retirement on physical activity are larger for persons with higher levels of education and wealth.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Trends in Engagement in Advance Care Planning Behaviors and the Role of Socioeconomic Status - Khosla, Nidhi; Angela L Curl; Washington, Karla T. (American Journal of Hospice and Palliative Medicine, 2016)
We investigated the trends in advance care planning (ACP) between 2002 and 2010 and whether socioeconomic status explained such trends. We conducted a pooled regression analysis of Health and Retirement Study data from 6052 proxies of deceased individuals. We studied 3 ACP behaviors, discussing end-of-life (EOL) care preferences, providing written EOL care instructions, and appointing a durable power of attorney for health care (DPAHC). ACP increased by 12 to 23 every 2 years from 2002 to 2010. Higher household income increased the odds of having a DPAHC. Education was not associated with ACP. Socioeconomic status alone appears to play a very limited role in predicting ACP. Engagement in ACP likely depends on a constellation of many social and contextual factors.
Keywords: Demographics; End of life decisions; Methodology; Retirement Planning and Satisfaction

Trends in Retirement Satisfaction in the United States: Fewer Having a Great Time - Sudipto Banerjee (EBRI Notes, 2016)
Most of the existing research on overall retirement satisfaction of retirees uses single-year data and focuses on identifying and measuring the factors that may affect retirement satisfaction. However, the analysis presented in this paper uses data from the 1998-2012 rounds of the Health and Retirement Study (HRS) to illustrate longer trends in retirement satisfaction and the relationships with various other factors. The cross-sectional results in this study show that the share of respondents reporting very satisfying retirements dropped from 60.5 percent in 1998 to 48.6 percent in 2012. On the other hand, the share of respondents reporting moderately satisfying and not at all satisfying retirements increased from 31.7 percent to 40.9 percent and from 7.9 percent to 10.5 percent, respectively. The longitudinal results from a fixed sample observed over the 15-year period from 1998 to 2012 show similar declines in the share of respondents reporting very satisfying retirements and similar increases in the share of respondents reporting moderately satisfying retirements. This is in contrast to some of the previous research, which shows that retirement satisfaction increases with age. These trends are not limited to particular economic groups: Both the highest- and lowest-asset quartiles show similar trends. Also, people with and without pension income show similar trends in retirement satisfaction levels. As might be expected, net worth and health status are strongly correlated with retirement satisfaction. Higher net worth is associated with higher levels of satisfaction, and poorer health is associated with lower levels of satisfaction. There is no significant difference in retirement satisfaction levels between men and women. Although this study does not investigate the reasons behind the changes in retirement satisfaction levels, the reported shift in the retirement satisfaction trends raises an important question: Why is the share of very satisfied retirees dropping? Further research to answer this question might provide some important answers.
Keywords: Health Conditions and Status; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Understanding why black women are not working longer - Joanna N Lahey (NBER Working Paper Series, 2016)
Black women in current cohorts ages 50 to 72 years have lower employment than similar white women, despite having had higher employment when they were middle-aged and younger. Earlier cohorts of older black women also worked more than their white counterparts. Although it is not surprising that white women's employment should catch up to that of black women given trends in increasing female labor force participation, it is surprising that it should surpass that of black women. This chapter discusses factors that contribute to this differential change over time. Changes in education, marital status, home-ownership, welfare, wealth, and cognition cannot explain this trend, whereas changes in occupation, industry, health, and gross motor functioning may explain some of the trend.
Keywords: Employment and Labor Force; Older Adults; Racial/ethnic differences; Retirement Planning and Satisfaction; Women and Minorities

What Do Academic Studies Have to Say About Americans' Retirement Saving? - Andrew G. Biggs (Forbes, 2016)
Keywords: Income; Older Adults; Retirement Planning and Satisfaction; Saving

Work a Little, Play a Little: A New Retirement Strategy - Hannon, Kerry (The New York Times, 2016)
Keywords: Older Adults; Part-time work; Retirement Planning and Satisfaction

Are cancer survivors who are eligible for social security more likely to retire than healthy workers? Evidence from difference-in-differences - Candon, David (Dublin, UCD School of Economics, University College Dublin, 2015)
Despite the fact that there are over a million new cancer cases detected in the U.S. every year, none of retirement-health literature focuses specifically on the effect that cancer has on retirement. Social Security may offer a pathway to retirement for eligible workers but the separate effects of both cancer, and Social Security, on retirement, need to be accounted for. I use the fact that some workers will be eligible for Social Security when they are diagnosed with cancer, while some will not, as a source of exogenous variation to identify the joint effect of cancer diagnosis and Social Security eligibility on retirement. With data from the Health and Retirement Study (HRS), I use a difference-in-differences model to show that being eligible for Social Security, and surviving cancer, increases the probability of retirement by 11.2 for male workers. Given the increase in both cancer survival rates, and the number of older workers in the labour force, it is important to know if cancer is causing permanent exits, in a population who otherwise would continue working.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction; Social Security

Assessing the burden of worsening self-reported vision in older Americans using the Health and Retirement Study - Shih, Vanessa (Pharmacy, 2015)
Background Visual disorders are estimated to affect about 3.6% of Americans by 2020. Vision impairment has a substantial impact on individuals functionally. Vision impairment is associated with many comorbidities, functional limitations, as well as higher caregiving needs. This study aims to assess the transition to self-reported vision impairment and the effect on an individual's functionality and ability to live independently. Methods The Health and Retirement Study is an ongoing, biennial survey of older Americans that collects an abundance of data on an individual's family, health, and financial circumstances. The explanatory variable of interest was a dichotomous variable of vision impaired or not vision impaired as defined by their self-reported vision status. Outcomes studied were functional limitations defined as difficulty performing activities of daily living (ADLs) and instrumental activities of daily living (IADLs), likelihood of move to nursing home, and both informal and formal caregiving needs. Descriptive univariate and bivariate statistics were performed to describe the demographics of the sample over the ten waves of data used, from 1995-2012. Multivariable logistic regressions controlling for sociodemographic characteristics, were performed to test the association between vision status and outcomes of interest for specific representative waves. Panel data methods of logistic regression were used to measure the association between a transition to impaired vision and the effect on functional limitations and nursing home residence while controlling for potential confounders and within-patient correlation. Specifically, mixed-effects logistic regressions with subject-level random-effects were conducted for the binary outcomes of nursing home residence, difficulty in performing at least one ADL, and difficulty in performing at least one IADL. Results The prevalence of overall vision impairment was, on average, about 6%. On average, about 5% and 7% of respondents had near and distal vision impairment, respectively. The overall prevalence of nursing home residence in our sample was approximately 2%. Prevalence of ADL and IADL limitations was stable across waves but ranged from 1%-20% for each of the six ADL and five IADL limitations. More respondents reported receiving informal caregiving versus formal caregiving; however the hours of caregiving received was similar for both formal and informal caregiving recipients. Multivariable logistic regression for three representative waves found numerically higher odds of a nursing home residence for vision impaired individuals compared to individuals with no vision impairment, though the difference was not significant. The odds ratios for 1998, 2006, and 2012 were 1.08 (95% CI: 0.64, 1.84), 1.09 (95% CI: 0.64, 1.86), and 1.22 (95% CI: 0.76, 1.97), respectively. Significant associations were found between vision impairment and functional limitations. Using a similar approach, the odds ratio for difficulty performing at least one ADL was 2.57 (95% CI: 2.16, 3.05), 2.37 (95% CI: 1.97, 2.84), and 2.31 (95% CI: 1.92, 2.77) in 1998, 2006, and 2012, respectively. The odds ratios for difficulty performing at least one IADL was 3.78 (95% CI: 3.15, 4.53), 3.94 (95% CI: 3.26, 4.76), and 3.49 (95% CI: 2.89, 4.22) in 1998, 2006, and 2012, respectively. In the mixed-effects logistic regression of the total study panel, a transition from no vision impairment to vision impairment was significantly associated with 1.37 times higher odds of a nursing home residence (95% CI: 1.05, 1.78), a 2.96 times higher odds of difficulty performing at least one ADL (95% CI: 2.71, 3.24), and a 4.02 times higher odds of difficulty performing at least one IADL (95% CI: 3.70, 4.37), after controlling for confounders. Discussion We found the estimated prevalence of visual impairment and functional limitations within our sample, and the association between the two, to remain relatively stable over time. Additionally, we found an age-adjusted transition to self-reported vision impairment within n in ividual to have significant detrimental effects on the ability to live independently and perform ADLs and IADLs without difficulty. Thus, prevention of this transition can substantially impact an individual's quality of life, and benefits derived from early detection and improved treatment of medical conditions that contribute to vision loss can have extensive value beyond simply improving vision.
Keywords: Health Conditions and Status; Healthcare; Public Policy; Retirement Planning and Satisfaction

Change in Household Spending After Retirement: Results from a Longitudinal Sample - Sudipto Banerjee (Washington, DC, Employee Benefit Research Institute, 2015)
This paper shows how household spending changed in the immediate years following retirement by analyzing the spending patterns of a fixed group of households up to six years after their retirement. Two sources of data are used for this study. First is the Health and Retirement Study (HRS), which is a study of a nationally representative sample of U.S. households with individuals over age 50. The other source of data is the Consumption and Activities Mail Survey (CAMS), which was started in 2001 as a supplement to the HRS. The data show that household spending dropped at the beginning of retirement. In the first two years of retirement, median household spending dropped by 5.5 percent from preretirement spending levels, and by 12.5 percent by the third or fourth year of retirement. But the spending reduction slowed down after the fourth year. Although average spending in retirement fell, a large percentage of households experienced higher spending following retirement. In the first two years of retirement, 45.9 percent of households spent more than what they had spent just before retirement. This declined to 33.4 percent by the sixth year of retirement. Households that spent more in the first two years of retirement were not exclusively high-income households; rather they were distributed similarly across income levels. In the first two years of retirement, 2 in 5 households (39.3 percent) spent less than 80 percent of their preretirement spending. By the sixth year of retirement, a majority (53.1 percent) of households did so. In the first two years of retirement, 28.0 percent of households spent more than 120 percent of their preretirement spending. By the sixth year of retirement, 23.4 percent of households still did so. A very small percentage of the household budget was spent on durable goods. The median household (half above and half below) spent nothing on durables in retirement. Transportation spending showed the highest drop in the first two years of retirement. Median spending on transportation went down by 25.1 percent in the first two years of retirement, although the reduction in subsequent years was small. The median household had a mortgage payment before retirement but none after retirement.
Keywords: Consumption and Savings; Income; Net Worth and Assets; Retirement Planning and Satisfaction

The Changing Nature of the Retirement Transition for Dual Earning Couples (The Changing Nature of the Retirement Transition for Dual Earning Couples, 2015)
My dissertation examines how dual-earning couples navigate the retirement transition differently now that women's and men's work lives have become more similar. As the retirement transition has become more complex, understanding how and when people retire requires researchers and policymakers to be attuned to the family lives in which individuals are embedded. The decision to retire is an individual choice but one's family circumstances, particularly one's spouse, can influence the process. Couples must often factor in spouses' age, health, pension assets, and health insurance coverage, especially since the work lives of many women have become much more similar to men. Whereas men's retirement decisions were seen to depend on their employment situation and women's' on their husband's, women's rising attachment to the labor force means their work lives should be increasingly important in understanding the retirement transition of couples. This dissertation fills a gap in retirement research by utilizing a life course perspective to systematically study change across cohorts in how marital partners manage the retirement transition amidst rapid structural changes in the economy. Analyses use multiple waves of data from the Health and Retirement Study, applying a variety of modeling techniques to investigate the way that couples move from employment to retirement. Specifically, I focus on retirement expectations and timing, looking at whether dual earning couples influence and synchronize each other's retirement and how this may change across cohorts. Results suggest that coordination between couples may be declining, as both husbands and wives influence their respective partners' retirement expectations less in later cohorts. Analysis of the degree to which dual-earning couples synchronize their retirement expectations show that such couples expect to retire together when they both have the pension resources to do so. Results from event history models further indicate that the retirement trajectories have changed for the leading baby boom cohort, as evidence implies they are delaying retirement longer than previous cohorts. The findings provide mixed support for the notion that wives are influencing their husbands' retirement timing more in later cohorts or that the influence of husbands on wives' retirement timing has declined across cohorts.
Copyright - Copyright ProQuest Dissertations Publishing 2015 Last updated - 2015-09-08 First page - n/a
Keywords: Adult children; Demographics; Employment and Labor Force; Event History/Life Cycle; Health Conditions and Status; Methodology; Pensions; Policy; Retirement Planning and Satisfaction

Cognitive Ability and the Stock Reallocations of Retirees during the Great Recession - Chris Browning; Michael S. Finke (Journal of Consumer Affairs, 2015)
Retirees are increasingly responsible for managing their retirement savings. The ability to manage these assets efficiently can have an important impact on retirement well-being. Lower levels of cognitive ability in old age can reduce an investor's ability to control emotional responses to a loss. Greater sensitivity to loss may increase preferences for safety following a market decline, resulting in allocations away from stocks that are associated with long-term underperformance. We investigate whether cognitive ability is related to stock reallocations among retirees during the Great Recession. Using the Health and Retirement Study, we find that cognitive ability is negatively related to allocations away from stock. Compared to those with the lowest levels of cognitive ability, respondents with higher cognitive ability are 40 less likely to reduce their stock allocation by 50 or more. These results suggest that the quality of investment decisions in old age may be compromised by cognitive decline.
Keywords: Health Conditions and Status; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Comparing Retirement Wealth Trajectories on Both Sides of the Pond - Richard Blundell; Crawford, Rowena; Eric French; Tetlow, Gemma (Promoting research on retirement and Social Security policy, 2015)
Keywords: Cross-National; Income; Older Adults; Retirement Planning and Satisfaction

Competing demands: Dependent children and parental retirement - Motro, Joanna (Competing demands: Dependent children and parental retirement, 2015)
The 1960s through the 1980s saw an expansion of generous pensions allowing workers to retire at younger ages. Since then, pensions have become less generous, and more people are working longer. Although previous research has often focused on financial and pension-related explanations for the postponement of retirement, little research has focused on how family demands shape retirement decisions. Changes in family formation in the second half of the 20th Century include delayed marriage, delayed childbearing, divorce, and remarriage. These trends, combined with the increasing time children are taking to transition to adulthood, means that parents are now more likely to be supporting children as they prepare to retire. This dissertation examines how demands from children affect older parents as they approach retirement. Using data from the Health and Retirement Study, I ask whether parents with adolescent or dependent adult children postpone retirement to later ages than other parents. I examine retirement both prospectively, by comparing parents' retirement expectations across cohorts, and then longitudinally, by modeling one cohort's transition from working to retirement. In both analyses, I focus on the impact of children who are either dependent-aged (<18), college-aged, coresident, or financially dependent. Results from this study show that needs of children do not appear to exert much influence over their parent's retirement plans. Net of parental characteristics, demands from children do not have an independent effect on retirement outcomes. It also does not appear that children in more recent cohorts exert a greater influence on parental retirement despite greater demands from children in recent years. For some subgroups (e.g. unmarried mothers and fathers, black and Hispanic parents) having certain types of demands from children is associated with greater expectations of working at older ages, while having other types of children is associated with a lower chance of expecting to work longer. For some subgroups (e.g. unmarried mothers), having certain types of dependent children are associated with retiring later. However, for the majority of adults, retirement plans and behaviors are driven more by parental retirement readiness (e.g. wealth, pension participation, and age) rather than the needs of children.
Copyright - Copyright ProQuest Dissertations Publishing 2015 Last updated - 2015-09-08 First page - n/a
Keywords: Adult children; Methodology; Policy; Retirement Planning and Satisfaction

Couples' and Singles' Savings after Retirement - Mariacristina De Nardi; Eric French; John Bailey Jones (SSRN Electronic Journal, 2015)
We model the saving problem of retired couples and singles facing uncertain longevity and medical expenses in presence of means-tested social insurance. Households can save to self-insure against uncertain longevity and medical expenses, and to leave bequests. Individuals in a couple can be altruistic towards their spouse and other heirs and split bequests optimally. Single people can care about leaving bequests to children and others. Using AHEAD data, we first estimate the model and we then evaluate the relative importance of the various savings motives and the risk exposure of couples’ versus singles.
Keywords: Marriage; Older Adults; Retirement Planning and Satisfaction; Singles

Did the Great Recession Influence Retirement Plans? - Maximiliane E Szinovacz; Adam Davey; Lauren Martin (Research on Aging, 2015)
The recent recession constitutes one of the macro forces that may have influenced workers retirement plans. We evaluate a multilevel model that addresses the influence of macro-, meso-, and micro-level factors on retirement plans, changes in these plans, and expected retirement age. Using data from Waves 8 and 9 of the Health and Retirement Study (N = 2,618), we find that individuals with defined benefit plans are more prone to change toward plans to stop work before the stock market declined, whereas the opposite trend holds for those without pensions. Debts, ability to reduce work hours, and firm unionization also influenced retirement plans. Findings suggest retirement planning education may be particularly important for workers without defined pensions, especially in times of economic volatility.
Keywords: Employment and Labor Force; Health Conditions and Status; Pensions; Retirement Planning and Satisfaction

Do Households Increase Their Savings When the Kids Leave Home? - Irena Dushi; Alicia H. Munnell; Geoffrey T. Sanzenbacher; Anthony Webb (Boston College, 2015)
Much of the disagreement over whether households are adequately prepared for retirement reflects differences in assumptions regarding the extent to which consumption declines when the kids leave home. If consumption declines substantially when the kids leave home, as some life-cycle models of retirement saving assume, households need to achieve lower replacement rates in retirement and need to accumulate less wealth. Using administrative tax data from the Health and Retirement Study (HRS), as well as the Survey of Income and Program Participation (SIPP), this paper investigates whether household consumption declines when kids leave the home and, if so, by how much. Because consumption data are noisy and savings is the flip side of consumption, this paper examines whether savings in 401(k) plans increase when the kids leave home. The paper also investigates alternative methods of saving, including non-401(k) savings and increased mortgage payments.
Keywords: Consumption and Savings; Event History/Life Cycle; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Do Retired Americans Annuitize Too Little? Trends in the Share of Annuitized Income - Barry Bosworth; Gary T. Burtless; Mattan Alalouf (Center for Retirement Research at Boston College, 2015)
This paper examines the importance of annuity-like income as a share of total money income received by aged families. The analysis considers the aged (62+) population as a whole as well as different parts of the aged families’ income distribution during the period from the early 1980s through 2009. We use survey data from 1983 through 2009 from the March Current Population Survey (March CPS) and the Survey of Consumer Finances (SCF). The total income amounts reported in the files are compared with data in the National Income and Product Accounts (NIPA). We calculate the family income consisting of annuitized income flows (primarily Social Security and pensions) and measure it as a share of families’ total money income. We also expand the definition of both annuitized and non-annuitized income to include income flows not captured in the surveys, namely, health insurance subsidies and the housing services received by homeowners. Finally, we consider the potential impact on aged families if they were to convert their wealth into private annuities.
Keywords: Annuitization; Income; Older Adults; Retirement Planning and Satisfaction

Does Age-Related Decline in Ability Correspond with Retirement Age? - Belbase, Anek; Geoffrey T. Sanzenbacher; Gillis, Christopher M. (Center for Retirement Research at Boston College, 2015)
While declines in physical and mental performance are inevitable as workers age, they are not uniform across the various systems of the body – some physical and cognitive abilities decline much earlier than others. This variance implies that workers in occupations that rely on skills that decline early may be unable to work until late ages, even as policy changes like increases in the Full Retirement Age (FRA) encourage them to. Researchers often estimate models of early retirement that include a control for whether a worker is in a blue-collar job – basically assuming that less-physical white-collar work allows longer careers. But this assumption ignores the fact that even workers in white-collar occupations may find themselves relying on skills that have declined. This paper instead reviews the literature on aging and constructs a Susceptibility Index meant to reflect how susceptible an occupation is to declines in ability, regardless of whether the occupation relies on physical abilities (as blue-collar occupations do) or cognitive ones.
Keywords: Bridge employment; Cognitive Ability; Health Conditions and Status; Older Adults; Physical Ability; Retirement Planning and Satisfaction

Does Mode of Contact with Different Types of Social Relationships Predict Depression in Older Adults? Evidence from a Nationally Representative Survey - Alan R Teo; Choi, Hwajung; Sarah B. Andrea; Marcia A. Valenstein; Jason T Newsom; Dobscha, Steven K.; Zivin, Kara (Journal of the American Geriatrics Society, 2015)
ObjectivesTo determine associations between use of three different modes of social contact (in person, telephone, written or e-mail), contact with different types of people, and risk of depressive symptoms in a nationally representative, longitudinal sample of older adults. DesignPopulation-based observational cohort. SettingUrban and suburban communities throughout the contiguous United States. ParticipantsIndividuals aged 50 and older who participated in the Health and Retirement Survey between 2004 and 2010 (N = 11,065). MeasurementsFrequency of participant use of the three modes of social contact with children, other family members, and friends at baseline were used to predict depressive symptoms (measured using the eight-item Center for Epidemiologic Studies Depression Scale) 2 years later using multivariable logistic regression models. ResultsProbability of having depressive symptoms steadily increased as frequency of in-personbut not telephone or written or e-mail contactdecreased. After controlling for demographic, clinical, and social variables, individuals with in-person social contact every few months or less with children, other family, and friends had a significantly higher probability of clinically significant depressive symptoms 2 years later (11.5 ) than those having in-person contact once or twice per month (8.1 ; P .001) or once or twice per week (7.3 ; P .001). Older age, interpersonal conflict, and depression at baseline moderated some of the effects of social contact on depressive symptoms. ConclusionFrequency of in-person social contact with friends and family independently predicts risk of subsequent depression in older adults. Clinicians should consider encouraging face-to-face social interactions as a preventive strategy for depression.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Does Retirement Impact Health Care Utilization? - Norma B Coe; Gema Zamarro (Los Angeles, CA, Center for Economic and Social Research, University of Southern California, 2015)
The objective of this paper is to estimate the causal effect of retirement on health care utilization. To do so, we use data from the 1992-2008 waves of the Health and Retirement Study (HRS) and the 2004-2006 waves of the Survey of Health, Aging, and Retirement in Europe (SHARE).In particular, we estimate the causal impact of retirement on health care utilization as measured by: doctor visits, visits to a general practitioner, nights in the hospital, and preventative care use. This paper uses panel data and instrumental variable methods, exploiting variation in statutory retirement ages across countries, to estimate the causal effects. Cross-country comparisons allow us to examine the role of a health care system s use of the general practitioner as a gate keeper to specialists in this relationship. We find that while retirement is associated with increased health care use, our causal estimates show that retirement leads to fewer doctor visits in both the US and continental Europe. Nights in the hospital are unaffected by retirement status. Further we find that health care systems with primary care physicians who act as gatekeepers are particularly effective at decreasing doctor visits at retirement. Therefore, we conclude that increasing the statutory retirement age to help the solvency of the retirement systems will also increase doctor visits as individuals continue to work longer. In the US, the burden of this increased utilization will likely be borne by private insurance companies and public insurance to the extent it covers working individuals in their 60 s. European evidence suggests that this increase in doctor visits due to delayed retirement will be particularly evident in health systems without strong gatekeeper roles for general practitioners.
Keywords: Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Does Retirement Improve Health and Life Satisfaction? - Gorry, Aspen; Gorry, Devon; Sita Nataraj Slavov (2015)
We utilize panel data from the Health and Retirement Study to investigate the impact of retirement on physical and mental health, life satisfaction, and health care utilization. Because poor health can induce retirement, we instrument for retirement using eligibility for Social Security and employer sponsored pensions and coverage by the Social Security earnings test. We find strong evidence that retirement improves both health and life satisfaction. While the impact on life satisfaction occurs within the first 4 years of retirement, many of the improvements in health show up 4 or more years later, consistent with the view that health is a stock that evolves slowly. We find little evidence that retirement influences health care utilization.
Keywords: Health Conditions and Status; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Does Social Security Continue to Favor Couples? - Nadia S. Karamcheva; April Yanyuan Wu; Alicia H. Munnell (Center for Retirement Research at Boston College, 2015)
While dramatic increases in women’s labor supply and earnings have led to a substantial decline in the fraction of women eligible for spouse benefits at retirement, most wives still receive a survivor benefit, as wives still typically have lower earnings than their husbands and live longer. Using the MINT microsimulation model and the HRS data linked with Social Security administrative earnings records, this paper examines the extent to which Social Security continues to favor couples and will do so in the future. The paper finds that while the OASI program still distributes lifetime income from singles to couples, the transfers appear to be shrinking over time. Nevertheless, couples are still projected to have a higher benefit/tax ratio, a lower median net tax rate, and a higher share of them will be receiving positive net transfers from the system as compared to those who are never married or divorced. The increased labor force participation and earnings of women have contributed significantly to the decline in redistribution from men to women, and from singles to couples, while the effect of declining marriage rates has only a modest effect.
Keywords: Divorce; Marriage; Older Adults; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Dynamic models of health and labor supply in later life - Lindsay Jacobs (Dynamic models of health and labor supply in later life, 2015)
In these essays, I develop and estimate life-cycle models aimed at explaining various patterns in labor supply behavior at older ages. The first study measures the extent to which later-life differences in health and disability risks across occupations affect retirement behavior and how these risks influence initial career choice. In the second essay, I look at the degree to which the changing composition of occupations over time--from more to less physically demanding--has contributed to the increase in labor force participation at older ages. The final study examines the effects of wage and health transition processes as well as the role of accrued work-related strain on the labor force participation decisions of older males, aimed particularly at accounting for the high rates of "reverse retirement" seen in the data.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2015 Last updated - 2015-08-27 First page - n/a
Keywords: Disabilities; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

The Effect of Health Reform on Retirement - Helen G Levy; Thomas Buchmueller; Sayeh Nikpay (University of Michigan Retirement Research Center (MRRC) Working Paper, 2015)
Many studies have shown that the availability of health insurance is an important determinant of the retirement decision. Beginning in January 2014, the Affordable Care Act (ACA) made affordable alternatives to employer-sponsored health insurance much more widely available than they had been previously through the establishment of health insurance exchanges and, in some states, the expansion of Medicaid eligibility to low-income, childless adults. We analyze whether these new health insurance options led to an increase in retirement or part-time work among individuals ages 55 through 64 during the first 18 months after the policy took effect. Using data from the basic monthly Current Population Survey from January 2005 through June 2015, we find that there was no increase in retirement in 2014 either overall or in Medicare expansion states relative to nonexpansion states. We also find no change in the fraction of older workers who are working part-time.
Keywords: Health Conditions and Status; Health Shocks; Medicare/Medicaid/Health Insurance; Older Adults; Retirement Planning and Satisfaction

The Effect of Retirement Date Expectations on Pre-retirement Wealth Accumulation: The Role of Gender and Bargaining Power in Married US Households - Romm, A. T. (Journal of Family and Economic Issues, 2015)
This paper used seven waves of data from the US Health and Retirement Study to investigate the impact of expectations regarding the timing of retirement on pre-retirement wealth accumulation of married households. More specifically, the effect of married individuals' subjective beliefs of working full time after age 62 on household wealth was analyzed. Individuals' perceptions of the usual retirement age on the job was used as an instrument for their subjective beliefs of working full time after age 62. On a whole, the point estimates suggested that the responsiveness of married mens' saving behavior to retirement dates expectations was larger than that of married women. In particular, wealth of married households where men had the bargaining power in terms of being sole earners, exhibited the largest decrease in response to increases in subjective probabilities of working past age 62.
Keywords: Adult children; Consumption and Savings; Employment and Labor Force; Expectations; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

Effects of social security policies on benefit claiming, retirement and saving - Alan L Gustman; Thomas L. Steinmeier (Journal of Public Economics, 2015)
An enhanced version of a structural model jointly explains benefit claiming, wealth and retirement, including reversals from states of lesser to greater work. The model is estimated with Health and Retirement Study data. Alternative beliefs about the future of Social Security affect claiming behavior. Effects of three potential policies are also examined: increasing the early entitlement age, increasing the full retirement age, and eliminating the payroll tax for seniors. Predicted responses to increasing the full entitlement age are sensitive to beliefs. 2015 Elsevier B.V.
Keywords: Consumption and Savings; Event History/Life Cycle; Health Conditions and Status; Methodology; Pensions; Retirement Planning and Satisfaction; Social Security

Essays on Health Economics - Ippolito, Benedic N. (Essays on Health Economics, 2015)
The first chapter, co-authored with Michael Batty, investigates how financial constraints influence hospital care. Specifically we study the impacts of recently enacted state "Fair Pricing" laws, which explicitly limit how much hospitals can collect from uninsured patients. Using the Nationwide Inpatient Sample, we find that the introduction of a fair pricing law leads to reductions in the amount of care delivered to uninsured patients, but find no evidence of deterioration of short-term quality of care. Overall, our results provide strong evidence that hospitals actively alter their behavior in response to financial incentives, and are consistent with the laws promoting a shift towards more efficient care delivery. In the second chapter I investigate how retirement incentives embedded in health insurance contracts influence labor market decisions of older workers. Employers typically offer one of two types of health plans: tied contracts (coverage ends at retirement) or retiree contracts (coverage continues in retirement). In comparison to a retiree plan, a tied contract provides an obvious incentive to delay retirement, but which workers stay? Particularly, what are the health characteristics of workers who respond to the incentives of the tied contract? I show that, contrary to suggestions in the literature, tied contracts produce advantageous selection. Additionally, I investigate the fact that tied contracts are consistently found to delay retirement even after age 65 - at which point workers are eligible for Medicare coverage. I show that this "excess retention" effect is entirely driven by workers with younger spouses who do not have their own insurance. The final chapter is joint work with Michael Batty and Joseph Levy, and examines how physician behavior responds to the introduction of a "panel-based" compensation structure - where a large portion of compensation is based on the number of patients a provider is responsible for, rather than the amount of work actually done. Taking advantage of a natural experiment at a large academic health system, we show that physician behavior is surprisingly unresponsive to changes in incentives - particularly for those who experienced a clear reduction in production incentives.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2015 Last updated - 2015-08-26 First page - n/a
Keywords: Employment and Labor Force; Healthcare; Income; Insurance; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Essays on Health Economics and Consumer Finance - Batty, Michael M. (Essays on Health Economics and Consumer Finance, 2015)
Chapter 1: Recently enacted state laws that limit how much hospitals can charge uninsured patients provide a unique opportunity to study how financial incentives of healthcare providers affect the care they deliver. Using an event study framework, we find that these fair pricing laws lead to a seven to nine percent reduction in the average length of hospital stay for uninsured patients. Although the longer-term effects of these care reductions are uncertain, they are not accompanied by worsening of short-term measures of quality of care. Overall, our results provide strong evidence that hospitals actively alter their behavior in response to financial incentives, and are consistent with the laws promoting a shift towards more efficient care delivery. Chapter 2: The list price for an average unit of care is more than three times what a hospital will be paid for treating a typical patient, and different hospitals charge widely different prices for the same service. These facts may seem innocuous, but many uninsured and out-of-network patients do pay list price. This paper uncovers patterns in hospital list prices, and explores several potential explanations. We find that markups vary much more across hospitals than within, but geography and quality of care explain little of the overall variation. Further, large, urban, well-equipped, for-profit hospitals have the highest list prices. A quirk in the Medicare Outlier Payment formula appears to have contributed to rapid price increases prior to 2004. Overall, our findings are consistent with more financially-sophisticated and profit-motivated hospitals more aggressively pursuing revenue from uninsured and out-of-network patients. Chapter 3: Many researchers and policy makers worry that Americans are not saving adequately for retirement. However, it is difficult to agree upon what constitutes adequate savings. This paper compares wealth accumulation patterns of different cohorts of Americans born in the first half of the 20th century. This comparative standard frames the retirement prospects of future and recent retirees in terms of the documented retirement experiences of older generations. Contrary to common perception, I find that the wealth accumulation of Americans nearing and entering retirement today is very similar to that of older generations.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2015 Last updated - 2015-08-26 First page - n/a
Keywords: Consumption and Savings; Healthcare; Methodology; Retirement Planning and Satisfaction

Essays on Health Insurance and Annuities - Shepard, Mark (Essays on Health Insurance and Annuities, 2015)
Insurance creates an important source of economic well-being by providing for beneficiaries in times of need. But because a variety of forces may inhibit the proper functioning of insurance markets, governments are deeply involved through regulation, subsidies, and direct provision of insurance. This dissertation studies insurance demand, supply, and the role of policy in two types of markets of direct interest to policymakers: health insurance and annuities. I highlight the importance of both traditional market failures (adverse selection and moral hazard) and less standard factors like limited competition (market power) and puzzlingly low insurance demand to influence insurance market outcomes. In the first chapter, I study how health insurers compete in individual insurance markets like those established in the Affordable Care Act. I focus on the role of an increasingly important benefit: plans' networks of covered medical providers. Using data from Massachusetts' pioneer insurance exchange, I show evidence of substantial adverse selection against plans covering the most expensive and prestigious academic hospitals. Individuals loyal to the prestigious hospitals both select plans covering them and are more likely to use these hospitals' high-price care. Standard risk adjustment does not capture their higher costs driven by preferences for using high-price providers. To study the welfare implications of network-based selection, I estimate a structural model of hospital and insurance markets and use the model to simulate insurer competition on premiums and hospital coverage in an insurance exchange. I find that with fixed hospital prices, adverse selection leads all plans to exclude the prestigious hospitals. Modified risk adjustment or subsidies can preserve coverage, benefitting those who value the hospitals most but raising costs enough to offset these gains. I conclude that adverse selection encourages plans to limit networks and star academic hospitals to lower prices, with the welfare implications depending on whether those high prices fund socially valuable services. Chapter 2 also studies health insurance exchanges and the competitive effect of a policy design choice: how the level of subsidies is determined. In the Affordable Care Act exchanges and other programs, subsidies depend on prices set by insurers – as prices rise, so do subsidies. I show that these "price-linked" subsidies incentivize higher prices, with a magnitude that depends on how much insurance demand rises when the price of uninsurance (the mandate penalty) increases. To estimate this effect, I use two natural experiments in the Massachusetts subsidized insurance exchange. In both cases, I find that a $1 increase in the relative monthly mandate penalty increases plan demand by about 1%. Using this estimate, my model implies a sizable distortion of $48 per month (about 12%). This distortion has implications for the tradeoffs between price-linked and exogenous subsidies in many public insurance programs. I discuss an alternate policy that would eliminate the distortion while maintaining many of the benefits of price-linked subsidies. Chapter 3 studies demand for annuities – insurance products that protect retirees against outliving their assets. Standard life cycle theory predicts that individuals facing uncertain mortality will annuitize all or most of their retirement wealth. Researchers seeking to explain why retirees rarely purchase annuities have focused on imperfections in commercial annuities – including actuarially unfair pricing, lack of bequest protection, and illiquidity in the case of risky events like medical shocks. I study the annuity choice implicit in the timing of Social Security claiming and show that none of these can explain why most retirees claim benefits as early as possible, effectively choosing the minimum annuity. Most early claimers in the Health and Retirement Study had sufficient liquidity to delay Social Security longer than they actually did and could have increased lifetime consumption by delaying. Because the marginal annuity obtained through delay is better than actuarially fair, standard bequest motives cannot explain the puzzle. Nor can the risk of out-of-pocket nursing home costs, since these are concentrated at older ages past the break-even point for delayed claiming. Social Security claiming patterns, therefore, add to the evidence that behavioral explanations may be needed to explain the annuity puzzle.
Keywords: Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Social Security

Essays on the economics of aging - Zhao, Zhendong (Economics, 2015)
The increase in life expectancy in the US and the changing labor supply of older workers have raised issues about the fiscal solvency of health care and pension systems, as well as labor market stability and employment opportunities for younger workers. In light of these facts, this dissertation consists of three essays that focus on the economic causes and consequences of changes in the labor supply of older workers due to population aging. The first essay examines the effect of longevity on older Americans' labor supply decisions of retirement and un-retirement. Instead of using self-rated survival probabilities as the proxy of longevity expectations, I use data from the Health and Retirement Study to predict longevity from a Gompertz survival model with a rich set of variables including parental mortality information, current health and socio-economic variables. I find that the predicted longevity fits actual longevity better than subjective survival rates. Using predicted longevity as one of the independent variables in a sequential logit model of retiring and un-retiring, I find that individuals retire and re-enter the labor market as if they knew their true potential longevity, i.e., individuals with higher predicted objective longevity retire later, and are more likely to return to the labor market after initial retirement. I further investigate the consequences of extreme mismatch between subjective survival rates and objective longevity implied by the model's prediction, and I find that the misperception leads to retirees' sub-optimal saving behaviors. The second essay makes an effort to explore the theoretical foundation for the mechanism through which the risk of mortality affects individuals' decisions about work. I construct a life-cycle model of labor supply with health investment and heterogeneous risk of mortality. The heterogeneity in mortality risk is modeled as a frailty parameter which shifts the mortality hazard proportionally. Individuals can invest in health in order to recover from an adverse health shock and revert the high propensity of death which they were born with. I estimate and calibrate the model using data from Health and Retirement Survey. I simulate the life cycle path of labor supply for two groups of representative individuals under the same condition except for different survival curves, one in year 2000 and one projected in 2100 where life expectancy is predicted to be increased by 9 years. I find that in a more favorable survival environment, individuals would choose to work more and spend more on health. The third essay examines a natural follow-up question about the consequence of a larger labor supply of older workers: does the higher labor force participation rate of the elderly crowd out employment opportunities of younger workers? I utilize the Social Security "Notch", a reduction in Social Security benefits for cohorts born after 1916 due to the 1977 Amendments, as an exogenous policy change to identify the effect on younger workers' employment. Using data from Current Population Survey from 1972 to 1981, I do not find any significant crowding-out effect of the notch generation on younger workers age 25-39. I further investigate the variations in different occupational categories and find that changes in employment rates of younger workers vary across occupations. Last, I do not find significant suppressing effect of increasing labor supply of older workers on younger workers' wage income.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Familial Caregiving and Timing of Retirement: A Gendered Cohort Analysis - Rachel R Stoiko (Familial Caregiving and Timing of Retirement: A Gendered Cohort Analysis, 2015)
Retirement timing has been linked to a host of outcomes for individuals, families, and communities. Well-known predictors of retirement timing include health, wealth, and cognitive capacity; a few studies have also linked gender and family caregiving to retirement timing. In the present study, data from the Health and Retirement Study were used to create profiles of pre-retirement family caregiving (operationalized as time and financial transfers to participants' aging parents and adult children). These profiles, as well as participant gender and cohort, were used to predict later retirement timing. All profiles retired, on average, earlier than their full eligibility for Social Security benefits. The Eldercare profile, which was characterized by high levels of time and financial transfers to aging parents, retired the earliest. On average, women retired earlier than men. Members of the War Babies cohort (b. 1941-1947) retired earlier than members of the HRS cohort (b. 1931-1941). There was not a significant interaction between caregiving profile and gender, revealing that when men enacted female-typical caregiving roles, their retirement timing resembled women's. Implications for individual retirement decision-making and policy are discussed.
Copyright - Copyright ProQuest Dissertations Publishing 2015 Last updated - 2015-09-02 First page - n/a
Keywords: Adult children; Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Other; Retirement Planning and Satisfaction

Go Gentle into That Good Night The Past, Present, and Future of End-of-Life Care - Adam E Singer (Go Gentle into That Good Night The Past, Present, and Future of End-of-Life Care, 2015)
End-of-life care has received increasing attention in recent years as the baby boomers age and health care costs continue to rise. This attention has brought with it remarkable growth in the field and improvement in care, but there remains work to be done in order to more consistently deliver high quality, compassionate, and patient- and family-centered end-of-life care. In this dissertation, I examine the past, present, and future of end-of-life care in order to shed light on the most effective ways to organize and deliver it. In the first analysis, I describe changes in symptom prevalence in the last year of life from 1998 to 2010. I find that the many important and troubling end-of-life symptoms, including pain and depression, became more common over that time frame, and that no symptom became less common. These changes occurred at the same time national efforts were underway to improve end-of-life care, which calls into question the nature of these changes and highlights the need to reexamine aspects of the delivery of end-of-life care. In the second analysis, I review the current evidence for palliative health services interventions to identify the populations that are appropriate for palliative care and the interventions that are effective in improving patient and family quality of life and reducing health care use and costs. I find that there are a broad range of currently available interventions that span a variety of goals, settings, and providers; that certain types of interventions are more or less effective for certain quality of life outcomes; and that health care use and cost outcomes are poorly studied overall. Some of these results enhance the existing understanding of what makes for effective end-of-life care. This information can be used in designing end-of-life care programs and in organizing research priorities for the field. In the third analysis, I simulate how cost and quality of life outcomes could fare through 2040 if three of the most effective palliative health services interventions identified in the second analysis were implemented today. I find that all three interventions lower health care costs, reduce mortality, improve quality-adjusted life years, and reduce pain, depression, and activities of daily living dependencies. These results highlight the benefit to individuals and to society of implementing evidence-based approaches to end-of-life care.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2015 Last updated - 2015-08-28 First page - n/a
Keywords: Gerontology; Health Conditions and Status; Healthcare; Methodology; Policy; Public Policy; Retirement Planning and Satisfaction

How Much Longer Do People Need to Work? - Alicia H. Munnell; Anthony Webb; Anqi Chen (Boston, Center for Retirement Research at Boston College, 2015)
Working longer is a powerful lever to enhance retirement security. Individuals should be able to extend the number of years they work because, on average, they are healthier, live longer, and face less physically demanding jobs. But averages are misleading when discrepancies in health, job prospects, and life expectancy have widened between individuals with low and high socioeconomic status (SES). To understand the magnitude of the problem, this paper, using data from the Health and Retirement Study (HRS), specifies how much longer households in each SES quartile would need to work to maintain their pre-retirement standard of living and compares those optimal retirement ages with their planned retirement ages to calculate a retirement gap. It then uses regression analysis to explore whether the gaps reflect poor circumstances or poor planning that is, the extent to which the retirement gap results from health, employment, and marital shocks that occur before the HRS interview but too late for the household to adjust saving (between ages 50 and 58), as opposed to a gap resulting from inadequate foresight. The analysis shows that households in lower-SES quartiles have larger retirement gaps, and this pattern remains true even after controlling for late-career shocks. In short, the most vulnerable have the largest retirement gaps, and these gaps arise from poor planning rather than late-career shocks.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

The Impact of a Randomly Assigned Time and Place Management Initiative on Work and Retirement Expectations - Kevin E. Cahill; Jacquelyn Boone James; Pitt-Catsouphes, Marcie (Work Aging and Retirement, 2015)
This article examines the causal relationship between a workplace flexibility arrangement and retirement expectations. The data come from a unique large-scale randomly assigned time and place management (TPM) initiative that recently took place at a regional healthcare system in the United States with more than 9,000 employees. A difference-in-differences approach was used to assess treatment impacts among older full-time career employees and comparisons were made with a nationally representative group of older Americans from the Health and Retirement Study (HRS). We found evidence that the TPM initiative had a statistically significant impact on employees' retirement expectations; employees in the treatment group were more likely than those in the control group to expect to remain with the organization until retirement, though treatment impacts dissipated somewhat toward the end of the study. The results indicate that workplace flexibility could be one solution to promote continued work later in life, as flexible work arrangements have the potential to impact retirement expectations and patterns of labor force withdrawal.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

The Impact of the Recession on the Wealth of Older Immigrant and Native Households in the United States - Amuedo-Dorantes, Catalina; Pozo, Susan (IZA Journal of Labor Policy, 2015)
Using the 2006 and 2010 Health and Retirement Study, we explore how the recent recession impacted the wealth holding and retirement plans of older households in the United States. Of particular interest to us is whether the impact on household asset ownership, asset wealth and household retirement behavior varied with the nativity of the household and its standing in the wealth distribution prior to the onset of the recession. We find that the so-called Great Recession made a significant dent on the portfolios of older American households by eroding the value of specific assets to the point of delaying their planned retirement. Furthermore, its impacts were unevenly distributed across demographic and economic groups, with mixed and immigrant households in the middle and top wealth quartiles prior to the recession enduring significantly larger wealth losses than natives due, primarily, to their greater losses in primary housing ownership and primary housing values.
Date revised - 2015-04-01 Availability - URL:http://www.izajolp.com/content Publisher's URL
Keywords: Employment and Labor Force; Housing; Net Worth and Assets; Pensions; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

Individual personality differences in adjustment to retirement - Eby, Rachel E. (Psychology, 2015)
Retirement is an important life event to study at present, because more people are entering their retirement years and are spending more time in retirement than ever before in our nation's history. Historically, research has shown mixed results on effects of retirement that are not accurately explained by any one theory. These mixed results suggest the possibility of individual differences in retirement adjustment that may not be accounted for with aggregated data. Wang, Henkens, and Shultz (2011) proposed a comprehensive framework of retirement adjustment: the resource-based dynamic perspective, which reasons that adjustment is influenced by antecedent variables, via level of resources possessed by the individual at a given time. The current study seeks to assess the relation between personality as an antecedent variable and retirement adjustment in a longitudinal analysis of participants from the nationally representative Health and Retirement Study. Resources are also modeled as covariates in the analysis. Results should be interpreted with caution due to limitations in model fit. Results from the Growth Mixture Model (GMM) revealed two classes of retirement trajectories and certain personality traits were significant as predictors for these trajectories. Implications for both research and practice are discussed.
Keywords: Health Conditions and Status; Healthcare; Other; Retirement Planning and Satisfaction

Marital History and Retirement Security: An Empirical Analysis of the Work, Family, and Gender Relationship - Palmer, Lauren A. Martin (Marital History and Retirement Security: An Empirical Analysis of the Work, Family, and Gender Relationship, 2015)
This dissertation investigates the relationship between marital history and individuals' retirement resources, namely Social Security, employer-sponsored pensions, and non-housing wealth. Prior research provides a foundation for understanding marriage's positive relationship to retirement security, and suggests that marriage is financially beneficial and can even lessen some external factors that would otherwise damage a family's financial situation. Yet changing demographics, with fewer people in first marriages and rising numbers of individuals experiencing divorce and choosing to remain unmarried, suggest our understanding of this relationship for today's retirees may be limited. The purpose of this research is to identify which aspects of complex marital histories are associated with individuals' retirement security, paying particular attention to gender differences. Using data from nine waves of the Health and Retirement Study (1992-2008), four facets of marital history are examined: marriage type, frequency, timing, and duration. Currently married and currently unmarried respondents are separated during the analyses in order to adequately capture the association between previous marital events and retirement resources. The results indicate that marital history is associated with Social Security, employer-sponsored pensions, and non-housing wealth differently, and that these relationships vary by gender and current marital status. The findings provide support for the argument that marital history, and in particular marital duration, has a strong relationship to retirement resources. Contrary to expectations, currently married women with longer marriages have less Social Security and pension income than married women who experienced shorter marriages. Marital history has no relationship to the retirement security of married men. For the unmarried groups, never married men have the lowest odds of receiving an employer-sponsored pension and have less non-housing wealth than both divorce and widowed men. Unmarried women's retirement security is associated with the type of disruption experienced; women with multiple past marriages have more resources if they are currently widowed but less if they are currently divorced. Further study is needed to understand how and why complex marital history factors have a relationship to retirement finances, and to expand our knowledge about certain understudied populations such as remarried women and never married men.
Keywords: Adult children; Net Worth and Assets; Retirement Planning and Satisfaction

The Mechanism of Ageism: The Relationship Between Perceived Ageism and Depressive Symptoms in Later Life - Kim, Hyejin (The Mechanism of Ageism: The Relationship Between Perceived Ageism and Depressive Symptoms in Later Life, 2015)
Extending the human life span has long been a desire of human beings. It seems the wish has been actualized. However, simply living a long life does not always seem to be a blessing. Older adults report a lower level of psychological well-being and quality of life and even have a higher rate of suicide, compared to the general population. Furthermore, as older adults are likely to experience the death of a loved one, deteriorating health, retirement, and changing relationships with others, older adults have a high risk of depression. Social work has a long history of providing social services to older adults. In particular, social work has provided older adults with a variety of services to enhance their quality of life and mental health status. Because ageism is one form of discrimination that social work has long been concerned with, this study focuses on the relationship between perceived ageism and depressive symptoms among older adults. Therefore, the purpose of this study is to examine the relationship between perceived ageism and depressive symptoms among older adults and to investigate the mechanism linking perceived ageism to late-life depression. Three primary effects were examined: the direct effect of perceived ageism on depressive symptoms in later life, the mediating effects of self-perception of aging and purpose in life on the relationship between perceived ageism and late-life depression, and the moderating effect of perceived ageism on the association between religiosity and depression among older adults. The stress process model was used to provide an overall idea to explain the three types of the effects related to the mechanism of ageism. Cooley's looking-glass self, Beck's cognitive theory of depression, and Levy's stress embodiment theory were used to explain the mediating effect of self-perception of aging, and Beck's cognitive theory of depression was applied again to clarify the mediating effect of purpose in life. The stress buffer theory and the life-span theory of control indicated the moderating effect of perceived ageism on the relationship between religiosity and depression. Secondary analysis of existing data was conducted using the Health and Retirement Study (HRS) datasets, a longitudinal panel study of the U.S. population ages 50 and over. The sample of this study was 3,991 participants, who were older adults ages 65 and over and whose answers were available for the study analyses. Descriptive and preliminary analyses were performed to roughly examine the relationships between variables. With regard to the direct effect of perceived ageism on depressive symptoms, multiple regression analyses were performed controlling for significant variables. With regard to the mediating effects of self-perception of aging and purpose in life, structural equation modeling (SEM) analyses using structural regression models were conducted. In respect to the moderating effect of perceived ageism on the relationship between religiosity and depression, SEM analyses with multiple groups were performed. Based on the results of the several different analyses, a direct relationship between perceived ageism and late-life depression was found. That is, older adults who perceive ageism are likely to have a higher level of depressive symptoms than their counterparts. This direct relationship between perceived ageism and late depressive symptoms among older adults, however, was not detected after controlling for self-perception of aging and purpose in life, indicating the full mediation effects of self-perception of aging and purpose in life. That is, older adults who perceive ageism are likely to have negative self-perception of aging, and this negative view of their own aging is likely to increase depressive symptoms. Additionally, older adults who have a negative view of their aging are likely to have a negative view of their future, and this lower purpose in life also increases depressive symptoms. The strength of the effect of religiosity on depression did not differ between the perceived age sm and the not perceived ageism groups, indicating no moderating effect of perceived ageism on the relationship between religiosity and depression. This study contributes to the existing body of knowledge by providing the information about the relationship between perceived ageism and depression and the mechanism of this relationship. Also, this study re-examined and supported established theories in the context of perceived ageism. Additionally, the current study suggests the necessity of anti-ageism policies and social work services and describes possible ways of providing such social policies and social work services at the micro, mezzo, and macro levels. The results of this study imply that more efforts and resources are necessary to reduce ageism and its negative effect on depression among older adults, and these efforts will eventually contribute to making a more just, better society.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2015 Last updated - 2016-01-07
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

No Place Like Home? Disability and Living Arrangements in Later Life - Carrie Elizabeth Henning-Smith (Health Services Research, Policy and Administration, 2015)
Current literature on the relationships between disability and both the physical and social environments of one's living arrangement is scarce. The relationship between disability and living arrangements in later life is inherently complex, yet it has the potential to impact older adults' lives in significant ways. With this dissertation, I sought to address this gap in the literature and add to our understanding of how older adults' environments and functional statuses interact. My specific aims were to: 1.) Describe the living arrangements of older adults with disabilities; 2.) Estimate the risk of developing disability by type of living arrangement (both housing type and household composition) for older adults; and, 3.) Estimate the risk of having a change in living arrangement by disability status for older adults. For all three aims, I also examined how the relationships between living arrangements and disability differed by age and socio-economic status. Data came from the American Community Survey (2012; n=504,371 adults age 65 and older) and the Health and Retirement Study (1998-2012; n=43,182 observations.) In Aim 1, I found that disability was most prevalent for older adults living in situations other than with a spouse only and that the odds of disability was highest for older adults living with children (without a spouse.) Compared with living in a single-family home, the odds of disability were higher for older adults living in mobile homes and large apartment buildings. In Aim 2, I found that living in a nursing home or with others was associated with an increased risk of disability, but that living alone was associated with a decreased risk of disabilities related to Instrumental Activities of Daily Living (IADLs.) This latter finding only held true for more affluent older adults, however; the poorest older adults faced an increased risk of disability if they lived alone. Finally, in Aim 3, I found that having IADL and ADL (Activities of Daily Living) disabilities together was predictive of moving, long nursing home stays, and death. ADL and IADL disabilities separately were predictive of long nursing home stays and death, while prior living arrangements were more predictive of moving than individual ADL or IADL disability status. For all of my findings, disability rates were highest among the poorest and oldest older adults. Older adults with the lowest socioeconomic status were also more likely to live alone, with non-spousal others, in rented homes, and in mobile homes or apartment buildings. This population may need additional resources to foster supportive living arrangements and to mitigate disability risk. These findings can be used to identify where older adults with disabilities live and where to target interventions to prevent worsening disability.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Public Policy; Retirement Planning and Satisfaction

Nonmonetary Job Characteristics and Employment Transitions at Older Ages - Marco Angrisani; Arie Kapteyn; Erik Meijer (Ann Arbor, MI, University of Michigan, 2015)
This paper studies to what extent job characteristics such as physical and cognitive demands, use of technologies, responsibility, difficulty, stress, peer pressure, and relations with co-workers are related to full or partial retirement. We study employment transitions and retirement expectations of older workers by exploiting the wealth of information about individuals older than age 50 in the Health and Retirement Study (HRS), and characteristics of different occupations provided by the Occupation Information Network (O NET) database. Controlling for basic demographics, wages, benefits, health, cognitive ability, personality, and other personal characteristics, we find strong and statistically significant relationships between labor force transitions and job characteristics. These relationships are typically more pronounced and more precisely estimated when we use objective job attributes taken from the O NET than when we use self-reported job characteristics taken from the HRS, but self-reported characteristics are more strongly related to moves from full-time to part-time employment. Using expected retirement age or subjective probabilities of working full-time at older ages gives similar results to using actual labor force transitions as the dependent variable. The estimated effects of job characteristics are again stronger and more robust to alternative specifications when measures of job attributes are taken from the O NET than from the HRS. Our findings suggest that nonmonetary job characteristics are important determinants of labor supply decisions at older ages, but our analysis is still preliminary in its attempt to uncover causal relationships: Unobservable individual characteristics responsible for sorting into specific occupations may also shape retirement decisions.
WP 2015-326
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Occupations and Work Characteristics: Effects on Retirement Expectations and Timing - McFall, Brooke Helppie; Amanda Sonnega; Robert J. Willis; Péter Hudomiet (Ann Arbor, MI, Michigan Retirement Research Center, 2015)
Population aging and attendant pressures on public budgets have spurred considerable interest in understanding factors that influence retirement timing. A range of sociodemographic and economic characteristics have been shown to predict both earlier and later retirement. Less is known about the role of occupations and their characteristics on the work choices of older workers. Knowing more about the occupations that workers seem to stay in longer or leave earlier may point the way to policy interventions that are beneficial to both individuals and system finances. This project uses detailed occupational categories and work characteristics in the Health and Retirement Study (HRS) linked to information in the Occupational Information Network (O NET) to examine compositional changes in occupations held by older workers over time; to provide some basic and interesting information about relationships between occupations and their characteristics and retirement expectations and outcomes; and to shed some light on which occupations and associated characteristics might encourage or discourage longer working lives. There are large percentage changes (increases in decreases) in the percentage of older workers in occupations over time. Considering detailed as opposed to aggregated occupational categories yields interesting additional information. Jobs that HRS respondents say entail less physical effort, less stress, and jobs that have not increased in difficulty in recent decades, and those in which people can reduce hours if desired, are associated with longer work. While the traditional blue collar-retire earlier and white collar-work longer associations emerge, we find interesting exceptions that suggest fruitful directions for future research.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Prolonged working years: Consequences and directions for interventions. - Gwenith G Fisher; Lindsay H Ryan; Amanda Sonnega (Sustainable working lives: Managing work transitions and health throughout the life course, 2015)
Keywords: Employment and Labor Force; Happiness; Older Adults; Retirement Planning and Satisfaction

Reconsidering the social security notch and retirement: Wealth and incentive effects - Jeremy G. Moulton; Ann H. Stevens (Economics Letters, 2015)
Using the Health and Retirement Study, we show that studies using the Social Security Notch cannot separately identify the effects of retirement wealth and forward-looking incentives on retirement because the Notch natural experiment changed both factors in offsetting ways. 2015 Elsevier B.V.
Keywords: Retirement Planning and Satisfaction; Social Security

Relationship of financial literacy to retirement preparedness among female baby-boomer cohorts - Womack, Barbara Klein (School of Public Service Leadership, 2015)
Studies have not examined the impact of components of financial literacy on retirement preparedness nor the relationship between financial literacy and decision-making among female baby-boomers. This study examined data from the 2010 wave of the Health and Retirement Study for females born between 1946 and 1959. This study defined financial literacy as including knowledge of investment strategies, the bond market, risk, and diversity. It defined retirement preparedness as the possession of specific financial assets. Financial decision-making was defined as the potential for mortgage default and carrying balances on credit cards. The study used a synthesis of rational choice and planned behavior theories. Correlation was used to describe the relationships between variables, and Fisher's transformation was used to determine significant differences between cohorts. Multiple linear regression was used to create predictive models for retirement planning, with the resultant finding that age was significant in predicting retirement preparedness ( p < .01). Older cohorts were more prepared, particularly in terms of owning IRA/Keogh plans. Understanding the effects of holding a variety of stocks and foreign stocks were most strongly related to retirement preparedness. There was a significant relationship between financial literacy and the potential for mortgage default ( p < .05) but not for carrying credit card balances. The regression produced a significant ( p < .05) predictive model for retirement preparedness, thought the relationship with financial literacy was slight. The research has implications in terms of housing, health, and municipal sustainability. Further research is necessary to define financial literacy, retirement preparedness, and their relationship.
Keywords: End of life decisions; Health Conditions and Status; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

The Retirement and Social Security Benefit Claiming of U.S. Military Retirees - Knapp, David; Asch, Beth; Hosek, James; Mattock, Michael (Ann Arbor, MI, Michigan Retirement Research Center, 2015)
After serving 20 years in the active component of the U.S. military, service members can retire from the military, as young as age 38, and begin collecting a monthly pension benefit for the remainder of their life. In this paper, we ask: do active duty military retirees exit the labor force earlier or later because of their access to military retirement benefits? Do they alter their Social Security claiming decisions? We theorize that access to a consistent source of income may encourage earlier retirement through a standard income effect, but the military pension may also increase a retiree s post-military job search, allowing for a greater wage and improved job satisfaction due to a better employer-employee match. Access to a steady source of pension income may also reduce short-term liquidity constraints, encouraging military retirees to delay claiming their Social Security benefit in order to benefit from delayed retirement. We estimate the impact of military retiree pension income on retirement empirically using the 1992 Health and Retirement Study cohort. We identify the military pension effect in a difference-in-difference model by exploiting a surprise change in military-retiree benefits in 2001 that extended Tricare health benefits to Medicare eligible military retirees and their spouses through the end of their lives. TFL eliminated the need to purchase Medigap coverage, thereby eliminating a cost that could cut into disposable income from their military annuity. A key limitation of the analysis is that the HRS includes relatively few military retirees.
Keywords: Demographics; Pensions; Retirement Planning and Satisfaction; Social Security

Retirement and the Great Recession - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Journal of Retirement, 2015)
This article uses data from the Health and Retirement Study to examine retirement and related labor market outcomes for the Early Boomer cohort, those in their mid-fifties at the onset of the Great Recession. Outcomes are then compared with older cohorts at the same age. The Great Recession increased their probability of being laid off and the length of time needed to find other full-time employment. Differences in layoffs between those affected by the recession and members of older cohorts in turn accounted for almost the entire difference between cohorts in employment change with age. However, The Great Recession does not appear to have depressed wages in subsequent jobs for those who experienced a layoff. In 2010, 17 of the Early Boomers were Not Working and Not Retired or Partially Retired, and 6 were unemployed, leaving at least 11 percent who were not unemployed but not retired or only partially retired. At the recession s peak, half of those who experienced a layoff ended up in the Not Retired or Partially Retired, Not Working category. But only a quarter of those who declared themselves to be Not Retired or Partially Retired, and were Not Working, had experienced a layoff. Most of the jump in Not Retired or Partially Retired, Not Working appears to reflect a change in expectations about the potential or need for future work, a change that is not the result of an actual job loss.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

Retirement Patterns and the Macroeconomy, 1992-2010: The Prevalence and Determinants of Bridge Jobs, Phased Retirement, and Reentry Among Three Recent Cohorts of Older Americans - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Gerontologist, 2015)
Purpose of the Study: Older Americans contemplating retirement today face a very different economic environment than prior cohorts did. This article examines whether the retirement patterns of older Americans have changed as a result. Design and Methods: Using data from 10 waves of the Health and Retirement Study (HRS), we examine the prevalence of bridge jobs, phased retirement, and labor market reentry among 3 recent cohorts of older Americans, from 1992 through 2010. Determinants of retirement transitions are examined using bivariate comparisons and multivariate logistic and multinomial logistic regression models. Results: We find that traditional one-time, permanent exits from the labor force continue to be the exception rather than the rule and that the retirement patterns of the Early Boomers, those on the cusp of retirement during the recent Great Recession, appear to be diverging from those of earlier cohorts. The Early Boomer women, in particular, were more likely than those in previous cohorts, the HRS Core and the HRS War Babies, to move to a bridge job prior to exiting the labor force completely and both Early Boomer men and women were more likely to leave their career jobs involuntarily, with layoffs being a key factor. Implications: The do-it-yourself approach to retirement planning-with individuals managing a large portion of their retirement finances-is now common among older Americans. This change in the retirement environment, combined with a significant and persistent cyclical downturn, may have long-lasting effects and suggests that the concept of retirement in the United States will continue to evolve.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Retirement Timing of Women and the Role of Care Responsibilities for Grandchildren - Lumsdaine, Robin L.; Stephanie J. C. Vermeer (Demography, 2015)
This article considers the potential relationship between providing care for grandchildren and retirement, among women nearing retirement age. Using 47,444 person-wave observations from the Health and Retirement Study (HRS), we find that the arrival of a new grandchild is associated with more than an 8 increase in the retirement hazard despite little overall evidence of a care/retirement interaction. We document that although family characteristics seem to be the most important factors driving the care decision, they are also important determinants of retirement. In contrast, although financial incentives such as pensions and retiree health insurance have the largest influence on retirement, the opportunity cost associated with outside income seems to have little effect on whether a grandmother provides care. There is little evidence of substitution between caring for grandchildren versus providing care for elderly parents or engaging in volunteer activities; grandchild care is instead taken on as an additional responsibility. Our findings suggest that policies aimed at prolonging work life may need to consider grandchild care responsibilities as a countervailing factor, while those policies focused on grandchild care may also affect elderly labor force participation.
Keywords: Adult children; Employment and Labor Force; Healthcare; Retirement Planning and Satisfaction

Revisiting the pathways to retirement: a latent structure model of the dynamics of transition from work to retirement - Tang, Fengyan; Jeffrey A Burr (Ageing and Society, 2015)
A dynamic latent structure model of the work-retirement transition process was identified, focusing on transitions of work and retirement status for men and women aged 51-74 years. Using the Health and Retirement Study data (1998-2004), latent transition analysis was used to identify a best fitting model capturing work-retirement statuses in four samples defined by age and sex. The prevalence of each status was described and the dynamic transition probabilities within the latent structure were examined. Using multinomial logistic regression, socio-demographic, health, family and occupational factors were assessed to determine how each was related to the likelihood of occupying a specific latent status at baseline. Results showed that study respondents were classified into distinct groups: full retiree, partial retiree or part-time worker, full-time worker, work-disabled or home-maker. The prevalence of full retiree status increased, while the prevalence for full-time worker status decreased over time for both men and women. Membership rates in the work-disabled and partial retiree status were generally consistent, with decreased probabilities of the work-disabled status in the older age groups and increased probabilities of partial retirees among younger men. Our findings indicated that many older Americans experience multiple transitions on the pathway to retirement. Future research on late-life labour-force transitions should evaluate the impact of the recent Great Recession and examine the role of larger socio-economic contexts.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Risk-Sharing within Families: Evidence from the Health and Retirement Study - Akin, S. Nuray; Leukhina, Oksana (Journal of Economic Dynamics and Control, 2015)
We report strong empirical support for the presence of self-interest-based risk sharing within extended families in the U.S. A standard model of self-interest-based risk sharing predicts that the share of current family income consumed by a child positively depends on that child's permanent income. It follows that parental transfers to children that are expected to earn more over the period of risk-sharing arrangements should exhibit less sensitivity to the recipient's income fluctuations. We test this distinguishing prediction of self-interest-based risk sharing by exploiting the variation of transfer receipts among siblings, observed over 17 years of longitudinal data spanned by the Health and Retirement Study.
Keywords: Adult children; Health Conditions and Status; Income; Retirement Planning and Satisfaction; Risk Factors

Symptom Trends in the Last Year of Life From 1998 to 2010 A Cohort Study - Adam E Singer; Meeker, Daniella; Joan M Teno; Lynn, Joanne; June R Lunney; Karl A Lorenz (Annals of Internal Medicine, 2015)
Background: Calls for improvement in end-of-life care have focused attention on the management of pain and other troubling symptoms at the end of life. Objective: To describe changes in pain intensity and symptom prevalence during the last year of life from 1998 to 2010. Design: Observational study. Setting: The HRS (Health and Retirement Study), a nationally representative longitudinal survey of community-dwelling U. S. residents aged 51 years or older. Participants: 7204 HRS participants who died while enrolled in the study and their family respondents. Measurements: Proxy-reported pain during the last year of life and other symptoms for at least 1 month during the last year of life. Trends in pain intensity and symptom prevalence were analyzed for all decedents and within the categories of sudden death, cancer, congestive heart failure or chronic lung disease, and frailty. Results: Between 1998 and 2010, proxy reports of the prevalence of any pain increased for all decedents from 54.3 (95 CI, 51.6 to 57.1 ) to 60.8 (CI, 58.2 to 63.4 ), an increase of 11.9 (CI, 3.1 to 21.4 ). Reported prevalences of depression and periodic confusion also increased for all decedents by 26.6 (CI, 14.5 to 40.1 ) and 31.3 (CI, 18.6 to 45.1 ), respectively. Individual symptoms increased in prevalence among specific decedent categories, except in cancer, which showed no significant changes. The prevalence of moderate or severe pain did not change among all decedents or in any specific decedent category. Limitation: Use of proxy reports and limited information about some patient and surrogate variables. Conclusion: Despite national efforts to improve end-of-life care, proxy reports of pain and other alarming symptoms in the last year of life increased from 1998 to 2010.
Keywords: Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

The Transition from Defined Benefit to Defined Contribution Pensions: Does It Influence Elderly Poverty? - Orlova, Natalia S.; Matthew S. Rutledge; April Yanyuan Wu (Boston College, 2015)
The transition from defined benefit (DB) to defined contribution (DC) pension plans has left workers forced to make choices that may decrease their financial resources in retirement: taking lump-sum distributions before retirement that divert funds that could support consumption in retirement, not annuitizing DC benefits, or choosing a single-life annuity over a joint-and-survivor option so that their surviving spouses are left susceptible to income loss. This study examines pension coverage, lump-sum distributions, annuitization, and annuity life options among Health and Retirement Study households observed at ages 65-69 and 75-79 and relates these pension provisions to poverty incidence and the risk of falling into poverty at older ages. The results indicate that households with pensions that are annuitized with the joint-and-survivor life option and that do not take lump-sum distributions before age 55 are best able to avoid income and asset poverty. The results emphasize the importance of making DC plans operate more like DB plans, because the opportunities for these poor financial choices are likely only to grow given the reliance on DC plans as the sole source of employer pension income for future cohorts of retirees.
Keywords: Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Well-being as a measure of inequality among the retirement-age population: An examination of the role of place, migration, and socioeconomic status in shaping happy and healthy older Americans - Henly, Megan (Sociology, 2015)
The proportion of the U.S. population comprised of seniors – those aged 65 and older – is projected to increase from 13% presently to 20% by 2030. With this demographic change, it is important to consider how older residents are faring, which older residents do best, and what communities are doing to support this population. Rather than examining income or wealth as a dependent variable, I predict two measures of well-being among older U.S. residents– one subjective and one objective. By linking survey data of the 50 and older population from the 2010 Health and Retirement Study (HRS) to a variety of county-level statistics from several government databases, this dissertation characterizes each respondent's community with respect to its demographics, economic structure, natural environment, social norms, and presence of community institutions. I examine the impact of individual and community characteristics, as well as whether someone had migrated within the last four years, on predicting well-being. My findings suggest that certain community variables may influence well-being – namely that social institutions may need to be tailored to support the needs of older residents and that counties we think of as privileged counties (with respect to the racial and socioeconomic make-up of its residents) may need to do more to serve older residents. In sum though, these county characteristics have a very minimal impact in predicting the well-being of older residents. The predictors that seemed to matter more were those of the individuals aged 50 and over themselves: their demographic characteristics, employment status, health, and social connectedness all mattered with respect to understanding which individuals were doing well. Whether someone had moved to a new county in the last four years did not appear to offer value to predicting well-being in a causal manner.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Methodology; Public Policy; Retirement Planning and Satisfaction

What Causes Workers to Retire Before They Plan? - Alicia H. Munnell; Geoffrey T. Sanzenbacher; Matthew S. Rutledge (Boston, Boston College, 2015)
This paper explores the extent to which health, employment, family, or finances are associated with earlier-than-planned retirement using the Health and Retirement Study (HRS). The importance of any shock that drives early retirement depends both on its effect on those experiencing it and its prevalence in the population; therefore, the analysis proceeds in two steps. First, a probit regression is used to determine the strength of the relationship between the shocks and earlier-than-planned retirement, controlling for individual characteristics. Second, to incorporate the prevalence of the shock, counterfactual experiments are run to determine how much early retirement would be reduced in the population if these shocks did not occur.
Keywords: Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

What impacts life satisfaction of aging adults following stressful life events?: An examination of the buffering effect of personal resources - Barragan, Cassandra (What impacts life satisfaction of aging adults following stressful life events?: An examination of the buffering effect of personal resources, 2015)
Purpose: Existing research has shown that elders experience changes in their life satisfaction following stressful life events. There is an abundance of literature supporting the predictive nature of not only stressful life events on life satisfaction, but social support, autonomy, and financial security. What the literature is lacking, is examination of the buffering effect of social support, autonomy, and financial security on the relationship between stressful life events and life satisfaction. This study hypothesizes that increases in social support, autonomy, and financial security will buffer the impact of SLEs for elders and thus, they will experience increases in their life satisfaction over time. It is also expected that social support and financial security will buffer differently among Black and White elders. Methods: The public use files of the Health and Retirement Study (HRS) between the years 2006 and 2012 are used to explore the interaction between social support, autonomy, and financial security with stressful life events and the impact on life satisfaction. Linear regression are conducted to explore each buffering impact on life satisfaction over time. Results: The research findings in this dissertation demonstrate that the changes in personal resources; social support, autonomy, and financial security; play an important role in changes in life satisfaction. Additionally, Black and White elders are impacted differently by changes in financial security. In general, the results from this study demonstrate that individuals who have declines in their personal resources following stressful life events also experience declines in their life satisfaction.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction; Women and Minorities

Why Retirees Claim Social Security at 62 and How It Affects Their Retirement Income: Evidence from the Health and Retirement Study - Glickman, Mark M.; Sharon Lynn Hermes (Journal of Retirement, 2015)
Despite higher monthly benefits for those who delay, many people still claim Social Security retirement benefits at age 62, the earliest age of eligibility. This study uses data from the Health and Retirement Study to examine the demographic and occupational characteristics associated with early claiming, as well as the retirement income of early claimers compared with those who delay. The authors find that several work-related factors may cause people to claim Social Security benefits early and suggest they may face challenges in continuing to work at older ages. For example, those who worked in physically demanding blue-collar jobs were 55 more likely to claim benefits prior to their full retirement age, after controlling for other factors, compared with those in all other occupations. Other factors, such as having lower expectations of living to age 75 significantly increase the likelihood of claiming early. The median income for those who claim at full retirement age or later was 45 higher after claiming benefits than for those who claimed early and 33 higher at age 72. Even when comparing early and delayed claimers with similar total income after claiming, average household income for delayed claimers was higher at age 72 than for early claimers.
Keywords: Retirement Planning and Satisfaction; Social Security

Will the Average Retirement Age Continue to Increase? - Matthew S. Rutledge; Gillis, Christopher M.; Anthony Webb (Boston, MA, Center for Retirement Research at Boston College, 2015)
Using Health and Retirement Study (HRS) data, this paper examines how changes in individual workers past and present pension coverage, retirement incentives in Social Security, and retiree health insurance have contributed to retirement decisions for the 1931-1953 birth cohorts. It then uses these findings to project retirement behavior for the 1955-1987 cohorts in the Survey of Income and Program Participation (SIPP). A key assumption is that younger cohorts will have no defined benefit (DB) pensions or retiree health coverage in their future jobs. A key limitation is the assumption of a stable relationship in each successive cohort between each factor and labor market decisions.
Keywords: Employment and Labor Force; Pensions; Retirement Planning and Satisfaction; Social Security

Advance directive completion by elderly americans: A decade of change - Maria J Silveira; Wiitala, W.; John D Piette (Journal of the American Geriatrics Society, 2014)
Objectives: To describe trends in advance directive (AD) completion from 2000 to 2010 and to explore the relationship between AD and hospitalization and hospital death at the end of life. Design: Retrospective cohort study. Setting: Health and Retirement Study (HRS). Participants: HRS participants who died between 2000 and 2010 and were aged 60 and older at death (N = 6,122). Measurements: Trends over time in rates of AD completion, hospitalization before death, and death in hospital are described. The association between trends in AD completion and hospital death was then assessed by comparing nested, multivariable logistic regression models predicting the odds of hospital death over time with and without adjusting for AD status and sociodemographic characteristics. The complex sampling design was accounted for in all analyses. Results: The proportion of decedents with an AD increased from 47 in 2000 to 72 in 2010. At the same time, the proportion of decedents with at least one hospitalization in the last 2 years of life increased from 52 to 71 , and the proportion dying in the hospital decreased from 45 to 35 . After adjusting for confounding by sociodemographic characteristics, the trend in declining hospital death over the decade was negligibly associated with the greater use of ADs. Conclusion: There has been a significant increase in rates of AD completion over the last decade, but this trend has had little effect upon hospitalization and hospital death, suggesting that AD completion is unlikely to stem hospitalization before death. 2014, The American Geriatrics Society.
Keywords: End of life decisions; Retirement Planning and Satisfaction

Age-related trajectories of physical functioning in work and retirement: The role of sociodemographic factors, lifestyle and disease - Stenholm, Sari; Westerlund, Hugo; Salo, P.; Hyde, Martin; Pentti, Jaana; Head, Jenny; Mika Kivimäki; Vahtera, Jussi (Journal of Epidemiology and Community Health, 2014)
Background: Loss of physical functioning is an early marker of declining health in older people. The objective of this study was to examine the age-related trajectories of physical functioning among those in full-time work and retirement. Methods: Based on the Health and Retirement Study, participants who were working full-time or were in full-time retirement and 65-85 years of age during the follow-up period from 1992 to 2010 were included (n=17 844, n of observations from repeated measures in full-time work 5891 and in retirement 57 117). Details of physical functioning were asked about at all study phases and 10 items related to mobility and activities of daily living were summed to obtain a physical functioning score (0-10). Results: The number of physical functioning difficulties increased every 10 years by 0.17 (95 CI 0.04 to 0.29) when in full-time work and by 0.46 (95 CI 0.41 to 0.50) in retirement after adjusting for age, sex, race, education, total wealth, Body Mass Index, smoking, physical activity and number of diseases. Factors that were associated with a significantly greater increase in number of physical functioning difficulties in full-time work and retirement include lifestyle-related risks and chronic conditions. Conclusions: Physical functioning declines faster in retirement than in full-time work in employees aged 65 years or older and the difference is not explained by absence of chronic diseases and lifestyle-related risks. 2014 by the BMJ Publishing Group Ltd.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Bequests and Informal Long-Term Care: Evidence from the HRS Exit Interviews - Groneck, Max; Krehl, Frederic (Cologne, Germany, University of Cologne, 2014)
Informal care of children for their frail elderly parents may induce parents to compensate their children for their help. To test this hypothesis, we use the Exit Interview from the Health and Retirement Study. Our results show that caregiving has a significant positive impact on the incidence and the amount of received bequests both at the extensive and intensive margin of help. Three pieces of evidence suggest exchange motives rather than altruism to be the main source for this outcome. First, financially more well off children are more likely to receive an inheritance. Second, we find that a positive impact of help on bequest requires a written will as a contract between the parent and the helping child. Third, our results are even more pronounced when employing a fixed effects model to control for family altruism.
Keywords: Adult children; Healthcare; Retirement Planning and Satisfaction

Characterizing the Genetic Influences on Risk Aversion - Harrati, Amal (Biodemography and Social Biology, 2014)
Risk aversion has long been cited as an important factor in retirement decisions, investment behavior, and health. Some of the heterogeneity in individual risk tolerance is well understood, reflecting age gradients, wealth gradients, and similar effects, but much remains unexplained. This study explores genetic contributions to heterogeneity in risk aversion among older Americans. Using over 2 million genetic markers per individual from the U.S. Health and Retirement Study, I report results from a genome-wide association study (GWAS) on risk preferences using a sample of 10,455 adults. None of the single-nucleotide polymorphisms (SNPs) are found to be statistically significant determinants of risk preferences at levels stricter than 5 x 10(-8). These results suggest that risk aversion is a complex trait that is highly polygenic. The analysis leads to upper bounds on the number of genetic effects that could exceed certain thresholds of significance and still remain undetected at the current sample size. The findings suggest that the known heritability in risk aversion is likely to be driven by large numbers of genetic variants, each with a small effect size.
Keywords: Genetics; Net Worth and Assets; Retirement Planning and Satisfaction; Risk Taking

Contribution of Leisure-Time Physical Activity on Psychological Benefits Among Elderly Immigrants - Kim, Junhyoung; Sanghee Chun; Jinmoo Heo; Lee, Sunwoo; Areum Han (Applied Research in Quality of Life, 2014)
Research provides evidence that leisure-time physical activity engagement promotes health and well-being among older adults. In this study, using data released from the Health and Retirement Study (HRS) in 2008, we focused on the exploration of the relationship between leisure-time physical activity and psychological benefits such as positive affect, optimism, psychological well-being, and life satisfaction among elderly immigrants. The results of this study demonstrated that leisure-time physical activities play an important role in gaining psychological benefits. This finding provided further evidence that leisure-time physical activities provides rich opportunities for elderly immigrants to experience psychological benefits, which may contribute to quality of life and successful aging.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Determinants of socioeconomic inequalities in subjective well-being in later life: a cross-country comparison in England and the USA - Jivraj, S.; James Nazroo (Quality of Life Research, 2014)
Purpose To explore country-specific influences on the determinants of two forms of subjective well-being (life satisfaction and quality of life) among older adults in England and the USA. Methods Harmonised data from two nationally representative panel studies of individuals aged 50 and over, the English Longitudinal Study of Ageing (ELSA) and the Health and Retirement Study (HRS), are used. Linear regression models are fitted separately for life satisfaction and quality of life scales using cross-sectional samples in 2004. The ELSA sample was 6,733, and the HRS sample was 2,300. Standardised coefficients are reported to determine the country-specific importance of explanatory variables, and predicted values are shown to highlight the relative importance of statistically significant country-level interaction effects. Results Having a disability, been diagnosed with a chronic conditions or having low household wealth are strongly associated with poorer life satisfaction and quality of life. These statistical effects are consistent in England and the USA. The association of years spent in education, however, varied between the two countries: educational inequalities have a greater adverse effect on subjective well-being in the USA compared with England. Conclusion Interventions are required to counterbalance health and socioeconomic inequalities that restrict sections of the population from enjoying satisfying and meaningful lives in older age. The differential association between education and well-being in England and the USA suggests that the provision of welfare benefits and state-funded public services in England may go some way to protect against the subsequent adverse effect of lower socioeconomic status on subjective well-being.
Keywords: Cross-National; Expectations; Health Conditions and Status; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Differential Aging-In-Place - So Jung Park (Differential Aging-In-Place, 2014)
This three-essay dissertation explores components of aging–in-place among adults living alone aged 65 and older using nationally representative data from the Health and Retirement Study (HRS). Drawing on the Person-Environment Fit and Person-Centered perspectives, the overall goal is to examine the extent to which three dimensions of aging-in-place, namely the environment, the older individual, and individual agency (efficacy), are inter-related in order to enable independent living among this subgroup of older persons. Together, these three components help to characterize the heterogeneity of the life contexts and personal resources of older adults who live alone and are aging-in-place. The first paper explored to what degree the environment and health subgroups are associated with subjective well-being among older adults living alone. Through clustering analysis, the four health subgroups of sensory-cognitive impaired, physically impaired, frail, and healthy were identified. The intersection of these health subgroups with three environmental contexts that reflect different levels of physical and social support were examined. The frail group was more likely to show depressive symptoms if they lived in a physically average and socially unsupported environment. The sensory-cognitive impaired group was more likely to report depressive symptoms when they lived in a physically-unsupported but socially-supported environment. The second paper asked if changes in depressive symptomatology over time are mediated by changes in perceived control. The findings confirm a stronger negative influence of membership in a vulnerable health subgroup on perceived control, which in turn affects depressive symptoms over time. Among the environmental contexts, only greater social support was associated with a decrease in depressive symptoms over time via perceived control. The third paper extended the empirical examination of proposals drawn from the Person-Environment Fit perspective. I asked how much environments moderate the effects of health profiles and low socioeconomic status on mortality risk. The results show that for individuals in the sensory-cognitive impaired and physically impaired groups, broader social network was associated with an increased risk of death. In addition, the study revealed that older adults living alone with low socioeconomic status who live in a senior housing environment had a reduced risk of death.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Does Working for Oneself, not Others, Improve Older Adults Health? An Investigation on Health Impact of SelfEmployment - Zhang, Ting (American Journal of Entrepreneurship, 2014)
This paper examines the health impact of being self-employed versus working for others among older adults (aged 50 ) and its implications. Facing an aging workforce, self-employment at older ages may provide an economic benefit via an alternative to retirement. However, little research has examined the health effects of self-employment in later life. Relying on the latest 7 waves of data from the Health and Retirement Study, this study comprehensively examines health using a 29-item index to measure the impact of self-employment status on changes in older adults overall health. We conduct a 2-stage generalized panel data instrument variables regression model, with lagged values to control potential endogeneity and simultaneity issues. We find self-employment compared to wage-and-salary jobs result in better health, controlling for job stress and work intensity, cognitive performance, prior health conditions, socioeconomic and demographic factors. This positive self-employment impact stands our in knowledge-based industry sectors. In labor intensive industry sectors such as Durable Goods Manufacturing, self-employed older adults' more gradual retirement seems to result in a health advantage over wage-and-salary employees. Limitations of the study and future research directions are discussed.
Keywords: Employment and Labor Force; Health Conditions and Status; Other; Retirement Planning and Satisfaction

Dying in America: Improving Quality and Honoring Individual Preferences Near the End of Life (National Academies Press, 2014)
Keywords: End of life decisions; Health Conditions and Status; Healthcare; Public Policy; Retirement Planning and Satisfaction

Dynamic models of individual and household retirement behavior - Merkurieva, Irina S. (Dynamic models of individual and household retirement behavior, 2014)
Chapter 1: Estimating the Returns of Attending a Selective University on Earnings using Regression Discontinuity with Multiple Admission Cutoffs. Abstract: The first chapter estimates the effect attending a selective university has on earnings. I show that using the admission cutoffs of two related majors offered by selective universities is enough to identify the isolated "university effect" on wages. To do so, I propose a novel identification framework using the cutoffs of two related majors in a regression discontinuity design that distinguishes the effect of graduating from a selective university from the effects of the confounding factors correlated with the student application and enrollment decision. This design requires a system with strict cutoffs and simultaneous decision making of university and major upon application. The university admission system in Chile has a strict admission criteria based solely on the university selection test and high school grades, and has students choose their school and major simultaneously. This admission system leads naturally to a regression discontinuity design because we can compare the earnings of those above and below the cutoff to estimate the "university effect". My main findings suggest that, on average, attending a selective university in Chile significantly increases earnings, that is, selective universities not only select the best students, but also play a role increasing their future earnings. Chapter 2: The Effects of Private High Schools, University Rankings and Employer Learning on Wages in Chile. Abstract: The second chapter studies the effects of attending a private high school, university ranking and employer learning on wages. My empirical strategy is based on the Mincer-type wage regressions. I carry out my analysis using individual-level data from Chile. I find a large and significant effect on wages at the beginning of workers' careers from attending a private high school and from attending a highly ranked university. These findings can be rationalized by the statistical discrimination and employer learning model since the effects of attending a private high school or highly ranked university decrease with experience. I construct an employer learning model to explain these decreases and find employers decrease by fifty percent the weight they place on university ranking when setting wages in three years. My findings further indicate that incorporating university admission test percentile rankings in employment applications can significantly improve the market's ability to appropriately assign wages by decreasing the information gap between potential employees and employers. Chapter 3: College-Major Choice to College-Then-Major Choice. Abstract: Many countries use college-major-specific admissions policies that require a student to choose a college-major pair jointly. Motivated by potential student-major mismatches, we explore the equilibrium effects of postponing student choice of major. We develop a sorting equilibrium model under the college-major-specific admissions regime, allowing for match uncertainty and peer effects. We estimate the model using Chilean data. We introduce the counterfactual regime as a Stackelberg game in which a social planner chooses college-specific admissions policies and students make enrollment decisions, learn about their fits to various majors before choosing one. We compare outcomes and welfare under the two different regimes.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-09-20 First page - n/a
Keywords: Adult children; Cross-National; Employment and Labor Force; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

The effect of retirement on alcohol consumption: results from the US Health and Retirement Study - Wang, Xu; Steier, Jessica B.; William T Gallo (The European Journal of Public Health, 2014)
Background: Prior research examining the association between retirement and alcohol consumption is inconsistent with respect to salience, direction and magnitude. Reasonable conceptual arguments for both positive (e.g. coping, introduction of leisure time) and negative (e.g. severance of work-related social relationships) changes further complicate investigations of this critical association, as do differences in study design, national setting and measurement of alcohol use. Methods: This prospective longitudinal study analyses 2-year wave-pairs drawn from seven waves (14 years) of data from the US Health and Retirement Study to assess the effect of complete retirement on weekly alcohol consumption (n = 9979 observations; 4674 unique participants). We use multiple regression analysis in a two-period follow-up design and account for potential selection bias and reverse causality not addressed in prior research on this topic. Results: We find that retirement is positively associated with subsequent weekly alcohol consumption for men who reported drinking at both follow-up and the prior study wave ( = 1.9, 95 confidence interval = 0.43 3.36). No association was observed among women. Conclusion: Our results suggest that health care professionals should monitor the drinking habits of retired men, as older individuals are particularly susceptible to the adverse effects of heavy alcohol use.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

The Effect of Sleep Medication Use and Poor Sleep Quality on Risk of Falls in Community-Dwelling Older Adults - Min, Yaena (The Effect of Sleep Medication Use and Poor Sleep Quality on Risk of Falls in Community-Dwelling Older Adults, 2014)
The work presented in this dissertation focuses on the association between sleep medication use, poor sleep, and falls in community-dwelling adults 65 years or older. Sleep complaints and the consumption of medications to aid sleep are common in older adults. Psychotropic medications, such as sedative hypnotics, are associated with risk of falls in older adults. However, very few studies have assessed the impact of poor sleep and sleep medication use on the risk of falls in community-dwelling older adults. In the first project, a cross-sectional analysis of the Health and Retirement Study (HRS) 2010 data was conducted to determine the prevalence of sleep problems, sleep medication use and falls; and to evaluate the association between sleep problems, sleep medication use, and falls in community-dwelling older adults. A multiple logistic model adjusted for covariates was used. In the sample of community-dwelling older adults, 35.8% had reported a fall and 40.8% had reported sleep problems in the past two years. Sleep medication use was reported by 20.9% of the older adults. Older adults who had sleep problems and took sleep medications had a significantly higher risk of falls compared with older adults who did not have sleep problems and did not take sleep medications. The other two groups, older adults who had sleep problems and did not take sleep medications, and those who did not have sleep problems and took sleep medications also had a significantly greater risk for falls. The second project was a prospective cohort study of independently-living older adults from senior congregate housing. The effect of combined poor sleep quality and sleep medication use on risk of falls was assessed using logistic regression modeling. In this study of 113 community-dwelling older adults, 46.9% had at least one fall, and 62.8% had poor sleep quality. Sleep medication use was reported by 44.2% of the older adults. Older adults with poor sleep quality and sleep medication use had a significantly increased risk of falls compared with older adults with good sleep quality and no sleep medication use. Older adults with good sleep quality and sleep medication use, and those with poor sleep quality and no sleep medication use did not have a significantly greater risk for falls. In conclusion, poor sleep added to sleep medication use significantly increased the risk of falls in community-dwelling older adults. The research undertaken in this dissertation was the first to evaluate the associations between poor sleep, use of sleep medications, and falls in community-dwelling older adults.
Keywords: Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

The effect of state non-group health insurance market regulations on labor and insurance markets: From theory to policy - Lin, Lee-Kai (The effect of state non-group health insurance market regulations on labor and insurance markets: From theory to policy, 2014)
Health insurance coverage among the working nonelderly population is highly concentrated on employer sponsored health insurance (ESI). State governments in the early 1990s and the Federal Health Insurance Portability and Accountability Act (HIPAA) of 1996 made efforts to provide health insurance to individuals who do not have access to ESI by regulating the non-group market. In the first chapter, I propose a theoretical framework to analyze the effects of state non-group health insurance market regulations on the market equilibrium and on the job choices focusing on the guaranteed issue, rating restriction and the combination of these two regulations. In the second chapter I estimate the impact of these regulations on the retirement decision by difference-in-difference regressions using data collected from the Health and Retirement Study (HRS) and the Current Population Survey (CPS). My results provide evidence that guaranteed issue significantly increases the retirement rate by 1.2 percentage points. Guaranteed issue several plans with rating restrictions also significantly increases retirement rate by 1.5 percentage points. Workers who have chronic health problems are more likely to retire in response to both types of regulations than the healthy. I study the effects of these state regulations on the non-group health insurance coverage and on the transition from group to non-group health plans in the third chapter. The results suggest that guaranteed issue alone encourages individuals to transition from group to non-group health coverage. If guaranteed issue, together with rating restrictions, is forced upon some of the health plans, the transition from group to non-group coverage would increase while the non-insured also increases. If all plans are guaranteed issue with rating restrictions, non-group coverages are not affected but more people become uninsured.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2015-01-31 First page - n/a
Keywords: Insurance; Methodology; Public Policy; Retirement Planning and Satisfaction

Effects of cost-related medication nonadherence on financial health and retirement decisions among adults in late midlife - Gail A Jensen; Yong Li (Journal of Pharmaceutical Health Services Research, 2014)
Objectives Suboptimal adherence to prescribed medications due to cost is known to adversely affect physical health. In this study, we examine whether cost-related nonadherence (CRN) also affects financial health , e.g. an individual's personal finances or the timing of their retirement. Methods We examine this issue for 2927 adults in late midlife with chronic medical conditions who participated in the Health and Retirement Study and who reported regularly taking medication(s) for their condition over the period 1994 to 2004. We hypothesize CRN may indirectly influence financial health by contributing to the occurrence of negative health shocks. We estimate two sets of models, one to quantify the effects of CRN on the occurrence of adverse health events, and another to quantify the effects of adverse health events on personal finances in 2004 and the timing of retirement. We then derive estimates of the indirect effects of CRN on financial health and on retirement decisions. Key findings Among adults in late midlife, CRN contributes significantly to reduced earnings and premature retirements. These effects happen because CRN raises the risk that serious health shocks occur over time, and such adverse events subsequently limit an individual's ability to continue working and accumulating wealth. Conclusions CRN can threaten more than just personal health. In late midlife, CRN can threaten an individual's ability to continue working and saving towards retirement.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

End-of-life care planning and its implementation - Inoue, Megumi (End-of-life care planning and its implementation, 2014)
End-of-life care planning is an opportunity for people to express how they want to spend the final stage of their lives by directing what type of medical treatment they wish or do not wish to receive. The completion of such planning is a way to exercise their autonomy, which is one of the fundamental ethical principles in medicine in the United States. Many older adults in the U.S., however, do not have such a plan or even discuss the topic with anyone. In order to understand the circumstances in which end-of-life planning is enacted, this study investigated two important research questions: (1) What are the sociodemographic and psychosocial factors that enhance or impede the completion of end-of-life planning? (2) How consistent is the content of a living will with the person's actual dying experience? These research questions were developed and examined as an application of expectancy theory, which explains the concepts of motivation and action. A series of logistic regression analyses were conducted. This study analyzed data from the Health and Retirement Study (HRS), which is a nationally representative sample of Americans over the age of 50. The analytic subsample included those who died between 2000 and 2010 ( N = 6,668). The study found that persons who were older, who identified themselves as White, who had higher levels of income and education, and who were widowed or separated were more likely to be motivated to complete end-of-life planning. A higher level of sense of mastery was specifically relevant to documentation of living wills. On the other hand, a lower level of religiosity was specifically associated with having a durable power of attorney for health care. In addition, there was a clear connection between a request for palliative care and less troubling pain. Implications include conducting a community- or workplace-based public educational campaign, incorporating a culturally tailored approach for racial/ethnic minorities (e.g. faith-based interventions), using advance directives written in easy to understand language (e.g. Five Wishes), and funding Medicare provision for end-of-life care consultations between doctors and patients during annual physical exams.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-10-14 First page - n/a
Keywords: End of life decisions; Expectations; Healthcare; Medicare/Medicaid/Health Insurance; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Essays on health and retirement - Basu Roy, Subhasree (Essays on health and retirement, 2014)
The essays in this dissertation explore issues related to health and retirement of older Americans, using longitudinal data on older Americans from ten waves of the Health and Retirement Study (1992-2010). The first essay explores the effect of both subjective and relatively more objective physical and mental health conditions on the probability of exit from full-time employment. Eight health indices (factors) are created from a wide range of health measures by principal component analysis. The effect of these health factors on the time until exit from full-time employment is empirically examined in a proportional hazard model. Single and competing risk specifications are estimated that allow for multiple spells of full-time employment and control for unobserved heterogeneity. The main results suggest that increase in functional limitation factor makes an individual more likely to exit via any route in general and the complete retirement route in particular. For mental health problems, increase in the depression factor increases the likelihood of exit from full-time employment via the complete retirement, part-time work and unemployment routes. While increase in cognitive disorders factor has no significant effect on the likelihood of exit via complete retirement, but increases the likelihood of exit via the disability route. These results have implications for public policies targeted towards retaining older workers within the labor market. The second essay examines the effect of retirement on post retirement physical and mental health and the extent to which the effects differ across these different health outcomes. The inherent issue of reverse causality between health and retirement that leads to endogeneity is addressed by using multiple sample stratification and instrumental variable estimation strategies. The stratified samples include individuals who are physically and mentally healthy prior to their retirement so that pure effect of retirement on post retirement health may be found. Five different instruments for complete retirement are also used to deal with endogeneity. The sample stratification results unanimously indicate that complete retirement has adverse effect on post retirement physical and mental health. While the instrumental variables approach results are mixed and are based on the choice of instrument for complete retirement.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-11-21 First page - n/a
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Public Policy; Retirement Planning and Satisfaction; Risk Taking

Financial Literacy Among American Indians and Alaska Natives - Murphy, John L.; Gourd, Alicia; Begay, Faith (Social Security Administration, Office of Retirement and Disability Policy, Office of Research, Evaluation, and Statistics, 2014)
Many Americans lack important financial skills and knowledge of critical concepts that can help ensure sound retirement planning and future economic security. Prior research has suggested that low levels of financial literacy are particularly acute among certain groups such as women, blacks, and persons with lower levels of educational attainment (Dunaway-Knight and others 2012; Hung, Parker, and Yoong 2009; Huston 2010; Lusardi 2008; A. Murphy 2005). This study adds to previous work on financial literacy among minority groups by examining the American Indian and Alaska Native (AIAN) population. Prior research on AIANs has often used convenience samples of university students and has been limited by the lack of nationally representative samples (for example, Anderson and others (2010); Chen and Volpe (2002); Mandell (2009); and Mandell and Klein (2007)). In this note, we use a nationally representative sample from the Health and Retirement Study (HRS) to analyze how AIAN respondents scored on the 2008 HRS financial literacy module compared with white respondents (reference group) and other minority groups. The HRS is one of the foremost sources of information on the population aged 50 or older. We use an 18-item financial sophistication and investment decision-making (FSIDM) questionnaire.1 Each correct answer receives one point; thus, the scale ranges from 0 to 18, with higher values representing more financial sophistication. The FSIDM questionnaire has been widely used in other studies to investigate financial literacy (for example, Agarwal and others (2009); Lusardi (2008); Lusardi and Mitchell (2007, 2008, 2011); and Lusardi, Mitchell, and Curto (2009)). Researchers have primarily used the FSIDM questionnaire to examine overall knowledge of financial literacy across broad swaths of the older U.S. population by sex, age, income, and race. However, racial differences in the aforementioned studies have been primarily limited to those between blacks and whites. Our analysis finds that the mean number of questions that AIAN respondents correctly answered was significantly lower than the comparable figures for white, black, and Asian respondents. For each of the 18 questions in the module, we find that there are specific financial literacy topics in which the knowledge gap between AIANs and other race/ethnic groups was particularly large. However, a limited sample size constrains this analysis, and additional data and research are needed to fully address financial literacy within the AIAN population.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

Financial literacy and financial sophistication in the older population - Annamaria Lusardi; Olivia S. Mitchell; Vilsa Curto (Journal of Pension Economics and Finance, 2014)
Using a special-purpose module implemented in the Health and Retirement Study, we evaluate financial sophistication in the American population over the age of 50. We combine several financial literacy questions into an overall index to highlight which questions best capture financial sophistication and examine the sensitivity of financial literacy responses to framing effects. Results show that many older respondents are not financially sophisticated: they fail to grasp essential aspects of risk diversification, asset valuation, portfolio choice, and investment fees. Subgroups with notable deficits include women, the least educated, non-Whites, and those age 75 . In view of the fact that retirees increasingly must take on responsibility for their own retirement security, such meager levels of knowledge have potentially serious and negative implications.
Keywords: Demographics; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Health and Living Arrangements among Older Adults in Diverse Social and Cultural Contexts - BoRin Kim (Health and Living Arrangements among Older Adults in Diverse Social and Cultural Contexts, 2014)
This dissertation consists of three empirical papers on health and living arrangements among older adults. It aims to investigate the dynamic associations between living arrangements and the physical/mental health among older adults, and to examine how these associations are influenced by various cultural factors, such as age cohort, race/ethnicity, and nationality. To accomplish these specific aims, two nationally representative panel data for older populations are examined: the 2006-2008 Korean Longitudinal Study of Ageing and the 1998-2010 Health and Retirement Study. The first study explores the effects of physical/mental health on transitions in living arrangements among older Koreans. The effects of health on living arrangements vary by marital status; while unmarried elders with health problems are more likely to live with their children, married elders tend to live near their children. The second study investigates how different types of living arrangements influence physical function and psychological well-being in old age, and how these effects differ between the old-old and the young-old. The results show that co-residence does not always positively influence health and well-being, particularly among the young-old. Finally, the third study analyzes the trajectories of living arrangements among older Americans over a twelve-year period. This study examines to what extent physical/mental health influence the trajectories of living arrangements, and if there are racial/ethnic variations. Older Americans are more likely to move closer in proximity to one of their children, but they do not usually move into the same household. The onsets and aggravations of health problems affect changes in living arrangements, and these linkages are stronger among Whites than African Americans and Hispanics. The findings highlight the importance of social and cultural contexts in understanding the linkages between health and living arrangements in old age. Given the increase of rapidly aging societies, understanding the dynamic linkages between health and living arrangements is important for social, health, and long-term care policies. My dissertation can contribute to a clearer identification of the groups of elderly who are at high risk for health problems and social isolation as well as to the design and implementation of service programs for these high-risk groups.
Keywords: Adult children; Cross-National; Demographics; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction

A holistic approach to understanding retirement preparedness - Yook, Miyoung (A holistic approach to understanding retirement preparedness, 2014)
There has been increased interest in understanding the significant disparity in U.S. households' retirement preparedness due to concern about the stability of Social Security benefits, the shift from defined benefit plans to defined contribution plans, and the decreased rate of saving. This dissertation explores a model that can be utilized to understand and enhance retirement preparedness by individuals, educators, practitioners, and policy makers. Retirement preparedness was measured in two different ways--using the income replacement rate and the capital accumulation ratio--for two separate empirical models. The general conceptualization of the framework is based on the retirement planning work of Hershey (2004). This study utilized the 2008 Rand version (Version L) of the Health and Retirement Study (HRS) and 2006, 2008, and 2010 psychosocial and lifestyle questionnaire. The Rand HRS data file is a user-friendly version of the HRS data and contains cleaned data. The two hierarchical regressions were used to analyze the association between retirement preparedness and the theoretical concepts of cultural influence, environmental influence, task components, and psychological influence. Entering the conceptual components as four separate blocks allows for observation of changes in R 2 based on the addition of the conceptual components. This research investigates the following research questions: (a) How strongly are cultural influences associated with retirement preparedness?, (b) How strongly are environmental influences associated with retirement preparedness?, (c) How strongly are task components associated with retirement preparedness?, and (d) How strongly are psychological influences associated with retirement preparedness? Current retirement planning practices are often based on structural profiles such as financial resources, financial needs, and goals. The holistic approach used for this dissertation is based on the awareness of the influence of psychological and personal factors on financial decision making. The results showed that the variables positively associated with the retirement income replacement rate were self-perception of aging, homeownership, stock ownership, household pension ownership, IRA/Keogh ownership, and business ownership. Pre-retirement income log had a highly negative association with the retirement income replacement ratio. Big Five personality and perceived mastery were not significant. However, when asset ownership (excluding homeownership) was not controlled, conscientiousness and low emotional stability became significant and showed a positive association for conscientiousness and a negative association for low emotional stability. Self-perception of aging was a significant psychological variable in both models. The significant variables from the second model measured by the capital accumulation ratio were asset ownerships including homeownership, stock ownership, IRA ownership, real estate ownership, and business ownership. None of the psychological variables were significant, except for agreeableness, which was related negatively to the capital accumulation ratio when the asset ownerships (excluding home ownership) were not controlled. Other significant variables, when asset ownership was not controlled, were home ownership, pre-retirement income log, being non-White.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-11-24 First page - n/a
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction; Social Security

How Does Household Expenditure Change With Age for Older Americans? - Sudipto Banerjee (EBRI Notes, 2014)
Retirement saving involves a lot of unknowns, the most important being not knowing how much money will be needed in retirement. Although it is impossible to predict the retirement expenses of any particular household, the average amounts spent by current retirees can serve as important benchmarks for individual savers as well as for industry experts and policymakers. This paper examines the expenditure pattern of the older segment of the U.S. population. The majority of the households studied here have either reached retirement age or are on the cusp of retirement. The data come from the Health and Retirement Study (HRS) and the Consumption and Activities Mail Survey (CAMS), which is a supplement of the HRS. CAMS contains detailed spending information on 26 nondurable and six durable categories, and it follows the same group of people over time. Using this information coupled with the income information available in the HRS, this study summarizes the consumption behavior of the American elderly. The primary goal is to examine how overall spending and spending in different categories change with age. Home and home-related expenses is the largest spending category for every age group. Health expenses increase steadily with age. In 2011, households with at least one member between ages 50 and 64 spent 8 percent of their total budget on health items, compared with 19 percent for those age 85 or over. Health-related expenses occupy the second-largest share of total expenditure for those ages 75 or older. The two components of household expenditures that show a declining pattern across age groups are transportation expenses and entertainment expenses. Food and clothing expenses (as a share of total expenditure) remain more or less flat across the different age groups. There is a large increase in spending at the 95th percentile for those ages 90 or older, which can be attributed to very high health care expenses.
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Net Worth and Assets; Retirement Planning and Satisfaction

How does personality contribute to retirement savings? - Chan, Wai (How does personality contribute to retirement savings?, 2014)
The aim of this dissertation was to explore how personality factors explain retirement savings over time. Past studies did not systematically examine individual characteristics on financial preparation for retirement or did not adopt a monetary outcome to exemplify retirement investments. Thus, this dissertation modeled two outcomes for retirement savings, i.e., Individual Retirement Accounts (IRAs) ownership and IRA balances. Guided by the Investor Behavior Model and the Behavioral Economics Perspective, conscientiousness and personal mastery were hypothesized to bolster IRA investments, while agreeableness and perceived constraints were hypothesized to undermine IRA investments. Multilevel model techniques were applied to depict the trajectory of IRA investments with longitudinal data from the Health and Retirement Study (HRS 2006, 2008, 2010). Findings were partly consistent with hypotheses. The Individual Sample ( N = 4,117) documented that higher levels of conscientiousness and personal mastery predicted greater odds of IRA ownership. Perceived constraints were associated with lower odds of IRA ownership, while agreeableness was linked to lower IRA balances. Saving horizons and financial controls were found to partially mediate the relationship between personality factors and IRA investments. Based on the findings from the Individual Sample, a Spousal Sample ( N = 4,257) was developed to examine whether perceived spousal relationship qualities accounted for IRA investments above and beyond personality factors. In addition, perceived spousal relationship qualities were explored to mitigate or accentuate the effects of personality factors. Relationship strain was found to undermine IRA ownership while spousal support was associated with higher IRA balances. Interaction effects of spousal relationships were detected only for exploratory personality traits (i.e., openness and extraversion) for IRA ownership. Overall, findings provided empirical support for theoretical perspectives that include personality factors as impacting retirement preparations. Likewise, personality factors demonstrated differential effects on IRA outcomes. With regard to practical implications, this dissertation provides educators and policymakers with insights to improve the existing financial education and social welfare systems.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2015-01-17 First page - n/a
Keywords: Adult children; Health Conditions and Status; Methodology; Pensions; Public Policy; Retirement Planning and Satisfaction

How does retiree health insurance influence public sector employee saving? - Robert Clark; Olivia S. Mitchell (Journal of health economics, 2014)
Economic theory predicts that employer-provided retiree health insurance (RHI) benefits have a crowd-out effect on household wealth accumulation, not dissimilar to the effects reported elsewhere for employer pensions, Social Security, and Medicare. Nevertheless, we are unaware of any similar research on the impacts of retiree health insurance per se. Accordingly, the present paper utilizes a unique data file on respondents to the Health and Retirement Study, to explore how employer-provided retiree health insurance may influence net household wealth among public sector employees, where retiree healthcare benefits are still quite prevalent. Key findings include the following:
Keywords: Demographics; Pensions; Public Policy; Retirement Planning and Satisfaction

How is economic hardship avoided by those retiring before the Social Security entitlement age? - Kevin Milligan (Journal of Pension Economics and Finance, 2014)
Governments around the world are reacting to extended lifespans and troubled pension finances by increasing the age of retirement benefit entitlement. This paper studies those who retire before the age of full pension entitlement in the USA using data drawn from the Health and Retirement Study. The major finding is that four out of five people who have zero earnings at pre-entitlement ages are able to find a way to lift their incomes over the poverty line. For men, pension and annuity income are important while for women, spousal income helps most to get them over the line.
Keywords: Health Conditions and Status; Income; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Immigrants and retirement resources - P. Sevak; Lucie Schmidt (Social Security Bulletin, 2014)
The extensive literature documenting differences in wages between immigrant and native-born workers suggests that immigrants may enter retirement at a significant financial disadvantage relative to workers born in the United States. However, little work has examined differences in retirement resources and retirement security between immigrants and natives. In this article, we use data from the Health and Retirement Study linked with restricted data from the Social Security Administration to compare retirement resources of immigrants and natives. Our results suggest that while immigrants have lower levels of Social Security benefits than natives, when holding demographic characteristics constant, immigrants have higher levels of net worth. The estimated immigrant differentials vary a great deal by number of years in the United States, with the most recent immigrants being the least prepared for retirement.
Keywords: Demographics; Net Worth and Assets; Retirement Planning and Satisfaction; Social Security

Improving retirement security in the United States - Burns, Michael J. (Improving retirement security in the United States, 2014)
The public media, surveys of workers and the general public have indicated increasing concern with retirement security in the face of lengthening life expectancies, the costs of retirement living, and anxieties over the reported insufficiency of retirement savings balances to fund a decent retirement. The major questions of this dissertation are, first, whether the major parts of the United States retirement income security system, namely Social Security and the private pension system, are currently providing sufficient retirement security for all retirees? And second, how could this national system be reformed, if necessary, to provide greater retirement income security? Because the problem of elderly security is an international one, the United States retirement income security system is compared to those of some of the other economically advanced countries of the OECD (Organization for Economic Cooperation and Development), and more particularly, France, Sweden and Japan. An assessment of the contrasting design elements and retirement income security outcomes is made. Recommendations for reform of the United States system are offered which are based on an appraisal of the peculiar strengths and weaknesses of the United States system as well as on any promising design elements of the other examined national systems that might be adaptable to the United States.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-10-22 First page - n/a
Keywords: Cross-National; Health Conditions and Status; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Internet use and mental health/well-being in old age: Exploring the roles of social integration and social support - Berkowsky, Ronald W. (Internet use and mental health/well-being in old age: Exploring the roles of social integration and social support, 2014)
The escalating pressures put on the US healthcare system, due in part to the growing needs of the expanding older adult population, has motivated research dedicated to more fully understanding the mental health and mental well-being needs of this population and ways to address these needs and alleviate the pressure on the healthcare system. An increasing area of interest is in examining the role information and communication technologies (ICTs), such as Internet-connected computers and smartphones, in the health of older adults. Research has shown that ICTs can successfully be used to help treat, manage, and cope with mental health/well-being issues, but previous literature also finds that ICTs can contribute to mental health/well-being outcomes more directly. While studies have shown that ICTs may benefit older adults with regards to mental health/well-being, less is known through what mechanisms this relationship is enacted. This study uses data from the Health and Retirement Study to compare Internet-using older adults (aged 65+) with non-users on depression, life satisfaction, loneliness, personal growth, and purpose in life. Specific attention is given to examining the potential mediating roles of social integration (i.e., quantity of social ties) and social support (i.e., quality of social ties), as a Durkheimian perspective of Internet use argues that Internet use can be both beneficial and detrimental to an individual's social life, and changes in social life through Internet use can in turn affect mental health/well-being. Results of cross-sectional and longitudinal analyses finds Internet users, compared to non-users, typically enjoy more favorable mental health/well-being outcomes. Measures of social integration and social support are found to mediate the relationship between Internet use and mental health/well-being, but only partially. Additional analyses find that demographic characteristics, such as income and functional limitations, moderate the relationship between Internet use and mental health/well-being in older adults. The findings suggest that ICT interventions that incorporate elements that help older adults maintain social contacts and develop new ones may lessen mental health/well-being issues and the burdens associated with them.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-06-21 First page - n/a
Keywords: Adult children; Health Conditions and Status; Other; Retirement Planning and Satisfaction

Involuntary Retirement, U.S. Social Security Program Participation and the Great Recession - Seligman, Jason S. (Public Finance and Management, 2014)
Involuntary retirement covers economic and health related dislocations. Over 1992-2011, three-in-ten retirees in the Health and Retirement Study (HRS) report an involuntary retirement. Roughly half of these involuntary retirements are health-related. Following the Great Recession, involuntary retirement in the U.S. grew much faster than voluntary retirement. I find that while the population receiving Social Security retirement benefits grew 6 slower than average, the population receiving no public retirement or disability benefits grew 79 faster than average and the population reporting health-related involuntary retirement grew 270 faster than average. While incomes are found to have fallen for all retiree groups, those reporting health-related involuntary retirements are found to have retirement income declines of 38 and the lowest pre-retirement incomes of any measured group. These findings suggest patterns of vulnerability that have important implications for proposals seeking to reform the U.S. Social Security Program.
Date revised - 2015-03-01 Availability - URL:http://www.spaef.com/pfm.php Publisher's URL
Keywords: Disabilities; Employment and Labor Force; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Job Displacement, Retirement and the Roles of Government Programs among Older American Workers - Liu, Jieruo (Job Displacement, Retirement and the Roles of Government Programs among Older American Workers, 2014)
The world has been going through one of worst economic recessions in history with severe job market downturns. In October 2009, the U.S. civilian unemployment rate reached a historical 10% and nearly 50% of the unemployed exhausted their 26-week regular Unemployment Insurance (UI) benefits and in consequence, UI was extended to 99 weeks. This dissertation examines the empirical facts of job displacement among the older American workers during the recent economic crisis, and studies their subsequent labor market and retirement decisions, with focus on the roles of government programs including UI and Social Security Old-Age Benefits (OA). Job displacement is empirically shown to have both short term and long term negative effects on workers' future employment. While young and prime-aged workers usually increase labor supply to compensate for the drops in assets and incomes, it is ambiguous how older workers would response and whether premature retirement would follow. For workers who are approaching their retirement age when OA becomes available, both OA and UI could be claimed for that purpose. The extent to which they rely on these two programs is affected by factors including age, wealth, income profiles and the institutional details of UI and OA. Using data from the Health and Retirement Study (HRS), I estimate a dynamic life-cycle utility maximization model with separate decisions on consumption/savings, labor market status and OA take-ups. With the structural model, I am able to isolate the effects of changes in UI coverage from changes in other relevant aspects including changes in the Normal Retirement Age (NRA), and analyze such effects in a deteriorating labor market. I conduct several experiments on UI generosities and evaluate the consequences on the mean individual as well as across the distributions of wealth and income. I find that in a severe labor market downturn, those who are on the lower end of wealth and income distributions are forced to claim OA early while the wealthier and high-income individuals typically postpone OA claiming to reduce early claiming penalties. However, with the extra help of a 99-week UI, some of the poor and low-income individuals can also afford to postpone OA claiming using UI as a stepping-stone. Specifically, among those who originally claim OA at an early 62 years old during a severe labor market downturn, 6.34% of the poorest individuals and 2.52% of the lowest-incomers postpone OA take-ups, resulting in slight increases in the average OA entitlement ages. However, the role of UI as a stepping stone is more prominent among those with high income profiles whose OA take-ups are postponed for almost a quarter year.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-11-27 First page - n/a
Keywords: Demographics; Employment and Labor Force; Methodology; Public Policy; Retirement Planning and Satisfaction; Social Security

Latinos in an Aging World: Social, Psychological, and Economic Perspectives - Ronald J. Angel; Jacqueline L. Angel (Routledge, 2014)
The introduction motivates the book and sets the stage for the entire discussion. Chapter 1 reviews the histories of the major Hispanic subgroups along with various theories as they relate to race, ethnicity, and gender that provide a conceptual framework for understanding the later chapters. Demographic, economic, and social profiles of the various Hispanic subgroups are explored in chapter 2. Next the Latino population is explored from various perspectives including the economic and social situations of men and women and their educational, marital and family, and labor force experiences. Chapter 4 examines older immigrants and their families and identifies the resources available to them in their communities that often replicate the cultural and social support system of the old country. Major health risks that older Latinos face as a result of the disadvantages they experience throughout life are examined in chapter 5. Family situations and long-term care and living arrangements of older Hispanics are examined in chapter 6. The impact of neighborhood on quality of life in terms of safety and physical and mental wellbeing is explored in chapter 7. The burden that eldercare can place upon those who bear the responsibility of their daily care is explored in chapter 8. Chapter 9 investigates the gaps in income between minority and non-Hispanic white Americans and reviews what individuals with few resources need to know about financial management. The book concludes with the social, political, and economic implications of the growing Hispanic population and the role of NGOs and other organizations in providing services to older populations.
Keywords: Demographics; Retirement Planning and Satisfaction; Women and Minorities

Lifetime Job Demands, Work Capacity at Older Ages, and Social Security Benefit Claiming Decisions - Lauren Hersch Nicholas (Boston, Center for Retirement Research at Boston College, 2014)
We use Health and Retirement Study data linked to the Department of Labor s O Net classification system to examine the relationship between lifetime exposure to occupational demands and retirement behavior. We consistently found that both non-routine cognitive analytic and non-routine physical demands were associated with worse health, earlier labor force exit, and increased use of Social Security Disability Insurance. The growing share of workers in jobs with high levels of cognitive demand may contribute to growth in DI use.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction; Social Security

Love, toil, and health insurance: Why American husbands retire when they do - Joshua Congdon-Hohman (Contemporary Economic Policy, 2014)
The provision of health insurance has previously been shown to be an important determinant of retirement timing among older Americans, but the existing literature has largely ignored some aspects of the interspousal dependence of health insurance benefits. Specifically, the literature examines only how retirement may affect the health insurance available to the potential retiree but not how it might affect a spouse's options. Using data from the Health and Retirement Study, I find that the impact a husband's retirement might have on a wife's health insurance options has a statistically significant impact on a husband's rate of retirement that is independent of considerations of his own health insurance options. In households where the wife is the only one at risk of losing affordable health insurance if the husband retires, the husband is 30 less likely to retire than if neither spouse is at risk (a 5 percentage point decrease in the retirement rate). Based on these findings, prior research is missing one avenue that changes to the Medicare eligibility age and health insurance policy changes through the Affordable Care Act might impact the labor supply of older workers. 2014 Western Economic Association International.
Keywords: Adult children; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Mismeasurement of pensions before and after retirement: the mystery of the disappearing pensions with implications for the importance of Social Security as a source of retirement support - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Journal of Pension Economics and Finance, 2014)
A review of the literature suggests that when pension values are measured by the wealth equivalent of promised defined benefit pension benefits and defined contribution balances for those approaching retirement, pensions account for more support in retirement than is suggested when their contribution is measured by incomes received directly from pension plans by those who have already retired. Estimates from the Health and Retirement Study for respondents in their early fifties suggest that pension wealth is about 82 as valuable as Social Security wealth. In data from the Current Population Survey (CPS), for members of the same cohort, measured when they are 65-69, pension incomes are about 58 as valuable as incomes from Social Security. Our empirical analysis uses data from the HRS to examine the reasons for these differences in the contributions of pensions as measured in income and wealth data. Key factors accounting for these differences include: a difference in methodology between surveys affecting what is included in pension income; some pension wealth 'disappears' at retirement because respondents change their pension into other forms that are not counted as pension income; and the form of annuitization may influence the measure of pension income. A series of caveats notwithstanding, the bottom line is that CPS data on pension incomes received in retirement understates the full contribution pensions make to supporting retirees. PUBLICATION ABSTRACT
Keywords: Net Worth and Assets; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

A Multilevel Dyadic Study of the Impact of Retirement on Self-Rated Health: Does Retirement Predict Worse Health in Married Couples? - Angela L Curl; Aloen L. Townsend (Research on Aging, 2014)
Objectives: This study examined the effects of retirement on self-rated health for married couples, using interdependence and social stratification theoretical frameworks. Method: Dyadic multilevel modeling of data (N = 2,213 non- Hispanic couples) from 1992 to 2010 of the Health and Retirement Survey. Results: Retirement was associated with worse self-ratings of health (SRH) short term (ST) for both husbands and wives during the first couple of years of retirement. In addition, the longer the husbands (but not wives) were retired, the worse was their SRH. Cross-spouse effects varied by gender: When wives retired, their husbands SRH improved ST, but when husbands retired their wives SRH improved long term. Spouse education moderated the relationship between years since spouses retirement and SRH for wives. Discussion: Practitioners can use this information to help married couples through retirement planning and transitions. Results suggest that models of retirement in couples should pay greater attention to gender and other social stratification factors, spousal interdependence, and length of time since retirement.
Date revised - 2014-12-01 Number of references - 58
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Perceived control relates to better functional health and lower cardio-metabolic risk: The mediating role of physical activity - Frank J Infurna; Denis Gerstorf (Health psychology : official journal of the Division of Health Psychology, American Psychological Association, 2014)
Objective: The objective of the current study was to examine empirically associations between perceived control and indicators of functional health (grip strength) and cardio-metabolic risk (hemoglobin A1C, High Density Lipoprotein Cholesterol HDL-C , Systolic Blood Pressure SBP , Pulse Rate PR , and Waist Circumference WC ) and to explore the mediating role of physical activity. Method: Using cross-sectional data from the nation-wide Health and Retirement Study (N = 4,292; Mean age = 68, range 50-97; 59 women), we examined whether perceived control was predictive of the various health indicators over and above sociodemographic characteristics. We also used mediation models to test whether those direct associations were mediated by physical activity. Results: Findings indicated that perceiving more control related to better grip strength and lower cardio-metabolic risk. To illustrate, a 1 SD increase in control is associated with 2.5 fewer years of aging on grip strength, 10 fewer years of aging for hemoglobin A1C, 14.5 fewer years of aging for HDL-C, 3.7 fewer years of aging for pulse rate, and 5.75 fewer years of aging for waist circumference. We also found that physical activity mediated five of the six control-health associations. Conclusions: Our findings demonstrate the importance of perceived control as predictor of functional and physiological health and the role of physical exercise as a behavioral mediator of these associations. Our results suggest that control may serve as a facilitator of positive health outcomes, including functional health, cardio-metabolic risk, and physical activity. Findings provide impetus for future research to elucidate mechanisms underlying the health implications of perceived control. (PsycINFO Database Record (c) 2014 APA, all rights reserved).
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction; Risk Taking

Physical Activity and Mortality Among Middle-Aged and Older Adults in the United States - Wen, Ming; Li, Lifeng; Su, Dejun (Journal of Physical Activity and Health, 2014)
Background: Physical activity (PA) has been routinely linked to lower all-cause mortality, yet extant research in the United States is primarily based on nonrepresentative samples. Evidence is scant on the relative and independent merits of leisure-time (LTPA) versus non-leisure-time (NLTPA) activities and how the PA-mortality link may vary across racial-ethnic-gender groups. Methods: Data were from Health and Retirement Study which began in 1992 collecting data on individuals aged 51-61 years who were subsequently surveyed once every 2 years. The current study assessed group-specific effects of LTPA and NLTPA measured in 1992 on mortality that occurred during the 1992-2008 follow-up period. Cox proportional hazard analyses were performed to examine the PA-mortality link. Results: Net of a wide range of controls, both LTPA and NLTPA showed a gradient negative relation with mortality. No gender-PA interaction effects were evident. Some interaction effects of PA with race-ethnicity were found but they were weak and inconsistent. The mortality reduction effects of PA seemed robust across racial-ethnic-gender groups. Conclusions: Regardless of personal background, PA is a major health promoting factor and should be encouraged in aging populations. More research is needed to assess relative merits of different types and domains of PA.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction; Women and Minorities

Positive and Negative Social Exchanges and Cognitive Aging in Young-Old Adults: Differential Associations Across Family, Friend, and Spouse Domains - Tim D Windsor; Denis Gerstorf; Pearson, Elissa; Lindsay H Ryan; Kaarin J. Anstey (Psychology and Aging, 2014)
We examined how positive and negative social exchanges with friends, family, and spouses were related to cognitive aging in episodic and working memory, and perceptual speed. To do so, we used a large sample of cognitively intact young-old participants from the PATH Through Life Study ( PATH; aged 60 to 64 years at baseline, n = 1,618) who were assessed on 3 occasions over 8 years. Additional replication analyses were conducted using the Health and Retirement Study (HRS), which provided data on episodic memory. The main analysis of PATH Through Life showed that positive exchanges with friends and family were associated with less decline in perceptual speed, with these associations attenuated by adjustment for physical functioning and depressive symptoms. Negative exchanges with spouses were associated with poorer working memory performance. Positive exchanges with friends were associated with better initial episodic memory in both PATH and HRS. More frequent negative exchanges with friends and family were associated with better episodic memory in the PATH sample. However, these findings were not replicated in HRS. Our findings provide indirect support for the role of social exchange quality in contributing to cognitive enrichment. However, the inconsistent pattern of results across cognitive and social exchange domains points to possibilities of reverse causality, and may also indicate that social exchange quality plays a less important role for cognitive enrichment than other psychosocial characteristics.
Keywords: End of life decisions; Event History/Life Cycle; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Positive Psychological Attributes and Retirement Satisfaction - Asebedo, Sarah D.; Martin C. Seay (Journal of Financial Counseling and Planning, 2014)
This study investigated the association between positive psychological attributes and retirement satisfaction using a sample of 5,146 retired individuals from the 2006 and 2008 waves of the Health and Retirement Study (HRS). Utilizing Seligman s (2012) well-being theory, positive psychological attributes, as represented by the acronym PERMA, were measured by dispositional optimism (Positive emotion), reading the newspaper daily and having a hobby (Engagement), family support (Positive relationships), purpose in life and religiosity (Meaning), and perceived mastery (Accomplishment). Significant evidence was found supporting the association between positive psychological attributes and retirement satisfaction. Specifically, results of the ordinal logistic model revealed that, holding all else constant, dispositional optimism, family support, purpose in life, and perceived mastery were each positively associated with retirement satisfaction. Relevant implications for financial planners, counselors and educators include learning and developing optimism, cultivating family relationships, fostering purpose in life, discovering accomplishment during retirement, and structuring a phased transition to retirement.
Keywords: Demographics; Expectations; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Recession and Expected Retirement Age: Another Look at the Evidence - Maximiliane E Szinovacz; Lauren Martin; Adam Davey (Gerontologist, 2014)
Purpose: This article expands on earlier analyses that assessed whether the recent recession influenced retirement expectations. Design and Methods: Acknowledging that planning for retirement is a complex process influenced by personal preferences, resources, economic factors, institutional policies, and social norms, we test more comprehensive models than those used in previous studies, using data from the 2006 and 2008 waves (Waves 8 and 9) of the Health and Retirement Study. Results: Our results confirm that economic changes impinge on retirement expectations, but they also show stronger influences of other factors such as debts and the work environment. Implications: As the baby boom cohorts approach retirement age, it will be important to better understand how workers consider macro factors such as the state of the economy and firm-level factors and personal finances when planning for retirement.
Keywords: Employment and Labor Force; End of life decisions; Income; Pensions; Public Policy; Retirement Planning and Satisfaction

Residential Satisfaction, Psychological Well-Being, and Personality Traits: Effects on Relocation among Older Adults - Smith, Erin Kate (Residential Satisfaction, Psychological Well-Being, and Personality Traits: Effects on Relocation among Older Adults, 2014)
The focus of this study is the moves made voluntarily in later life. Older adults who engage in voluntary late life relocation are more likely to be white, have better health, have higher socioeconomic status, and have retired from full-time employment. The amenity move, a type of voluntary late life move, is often made by older adults with the above characteristics to a place specifically for community features such as weather, activities, or housing characteristics. The environmental gerontology literature offers some theoretical insight into understanding how an older adult evaluates their environment and suggests that relocation is one possible outcome when an older adult is not satisfied with the environment. This research highlights a new theoretical model, which proposes how personal characteristics and preferences and environmental characteristics influence an individual's evaluation of the environment. The model postulates that a negative evaluation of the environment can lead to relocation. The current study attempts to understand part of the model by examining how personal characteristics such as demographic information, socioeconomic measures, measures of health, retirement status, and personality impact relocation and more specifically amenity relocation directly and indirectly through the appraisal of the environment (residential satisfaction and psychological well-being). The study utilizes the Health and Retirement Study datasets from 2006-2008 and 2008-2010 to test the model because of its psycho-social measures and questions related to relocation. The results indicate that personality and neighborhood social cohesion directly and indirectly influence the decision to engage in relocation and amenity relocation. Specifically, higher levels of openness to experience are directly predictive of relocation in general and amenity relocation. Conscientiousness, extraversion, agreeableness, and neuroticism also influence the decision to relocate through a mediated relationship with neighborhood social cohesion. The results show that when older adults consider relocation, the social aspects of the environment can be just as important as the environment's physical aspects. Governments and senior housing developers can utilize information from this study to improve communities and develop a better understanding of the relocating older adult.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-12-29 First page - n/a
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction

Retirement Planning and Financial Literacy - Annamaria Lusardi (International Handbook on Ageing and Public Policy, 2014)
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Timing of Women and the Role of Care Responsibilities for Grandchildren - Lumsdaine, Robin L.; Stephanie J. C. Vermeer (Cambridge, MA, National Bureau of Economic Research, 2014)
This paper considers the potential relationship between providing care for grandchildren and retirement, among women nearing retirement age. Using 47,400 person-wave observations from the Health and Retirement Study (HRS), we find the arrival of a new grandchild is associated with a more than eight percent increase in the retirement hazard despite little overall evidence of a care/retirement interaction. We document that while family characteristics seem to be the most important factors driving the care decision, they are also important determinants of retirement. In contrast, while financial incentives such as pensions and retiree health insurance have the largest influence on retirement, the opportunity cost associated with outside income seems to have little effect on whether or not a grandmother provides care. There is little evidence of substitution between caring for grandchildren versus providing care for elderly parents or engaging in volunteer activities; grandchild care is instead taken on as an additional responsibility. Our findings suggest that policies aimed at prolonging worklife may need to consider grandchild care responsibilities as a countervailing factor while those policies focused on grandchild care may also affect elderly labor force composition.
Keywords: Adult children; Healthcare; Retirement Planning and Satisfaction

The role of satisfaction and switching costs in Medicare Part D choices - Han, Jayoung; Michelle J Ko; Julie M. Urmie (Research in Social and Administrative Pharmacy, 2014)
Background Most U.S. states had over 50 Medicare Prescription Drug Plans (PDPs) in 2007. Medicare beneficiaries are expected to switch Part D plans based on their health and financial needs; however, the switching rate has been low. Such consumer inertia potentially has negative effects on both beneficiaries and the insurance market, resulting in a critical need to investigate its cause. Objectives To 1) describe how Medicare beneficiaries who were satisfied with their current Part D plan differed from those who were not satisfied; 2) examine the effect of switching costs on consideration of switching among Medicare beneficiaries who were dissatisfied with their current Part D plan. Methods Data from the 2007 Prescription Drug Study supplement to the Health and Retirement Study (HRS) survey were used in this study. The satisfied and dissatisfied groups were compared in terms of cost variables, switching costs, and perception of Part D complexity. Structural equation modeling was used to examine relationships among switching costs, Part D complexity, cost variables, and consideration of switching for beneficiaries who were dissatisfied with their current Part D coverage. Results Out of 467 participants, a total of 255 (54.6 ) were satisfied with their current Part D plan. The satisfied group paid lower out-of-pocket costs ( 50.63 vs. 114.60) and premiums ( 30.88 vs. 40.77) than the dissatisfied group. They also had lower switching costs. Only 11.3 of the dissatisfied beneficiaries switched plans. Among respondents who were dissatisfied with their current plan, those who perceived Part D as complex had high switching costs and were less likely to consider switching plans. Out-of-pocket cost did not have a statistically significant association with consideration of switching. Conclusions Medicare beneficiaries who were satisfied with their current Part D plans had lower out-of-pocket costs and premiums as well as higher switching costs. Among beneficiaries who were dissatisfied with their current Part D plan, those who had higher switching costs were less likely to consider switching Part D plans.
Keywords: Medicare/Medicaid/Health Insurance; Methodology; Retirement Planning and Satisfaction

The Role of Spousal Characteristics on the Use of Formal Long-Term Care of Elderly Couples in the United States - Eom, Jinyoung (The Role of Spousal Characteristics on the Use of Formal Long-Term Care of Elderly Couples in the United States, 2014)
In the United States, the last decades have witnessed a steady increase in the percent of formal long-term care (nursing home care and paid home health care) uses. Specifically, it is shown that the percent of elderly couples, who use formal long-term care is much lower than that of single-living elderly to use formal long-term care. However, it has not been fully understood what factors determine the use of formal long-term care for elderly couples. Different from the previous studies, I scrutinize not only own individual factors but also spousal characteristics in terms of spouses health conditions, which may determine the use of formal long-term care of elderly couples. Detailed health conditions of spouse are considered; spouse's health dynamics and diagnosed illness by doctors. In addition, I carefully consider two different cases, according to the identity of the principal decision-maker regarding uses of formal long-term care: (i) An individual who needs long-term care decides formal long-term care uses himself/herself, and (ii) the spouse of the individual decides the individual's formal long-term care utilization. Models are estimated using multinomial logit specification using data from the Health and Retirement Study. Results suggest that the age, education level, the individual's health conditions and Activities of Daily Living ("ADL") changes are key factors that strongly affect the decision for utilization of formal long-term care for the elderly couples. When the individual has more disabilities in daily living, or has illnesses such as cancer, diabetes, stroke, psychological problem, or memory problem, he/she is more likely to use formal long-term care. I have also found that the spouse's health conditions, such as Instrumental Activities of Daily Living ("IADL"), ADL, diabetes, cancer or psychological problems affect the formal long-term care of the individual. This study shows that the spouse has an important effect on the individual's decision-making, regardless of who is ultimately in charge of that decision. However, when the group is classified according to `decision maker', the role of the spouse in the decisions regarding the individual's utilization of formal long-term care is more clearly understood.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-10-13 First page - n/a
Keywords: Adult children; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

The Social Security Windfall Elimination and Government Pension Offset Provisions for Public Employees in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Social Security Bulletin, 2014)
This article uses Health and Retirement Study data to investigate the effects of Social Security's Windfall Elimination Provision (WEP) and Government Pension Offset (GPO) on Social Security benefits received by households. The provisions reduce benefits for individuals or the dependents of individuals whose work histories include jobs for which they were entitled to a pension and were not subject to Social Security payroll taxes ( noncovered employment). We find that about 3.5 percent of households are subject to either the WEP or the GPO, and that the provisions reduce the present value of their Social Security benefits by roughly one-fifth. Households affected by both provisions experience benefit reductions of about one-third. Under the WEP, the Social Security benefit reduction is capped at one-half of the amount of the pension from noncovered employment, which substantially reduces the WEP penalty and prevents the WEP adjustment from falling disproportionately on households in the lowest earnings category.
Date revised - 2015-04-01 Availability - URL:http://www.ssa.gov/policy/docs/ssb/ Publisher's URL
Keywords: Employment and Labor Force; Income; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

A Three Essay Examination of Life Insurance - Mulholland, Barry S. (A Three Essay Examination of Life Insurance, 2014)
Life insurance is an important risk management and financial tool, both for insurance companies and individual households. This dissertation is a combined study of various factors that may be influencing the life insurance sales process and the factors used by households in their decisions to purchase and maintain ownership of life insurance policies. The first study is an attempt to understand factors that affect the demand for life insurance. Life insurance demand has been experiencing a 50-year decline in the U.S. while there has also been a shift away from permanent life insurance products to term life insurance products. We identify exogenous factors influencing the demand for cash value life insurance and examine their importance in explaining the sharp decline in demand for permanent insurance. We find that demographic and tax code changes do not explain the magnitude of decline. Using data from the 1992 through 2010 Surveys of Consumer Finances, we find a consistent downward trend in life insurance ownership, especially among younger and middle-age households. We find the demand for cash value life insurance is centered on households that are wealthier and more financially sophisticated suggesting these products are being used more for their tax-sheltering properties than as a hedge against the loss of human capital. The second study in this dissertation examines advisor beliefs about life insurance illustration effectiveness and advisor attributes that may influence those beliefs. The life insurance illustration is the primary disclosure document used in the sale of life insurance. When an insurance company designates a life insurance policy form to be marketed with a life insurance illustration during the presentation and sale of a life insurance policy, state regulation dictates the content and structure of the illustration. Using data collected in 2012 through an online survey targeting financial advisors providing life insurance advice, we find that over one-third of survey respondents believe the mandated life insurance illustration is a less than effective consumer education and protection tool. We find the contractual relationships between advisors and insurers and between advisors and consumers significantly impact advisor opinions about life insurance illustrations. We find advisors display overconfidence in their knowledge and understanding of life insurance illustrations and this overconfidence appears to impact their opinions about illustrations. We find no significant evidence that the method by which advisors are compensated impacts their opinions about life insurance illustrations. In the third study, we examine life insurance policy lapsation to understand the impact of various factors on the decision to voluntarily lapse a policy. We introduce and test individual cognitive ability variables in a model of the life insurance voluntary lapse decision by individual policyholders using data from the 2008 and 2010 waves of the Health and Retirement Study. We find that one measure of cognitive ability, numeracy, is related to the voluntary lapse decision. While controlling for numeracy, we find evidence supporting the emergency fund hypothesis, finding that those individuals with higher levels of net worth are less likely to voluntarily lapse a policy. We introduce a new measure of shock, kids moving home, and find it has a strong positive relation with the decision to voluntarily lapse a policy. Consistent with life insurance demand theory, we find that those who have recently entered retirement are reducing their life insurance holding.
Keywords: Health Conditions and Status; Insurance; Other; Retirement Planning and Satisfaction

Three Essays in Health, Education, and Retirement - Arons, Robert (Three Essays in Health, Education, and Retirement, 2014)
In chapter one I examine the impact of Health Maintenance Organization (HMO) coverage on the provision of preventive medicine procedures and undiagnosed disease. Rates of missed preventive care and undiagnosed conditions are substantially lower for middle-aged HMO enrollees compared to non-HMO enrollees. I control for selection with a novel quasi-experiment: turnover in group health insurance contracts at the firm level creates exogenous variation in plan type. The large age heterogeneity in the effect of HMO contracts is consistent with incentive structures in HMOs playing a role in the quality of patient care. In chapter two I use a regression discontinuity framework to analyze the No Child Left Behind (NCLB) Act's attempt to reduce the achievement gap by requiring sociodemographic groups meet group based proficiency count targets. Using a panel of North Carolina public school students in grades three through eight from 2003-2012, I find when a student's group is added to the set of existing accountable groups, it has a small positive impact on subject matter proficiency and test scores. Variation in the application of these laws comes the fact that groups are only held to academic proficiency standards if there are 40 or more tested students in the group within the school. In chapter three I estimate the potential earnings of retirees. Estimating the earnings structure of those no longer working is complex, because (1) health and cognition decline at older ages and drive workers into retirement, (2) retirement may cause changes in health and cognition, and (3) unobserved wage shocks may also drive workers into retirement and bias estimates depending on the direction of selection. Issue (1) is solved by using health and cognitive measures from the data, the Health and Retirement Study. Issues (2)-simultaneity of retirement with health and cognition, and (3)-selection out of the labor force, are controlled for with four instruments, self-reported probability of retirement at age 62 and 65 reported at age 55 and age dummies for 62 and 65. We find that retirees would earn less than a selection corrected estimator would suggest by about $13,000 per year.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-12-27 First page - n/a
Keywords: Adult children; Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Three essays on personality and net worth - Nabeshima, George (Three essays on personality and net worth, 2014)
This dissertation consists of three studies exploring the relationship between personality and wealth related variables. The psychological type theory was used as the theoretical framework for the first two studies, while the doctrine of interactionism was used in the third study. All three studies utilized data from the 2010 panel of the Health and Retirement Study (HRS). The first study examined the relationship between personality traits and net worth. Linear regression results identified the extroversion and conscientiousness traits as being positively associated with net worth. Furthermore, the agreeableness trait was negatively associated with net worth. The second study explored the relationship between personality preference and stock ownership. This study's logistic regression results identified the preference for high openness and high neuroticism as significant and positively associated with stock ownership. A high agreeableness preference was significant and negatively associated with stock ownership. The focus of the third study examined how net worth and income mediated the association between personality and life satisfaction. Regression results from this study identified net worth as being a significant mediating variable in the association between the conscientiousness trait and life satisfaction levels. However, income, in addition to net worth, was also a significant mediating variable when the extroversion and neuroticism traits were used to represent personality trait variables. Results from the three studies identified significant associations between personality traits and components of net worth. These findings contribute to the financial planning field by providing useful information in regards to how mental preferences expressed outwardly though personality traits are related to wealth related variables and life satisfaction. Financial planning practitioners can apply these findings to formulate strategies to assist people grow their wealth levels.
Keywords: Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

What Impact Does Old-Age Pension Receipt Have on the Use of Public Assistance Programs Among the Elderly? - Norma B Coe; April Yanyuan Wu (Safety Nets and Benefit Dependence, 2014)
Keywords: Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction; Social Security

Women s Timing of Receipt of Social Security Retirement Benefits - Gillen, Martie; Claudia J Heath (Journal of Family and Economic Issues, 2014)
The 2000 2006 waves of Health and Retirement Study data were used to estimate the effects of human capital characteristics and income sources on women s timing of receipt of Social Security retirement benefits. Using logistic regression, the likelihood of early election of benefits was increased by earnings regardless of marital status; and, for married women, by husband s age being greater than wife s, and by other income. For married women, education decreased the likelihood of electing early benefits. For unmarried women, IRA/annuity income reduced the likelihood of early receipt of benefits. Using multinomial logistic regression, the likelihood of combinations of expected and actual benefit receipt options were estimated. A greater percentage of married, compared to unmarried, women expected and elected early benefits.
Keywords: Retirement Planning and Satisfaction; Social Security; Women and Minorities

Anticipatory Socialization for Retirement: A Multilevel Dyadic Model - Angela L Curl; Ingram, J. G. (CLINICAL GERONTOLOGIST, 2013)
Role theory, widely used to examine human behavior, has often been used to describe the transition from work to retirement. Anticipatory socialization, a role theory concept, describes the process that occurs prior to role transitions and assists in that transition by helping individuals learn the norms for the new role. However, not all workers engage in retirement planning. Lack of retirement planning is of concern because those individuals who do not plan for major life transitions tend to be less successful in adjusting to role changes. Data from the Health and Retirement Study were used; selection criteria required participants to be age 45 or older, working full- or part-time, and have complete data for the study variables. Multilevel modeling results of dyadic data from the Health and Retirement Study (N=1,028 dual-earner couples) indicate that older age, being White, higher income, greater retirement wealth, and looking forward to retirement predicted greater anticipatory socialization (i.e., thinking about and discussing retirement) by both husbands and wives. For wives only, having a health problem limiting work, higher spouse occupational status, and having a spouse who was looking forward to retirement predicted more anticipatory socialization. For husbands only, higher education, higher depressive symptomatology, and lower occupational status predicted more anticipatory socialization. This study found evidence of spousal congruence, with husbands, on average, engaging in more anticipatory socialization than wives. These findings identify couples that could most benefit from targeted efforts to increase anticipatory socialization, which predicts better retirement adjustment and satisfaction.
Keywords: Adult children; Demographics; Healthcare; Other; Retirement Planning and Satisfaction

Are Gender Differences Emerging in the Retirement Patterns of the Early Boomers? - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Washington, DC, Bureau of Labor Statistics, 2013)
Controlling for career employment later in life, the retirement patterns of men and women in America have resembled one another for much of the past two decades. Is this relationship coming to an end? Recent research suggests that the retirement patterns of the Early Boomers those born between 1948 and 1953 have diverged from those of earlier cohorts. Gender differences appear to be emerging as well in the way that career men and women exit the labor force, after nearly two decades of similarities. This paper explores these gender differences in detail to help determine whether we are witnessing a break in trend or merely a short-term occurrence. We use data on three cohorts of older Americans from the nationally-representative, longitudinal Health and Retirement Study (HRS) that began in 1992. We explore by gender the types of job transitions that occur later in life and explore, in particular, the role of four potentially relevant determinants: the presence of dependent children; a parent in need of caregiving assistance; occupational status on the career job; and self-employment status. We find that, among career men and women, child and parental caregiving are not significant drivers of the retirement transitions of the Early Boomers, all else equal. Gender differences that may exist with respect to these characteristics are therefore unlikely to lead to persistent gender differences in retirement patterns. In contrast, self employment continues to be a statistically significant determinant of bridge job transitions and phased retirement. This finding, combined with the fact that men are much more likely than women to be self employed later in life, could lead to some differences by gender going forward, though the impact is likely to be limited given that the large majority of older workers are in wage-and-salary employment. Older Americans both men and women are responding to their economic environment by working later in life and exiting the labor force gradually. While some determinants of these decisions likely impact men and women differently, gender differences with respect to the retirement patterns of the Early Boomers appear to be the result of broader macroeconomic forces. The evidence to date suggests that gender differences may dissipate as the recovery ensues.
Keywords: Demographics; Employment and Labor Force; Healthcare; Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

The Asset and Income Profiles of Residents in Seniors Housing and Care Communities: What Can Be Learned From Existing Data Sets - Norma B Coe; Melissa A. Boyle (Research on Aging, 2013)
The authors use existing, nationally representative surveys to assess the economic characteristics of individuals in three categories of seniors housing and care facilities: independent living communities (ILCs), assisted living residences (ALRs), and continuing care retirement communities (CCRCs). The findings highlight the strengths and weaknesses of using the Health and Retirement Study, National Long-Term Care Survey, and Medicare Current Beneficiary Survey to describe this segment of the population. The results suggest that residents in ILCs and ALRs have lower average incomes than the average costs of these care communities. Conversely, CCRC residents have higher incomes and more assets than those living in private homes, suggesting that CCRCs attract the wealthiest seniors. However, longitudinal analysis is prohibited by the small sample sizes.
Keywords: Health Conditions and Status; Healthcare; Housing; Retirement Planning and Satisfaction

A Bumpy Road: Asset Accumulation, Unexpected Life Course Events, and Later Life Economic Security - Sullivan, Laura Anne (A Bumpy Road: Asset Accumulation, Unexpected Life Course Events, and Later Life Economic Security, 2013)
This dissertation examines retirement security through an analysis of asset holdings among today's older adults, with a particular focus pre-retirees, who are near retirement. The research seeks to better understand households' retirement resources and later life economic vulnerabilities by: 1.) assessing existing assets among all older U.S. households (51+) and exploring the racial wealth gap among this group; 2.) measuring the direction and magnitude of impacts from several household level economic shocks on the wealth of older households; and 3.) investigating how households prepare for retirement and approach retirement saving. Several theoretical frameworks help to guide the study including the life-cycle hypothesis of saving established by economist Modigliani, life course scholarship by sociologists Elder, Rank, and Kemp, the assets framework expounded by Sherraden and Shapiro, and the institutional model of savings. The mixed-methods study integrates analysis from the Health and Retirement Study (HRS), providing a longitudinal look at the assets of older households 51+ for a decade from 1998 to 2008, and data from semi-structured qualitative interviews. Multivariate fixed effects regression on the panel data assesses the long-term impacts of household economic shocks on wealth. The data reveal largely inadequate savings overall and the racial wealth gap, which has been documented among the general U.S. population, remains large for older adults 51+. The analysis reveals significant negative declines in wealth due to common household events for older adults. Qualitative semi-structured interviews among 16 individuals close to or recently retired (ages 50-65) reveal barriers to saving for retirement such as limited financial knowledge about savings mechanisms, inadequate income sources, and unexpected financial events. The data also point to the important role of institutional structures in shaping retirement decisions. Given the challenges in saving for retirement at the household level, policy should seek to support programs which pool risk across groups, such as Social Security and pensions. Evidence from the study suggests that household-level strategies are likely to be limited in their effectiveness without adequate institutional mechanisms for fostering retirement resources.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2014-01-22 First page - n/a
Keywords: Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Social Security

Causal effects of retirement timing on subjective physical and emotional health - Calvo, Esteban; Sarkisian, Natalia; Tamborini, Christopher R. (The journals of gerontology. Series B, Psychological sciences and social sciences, 2013)
This article explores the effects of the timing of retirement on subjective physical and emotional health. Using panel data from the Health and Retirement Study (HRS), we test 4 theory-based hypotheses about these effects-that retirements maximize health when they happen earlier, later, anytime, or on time. We employ fixed and random effects regression models with instrumental variables to estimate the short- and long-term causal effects of retirement timing on self-reported health and depressive symptoms. Early retirements--those occurring prior to traditional and legal retirement age--dampen health. Workers who begin their retirement transition before cultural and institutional timetables experience the worst health outcomes; this finding offers partial support to the psychosocial-materialist approach that emphasizes the benefits of retiring later. Continued employment after traditionally expected retirement age, however, offers no health benefits. In combination, these findings offer some support for the cultural-institutional approach but suggest that we need to modify our understanding of how cultural-institutional forces operate. Retiring too early can be problematic but no disadvantages are associated with late retirements. Raising the retirement age, therefore, could potentially reduce subjective health of retirees by expanding the group of those whose retirements would be considered early.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Disability and Subjective Well-being - Mary C. Daly; Gardiner, Colin S. (Lifecycle Events and Their Consequences: Job Loss, Family Change, and Declines in Health, 2013)
The authors examine the relationship between disability, its onset, and subjective well-being in Chapter 15. Individuals with a work-limitating disability self-reported lower levels of life satisfaction. Consistent with previous studies, the authors find a negative relationship between disability status and subjective well-being. Employment status, income, and wealth, mitigates this negative relationship, but disability still emerges as a salient determinant of subjective well-being throughout the analysis.
Keywords: Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare; Income; Retirement Planning and Satisfaction

Disability Shocks Near Retirement Age and Financial Well-Being - Irena Dushi; Rupp, Kalman (Social security bulletin, 2013)
Using Health and Retirement Study data, the authors examine three groups of adults aged 51 56 in 1992 with different disability experiences over the following 8 years. Our analysis reveals three major findings. First, people who started and stayed nondisabled experienced stable financial security, with substantial improvement in household wealth despite substantial labor force withdrawal. Second, people who started as nondisabled but suffered a disability shock experienced a substantial increase in poverty rates and a sharp decline in median incomes. Average earnings loss was the greatest for that group, with public and private benefits replacing less than half of the loss, whereas the reduction in private health insurance coverage was more than alleviated by the increase in public health insurance coverage. Third, people who started and stayed disabled were behind at the baseline and have fallen further behind on most measures. An important exception is substantial improvement in health insurance coverage because of public safety nets.
Keywords: Employment and Labor Force; Health Conditions and Status; Income; Medicare/Medicaid/Health Insurance; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Does Retirement Induced through Social Security Pension Eligibility Influence Subjective Well-being? A Cross-Country Comparison - Arie Kapteyn; Jinkook Lee; Gema Zamarro (Ann Arbor, MI, University of Michigan Retirement Research Center, 2013)
How does retirement influence subjective well-being? Some studies suggest retirement does not affect subjective well-being or may improve it. Others suggest it adversely affects it. This paper aims at advancing our understanding of the effect of retirement on subjective well-being by (1) using longitudinal data to tease out the retirement effect from age and cohort differences; (2) using instrumental variables to address potential reverse causation of subjective well-being on retirement decisions; and (3) conducting cross-country analyses, exploiting differences in eligibility ages for retirement benefits across countries and within countries. We use panel data from the US Health and Retirement Study and the Survey of Health, Ageing, and Retirement in Europe. This allows us to use a quasi-experimental approach where variations in public pension eligibility due to country and cohort specific retirement ages help identify retirement effects. For both the U.S. and Europe we find that retirement is associated with higher levels of depression. However, when we use instrumental variables we find the opposite result. Retirement induced through Social Security pension eligibility is found to have a positive effect, reducing depression symptoms, although only marginally significant for the U.S. when considering the depression indicator. Retirement is not found to have a significant effect on life satisfaction measures for either the U.S. or Europe.
Keywords: Cross-National; Expectations; Health Conditions and Status; Retirement Planning and Satisfaction; SHARE

The Effect of Local Labor Demand Conditions on the Labor Supply Outcomes of Older Americans - Nicole Maestas; Kathleen J Mullen; David Powell (RAND, 2013)
A vast literature in labor economics has studied the relationship between local labor demand shifts and the outcomes of the working age population. This literature has ignored the impacts that these shocks have on older individuals, though there are reasons to believe that the effects are not uniform by age. Using data from the Census and the Health and Retirement Study, we measure the effects of local labor demand conditions on a host of outcomes for older individuals including employment, retirement, Social Security claiming, wages, and job characteristics. We find that local labor demand conditions do affect the labor and retirement behavior of the older segment of the population, including Social Security claiming decisions. We also find evidence that older individuals are especially responsive to local labor demand shifts in the service industry, which we show has observably different job characteristics that may be especially attractive to older workers. Similarly, we find evidence that labor demand shocks not only increase the wages of older workers but also make the jobs more attractive on non-pecuniary dimensions.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security

The effect of social security, health, demography and technology on retirement - Ferreira, Pedro Cavalcanti; dos Santos, Marcelo Rodrigues (Review of Economic Dynamics, 2013)
This article studies the determinants of the labor force participation of the elderly and investigates the factors that may account for the increase in retirement in the second half of the last century. We develop a lifecycle general equilibrium model with endogenous retirement that embeds Social Security legislation and Medicare. Individuals are ex ante heterogeneous with respect to their preferences for leisure and face uncertainty about labor productivity, health status and out-of-pocket medical expenses. The model is calibrated to the U.S. economy in 2000 and is able to reproduce very closely the retirement behavior of the American population. It reproduces the peaks in the distribution of Social Security applications at ages 62 and 65 and the observed facts that low earners and unhealthy individuals retire earlier. It also matches very closely the increase in retirement from 1950 to 2000. Changes in Social Security policy which became much more generous and the introduction of Medicare account for most of the expansion of retirement. In contrast, the isolated impact of the increase in longevity was a delaying of retirement.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction; Social Security

Effects of Late-Life Job Loss on Wealth and Labor Supply - Ann H. Stevens; Jeremy G. Moulton (Lifecycle Events and Their Consequences: Job Loss, Family Change, and Declines in Health, 2013)
This chapter considers the impact of job loss on economic well-being during retirement. Using data from the Health and Retirement Study (HRS), it compares retirement wealth across individuals who experience a job loss and those who do not. Sizeable differences are reported, especially when the job loss occurs at young ages. Little evidence is found that displaced workers can make up these differences by shifting retirement to a later date. The inability to recover appears related to both the difficulty in becoming reemployed and, if a new job is found, working sufficiently long before retirement to offset the initial declines in assets.
Keywords: Employment and Labor Force; Net Worth and Assets; Other; Retirement Planning and Satisfaction

The Effects of Race, Socioeconomic Status, and Religion on Formal End-of-Life Planning - Burdsall, Tina Dawn Lillian (The Effects of Race, Socioeconomic Status, and Religion on Formal End-of-Life Planning, 2013)
Individuals who are facing death today are doing so in an environment that is significantly different than it was in the past. Medical technology is increasingly able to keep people alive even with multiple complex chronic conditions. While these advances in medicine are beneficial to many, it can also unnecessarily prolong inevitable deaths. Concerns over the ability to have a death that is in alignment with personal values has increased the interest in the use of formal end-of-life planning including writing an advance instructional directive and assigning a durable power of attorney for health care. Although research has indicated that the use of these formal planning strategies is beneficial, not everyone completes them. Using a current nationally representative sample, the three specific aims of this study were to examine whether there are racial and ethnic differences in formal end-of-life planning done by older African American, Hispanic, and White adults; to examine socioeconomic factors including education and income in formal end-of-life planning as well as assess the contribution of these factors in explaining racial and ethnic differences in formal end-of-life planning; and to examine the role of religiosity in formal end-of-life planning and to assess its influence on racial and ethnic differences in explaining formal end-of-life planning. Logistic regression was run on data from the Health and Retirement Study (HRS) in order to analyze the completion of formal end-of-life plans by African American, Hispanic, and White decedents. Exit interviews conducted with knowledgeable proxies in 2008 or 2010 were combined with data from earlier waves of the HRS survey in order to analyze the completion of formal end-of-life plans, race and ethnicity, socioeconomic status, and religion. Both Blacks and Hispanics were less likely to complete a written advance directive, assign a proxy, or complete both forms of formal planning than were Whites. Group differences remained after controlling for region of death and cause of death. Both Blacks and Hispanics were less likely to complete any form of formal planning than Whites. Group differences remained after additionally controlling for gender, age, marital status, whether the decedent had children, income, education, religious preference, importance of religion, and frequency of attending religious services. Higher levels of income and education both increased the odds that formal advance planning would take place. Religious preference was not significant, but decedents who had stated that religion was very important were less likely to plan while those that attended services frequently were more likely to plan. I speculate that the role of cultural capital may partially explain the persistent racial and ethnic disparities and the importance of income and education. Additionally the dominant religious doctrines of Christianity may have a greater influence than the different religious teachings of Protestant and Catholics around end-of-life medical care. Contrary to expected findings, reference groups of those who attend religious services frequently may assist in formal planning. These finding may help guide interventions that can diminish disparities in the end-of-life experience. Understanding who are completing formal plans can help ensure end-of-life care that is in alignment with personal beliefs and values.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2013-08-27 First page - n/a
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Public Policy; Retirement Planning and Satisfaction

Effects of Social Security Policies on Benefit Claiming, Retirement and Saving - Alan L Gustman; Thomas L. Steinmeier (Cambridge, MA, National Bureau of Economic Research, 2013)
An enhanced version of a structural model jointly explains benefit claiming, wealth and retirement, including reversals from states of lesser to greater work. The model includes stochastic returns on assets. Estimated with Health and Retirement Study data, it does a better job of predicting claiming than previous versions. Alternative beliefs about the future of Social Security affect predicted outcomes. Effects of three potential policies are also examined: increasing the early entitlement age, increasing the full retirement age, and eliminating the payroll tax for seniors. Predicted responses to increasing the full entitlement age are sensitive to beliefs.
Keywords: Consumption and Savings; Healthcare; Public Policy; Retirement Planning and Satisfaction; Social Security

Essays on health economics - Beck, Laurel (Essays on health economics, 2013)
Chapter 1: Medicare provides nearly-universal health insurance for individuals aged 65 and older. The discontinuity in eligibility for Medicare provides an instrument for assessing the effects of insurance coverage on health outcomes. Using regression discontinuity analysis and data from the BRFSS, this paper finds an increase in utilization of preventive health services, as well as an improvement in self-reported health, at age 65. The effects vary across education level and gender. However, these results would be biased by high retirement rates at age 65. To address this issue, I run similar analysis at age 62, when individuals are first eligible to collect Social Security. I find that utilization is positively correlated with insurance but not retirement. The implications of these findings for assessing the cost-effectiveness of preventive care are limited, because the cross-sectional data do not capture the long-term benefits of diagnostic procedures. Chapter 2: This paper assesses the effects of working on the health of less-educated women, particularly mothers. These effects are difficult to estimate because health status affects labor force participation. To address this endogeneity problem, I use an instrumental variables estimation approach. Throughout the 1990s, changes in the EITC and the transition from AFDC to TANF provided exogenous incentives for women to enter the work force, independent of their own health status. This paper builds on the literature by including the incentives created by welfare reform and EITC which vary by state. It also includes measures of both physical and mental self-reported health, giving a broad picture of the effects of entering the labor force on the health of this population. Chapter 3: This chapter (with Atsuko Tanaka), examines the effect of depression on various labor force outcomes, including hours worked and wages. We use panel data from the Japanese Panel Survey of Consumers (JPSC) and the Health and Retirement Study (HRS) to follow respondents over several years, using questions about both mental health and labor force outcomes. In order to understand the causal effect of depression on work participation and compensation, we use deaths of the parents of respondents as an exogenous shock to mental health.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2014-02-22 First page - n/a
Keywords: Employment and Labor Force; Health Conditions and Status; Insurance; Methodology; Other; Retirement Planning and Satisfaction; Women and Minorities

Evidence that Self-Regulatory Mode Affects Retirement Savings - Hyungsoo Kim; Franks, Becca; Higgins, E. Tory (Journal of Aging and Social Policy, 2013)
We examine how self-regulatory motivations of locomotion (initiation) and assessment (evaluation) are related to retirement wealth in middle-aged and older Americans. We test a hypothesis that high locomotion and some assessment levels predict high wealth levels. We use two national data sets: the 2008 Health and Retirement Study (N = 6,464) and the 2005 Midlife in the United States (N = 4,963). We found that a combination of high locomotion and moderate assessment motivation can maximize wealth accumulation. By creating this combination of locomotion and assessment motivations, policy interventions can be more effective in motivating wealth accumulation for retirement, such as a required annual review of retirement savings plans and understandable disclosure of the plans' costs. PUBLICATION ABSTRACT
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

An Examination on Un-Retirement: Retirees Returning to Work - Guillermo Ernest Gonzales (An Examination on Un-Retirement: Retirees Returning to Work, 2013)
Research that examines retirees returning to work--defined here as un-retirement--is important, given increases in life expectancy and retirement insecurity. Unfortunately research in this area is nascent, limited in scope, and riddled with mixed findings. The current study is guided by three research questions: (1) how do economic resources, as well as human and social capital, relate to un-retirement?; (2) how do other productive activities, including formal and informal volunteering and caregiving, relate to un-retirement?; and (3) how does the retirement experience, including reasons to retire and retirement satisfaction, relate to un-retirement? The empirical literature on wealth and its association with un-retirement is mixed, and thus, an exploratory approach is taken. It is hypothesized that other economic resources (income, pension presence, and health insurances) are negatively related to un-retirement; for example, people with lower levels of income are more likely to return to work. It is hypothesized that higher levels of human capital and social capital are positively associated with un-retirement. It is also hypothesized that productive activities both compete with, and complement each other, and it depends on intensity and timing of events. Specifically, volunteering is a positively associated with un-retirement; that is volunteering complements going back to work. It is also suggested that caregiving is a barrier to un-retirement; that is, the two activities compete. It is hypothesized that forced retirement is positively associated with un-retirement. And finally, it is hypothesized that retirement satisfaction is negatively associated with un-retirement. Data were drawn from the Health and Retirement Study (HRS) which provided a nationally representative sample of fully retired older adults aged 62 and older in 1998 (n=8,334). This sample was followed to 2008, which offered a 10-year period to observe factors associated with un-retirement. The fully conditional specification imputation method was used to complete all missing values of the study variables. Survival analysis tested the hypotheses and yielded information on the significant factors associated with un-retirement. Findings reveal that total household net worth and income were not significantly related to un-retirement. Retirees who possessed a pension (p <.05, hazard ratio (HR):0.78, confidence limits (CL):0.63-0.97) and employer sponsored retiree health insurance (p <.05, HR:0.77, CL:0.62-0.95) were 22% and 23% less likely to return to work when compared to people who did not possess such economic resources for retirement. Generally, individuals with higher levels of human capital--better health (p <.0001, HR:1.31, CL:1.20-1.44), high-skilled (p <.05, HR:1.82, CL:1.20-2.75) and mid-skilled occupational workers (p <.05, HR:1.57, CL:1.07-2.28)--were more likely to return to work when compared to low-skilled occupational workers. This suggests that the probability of returning to work increased by 31% for every one unit increase in self-rated health; and the probability of returning to work were 82% and 57% higher for high and mid-skilled workers compared to low-skilled workers. Education, however, was negatively related to un-retirement when other productive activities were examined ( p <.05, HR: 0.96, CL:0.93-0.99), which suggests that for every unit increase in education, the probability of returning to work decreased by 4%. Certain dimensions of social capital were also significantly related to un-retirement; where the probability of returning to work increased by 75% for people who were married to an employed spouse/partner ( p <.0001, HR:1.75, CL:1.36-2.23). Formal and informal volunteering were significant predictors to work; where volunteers were between 38% and 58% more likely to return to work when compared to non-volunteers. However, providing care to a spouse was a major barrier to returning to work; where caregivers were approximately 80% less likely to return to work in subsequent waves when ompared to non-caregivers ( p <.01
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2014-01-21 First page - n/a
Keywords: Adult children; Employment and Labor Force; Healthcare; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Fact Sheet: What Influences Plans to Work after Ages 62 and 65? - Maximiliane E Szinovacz (Boston, MA, University of Massachusetts Boston, 2013)
Timing of retirement and, implicitly, plans to work in later life have great policy relevance. They affect Social Security expenditures, employers pension expenditures, as well as labor force supply and demand. In light of the recent recession, it is particularly important to explore whether economic downturns and workers financial status influence their later-life work plans. To answer this question, we analyzed data from the nationally representative Health and Retirement Study (HRS), which included questions about expectations to work full-time after age 62 and age 65.
Keywords: Employment and Labor Force; Expectations; Public Policy; Retirement Planning and Satisfaction

The Great Recession and Health: People, Populations, and Disparities - Sarah A. Burgard; Jennifer A Ailshire; Lucie Kalousova (Annals of the American Academy of Political and Social Science, 2013)
Two research traditions have evolved to assess links between recessions and health, with seemingly divergent findings. Aggregate-level studies generally find that mortality rates decline during recessionary periods. By contrast, individual-level studies generally find that events that frequently occur during recessions, like job loss, unemployment, and material hardship, carry negative health consequences. We comprehensively review evidence from these two bodies of research, illustrate key findings, and show how the different mechanisms can operate in parallel. We also outline some of the limitations of the extant evidence, discuss studies emerging to address these limits and directions for future research, and provide brief empirical examples to illustrate some of these limits and directions using the Health and Retirement Study and the Michigan Recession and Recovery Study. Our review emphasizes the importance of considering both the aggregate- and individual-level associations when evaluating the likely short- and longer-term consequences of the Great Recession for health and health disparities.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Public Policy; Retirement Planning and Satisfaction

Health and Wealth in Early Retirement - Geoffrey L Wallace; Haveman, Robert; Karen C. Holden; Barbara Wolfe (Lifecycle Events and Their Consequences: Job Loss, Family Change, and Declines in Health, 2013)
Retirement years are a precarious time for many older Americans. Even if successful in accumulating resources expected to be sufficient to maintain their pre-retirement standard of living, many retirees face unexpected adverse health shocks after retirement. Because of the uncertainty of shocks to physical and cognitive health, there exists the potential for significant deterioration in resource adequacy both at the time of retirement and into the retirement years due to their occurrence. In this study, we select a sample of new retirees constructed from the Health and Retirement Study (HRS) data and follow them during the first decade of their retirement. Using these data, we identify the nature of shocks to physical and cognitive health for which individuals are at risk during their retirement years, and estimate both the absolute and relative risk of these shocks. We then estimate the impact of the occurrence of these shocks on wealth-based measures of retirement adequacy.
Keywords: Health Conditions and Status; Income; Retirement Planning and Satisfaction

Health, Education, and the Post-Retirement Evolution of Household Assets - James M. Poterba; Steven F Venti; David A Wise (Cambridge, MA, National Bureau of Economic Research, 2013)
This paper explores the relationship between education and the evolution of wealth after retirement. Asset growth following retirement depends in part on health capital and financial capital accumulated prior to retirement, which in turn are strongly related to educational attainment. These initial conditions for retirement can have a lingering effect on subsequent asset evolution. Our aim is to disentangle the effects of education on post-retirement asset evolution that operate through health and financial capital accumulated prior to retirement from the effects of education that impinge directly on asset evolution after retirement. We consider the indirect effect of education through financial resources in particular Social Security benefits and defined benefit pension benefits and through health capital that was accumulated before retirement. We also consider the direct effect of education on asset growth following retirement, emphasizing the correlation between education and the returns households earn on their post-retirement investments. Households with different levels of education invest, on average, in different assets, and they may consequently earn different rates of return. Finally, we consider the additional effects of education that are not captured through these pathways. Our empirical findings suggest a substantial association between education and the evolution of assets. For example, for two person households the growth of assets between 1998 and 2008 is on average much greater for college graduates than for those with less than a high school degree. This difference ranges from about 82,000 in the lowest asset quintile to over 600,000 in the highest.
Keywords: Demographics; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Health, retirement, and migration from metro counties: evidence from the health and retirement study - Nan E. Johnson (Biodemography and Social Biology, 2013)
Event history analyses and difference-in-proportions tests are used to analyze 1994-2003 data from the Health and Retirement Survey. For young-old metropolitan adults who had never retired, self-rated health (SRH) was unrelated to the odds of becoming a migrant, but for those who had retired, better SRH raised the odds. Neither SRH nor its interwave change was related to the risk of a nonmetro or metro destination. Metro-metro and metro-nonmetro migrants were indistinguishable in their recalled reasons for migration. The implications of the findings for theory and future research are discussed.
Keywords: Demographics; Event History/Life Cycle; Health Conditions and Status; Retirement Planning and Satisfaction

Health shocks in patients with cancer: A longitudinal analysis of financial and retirement trends using the Health and Retirement study - Adrienne M. Gilligan (Health shocks in patients with cancer: A longitudinal analysis of financial and retirement trends using the Health and Retirement study, 2013)
Objectives: Evaluate the association of cancer on net worth, consumer debt, mortgage debt, home equity and changes in retirement trends. Methods: Data from the Health and Retirement Study from 1998-2010 was used. Persons had to have a diagnosis of cancer. The index date was the corresponding HRS wave of the year of the first diagnosis of cancer. The pre-index date was 2 years and a 2-year and 4-year post index was observed. Primary outcomes of interest were zero/negative net worth and net worth. Multiple logistic regression was used to test for the association between demographic, economic, human capital, and cancer-related variables on outcomes. Generalized linear models were conducted to assess the association of cancer on net worth, consumer debt, mortgage debt, and home equity. Multinomial logistic regression was performed to assess the association of cancer on retirement. Results: A total of 6,055,110 individuals (weighted) qualified. The majority of patients in this sample were male (53.8%), non-Hispanic (95.5%), and white (90.3%). Marital status (p<0.05), alcohol consumption (p=0.046), hypertension (p = 0.034), private insurance (p=0.001), cancer status (p<0.001), and cancer treatment (p=0.022) were significant predictors of zero/negative net worth 4-years after cancer diagnosis. Patients receiving treatment for their cancer were 71% more likely to have consumer debt 4-years post diagnosis (p=0.006). Patients who reported their cancer improving 4-years post diagnosis were significantly less likely (p=0.008) to have consumer debt (OR=0.59; 95%CI: 0.41-0.87). Cancer treatment and cancer status were significant predictors of mortgage debt (p<0.001 and 0.024, respectively). For individuals whose cancer either improved (OR=1.46; 95%CI: 1.04-2.06) or worsened (OR=4.09; 95%CI: 1.38-12.15), both groups were significantly more likely (p=0.030 and 0.011, respectively) to have home equity 4-years post diagnosis. Cancer status was a significant predictor of individuals transitioning from working to retired (p=0.022). Conclusion: This nationally representative investigation of 6.1 million patients over 50 years of age with cancer found that approximately 65% of cancer patients reported zero/negative net worth of cancer and almost 45% of cancer patients reported consumer debt four-years post diagnosis. Cancer-related characteristics explain a significant amount of the change in net worth four-years post diagnosis of cancer.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2013-05-30 First page - n/a
Keywords: Health Conditions and Status; Healthcare; Net Worth and Assets; Other; Public Policy; Retirement Planning and Satisfaction

Heterogeneity in spending change at retirement. - Michael D Hurd; Susann Rohwedder (Journal of the Economics of Ageing, 2013)
The simple one-good model of life-cycle consumption requires that consumption be continuous over retirement; yet prior research based on partial measures of consumption or on synthetic panels indicates that spending drops at retirement, a result that has been called the retirement-consumption puzzle. Using panel data on total spending, nondurable spending and food spending, we find that spending declines at small rates at retirement, rates that could be explained by mechanisms such as the cessation of work-related expenses, unexpected retirement due to a health shock or by the substitution of time for spending. We find substantial heterogeneity in spending change at retirement: in the upper half of the wealth distribution spending increased. In the low-wealth population where spending did decline at higher rates, the main explanation for the decline appears to be early retirement due to poor health, possibly augmented by a short planning horizon by a minority of the population.
Keywords: Older Adults; Retirement Planning and Satisfaction

How do couples influence each other's physical activity behaviours in retirement? An exploratory qualitative study - Barnett, Inka; Guell, Cornelia; Ogilvie, David (BMC Public Health, 2013)
Physical activity patterns have been shown to change significantly across the transition to retirement. As most older adults approach retirement as part of a couple, a better understanding of how spousal pairs influence each other's physical activity behaviour in retirement may help inform more effective interventions to promote physical activity in older age. This qualitative study aimed to explore and describe how couples influence each other's physical activity behaviour in retirement. A qualitative descriptive study that used purposive sampling to recruit seven spousal pairs with at least one partner of each pair recruited from the existing EPIC-Norfolk study cohort in the east of England, aged between 63 and 70 years and recently retired (within 2-6 years). Semi-structured interviews with couples were performed, audio-recorded, transcribed verbatim and analysed using data-driven content analysis. Three themes emerged: spousal attitude towards physical activity, spouses' physical activity behaviour and spousal support. While spouses' attitudes towards an active retirement were concordant, attitudes towards regular exercise diverged, were acquired across the life course and were not altered in the transition to retirement. Shared participation in physical activity was rare and regular exercise was largely an individual and independent habit. Spousal support was perceived as important for initiation and maintenance of regular exercise. Interventions should aim to create supportive spousal environments for physical activity in which spouses encourage each other to pursue their preferred forms of physical activity; should address gender-specific needs and preferences, such as chances for socialising and relaxation for women and opportunities for personal challenges for men; and rather than solely focusing on promoting structured exercise, should also encourage everyday physical activity such as walking for transport.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

How Do People Form Longevity Predictions? The Effect of Parents and Parents-in-law s Death on Beliefs about Mortality Risk - Chen, Lizi; Economics (Wellesley, MA, Wellesley College, 2013)
In this paper, we use data from the Health and Retirement Study (HRS) panel, which surveys a representative sample of US seniors about their longevity prospects to examine whether the Bayesian assumption holds. Specifically, I test for (1) whether people s longevity predictions are responsive to new information, e.g., recent parental death which conveys information about genetic risks, lifestyle-related health risks, etc; (2) whether people s longevity predictions respond more to the arrival of precise information (parental death) than less clear information (parent-in-law s death); (3) whether the magnitudes of these updates are in accordance with theoretical predictions. We find that individuals longevity predictions are responsive to new health-related information, and consistently more responsive to precise information (parental death) than imprecise information (parent-in-law s death). The magnitudes of these updates lie between the predicted lower and upper bounds of rational updates, but do not perfectly coincide with the predicted values and are sensitive to model specifications. We conclude that there is no strong evidence against the Bayesian assumption. We point out that the Bayesian assumption is only one aspect of the rationality hypothesis. From qualitative survey data, We find evidence of inattention to government subsidy of long-term care insurance, mistaken beliefs that long-term care is covered by Medicare and tendency to procrastinate on long-term care insurance purchasing decision. The evidence suggests irrationality may cause individuals to under-insure through these other venues.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

How Does Bankruptcy Law Impact the Elderly' s Business and Housing Decisions? - Nadia Greenhalgh-Stanley; Rohlin, Shawn (The Journal of Law and Economics, 2013)
The elderly are the population most likely to file for bankruptcy, with filings increasing by 150 percent from 1991 to 2007. This is likely because they live with relatively flat incomes and high medical expenses, and their retirement and housing assets are typically exempt from bankruptcy filings. In addition, nine states adopted higher asset exemptions specifically for the elderly. Using the Health and Retirement Study and recent state-by-time variation in homestead exemptions, we are the first to test whether the benefits of partial wealth insurance or the cost of supply-side credit constraints are predominant for the elderly. Using pooled cross-sectional analysis, we find that an increase in a state' s homestead exemption increases the elderly' s home equity and business ownership; however, the credit constraint is dominant in unlimited-exemption states, which decreases home and business ownership. Panel analysis reveals that an increase in the homestead exemption positively affects home ownership rates and home equity.
Keywords: Housing; Net Worth and Asset; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

How Does Retiree Health Insurance Influence Public Sector Employee Saving? - Robert Clark; Olivia S. Mitchell (Cambridge, MA, National Bureau of Economic Research, 2013)
Economic theory predicts that employer-provided retiree health insurance benefits crowd-out household wealth accumulation. Nevertheless, there is little research on the impacts of retiree health insurance on wealth accruals, so this paper utilizes a unique data file on three baseline cohorts from the Health and Retirement Study to explore how employer-provided retiree health insurance may influence net household wealth among public sector employees, where retiree healthcare benefits are still quite prevalent. We find that most full-time public sector employees who anticipate receiving employer-provided health insurance coverage in retirement save less than their private sector uncovered counterparts.
Keywords: Insurance; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

How Important Is Medicare Eligibility in the Timing of Retirement? - Norma B Coe; Khan, Mashfiqur R.; Matthew S. Rutledge (Boston, Center for Retirement Research at Boston College, 2013)
Eligibility for Medicare at age 65 is widely viewed as an important factor in retirement decisions. However, it has been difficult to quantify the influence of Medicare because eligibility for Medicare came at the same age as Social Security s Full Retirement Age (FRA). The recent rise in the FRA, along with other changes, has decoupled the age-related incentives in the two programs, making it easier to estimate the effect of Medicare eligibility on the timing of retirement. This brief, based on a recent study, provides such estimates of the importance of Medicare on retirement decisions.
Keywords: Medicare/Medicaid/Health Insurance; Public Policy; Retirement Planning and Satisfaction; Social Security

Labor Force Transitions at Older Ages: The Roles of Work Environment and Personality - Marco Angrisani; Michael D Hurd; Erik Meijer; Andrew M Parker; Susann Rohwedder (Ann Arbor, The University of Michigan, 2013)
Besides compensation and financial incentives, several other work-related factors may affect individual retirement decisions. Specifically, job characteristics such as autonomy, skill variety, task significance and difficulty, stress and physical demands, peer pressure and relations with co-workers, play a crucial role in determining psychological commitment to work at older ages. While financial preparedness for retirement and health shocks are often cited as main predictors of the choice to exit the labor force, there exists relatively little research documenting the extent to which the work environment itself and its interaction with economic variables influence retirement decisions. We document that job characteristics are associated with labor force transitions at older ages, in particular transitions to retirement and part-time employment. Additionally, we show that while personality traits do not directly drive labor force transitions, the effect of job characteristics on labor supply outcomes varies with the intensity of personality traits. We also document that job characteristics themselves are strongly related to personality traits. This suggests that, depending on their personality, individuals may select into specific jobs, whose characteristics ultimately shape their retirement paths.
Keywords: Employment and Labor Force; Health Conditions and Status; Other; Retirement Planning and Satisfaction

Labor Supply Preferences around Retirement for US Households - Yu, Zhiyu (Labor Supply Preferences around Retirement for US Households, 2013)
We analyze labor supply preferences around retirement for US households coming from the Health and Retirement Study. A collective structural life cycle model of joint retirement of couples is speciﬁed and estimated. Respondents were given hypothetical retirement scenarios describing age(s) of retirement of both spouses and replacement rate(s). Preferences and the intrahousehold bargaining process are identiﬁed by using stated preference data. Parameters of the utility functions vary with observed and unobserved characteristics. Our results support the collective model rather than the unitary model.
Keywords: Adult children; Employment and Labor Force; Retirement Planning and Satisfaction

Leaving Retirement: Age-Graded Relative Risks of Transitioning Back to Work or Dying - Ben Lennox Kail; David F Warner (Population Research and Policy Review, 2013)
Demographic research has documented the age-graded risk of returning to work after a period of retirement; few studies, however, have disaggregated this risk into the different forms work takes in later life. Moreover, prior research has not explored the age-graded risk of re-retiring after reentry. This study uses the 1992-2008 Health and Retirement Study to first examine the age-graded and duration dependent risks of transitioning to full-time work, part-time work, and mortality from full retirement. Second, this study documents the age-graded duration of reemployment, and the age-graded risk of re-retiring. Results from multi-decrement life tables indicate reemployment both occurs more frequently and lasts longer than previously estimated. The gender differences in risk of reemployment are modest, although women are at greater risk of returning to part-time work, whereas men are at greater risk of returning to full-time work. Additionally, retirees from services-producing industries are at lower risk of transitioning to work, but greater risks of mortality, suggesting retirement is a less permanent feature in the life course of retirees from goods-producing industries. Finally, the results suggest Social Security benefit eligibility plays a part in reducing reentry at later ages.
Copyright - Springer Science Business Media Dordrecht 2013 Document feature - References; Tables Last updated - 2013-03-19 DOI - 2918962981; 76329142; 53495; PPRP; SPVLPPRP111133229256 SubjectsTermNotLitGenreText - United States--US Brown, T., and Warner, D. (2008). Divergent pathways? Racial/ethnic differences in older women's labor force withdrawal. Journal of Gerontology: Social Sciences, 63 (3), S122 S134. Brown, T., and Warner, D. (2008). Divergent pathways? Racial/ethnic differences in older women?s labor force withdrawal. italic Journal of Gerontology: Social Sciences, /italic italic 63 /italic (3), S122S134. Bureau of Labor Statistics. (2011). B-1. Employees on nonfarm payrolls by major industry sector, 1961 to date. U.S. Department of Labor. Bureau of Labor Statistics. (2008). BLS Standard for Sector Aggregation Titles for NAICS. U. S. Department of Labor. Burkhauser, Richard V.; Rovba, Ludmila. Institutional and individual responses to structural lag: The changing patterns of work at older ages. Aging and work: Issues and implications in a changing landscape. (2009): 9-34. Johns Hopkins University Press Burr, Jeffrey A; Mutchler, Jan E; Burr, Jeffrey A. Employment in Later Life: A Focus on Race/Ethnicity and Gender. Generations, 31. 1 (2007): 37-44. American Society on Aging, San Francisco CA Cahill, K., Giandrea, M., and Quinn, J. (2007). Down shifting: The role of bridge jobs after career employment. The Boston College Center on aging and work issue brief 6. Cahill, Kevin E.; Giandrea, Michael D.; Quinn, Joseph F. Retirement Patterns from Career Employment. The Gerontologist, 46. 4 (2006): 514-523. Gerontological Society of America Clark, Robert L; Clark, Robert L; Quinn, Joseph F. Patterns of work and retirement for a new century. Generations, 26. 2 (2002): 17-24 Costa, Dora L; Costa, Dora L. The evolution of retirement: An American economic history, 1880-1990. (1998): xiii, 234. NBER Series on Long-Term Factors in Economic Development. Chicago and London: University of Chicago Press Czaja, Sara J; Sharit, Joseph. Aging and work: issues and implications in a changing landscape. Aging and work: issues and implications in a changing landscape (2009): xvi, 432. Johns Hopkins University Press Ekerdt, D J; DeViney, S. ON DEFINING PERSONS AS RETIRED. JOURNAL OF AGING STUDIES, 4. 3 (1990): 211-229. JAI PRESS INC Even, William; MacPherson, David. Defined contribution plans and the distribution of pension wealth. INDUSTRIAL RELATIONS, 46. 3 (2007): 551-581. BLACKWELL PUBLISHING Flippen, Chenoa; Tienda, Marta. Pathways to retirement: patterns of labor force participation and labor market exit among the pre-retirement population by race, Hispanic origin, and sex. Journals of Gerontology, Series B, Psychological Sciences and Social Sciences H.W. Wilson - SSA , 55B. 1 (2000): S14-S27 Han, S K; Moen, P. Clocking out: Temporal patterning of retirement. AMERICAN JOURNAL OF SOCIOLOGY, 105. 1 (1999): 191-236. UNIV CHICAGO PRESS Hardy, Melissa. Older Workers. Handbook of aging and the social sciences (6th ed.). (2006): 201-218. Elsevier Hardy, Ma. EMPLOYMENT AFTER RETIREMENT - WHO GETS BACK IN. RESEARCH ON AGING, 13. 3 (1991): 267-288. SAGE SCIENCE PRESS HARDY, Melissa A.; SHUEY, Kim. Pension decisions in a changing economy : Gender, structure, and choice. The Journals of gerontology. Series B, Psychological sciences and social sciences, 55. 5 (2000): S271-S277. Gerontological Society of America Hardy M. Handbook of aging and the social sciences. Hayward, M D; Grady, W R; Hardy, M A; Sommers, D. Occupational influences on retirement, disability, and death. Demography, 26. 3 (1989): 393-409. Population Association of America Hayward, M., and Grady, W. (1990). Work and retirement among a cohort of older men in the United States, 19661983. italic Demography, /italic italic 27 /italic (3), 337356. Hayward, M., and Grady, W. (1990). Work and retirement among a cohort of older men in the United States, 1966 1983. Demography, 27 (3), 337 356. Hayward, Mark D; Hardy, Melissa A; Liu, Mei-Chun; Hayward, Mark D. Work after Retirement: The Experiences of Older Men in the United States. Social Science Research, 23. 1 (1994): 82-107 Health and Retirement Study. (2008). Public use dataset. Produced and distributed by the University of Michigan with funding from the National Institute on Aging (Grant Number NIA U01AG009740). Ann Arbor, MI. Hinterlong, James E; Hinterlong, James E. Productive Engagement Among Older Americans: Prevalence, Patterns, and Implications for Public Policy. Journal of Aging and Social Policy, 20. 2 (2008): 141-164. The Haworth Press, Binghamton NY Hogan, Richard; Perrucci, Carolyn C. Black women: Truly disadvantaged in the transition from employment to retirement income. SOCIAL SCIENCE RESEARCH, 36. 3 (2007): 1184-1199. ACADEMIC PRESS INC ELSEVIER SCIENCE Howard, Christopher. The hidden welfare state: tax expenditures and social policy in the United States. The hidden welfare state: tax expenditures and social policy in the United States (1997): xi, 250. Princeton University Press Idler, Ellen L; Idler, Ellen L. Discussion: Gender differences in self-rated health, in mortality, and in the relationship between the two. The Gerontologist, 43. 3 (2003): 372-375 Juster, F Thomas; Suzman, Richard. An overview of the Health and Retirement Study. Journal of Human Resources, v30. n1 (1995): pS7(50). University of Wisconsin Press Kail, Ben Lennox. Coverage or Costs: The Role of Health Insurance in Labor Market Reentry Among Early Retirees. The Journals of Gerontology 67B:1 Jan 2012 Li, X., Hurd, M., and Loughran, D. (2008). The characteristics of social security beneficiaries who claim benefits at the early entitlement age. AARP Research Report 2008-19. Maestas, Nicole. Back to Work: Expectations and Realizations of Work after Retirement. Journal of Human Resources, 45. 3 (2010): 718-748. University of Wisconsin Press. 1930 Monroe Street Mitchell, O S; Levine, P B; Pozzebon, S. RETIREMENT DIFFERENCES BY INDUSTRY AND OCCUPATION. GERONTOLOGIST, 28. 4 (1988): 545-551. GERONTOLOGICAL SOCIETY AMER Munnell, Alicia Haydock; Sass, Steven A. Working longer: the solution to the retirement income challenge. Working longer: the solution to the retirement income challenge (2008): vii, 207. Brookings Institution Press O'Rand, Angela M.; Shuey, Kim M. Gender and the devolution of pension risks in the US. CURRENT SOCIOLOGY, 55. 2 (2007): 287-304. SAGE PUBLICATIONS LTD Padavic I, Reskin B. Women and men at work. Pleau, Robin L. Gender Differences in Postretirement Employment. RESEARCH ON AGING, 32. 3 (2010): 267-303. SAGE PUBLICATIONS INC Quadagno, Jill; Street, Debra. Recent trends in U.S. social welfare policy: Minor retrenchment or major transformation? Research on Aging, 28. 3 (2006): 303-316. SAGE Publications Inc RAND Center for the Study of Aging. (2008). RAND HRS Data, Version H. Santa Monica, CA, With Funding From the National Institute on Aging and the Social Security Administration. Reskin, Barbara F; Padavic, Irene; Reskin, Barbara F. WOMEN AND MEN AT WORK. (1994): xv 218. Pine Forge Press Rosenfeld, Rachel A; Rosenfeld, Rachel A. Women's Work Histories. Population and Development Review, 22. (1996): 199-222 Ruhm, C J. BRIDGE JOBS AND PARTIAL RETIREMENT. JOURNAL OF LABOR ECONOMICS, 8. 4 (1990): 482-501. UNIV CHICAGO PRESS Schoen, Robert. Modeling multigroup populations. Modeling multigroup populations (1988): xii, 308. Plenum Shuey, Kim M.; O'Rand, Angela M. New Risks for Workers: Pensions, Labor Markets, and Gender. Annual Review of Sociology, 30. (2004): 453-477. Annual Reviews Skoog, Gary R.; Ciecka, James E. MEASURING YEARS OF INACTIVITY, YEARS IN RETIREMENT, TIME TO RETIREMENT, AND AGE AT RETIREMENT WITHIN THE MARKOV MODEL. DEMOGRAPHY, 47. 3 (2010): 609-628. POPULATION ASSOC AMER Social Security Administration. (2010b). Social security retirement benefits. SSA Publications 05-10035. Social Security Administration. (2011). Exempt amounts under the earnings test. Retrieved January 15, 2012, from http://www.ssa.gov/oact/COLA/rtea.html . Social Security Administration. (2010a). Historical background and development of social security. Szinovacz, Maximiliane E; DeViney, Stanley. The retiree identity: gender and race differences. Journals of Gerontology, Series B, Psychological Sciences and Social Sciences H.W. Wilson - SSA , 54B. 4 (1999): S207-S218 U.S. Census Bureau. Statistical Abstract of the United States: 2003 (2003): U.S. Census Bureau (Washington, DC) Warner, David F.; Hayward, Mark D.; Hardy, Melissa A. The Retirement Life Course in America at the Dawn of the Twenty-First Century. POPULATION RESEARCH AND POLICY REVIEW, 29. 6 (2010): 893-919. SPRINGER Warner, D. and Hofmeister, H. (2006). Late career transitions among men and women in the United States. In H.-P. Blossfeld, S. Buchholz, and D. Hof cker (Eds.), italic Globalization, uncertainty and late careers in society /italic (pp. 141181). London: Routledge. Warner, D. and Hofmeister, H. (2006). Late career transitions among men and women in the United States. In H.-P. Blossfeld, S. Buchholz, and D. Hof cker (Eds.), Globalization, uncertainty and late careers in society (pp. 141 181). London: Routledge. Wise, David A. FACILITATING LONGER WORKING LIVES: INTERNATIONAL EVIDENCE ON WHY AND HOW. DEMOGRAPHY, 47. (2010): S131-S149. POPULATION ASSOC AMER Wise, D. A. (2004). Social security provisions and the labor force participation of older workers. Population and Development Review, 30, Supplement (Aging, Health, and Public Policy), 176 205. Wise, D. A. (2004). Social security provisions and the labor force participation of older workers. italic Population and Development Review, 30, Supplement /italic (Aging, Health, and Public Policy), 176205.
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Public Policy; Retirement Planning and Satisfaction; Risk Taking

Life expectancy as a constructed belief: Evidence of a live-to or die-by framing effect - Payne, John W.; Sagara, Namika; Shu, Suzanne B.; Appelt, Kirstin C.; Johnson, Eric J (Journal of Risk and Uncertainty, 2013)
Life expectations are essential inputs for many important personal decisions. We propose that longevity beliefs are responses constructed at the time of judgment, subject to irrelevant task and context factors, and leading to predictable biases. Specifically, we examine whether life expectancy is affected by the framing of expectations questions as either live-to or die-by, as well as by factors that actually affect longevity such as age, gender, and self-reported health. We find that individuals in a live-to frame report significantly higher chances of being alive at ages 55 through 95 than people in a corresponding die-by frame. Estimated mean life expectancies across three studies and 2300 respondents were 7.38 to 9.17 years longer when solicited in a live-to frame. We are additionally able to show how this framing works on a process level and how it affects preference for life annuities. Implications for models of financial decision making are discussed. PUBLICATION ABSTRACT
Keywords: Expectations; Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Managing retirement resources: evidence from the HRS - Chris Browning (Managing retirement resources: evidence from the HRS, 2013)
Households are required to make a variety of decisions in pursuit of their retirement goals. These decisions are often complex and require the estimation and input of multiple factors when analyzing alternatives. Complexity and uncertainty have been found to lead to behavioral biases and a dependence on heuristics when making decisions. These deficiencies create a failure to incorporate valuable information, an overreliance on recent events, and inaccurate estimations of future outcomes. When these factors are combined with widespread low levels of financial sophistication and declining cognition the result is often behavior that is contradictory to rational expectations and detrimental to lifetime wealth and utility. Households are bound at a variety of levels by the limitations described above. Sophisticated households and those with higher levels of cognitive ability are more likely to participate in financial markets, enjoy higher returns on investments, and greater levels of wealth. Those with less sophistication and cognitive ability may fail to understand complex financial products, have less consistent preferences, and be more likely to engage in behavior that is inconsistent and detrimental to long-term goals and overall well-being. Given the variation in levels of financial sophistication and cognitive ability, we seek to evaluate how households make decisions in the face of market complexity, and in some cases how these decisions affect financial outcomes. Using the Health and Retirement Study (HRS) we give special focus to the decisions and behavior of older households. We look specifically at the impact of financial sophistication on individuals' ability to accurately value life annuities, how cognitive ability is related to stock reallocations during the great recession, and how cognitive ability relates to the asset decumulation decisions of retirees.
Keywords: Expectations; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

The Market for Financial Advice - Olivia S. Mitchell; Smetters, Kent (Pension Research Council Series, 2013)
Keywords: Economics; Financial literacy; Market analyses; Older Adults; Retirement Planning and Satisfaction

Mechanisms of the effect of involuntary retirement on older adults' health and mental health - Min-Kyoung Rhee (Mechanisms of the effect of involuntary retirement on older adults' health and mental health, 2013)
The purpose of the present study is to provide in-depth information on older adults' experience of involuntary retirement by examining mechanisms of the effect of involuntary retirement on self-rated health and mental health among adults aged 50 years or older. Although it is a normative expectation to perceive retirement as a phase of life in which older adults become disengaged from paid work, volunteer, and enjoy leisure time with family, not everyone has the luxury of maintaining control over their retirement decisions. Approximately one third of retirees perceive their retirement as forced rather than voluntary. Involuntary retirees are likely to face greater challenges than voluntary retirees during their postretirement adjustment period because they have multiple burdens of health, mental health, and job displacement issues that may have partially led them to involuntarily retire. The prevalence of involuntary retirement is likely to increase because older adults are expected to work longer due to increased financial responsibility despite the challenge of securing or maintaining employment. Although an expanding body of research has addressed various topics of retirement including preretirement planning and decision making, relatively few studies on retirement have focused on the voluntariness of retirement or its varied contexts. Research that has explored health and mental health outcomes after retirement without accounting for voluntariness has reported mixed findings. Considering the fact that retirement has become a more complex and diverse life transition, it is critical to consider the nature of retirement as well as its contexts. To fill this gap of knowledge in research and practice, this study had two specific aims: (1) to explore the prevalence of involuntary retirement among older adults and the extent to which the characteristics of involuntary retirees are different from voluntary retirees or those who did not retire, and (2) to investigate the mechanisms of the health and mental health effect of involuntary retirement by examining the potential mediating effects of financial control, positive and negative family relationships, and social integration. The research questions and hypotheses were formulated based on the life course perspective and latent deprivation theory. Using two waves of longitudinal data extracted from Health and Retirement Study (2006 and 2010), a final sample of 1,280 individuals working for pay at baseline who responded to a lifestyle questionnaire in both waves was selected. Univariate, bivariate, and regression-based path analyses were conducted using SPSS 18.0. This study employed a multiple mediation model that considered four mediators simultaneously and the model was estimated in three phases. Results of the study found that 29.3% (n = 429) of the sample retired between 2006 and 2010, and 37.2% (n = 155) of those individuals reported that they retired involuntarily. Results of Phase 1, a multiple mediator model that did not account for voluntariness of retirement using a binary independent variable (retired or not), indicated that there was no significant direct or indirect effects of retirement on self-rated health and mental health outcomes. In Phase 2, in which the same model was estimated using a multicategorical independent variable (involuntarily retired, voluntarily retired, not retired), involuntary retirement had an direct adverse health effect compared to not retiring, whereas voluntary retirement had an indirect positive health effect via financial control. In terms of mental health outcomes, the positive mental health effect of voluntary retirement was mediated by financial control, whereas involuntary retirement had no significant effect. Results of Phase 3, a model that considered retirees only, revealed direct adverse health effects of involuntary retirement compared to voluntary retirement. Involuntary retirement also had an indirect effect on mental health via financial control. Findings of this stu y indicate the significance of specifying the nature of retirement when conducting retirement research and the need to pay more attention to potential detrimental effects of involuntary retirement. Implications of the findings are discussed with regard to retirement policy, research, and social work.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2014-03-18 First page - n/a
Keywords: Health Conditions and Status; Healthcare; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

Mental retirement and schooling - Bingley, Paul; Martinello, Alessandro (European Economic Review, 2013)
We assess the validity of differences in eligibility ages for early and old age pension benefits as instruments for estimating the effect of retirement on cognitive functioning. Because differences in eligibility ages across country and gender are correlated with differences in years of schooling, which affect cognitive functioning at old ages, they are invalid as instruments without controlling for schooling. We show by means of simulation and a replication study that unless the model incorporates schooling, the estimated effect of retirement is negatively biased. This explains a large part of the mental retirement effects which have recently been found.
Keywords: Cross-National; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Moving Considerations: A Longitudinal Analysis of Parent-Child Residential Proximity for Older Americans - Zhang, Yiduo; Michal Engelman; Emily M. Agree (Research on Aging, 2013)
Residential proximity is an important indicator of family members' availability to provide assistance to each other. We investigate proximity-enhancing moves by older parents and their children and the reasons for such moves. Using the 2000-2004 waves of the Health and Retirement Study, we fit multinomial logit models examining 2-year residential transitions for parents and children living 10 or more miles apart at baseline. Our results show that family members collectively adjust intergenerational proximity to facilitate mutual support. Despite the common assumption that older parents move closer to their children to receive assistance, more than two thirds of all proximity-enhancing moves are made by adult children. While greater anticipated longevity raises the probability that older parents will move closer to their children, parents' anticipated longevity does not influence children's moving decisions. Including individual variability in anticipated longevity in the life course framework helps account for relocation that precedes declines in health or increases in the need for support.
Keywords: Adult children; Demographics; Event History/Life Cycle; Expectations; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

New Evidence on Self-Employment Transitions Among Older Americans with Career Jobs - Kevin E. Cahill; Glandrea, Michael D.; Joseph F. Quinn (Washington, DC, U.S. Bureau of Labor Statistics, 2013)
How have post-career transitions into and out of self-employment been impacted by the Great Recession? Research from the 1990s and 2000s has shown that the prevalence of self employment increases substantially later in life, partly because self employment provides older workers with opportunities and flexibility not found in wage-and-salary jobs. Post-career transitions into and out of self employment have also been identified as an important pathway to retirement among older Americans. This paper examines post-career self-employment transitions during the recent recession that began in late 2007 and during the ensuing lackluster recovery. We utilize the Health and Retirement Study (HRS), a nationally-representative longitudinal dataset of older Americans, to investigate the role of self-employment in the retirement transitions of HRS Core respondents over nearly two decades, from 1992 to 2010, with particular emphasis on the most recent years. We find that post-career transitions into and out of self employment remain common in the face of the Great Recession, and that health status, occupation, and financial variables continue to be important determinants of switches from wage-and-salary career employment to self-employed bridge jobs. The latest evidence confirms that self employment continues to be an important pathway to retirement even during recessionary times.
Keywords: Employment and Labor Force; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Older Adult Debt and Financial Frailty - Annamaria Lusardi; Olivia S. Mitchell (Ann Arbor, The University of Michigan, 2013)
Of particular interest in the present economic environment is whether access to credit is changing peoples indebtedness over time, particularly as they approach retirement. This project analyzes older individuals debt, debt management practices, and financial fragility using data from the Health and Retirement Study (HRS) and the National Financial Capability Study (NFCS). Specifically, we examine three different cohorts (individuals age 56 61) in different time periods, 1992, 2002 and 2008, in the HRS to evaluate cross-cohort changes in debt over time. We also draw on recent data from the National Financial Capability Study (NFCS) which provides detailed information on how families manage their debt. Our goal is to assess how wealth and debt among older persons has evolved over time, along with the potential consequences for retirement security. We find that more recent cohorts have taken on more debt and face more financial insecurity, mostly due to having purchased more expensive homes with smaller down payments. In addition, Baby Boomers are more likely to have engaged in expensive borrowing practices. Factors associated with better debt outcomes include having higher income, more education, and greater financial literacy; those associated with financial fragility include having more children and experiencing unexpected large income declines. Thus, shocks do play a role in the accumulation of debt close to retirement. But it is not enough to have resources, people also need the capacity to manage those resources if they are to stay out of debt as they head into retirement.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Pain and Use of Alcohol in Later Life: Prospective Evidence from the Health and Retirement Study - Penny L. Brennan; SooHoo, Sonya (Journal of Aging and Health, 2013)
To determine whether (a) late-life pain predicts growth in older adults' use of alcohol, and elevated risk of drinking problems; and (b) sociodemographic characteristics moderate these relationships. Five times over an 8-year interval, N = 5,446 Health and Retirement Study (HRS) participants provided information about their pain and alcohol use. Two-part latent growth modeling and logistic regression were used to analyze these data. Participants with more pain at baseline had lower initial levels and a faster rate of decline over the next 8 years in alcohol consumption, but they also were at elevated risk of having drinking problems. Income and African American background interacted with pain to predict 8-year change in alcohol consumption and presence of drinking problems. Late-life pain does not predict growth in older adults' alcohol consumption, but is nonetheless linked to elevated risk of drinking problems, especially among African Americans.
Copyright - Copyright SAGE PUBLICATIONS, INC. Jun 2013 Last updated - 2013-06-18
Keywords: Demographics; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Perceived Weight Discrimination and Obesity - Angelina R Sutin; Antonio Terracciano (PLoS One, 2013)
Weight discrimination is prevalent in American society. Although associated consistently with psychological and economic outcomes, less is known about whether weight discrimination is associated with longitudinal changes in obesity. The objectives of this research are (1) to test whether weight discrimination is associated with risk of becoming obese (Body Mass Index 30; BMI) by follow-up among those not obese at baseline, and (2) to test whether weight discrimination is associated with risk of remaining obese at follow-up among those already obese at baseline. Participants were drawn from the Health and Retirement Study, a nationally representative longitudinal survey of community-dwelling US residents. A total of 6,157 participants (58.6 female) completed the discrimination measure and had weight and height available from the 2006 and 2010 assessments. Participants who experienced weight discrimination were approximately 2.5 times more likely to become obese by follow-up (OR = 2.54, 95 CI = 1.58-4.08) and participants who were obese at baseline were three times more likely to remain obese at follow up (OR = 3.20, 95 CI = 2.06-4.97) than those who had not experienced such discrimination. These effects held when controlling for demographic factors (age, sex, ethnicity, education) and when baseline BMI was included as a covariate. These effects were also specific to weight discrimination; other forms of discrimination (e.g., sex, race) were unrelated to risk of obesity at follow-up. The present research demonstrates that, in addition to poorer mental health outcomes, weight discrimination has implications for obesity. Rather than motivating individuals to lose weight, weight discrimination increases risk for obesity.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

The predictive validity of subjective mortality expectations: evidence from the health and retirement study - Todd E. Elder (Demography, 2013)
Several recent studies suggest that individual subjective survival forecasts are powerful predictors of both mortality and behavior. Using 15 years of longitudinal data from the Health and Retirement Study, I present an alternative view. Across a wide range of ages, predictions of in-sample mortality rates based on subjective forecasts are substantially less accurate than predictions based on population life tables. Subjective forecasts also fail to capture fundamental properties of senescence, including increases in yearly mortality rates with age. To shed light on the mechanisms underlying these biases, I develop and estimate a latent-factor model of how individuals form subjective forecasts. The estimates of this model's parameters imply that these forecasts incorporate several important sources of measurement error that arguably swamp the useful information they convey.
Keywords: Expectations; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

Recent Changes in the Gains from Delaying Social Security - John B. Shoven; Sita Nataraj Slavov (Cambridge, MA, National Bureau of Economic Research, 2013)
Social Security retirement benefits can be claimed at any age between 62 and 70, with delayed claiming resulting in larger monthly payments. In Shoven and Slavov (2013), we show that claiming later increases the present value of lifetime benefits for most individuals. However, this has not always been the case. During the late 1990s and early 2000s, a number of policy changes increased the gains from delay, particularly for couples. In addition, mortality improved and real interest rates fell substantially over this period, further increasing the attractiveness of delay. We perform simulations to examine the role of these factors in changing the gains from delay. We find that the gains from delay increased substantially after 2000, with changes in the interest rate playing the largest role in driving the increase. Using data from the Health and Retirement study, we show that individuals who turned 62 after 2000 are indeed more likely to delay than those who turned 62 before 2000. However, even in the younger cohort, most individuals still claim benefits soon after turning 62. Moreover, we find no evidence of a relationship between the probability of delay and the individual characteristics (e.g., gender, race, or health status) that affect the gains from delay.
Keywords: Retirement Planning and Satisfaction; Social Security

Reciprocity Between Depressive Symptoms and Physical Limitations Pre- and Postretirement: Exploring Racial Differences - Gayman, Mathew D.; Pai, Manacy; Ben Lennox Kail; Miles G Taylor (Journal of Aging and Health, 2013)
This study assesses (a) the reciprocity between mental and physical health pre- and postretirement, and (b) the extent to which these associations vary by race. Data are from the 1994 to 2008 waves of the Health and Retirement Study. Analyses based on structural equation modeling reveal that depression and physical health exert reciprocal effects for Whites pre- and postretirement. For Blacks preretirement, physical limitations predict changes in depression but there is no evidence of the reverse association. Further, the association between physical limitations and changes in depressive symptoms among Blacks is no longer significant after retirement. The transition into retirement alleviates the translation of physical limitations into depressive symptoms for Blacks only. The findings underscore the relevance of retirement for reciprocity between mental and physical health and suggest that the health implications associated with this life course transition vary by race.
Copyright - Copyright SAGE PUBLICATIONS, INC. Jun 2013 Last updated - 2013-06-18
Keywords: Demographics; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Retiree Health Benefits as Deferred Compensation: Evidence from the Health and Retirement Study - J. Marton; Stephen A. Woodbury (Public Finance Review, 2013)
Are early retiree health benefits (RHBs) a form of deferred compensation binding workers to an employer? Most employers who offer RHBs offer them only to workers who have ten or more years of tenure and have reached age fifty-five. Accordingly, workers in firms offering RHBs have an incentive to stay with a firm in the years before they attain eligibility for RHBs, and a greater incentive than otherwise to retire thereafter. The authors test for such a pattern of incentives by examining the age-specific relationship between workers' eligibility for RHBs and retirement. The findings suggest that workers in RHB-offering firms are less likely to retire at ages fifty and fifty-one than similar RHB-ineligible workers. Also, RHB-eligible workers aged sixty and sixty-one are more likely to retire than similar RHB-ineligible workers. These results are consistent with RHBs acting as part of a delayed payment contract of the kind described by Lazear. The Author(s) 2012.
Keywords: Income; Medicare/Medicaid/Health Insurance; Pensions; Public Policy; Retirement Planning and Satisfaction

Is Self-Rated Health Comparable Between Non-Hispanic Whites and Hispanics? Evidence From the Health and Retirement Study - Su, Dejun; Wen, Ming; Kyriakos S Markides (The Journals of Gerontology, 2013)
Using subsequent all-cause mortality as a yardstick for retrospective health, this study assessed the comparability of self-rated health (SRH) between non-Hispanic whites and Hispanics. Based on longitudinal data from 6,870 white and 886 Hispanic respondents aged between 51 and 61 in the 1992 Health and Retirement Study, we related SRH in 1992 to risk of mortality in the 1992-2008 period. Logit models were used to predict white-Hispanic differences in reporting fair or poor SRH. Survival curves and cox proportional hazard models were estimated to assess whether and the extent to which the SRH-mortality association differs between non-Hispanic whites and Hispanics. Hispanic respondents reported worse SRH than whites at the baseline, yet they had similar risk of mortality as whites in the 1992-2008 period. Overall, Hispanics rated their health more pessimistically than whites. This was especially the case for Hispanics who rated their health fair or poor at the baseline, whereas their presumed health conditions, as reflected by subsequent risk of mortality, should be considerably better than their white counterparts. Health disparities between whites and Hispanics aged between 51 and 61 will be overestimated if the assessment has been solely based on differences in SRH between the two groups. Findings from this study call for caution in relying on SRH to quantify and explain health disparities between non-Hispanic whites and Hispanics in the United States.
Copyright - Copyright Oxford University Press, UK Jul 2013 Last updated - 2013-06-21 SubjectsTermNotLitGenreText - United States--US
Keywords: Demographics; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction; Women and Minorities

Social Security Benefit Claiming and Medicare Utilization - John Bound; Helen G Levy; Lauren Hersch Nicholas (Ann Arbor, MI, University of Michigan Retirement Research Center, 2013)
Are early Social Security claimers too sick to work? We linked Health and Retirement Study data to Medicare claims to study health care utilization at ages 65 and 70. We find that Social Security Disability Insurance recipients use more health care on average than those who never received DI. At age 65, Medicare spending on SSDI recipients was 4,440 less than spending on retirees who claimed Social Security benefits prior to Full Retirement Age (FRA) and 4,727 less than those claiming at FRA. Differences in Medicare spending persist at all points of the spending distribution. They are robust to a variety of methodological approaches including general linear models, quantile regression, and reweighting, and in specifications limiting comparisons to beneficiaries claiming benefits at initial EEA. Our results suggest that poor health may contribute to EEA claiming decisions, though this group is considerably healthier than those who were too disabled to work and qualified for DI benefits.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction; Social Security

The Social Security Windfall Elimination and Government Pension Offset Provisions for Public Employees in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Ann Arbor, The University of Michigan, 2013)
This paper uses data from the Health and Retirement Study to investigate the effects of Social Security s Windfall Elimination Provision (WEP) and Government Pension Offset (GPO) provision on Social Security benefits received by individuals and households. WEP reduces the benefits of individuals who worked in jobs covered by Social Security and also worked in uncovered jobs where a pension was earned. WEP also reduces spouse benefits. GPO reduces spouse and survivor benefits for persons who worked in uncovered government employment where they also earned a pension. Unlike previous studies, we take explicit account of pensions earned on jobs not covered by Social Security, a key determinant of the size of WEP and GPO adjustments. Also unlike previous studies, we focus on the household. This allows us to incorporate the full effects of WEP and GPO on spouse and survivor benefits, and to evaluate the effects of WEP and GPO on the assets accumulated by affected families. Among our specific findings: About 3.5 percent of households are subject to either WEP or to GPO. The present value of their Social Security benefits is reduced by roughly one fifth. This amounts to five to six percent of the total wealth they accumulate before retirement. Households affected by both WEP and GPO lose about one third of their benefit. Limiting the Social Security benefit to half the size of the pension from uncovered employment reduces the penalty from WEP for members of the original HRS cohort by about 60 percent.
Keywords: Public Policy; Retirement Planning and Satisfaction; Social Security

Socioeconomic Status and Health Well-Being during Later Life: Potential Mediating Factors - Hsu, Tze-Li; Cossman, Jeralynn S. (Sociological Spectrum, 2013)
This study explores the socioeconomic status (SES)-perceived health association, with special attention on living arrangements. It improves upon existing explanations of causal mechanisms underlying the impact of SES on health among the elderly. Using Health and Retirement Study to run ordered logistic regression, it addresses the importance of living arrangements for self-reported health. Income and education are both important predictors of self-reported health and that after controlling them, living arrangements also affect self-reported health. Future research should highlight nuanced measures of living arrangements and should explore longitudinal analyses to determine the long-term effects of these factors on self-reported health.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

SSI Participation Among the Elderly: A Hazard Model Approach - Jin H. Kim (Journal of Poverty, 2013)
This study revisits the historic policy concern over nonparticipation in the Supplemental Security Income (SSI) program. The most contemporary research model suggests that from a cross-sectional perspective, the elderly take-up decision is primarily determined by the financial situation of the eligible individuals. Yet extant studies have yet to establish a longitudinal model of SSI participation that explicitly takes into account the changing circumstances of the elderly. As such, this study extends the current literature by exploring the time-varying processes leading to eventual take-up of benefits among the elderly. Methodologically, the research relies on event history analysis of data from the Health and Retirement Study spanning the years 1996 to 2006 to explain the varying rates of participation over time as well as the role of life events on the take-up decision. 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Demographics; Event History/Life Cycle; Methodology; Other; Retirement Planning and Satisfaction; Social Security

A taxa de atividade economica e saude mental: a relacao entre aposentadoria e depressao - Terra, Luisa Pimenta; Queiroz, Bernardo Lanza (Revista Debate Econ mico, 2013)
As ltimas d cadas observaram um crescimento acelerado de transtornos mentais na sociedade, com cerca de 450 milh es de pessoas com esse diagn stico no mundo. O alto custo para o sistema de sa de e para a qualidade de vida das pessoas refor a a discuss o do tema como uma quest o de sa de p blica. H uma ampla discuss o sobre o efeito da depress o na decis o de sa da do mercado de trabalho das pessoas mais idosas. Entretanto, h resultados recentes que apontam o aumento do n mero de aposentadorias precoces em diversos pa ses. O objetivo deste trabalho investigar qual a rela o entre a rec m-aposentadoria e a depress o em mulheres norte-americanas. Dados longitudinais do Health and Retirement Study entre 1992 e 2004 s o utilizados. A hip tese central que ser rec m-aposentada tem rela o negativa com o quadro de depress o, e baseada na ideia da intera o social como um agente protetor da depress o. Os resultados mostram que aposentar tem forte rela o com depress o. Mulheres rec m-aposentadas apresentam pior quadro de depress o do que as mulheres n o aposentadas e do que as que j est o aposentadas h mais de um ano. The last decades have observed a rapid increase of mental disorders in society, with about 450 million people with this diagnosis in the world. The high cost to the health system and the quality of life reinforces the discussion of the issue as a public health issue. There is an extensive discussion on the effect of depression in the decision to leave the labor market for older people. However, recent results indicate that the increase in the number of early retirement in many countries. The objective of this study is to investigate the relation between the newly-retirement and depression in U.S. women. Longitudinal data from the Health and Retirement Study between 1992 and 2004 are used. The central hypothesis is that being newly retired is negatively related to depressive states, and is based on the idea of social interaction as a protective agent of depression. The results show that retirement is strongly related to depression. Newly retired women have a worse picture of depression than women not retired and those who are already retired for over a year.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Three essays in family economics - Chan, Kwok Ho (Three essays in family economics, 2013)
This dissertation contains three essays. It provides analysis on issues concerning about family economics. The first essay investigates issues about intergenerational transfer in China. Does parental support in China respond to low income of the elderly? Intergenerational transfers from adult children to their parents are thought to contribute a significant portion of old-age support in China. With a fast growing elder population and an increasing old-age dependency ratio, it is important to understand these transfers. This study investigates the determining factors of intergenerational transfers in China. This line of research is still lacking due to the scarcity of detailed household data. Past studies on private transfers in China could not differentiate between intergenerational versus intragenerational transfers. Using pilot data from the newly released China Health and Retirement Longitudinal Study (CHARLS), I found that around half of the sampled households received transfers from adult children and the amount of transfer is as much as two-thirds of household income per capita. Data also showed that poorer households are more likely to receive transfers. Data suggested that people in the poor province (Gansu) have a higher degree of dependence on adult children, as the source of providing old-age support and living arrangement. Seeing how private transfers are large, widespread, and responsive to income, the benefits from instituting appropriate public policy would likely accrue in part to younger generations by lessening their burden of familial support. The second essay examines the effect of social father on the well-being of out-of-wedlock children. Social fathers, defined as stepfathers or unrelated cohabiting romantic partners of biological mothers, have become more widespread as a result of the increasing out-of-wedlock childbearing. With more young children living with social fathers, it is important to understand the effect of social fathers on the well-being of children. Previous research focused more on such effect on older children or adolescents. Using data from the Fragile Families and Child Wellbeing Study (FFCWS), I find that children with social fathers scored around three points less in a cognitive ability test than children living only with biological mothers. I used the propensity score matching method to address the selection issue for which the child's mother self-selected into having a new partner. Social fathers will be more common because of the widespread of non-marital births. Any negative effect caused by the social fathers will affect a large portion of child population. The third essay evaluates the association between the timing of parenthood and the timing of retirement. Is late parenting associated with late retirement? The trend of parenthood timing is under drastic change. The birth rate for women aged 30-34 rose from 52.3 births per 1000 women in 1975 to 96.5 births per 1000 women in 2010 while the birth rate for women aged 20-24 went down from 113 births to 90 births per 1000 women during the same period. The children may still be very young when their parents enter their retirement age. In the Health and Retirement Study (HRS), 20% of respondents' children lived with them while nearly 30% of these children were below 18 years of age. Despite the potential importance of this issue, economists have not done much research on it. Using the HRS, this study found that parents who have their first child before or at age 30 retire earlier than parents who have their first child after age 30. This positive association holds for different sub-groups of the sample. With significant portion of people delaying their parenthood and a large group of people entering their retiring age, it is very important for policy makers and economists to understand how the timing of parenthood associates with the timing of retirement.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2013 Last updated - 2013-08-23 First page - n/a
Keywords: Adult children; Cross-National; Event History/Life Cycle; Methodology; Retirement Planning and Satisfaction

Wages, Pensions, and Public-Private Sector Compensation Differentials for Older Workers - Bewerunge, Philipp; Rosen, Harvey S. (NBER Working Paper, 2013)
We use a sample of full-time workers over 50 years of age from the 2004 and 2006 waves of the Health and Retirement Study to investigate whether workers in federal, state, and local government receive more generous wage and pension compensation than private sector workers, ceteris paribus. With respect to hourly remuneration (wages plus employer contributions to defined contribution plans), federal workers earn a premium of about 28 log points, taking differences in employee characteristics into account. However, there are no statistically discernible differences between state and local workers and their private sector counterparts, ceteris paribus. These findings are about the same whether or not indicators of occupation are included in the model. On the other hand, pension wealth accumulation is greater for employees in all three government sectors than for private sector workers, even after taking worker characteristics into account. As a proportion of the hourly private-sector wage, the hourly equivalent public-private differentials are about 17.2 percent, 13.4 percent, and 12.6 percent for federal, state, and local workers, respectively. We find no evidence that highly-educated individuals are penalized by taking jobs in the public sector, either with respect to wages or pension wealth.
Keywords: Demographics; Employment and Labor Force; Pensions; Retirement Planning and Satisfaction

6 Ways Spending Changes in Retirement - Brandon, Emily (U.S. News & World Report, 2012)
Most people spend less money in retirement than they did while they were working. Retired households spend a median of $31,365 annually, which is about 80% of the $39,945 working households spend, according to a recent Employee Benefit Research Institute analysis of Health and Retirement Study data. Six major ways costs change in retirement are presented.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Behavioral Effects of Social Security Policies on Benefit Claiming, Retirement and Saving - Alan L Gustman; Thomas L. Steinmeier (MRDRC Working Paper, 2012)
This paper specifies three behavioral variants of a structural model of retirement and saving to bring predicted Social Security claiming rates closer to the rates observed in the data. The model, estimated with Health and Retirement Study data, is used to examine three potential policies: increasing early entitlement age, increasing normal retirement age, and eliminating payroll taxes after normal retirement age. Behavioral responses to increasing early entitlement age and eliminating the payroll tax are not affected by the behavioral variant used. Predicted effects of increasing the normal retirement age exhibit more sensitivity. Heterogeneity shapes the responses to these policy changes.
Keywords: Public Policy; Retirement Planning and Satisfaction; Social Security

Determinants of the retirement assets and the amount in stock within retirement assets: Evidence from the Survey of Consumer Finances and the Health and Retirement Study - Ting-Ying Yang; Feinberg, Richard A. (Purdue University, 2012)
The purpose of this research was to investigate the determinants of the retirement assets held in Individual Retirement Accounts, Keogh accounts, and current and future pensions. A second purpose was to investigate the determinants of the amount in stock within those retirement assets. Building upon the theory of human capital, the theory of planned behavior, and the bargaining power model, this study proposed that human capital, attitudes related to finances, and the relative bargaining power of the spouse would influence an individual's retirement assets and the amount in stocks within the retirement assets. Using data from the Survey of Consumer Finances, Study 1 explored the relationship between the three proposed domains and the amount in retirement assets and the amount in stock within the retirement assets. In Study 2, the relationship between the proposed domains was examined using similar variables but with a relatively older sample (e.g., the Health and Retirement Study). The results of both studies supported the theory of human capital and the theory of health capital. Those who had higher education and those who had better health were more likely to have more in retirement assets, and they have more in the amount of stock within retirement assets. Those who saved regularly and were more likely to take risk when saving and investing had more retirement assets and they have more in the amount of stock within retirement assets. The results on the influence of the spouse on retirement assets and the amount in stock within retirement assets showed some support for the bargaining power model. The retirement assets and the amount in stocks within retirement assets were influenced by the spouse. Age, education, working status of the spouse, and who was the more financial knowledgeable person among the two would influence the retirement assets and the amount in stock within retirement assets of the household head. The results of the study supported the existing literature on human capital and health capital. There was some support for the bargaining power model. The results suggest that educators and financial advisors should encourage couples to discuss their plans about saving for retirement with each other and their advisors. However, many people will be single during some or all of their retirement so individual plans for retirement savings should also be carefully developed. This is an important role for educators and financial advisors. However, older adults with fewer resources (e.g. education, employer-sponsored pension plans) will continue to need the support of Social Security.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Other; Pensions; Retirement Planning and Satisfaction

The Displacement Effect of Public Pensions on the Accumulation of Financial Assets. - Michael D Hurd; Pierre-Carl Michaud; Susann Rohwedder (Fiscal Studies, 2012)
The generosity of public pensions may depress private savings and provide incentives to retire early. While there is plenty of evidence supporting the latter effect, there remains considerable controversy whether public pensions crowd out private savings. This paper uses international micro-datasets collected over recent years to investigate whether public pensions displace private savings. The identification strategy relies not only on cross-country differences in generosity but also on differences in the progressivity or non-linearity of pension formulas across countries. We estimate that an extra dollar of pension wealth depresses accumulated financial assets around the time of retirement by 22 cents. An extra ten thousand dollars in public pension wealth reduces the average retirement age by roughly one month which implies an elasticity of retirement years with respect to pension wealth of -0.15.
Keywords: Finances; Older Adults; Pensions; Retirement Planning and Satisfaction

Do discriminatory attitudes to older workers at work affect their retirement intentions? - Pierre-Jean, Messe (International Journal of Manpower, 2012)
Purpose - The purpose of this paper is to investigate whether employers' attitudes towards older workers, especially regarding promotions, really affect their retirement intentions, distinguishing between men and women. Design/methodology/approach - First, the author uses the 1992 wave of the Health and Retirement Study to estimate, through a Fields decomposition, the relative contribution of the feeling of an older worker to be discriminated against regarding promotions; and to explain the self-reported probability to work full time after 62, decomposing by gender. Second, using the two first waves of HRS, the author removes any bias due to time-constant unobserved heterogeneity, to test whether the individual feeling of being passed over for promotion may be misreported, owing to a strong preference for leisure. Finally, the author examines the effect of a change in this variable over time on the intentions to exit early. Findings - The Fields decomposition shows that feeling passed over for promotion plays a non-negligible role to predict retirement plans but only for women. In addition, using panel data allows a misreporting bias to be exhibited that may lead to underestimating of the negative effect of discriminatory practices towards older workers on their retirement plans. Lastly, an increase between 1992 and 1994 in the age-discrimination towards older workers encouraged women to leave their job early, while it had no effect on retirement plans of men. Practical implications - Empirical results put forward the idea that retirement intentions may differ across gender, owing to the different nature of the employer-employee relation. While for men, this relation is characterized by delayed-payment arrangements signed ex ante with the employer, as already shown by Adams, it is not true for women. Consequently, the age-based preference of employers for promotion, leading to a lower probability of promotion for older workers, is treated by men as a consequence of ex ante arrangements and does not affect their retirement plans. However, women can attribute such attitudes of their employer to a kind of blatant discrimination, reducing therefore their attachment to their job. Originality/value - The paper presents a longitudinal approach towards the determinants of retirement intentions that allows the unobserved heterogeneity constant over time to be removed and to estimate to what extent the feeling of being passed over for promotion may be attributed, for each gender, to some arrangements signed ex ante with the employer.
Keywords: Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

Does stock market performance influence retirement intentions? - Gopi Shah Goda; John B. Shoven; Sita Nataraj Slavov (Journal of Human Resources, 2012)
Media reports predicted that the stock market decline in October 2008 would cause changes in retirement intentions, due to declines in retirement assets. We use panel data from the Health and Retirement Study to investigate the relationship between stock market performance and retirement intentions during 1998-2008, a period that includes the recent crisis. While we find a weak negative correlation between stock returns and retirement intentions, further investigation suggests that this relationship is not driven by wealth shocks brought about by stock market fluctuations, but by other factors that are correlated with both the stock market and retirement intentions. PUBLICATION ABSTRACT
Keywords: Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Dynamic Models of Labor Supply and Retirement - Fan, Xiaodong (Dynamic Models of Labor Supply and Retirement, 2012)
This dissertation contains three separate essays on the dynamic models of labor supply and retirement. The first essay documents "sharp retirement"--retirement accompanied by a discontinuous decline in labor supply--across three data sets, which previous literature found difficult to explain. I propose and estimate a life-cycle labor supply model with habit persistence wherein sharp retirement can be explained by workers quitting "cold turkey." In much the same way that one might quit smoking, workers with accumulated "working habit" exit the labor force with a pronounced, discontinuous decline in labor supply. The working habit model is consistent with the data, where workers reduce yearly labor supply by scaling back more in hours worked per week (over 50% reduction) than in weeks worked per year (20% reduction). The fixed costs approach, which has been the standard model used to understand sharp retirement, cannot explain these trends. After estimating the model, counterfactuals show that reducing Social Security benefits by 20% causes individuals work an additional 8.6 months. Individuals choosing sharp retirement respond mostly on the extensive margin by delaying retirement eight months, while individuals choosing smooth retirement respond mostly on the intensive margin by increasing yearly labor supply and delaying retirement only one month. The second essay develops and estimates a Ben-Porath human capital model in which individuals make decisions on consumption, human capital investment, labor supply, and retirement. The model allows both an endogenous wage process (which is typically assumed exogenous in the retirement literature) and an endogenous retirement decision (which is typically assumed exogenous in the human capital literature). This integration is important to obtain unbiased estimates, which are critical for most counterfactual analysis. For instance, when evaluating the effect of increasing the Social Security Normal Retirement Age (NRA) on workers' labor supply and retirement decisions, not only does one have to consider how the policy change affects the retirement decision directly, one also needs to consider how it affects the wage process and therefore affects retirement indirectly. We estimate the model using the Method of Simulated Moments to match the life-cycle profiles of wages and hours from the PSID data. Counterfactuals of delaying NRA and removing Social Security earnings test are conducted. We find significant increases in one individual's human capital investment at old ages, which leads to over 20% increase in the wage profile near retirement. Finally, the third essay tests for asymmetric employer learning in the labor market using a three-period model with a match component of wages. When a worker makes her quit/stay decision in a labor market with three periods, she must consider the signaling effect of her decision in subsequent periods. This breaks down some implications derived from two-period models, which are mostly used in the empirical literature. The unconditional quit rate is not necessarily negatively connected with ability in this three-period asymmetric learning model. I suggest two alternative hypothesis tests for asymmetric employer learning in the model. The first test scrutinizes the negative relationship between conditional quit rates and abilities. The second test examines the evolution of weighted average within-group ability variation. Under this model, the variation should decrease over one worker's career history due to sorting on ability. I use the NLSY79 Work-History data and find evidence of asymmetric employer learning from these tests.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2012 Last updated - 2013-04-18 First page - n/a
Keywords: Employment and Labor Force; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction; Social Security

Financial and health security in old age: Three essays - Diebold, Jeffrey (The University of North Carolina at Chapel Hill, 2012)
This dissertation is composed of three essays that examine issues and policies related to the well-being of the elderly in the United States. Using a randomized control design, I demonstrate the relative strength of incentives structured as a credit as opposed to an economically equivalent deduction within the framework of a retirement-based annuitization decision. Next, I exploit the natural experiment provided by the establishment of Medicare Part D in 2006 to evaluate health-related outcomes affected by this policy change. I provide evidence that Medicare Part D resulted in a number of positive health-related outcomes among those Medicare beneficiaries without prescription drug coverage prior to enrolling in Part D. Finally, I test whether the financially literate are more likely to make decisions that minimize the risks to their financial security. The results from this analysis are decidedly mixed. Financially literate individuals do not, necessarily make better financial and investment related decisions but appear more active in the decision-making process.
Keywords: Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Financial Knowledge and Financial Literacy at the Household Level - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (The American Economic Review, 2012)
There is evidence of a relation between numeracy and wealth held outside of pensions and Social Security. With pensions and Social Security accounting for half of wealth at retirement, and evidence that those with pensions save more in other forms, one would expect to find knowledge of pensions and Social Security influencing retirement saving. Yet we find no evidence that knowledge of pensions and Social Security is related to nonpension, non-Social Security wealth, to numeracy, or that it plays an intermediate role in the numeracy-wealth relation. Our findings raise questions about policies that would enhance numeracy to increase retirement saving. PUBLICATION ABSTRACT
Keywords: Net Worth and Assets; Other; Public Policy; Retirement Planning and Satisfaction; Social Security

Financial Sophistication in the Older Population - Annamaria Lusardi; Olivia S. Mitchell; Vilsa Curto (NBER Working Paper Series, 2012)
This paper examines data on financial sophistication among the U.S. older population, using a special-purpose module implemented in the Health and Retirement Study. We show that financial sophistication is deficient for older respondents (aged 55+). Specifically, many in this group lack a basic grasp of asset pricing, risk diversification, portfolio choice, and investment fees. Subpopulations with particular deficits include women, the least educated, persons over the age of 75, and non-Whites. In view of the fact that people are increasingly being asked to take on responsibility for their own retirement security, such lack of knowledge can have serious implications.
Keywords: Financial literacy; Retirement Planning and Satisfaction

The Great Recession, Older Workers with Disabilities, and Implications for Retirement Security - Onur Altindag; Lucie Schmidt; Purvi Sevak (MRDRC Working Paper, 2012)
Evidence suggests that older workers with disabilities have been hit particularly hard by the recent recession. The increased difficulty in finding a job faced by individuals with disabilities, combined with the longer spells of unemployment experienced by all workers in this recession, could mean that laid-off disabled workers in their pre-retirement years may never return to work. In this paper, we use data from the 2004-2010 waves of the Health and Retirement Study to examine how the great recession has affected workers with chronic health conditions that put them at greater risk of disability. Our results suggest that increases in job losses were 30 greater for those with greater underlying risk of disability than for the general HRS population, and decreases in consumption were 20 greater. These results have important implications for the well-being of disabled individuals nearing retirement.
Keywords: Disabilities; Employment and Labor Force; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction

How do the risks of living long and facing high medical expenses affect the elderly's saving behavior? - Mariacristina De Nardi; Eric French; John Bailey Jones (Chicago Fed Letter, 2012)
Although the elderly have a lot of wealth, people still do not fully understand their patterns of saving behavior. Many elderly individuals keep large amounts of wealth even as they near the ends of their lives. Furthermore, as one study shows, income-rich households are especially frugal. Among the motivations for saving are the risks of living long and having high medical expenses in old age. In recent research, the authors quantify the importance of forces by estimating and simulating a rich model of saving behavior. Life spans vary greatly in both predictable and unpredictable ways. Using mortality rates estimated from the AHEAD, they find that rich people, women, and healthy people live much longer than their poor, male, and sick counterparts. The risk of living far past one's expected life span is large and, under incomplete annuitization, a potentially important reason why so many elderly people run down their assets so slowly.
Keywords: Adult children; Consumption and Savings; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

How is Economic Hardship Avoided by Those Retiring Before the Social Security Entitlement Age - Kevin Milligan (NBER Working Paper, 2012)
Governments around the world are reacting to extended lifespans and troubled pension finances by increasing the age of retirement benefit entitlement. One concern that arises is how those who are not working before reaching entitlement age are able to bridge their consumption to the age of entitlement. This paper studies those who retire before the age of full pension entitlement in the United States using data drawn from the Health and Retirement Study. The major finding is that four out of five people who have zero earnings at pre-entitlement ages are able to find a way to lift their incomes over the poverty line. For men, pension and annuity income is important while for women, spousal income helps most to get them over the line. Reaching the early retirement entitlement age at 62 also has a significant impact on poverty avoidance.
Keywords: Consumption and Savings; Income; Public Policy; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Improving the Social Security Statement - Andrew G. Biggs (Rochester, Social Security Administration, 2012)
The Social Security Statement is sent annually to each individual over age 25. The Statement contains information regarding the Social Security program, the individual's past covered earnings and contributions, and an estimate of the individual's future retirement benefits. Given the complexity of the Social Security benefit formula, the Statement represents the best and perhaps only estimate of the benefits to which an individual may be entitled. Knowledge of benefits is important, as individuals must plan their own retirement saving around their Social Security benefits. However, little research has been conducted regarding how effectively the Statement has improved Americans' knowledge of benefit levels. We here use data from the Health and Retirement Study to gauge near-retirees' ability to predict their Social Security retirement benefits both before and after the Statement began universal distribution to all near retirees in 1995. Results are ambiguous. The initial automatic distribution of the Statement did not appear to produce an immediate increase in knowledge of retirement benefit levels. However, continued receipt over a number of years prior to claiming may have reduced individual errors in predicting benefits. Financial literacy with regard to Social Security benefit levels may be improved through greater research into the contexts in which recipients understand and retain the benefit estimates contained in the Statement.
Copyright - Copyright Social Science Research Network Jan 2012 Language of summary - English ProQuest ID - 919479167 Last updated - 2012-02-02 Place of publication - Rochester Corporate institution author - Biggs, Andrew G DOI - 2576680121; 67156722; 79688; 10.2139/ssrn.1991397; 1991397
Keywords: Public Policy; Retirement Planning and Satisfaction; Social Security

Income Replacement Ratios in the Health and Retirement Study - Patrick, J. Purcell (Social Security Bulletin, 2012)
This article describes the income replacement ratio as a measure of retirement income adequacy and identifies several issues analysts must consider when calculating a replacement ratio. The article presents the income replacement ratios experienced by participants in the original sample cohort of the Health and Retirement Study (HRS), who were born between 1931 and 1941. Replacement ratios are shown by the respondent's birth cohort, age when first classified as retired in the HRS, and preretirement income quartile. Median replacement ratios fall as the retirement period grows longer. PUBLICATION ABSTRACT
Keywords: Income; Retirement Planning and Satisfaction; Social Security

The Interplay of Wealth, Retirement Decisions, Policy and Economic Shocks - John Karl Scholz; Ananth Seshadri (Ann Arbor, The University of Michigan, 2012)
We develop a model of health investments and consumption over the life cycle where health affects longevity, provides flow utility, and retirement is endogenous. We develop a rich, numerical life-cycle model to study the complex interrelationship between health and wealth and the age of retirement. The decision to retire depends on a number of factors including earnings and health shocks, demographic characteristics, preferences, pensions, and social security. We incorporate these features in a computational model of optimal wealth and retirement decisions, solving the model household-by-household using data from the HRS. We use the model to study how workers would respond to an increase in the early eligibility age of retirement (EEA), and to what extent will the bad economy alter retirement plans. We find that increasing the EEA results in sizeable responses to the age of retirement but does not affect health outcomes very much. A 20 percent reduction in wealth induces households to delay retirement by one year, on average, with poor households being relatively unaffected.
Keywords: Consumption and Savings; Demographics; Event History/Life Cycle; Health Conditions and Status; Healthcare; Net Worth and Assets; Retirement Planning and Satisfaction; Social Security

Investment Choice and Savings in Defined Contribution Pensions - Li, Zhe (Pensions: An International Journal, 2012)
This article presents econometric evidence from Health and Retirement Study on the role that investment choice plays in the participants' saving levels in the defined contribution (DC) pensions. I distinguish the effect of unconstrained investment choice from the one constrained in company stocks. My preferred estimates indicate that participants with investment choice contribute over three percentage points more of their salary into the DC plan than people without choice, and people constrained in company stocks contribute about three percentage points less in their retirement saving account.
Journal Article
Keywords: Consumption and Savings; Event History/Life Cycle; Net Worth and Assets; Retirement Planning and Satisfaction

Market Performance And The Timing Of Retirement - Yao, Rui; Park, Eric (Journal of Personal Finance, 2012)
This study is the first to utilize nine interview waves of the Health and Retirement Study and multilevel discrete-time survival analysis to investigate the effect of market returns on individual elective retirement decisions. Individuals who retire at a market peak have an increased risk of shortening the longevity of their retirement income. Unfortunately, market returns were found to have a significant positive effect on the probability of retirement. Researchers, employers, financial educators and financial practitioners should help pre-retirees overcome the stock market's influence on their decision-making to avoid the negative effect of market sequencing on their retirement wealth. PUBLICATION ABSTRACT
Keywords: Consumption and Savings; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Mismeasurement of Pensions Before and After Retirement: The Mystery of the Disappearing Pensions with Implications for the Importance of Social Security as a Source of Retirement Support - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (MRDRC Working Paper, 2012)
A review of the literature suggests that when pension values are measured by the wealth equivalent of promised DB pension benefits and DC balances for those approaching retirement, pensions account for more support in retirement than is suggested when their contribution is measured by incomes received directly from pension plans by those who have already retired. Estimates from the Health and Retirement Study (HRS) for respondents in their early fifties suggest that pension wealth is about 86 percent as valuable as Social Security wealth. In data from the Current Population Survey (CPS), for members of the same cohort, measured when they are 65 to 69, pension incomes are about 56 percent as valuable as incomes from Social Security. Our empirical analysis uses data from the Health and Retirement Study to examine the reasons for these differences in the contributions of pensions as measured in income and wealth data. A number of factors cause the contribution of pensions to be understated in retirement income data, especially data from the CPS. One factor is a difference in methodology between surveys affecting what is included in pension income, especially in the CPS, which ignores irregular payments from pensions. In CPS data on incomes of those ages 64 to 69 in 2006, pension values are 59 percent of the value of Social Security. For the same cohort, in HRS data, the pension value is 67 percent of the value of Social Security benefits. Some pension wealth disappears at retirement because respondents change their pension into other forms that are not counted as pension income in surveys of income. Altogether, 16 percent of pension wealth is transformed into some other form at the time of disposition. For those who had a defined benefit pension just before termination, the dominant plan type for current retirees, at termination 12 percent of the benefit was transformed into a state that would not count as pension income after retirement. For those who receive benefits soon after termination, there is a 3.5 percent reduction in DB pension value at termination compared to the year before termination. One reason may be the form of annuitization that is chosen. A series of caveats notwithstanding, the bottom line is that CPS data on pension incomes received in retirement understates the full contribution pensions make to supporting retirees.
Keywords: Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

The national retirement risk index: An update. - Alicia H. Munnell; Anthony Webb; Golub-Sass, Francesca N. (Center for Retirement Research at Boston College Briefs, 2012)
The release of the Federal Reserve’s 2010 Survey of Consumer Finances is a great opportunity to reassess Americans’ retirement preparedness as measured by the National Retirement Risk Index (NRRI). The NRRI shows the share of working households who are “at risk” of being unable to maintain their pre-retirement standard of living in retirement. The Index compares projected replacement rates – retirement income as a percentage of pre-retirement income – for today’s working households with target rates that would allow them to maintain their living standard and calculates the percentage at risk of falling short. The NRRI was originally constructed using the Federal Reserve’s 2004 Survey of Consumer Finances (SCF). The SCF is a triennial survey of a nationally representative sample of U.S. households, which collects detailed information on households’ assets, liabilities, and demographic characteristics. The 2007 SCF did not allow for a meaningful update, because stock market and housing prices plummeted right after the survey interviews were completed. Thus, the 2010 survey is the first opportunity to see how the financial crisis and ensuing recession have affected Americans’ readiness for retirement. The discussion proceeds as follows. The first section describes the nuts and bolts of constructing the NRRI and how the new SCF data were incorporated. The second section updates the NRRI using the 2010 SCF, showing that the percentage of households at risk increased by nine percentage points between the 2007 and 2010 surveys – 44 percent to 53 percent. The third section identifies the impact of various factors on the change. The final section concludes that the NRRI confirms what we already know: today’s workers face a major retirement income challenge. Even if households work to age 65 and annuitize all their financial assets, including the receipts from reverse mortgages on their homes, more than half are at risk of being unable to maintain their standard of living in retirement.
Keywords: Restricted data; Retirement Planning and Satisfaction

Obesity, Depression, and Employment Related Outcomes Among Workers Near Retirement - Mustafa C. Karakus; Okunade, A. (Ageing International, 2012)
Obese individuals with comorbid depression face greater risks of atrophied health status alongside the associated adverse consequences, such as limitations of daily living and/or work related activities. This study uses the U.S. Health and Retirement Study database to investigate the likelihood of early retirement decisions (before age 62) of older working-age adults (ages 50 to 62). We find that obese subjects with comorbid depression are significantly more likely to reduce work-hours and seek early retirement. Survival models confirm the negative association between obesity with comorbid depression and the duration to early retirement. The bidirectional association between obesity and depression suggest that more carefully designed public policy interventions are necessary for improving the labor market attachments of the older working-age adults that are obese and clinically depressed. PUBLICATION ABSTRACT
Keywords: Health Conditions and Status; Methodology; Public Policy; Retirement Planning and Satisfaction

Older men: pushed into retirement in the 1970s and 1980s by the baby boomers? - Macunovich, Diane J. (Monthly Labor Review, 2012)
The post-World War II baby boomers began entering the labor market in the late 1960s, and their number swelled though the 1970s and into the 1980s. Their large size, relative to the size of the cohort of workers ages 45-54, forced a whole host of dislocations for the boomers: high unemployment, low relative wages, and increasing proportions forced into part-time and part-year work. The peak of the baby boom had entered the labor force by 1985, but the dislocations did not end there, because the bottleneck created by those in the peak continued to block the later-born boomers who followed. As the same time that was happening, the retirement rate rose fairly dramatically in the 1970s and 1980s among men ages 55 and older, and their labor force participation rates fell accordingly. The article is an attempt to address the long-term trend of labor force participation and retirement among men ages 55-69 in the approximately four decades from 1968 through 2009.
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Personality Traits and Economic Preparation for Retirement - Michael D Hurd; Angela Lee Duckworth; Susann Rohwedder; David R Weir (MRDRC Working Paper, 2012)
This paper assesses the effects of personality traits on economic preparation for retirement, wealth accumulation, and consumption, among persons 66 to 69 years of age. Among the five chief personality traits of neuroticism, extroversion, agreeableness, conscientiousness, and openness, we focus most on conscientiousness. We find levels of adequate economic preparation for retirement ranging from 29 percent to 90 percent and that conscientiousness positively affects the proportion of persons adequately prepared for retirement, while neuroticism negatively affects it. Both consumption and wealth increase with conscientiousness but wealth increases faster, indicating that more conscientious persons save more out of retirement resources.
Keywords: Consumption and Savings; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Recession impacted near-retirees housing wealth - Paula Aven, Gladych (Benefits Selling. Breaking News, 2012)
Using asset and labor market data from the Health and Retirement Study, the organization examined the population that was just reaching retirement age when the recession hit, those aged 53 to 58 in 2006.
Keywords: Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Social Security

Retiree Health Benefits as Deferred Compensation: Evidence from the Health and Retirement Study - J. Marton; Stephen A. Woodbury (Upjohn Institute Working Papers, 2012)
Are early retiree health benefits (RHBs) a form of deferred compensation binding workers to an employer? Most employers who offer RHBs offer them only to workers who have ten or more years of tenure and have reached age fifty-five. Accordingly, workers in firms offering RHBs have an incentive to stay with a firm in the years before they attain eligibility for RHBs, and a greater incentive than otherwise to retire thereafter. The authors test for such a pattern of incentives by examining the age-specific relationship between workers eligibility for RHBs and retirement. The findings suggest that workers in RHB-offering firms are less likely to retire at ages fifty and fifty-one than similar RHB-ineligible workers. Also, RHB-eligible workers aged sixty and sixty-one are more likely to retire than similar RHB-ineligible workers. These results are consistent with RHBs acting as part of a delayed payment contract of the kind described by Lazear.
Keywords: Income; Medicare/Medicaid/Health Insurance; Other; Pensions; Public Policy; Retirement Planning and Satisfaction

Retirement Consumption Behavior: Evidence from HRS CAMS 2001-2009 - Chiang, Mei-Fang (Human Ecology, 2012)
Recent studies across a number of countries evidence a substantial decline in household consumption expenditure around the time of retirement. This phenomenon, coined as the retirement consumption puzzle, brings a challenge to the traditional life-cycle model. The life-cycle model implies that household consumption should be continuous over time including the transition to retirement, provided that retirement is a foreseeable event. To address the retirement consumption puzzle, this dissertation brings current evidence by carrying out four studies on U.S. household consumption behavior at retirement. Study 1 is a cross-sectional study using the latest available data wave from 2009 HRS CAMS. The main interest is to compare consumption behavior between non-retired and retired households. Based on the life cycle hypothesis, regardless of employment status, households sharing similar socioeconomic characteristics should exhibit similar consumption behavior. The empirical findings, however, show that the consumption behavior between non-retired and retired households is significantly different, holding all other factors constant. Spending for retired households is 8.5% lower than spending for non-retired households. Study 2 is an aggregate-panel study using data from 2001-2009 HRS CAMS. The difference between Study 1 and Study 2 is that Study 2 tracks household consumption behavior over time and investigates whether there is a significant change in consumption pattern after retirement. Fixed-effects analysis is conducted to appropriately account for the effect of individual heterogeneity. The life cycle hypothesis predicts that when retirement is as planned by the household, there is no significant change in consumption after retirement. The fixed-effects regression indicates that there is an insignificant increase of 3% in household consumption after retirement. The discrepancy in the results from Study 1 and Study 2 regarding the retirement consumption puzzle comes from the lack of control of individual heterogeneity in the cross-sectional analysis. Study 3 is a subsamples-panel study. Within the life-cycle framework, if retirement is voluntary and expected, there should be no significant change in household consumption after retirement. However, if the household head is laid-off or experiencing poor health, this household may be forced to be out of the labor market, resulting in early retirement. Because involuntary early retirement reduces the household's lifetime resources, the household must reduce consumption and re-allocate to a new optimal consumption path. As predicted by the life-cycle model, the findings show that households with voluntary retirement have an insignificant increase in household consumption after retirement by 6%. Involuntary-retirement results in a decrease in consumption after retirement by 6-7%. The percentage difference in the household consumption change between these the two groups of households is 11-12% and statistically significant. Accordingly, these findings suggest that household consumption behavior differs by household type (voluntary versus involuntary retirement). These three studies use log consumption as the dependent variable. Alternatively, Study 4 uses consumption growth as the dependent variable to test the retirement consumption puzzle. The regression results provide no evidence of a retirement consumption puzzle, finding an insignificant 3% increase in consumption after retirement.
Keywords: Consumption and Savings; Demographics; Event History/Life Cycle; Healthcare; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Security: Older Women Remain at Risk - Statement of Barbara D. Bovbjerg - United States Governmental Office (Washington, DC, 2012)
This testimony examines women s retirement income security based on a GAO report that examined (1) how women s access to and participation in employer-sponsored retirement plans compare to men s and how they have changed over time; (2) how women s retirement income compares to men s and how the composition of their income the proportion of income coming from different sources changed with economic conditions and trends in pension design; (3) how later-in-life events affect women s retirement income security; and (4) what policy options are available to help increase women s retirement income security.
Keywords: Consumption and Savings; Health Conditions and Status; Income; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

Retirement Security: Women Still Face Challenges - United States Governmental Office (Washington, DC, U.S. Government Accountability Office, 2012)
This report examines (1) how women s access to and participation in employer-sponsored retirement plans compare to men s and how they have changed over time, (2) how women s retirement income compares to men s and how the composition of their income changed with economic conditions and trends in pension design, (3) how events occurring later in life affect women s retirement income security, and (4) what policy options are available to help increase women s retirement income security.
Keywords: Consumption and Savings; Health Conditions and Status; Income; Public Policy; Retirement Planning and Satisfaction; Women and Minorities

Tax Elasticity of Labor Earnings for Older Individuals - Abby Alpert; David Powell (MRRC Working Paper, 2012)
This paper studies the impact of income and payroll taxes on intensive and extensive labor supply decisions for workers ages 55-74 using the Health and Retirement Study. The literature provides little guidance about the responsiveness of this population to tax incentives, though the tax code is potentially an important mechanism that can alter retirement incentives. We model labor force participation decisions and labor earnings as functions of taxes, and we use the intensive margin to inform estimation of the extensive margin equation. Our method accounts for selection into labor force participation with a plausibly exogenous shock to employment. We use the results of our intensive labor supply estimation to predict the after-tax labor earnings of every person in our sample, including those that do not work. This method allows us to generate consistent estimates of the impact of taxes on employment and retirement. We find large compensated elasticities on the intensive margin. These results are imprecise, but they are statistically significant for women. On the extensive margin, we find significant effects on labor force participation and, for men, retirement decisions. Our estimates suggest that an age-targeted tax reform that eliminates payroll taxes for older workers would decrease the percentage of workers dropping out of the labor force by 1 percentage point, a 4 decrease.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

Three essays in health economics - Wang, Xu (Three essays in health economics, 2012)
This dissertation consists of three essays. In my first essay, I examine the relationship of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC program) to breastfeeding. Although WIC promotes breastfeeding among its participants through education, counseling, and the provision of enhanced food packages to breastfeeding women, the program has been criticized for discouraging breastfeeding by providing free infant formula. In order to estimate the extent to which participation in WIC discourages breastfeeding, I employ a methodology that disentangles selection bias associated with WIC participation from the incentives associated with the provision of free infant formula. Findings suggest that postpartum entrants are less likely to breastfed for at least 6 months and have shorter breastfeeding durations than non-participants, and the effects are significantly larger among twin mothers than among singleton mothers. In my second essay, I investigate the association between WIC participation and infant health. How effective WIC is at improving birth outcomes is under debate. Identifying treatment effect is challenged by selection bias and gestational age bias. We use twins to minimize selection bias associated with WIC participation because twin pregnancy increases the probability of adverse birth outcomes significantly but is unlikely related to other risky behaviors. Our focus is on measures of fetal growth as outcomes amenable to nutritional supplementation. Our findings from two national datasets, PNSS and ECLS-B, suggest that prenatal WIC participation has very limited effect on fetal growth. We do not find evidence of causal effect between WIC and better birth outcomes, especially among twin births. In my third essay, I turn my interest to a different research question, the association between retirement and alcohol consumption. Retirement is life transition whose significance may provoke lifestyle and health behavioral alterations such as alcohol consumption. We examine the effect of retirement on subsequent period alcohol consumption within a two period follow up. We use seven waves of the data from Health and Retirement Study (HRS) and found retirement lead to consume 1.3 more alcoholic drinks per day within men. No effect has been found within retired women.
Wang, Xu Breastfeeding 9781267688194 Alcohol 68148022 Health economics 3541918 0501: Economics 0573: Public health 66569 0630: Public policy n/a Social sciences Retirement English 1115316395 Copyright ProQuest, UMI Dissertations Publishing 2012 Infant health 2012 Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) 2799357101 2012-11-26 Health and environmental sciences
Keywords: Event History/Life Cycle; Health Conditions and Status; Healthcare; Public Policy; Retirement Planning and Satisfaction

Three Essays on the Labor Supply, Savings and Investment Behavior of Older Workers - Clift, Jack W. (The Pardee RAND Graduate School, 2012)
In this dissertation, I provide three distinct analyses addressing labor supply, saving and investment behavior of (older) workers, in the context of the incentives and constraints they face due to employer and government policies. In the first paper, I examine labor supply flexibility and its effect on the labor supply decisions of older workers. Previous literature suggests that people would like to reduce hours of work gradually over time as they get older, but do not have the flexibility to do so in their job, and consequently may retire early rather than continue to work high hours at older ages. If greater flexibility allows individuals to stay in the labor force longer, this could increase total labor supply, helping to increase both private resources for retirement and tax revenue to support public programs. Following a sample of older Americans for 16 years from 1992 to 2008, I find that there are noticeable differences in labor outcomes between those who had flexibility over their hours in 1992 and those who were not able to adjust their hours: those with flexibility worked fewer hours in their 50s, but tended to stay in the labor force longer; the major difference between groups occurred when individuals were in their early-mid 60s, at which time those who did not have flexibility in 1992 were much more likely to retire than those with flexibility. This work provides support for the theory that people prefer gradual retirement to more abrupt departures from the labor force, and indicates that flexibility around key retirement ages might have an impact on behavior. The overall effect on total labor supply of providing flexibility at all points of the lifecycle is ambiguous. In the second paper, we examine whether labor supply flexibility affects investment behavior. Individuals can receive higher returns (on average) on their investments if they are willing to bear more risk, which allows people to reach retirement with greater resources (on average) than if they had pursued low-risk strategies; but the fear of suffering big losses discourages people from taking risks. Theoretical work has argued that individuals with flexibility over their labor supply over the lifecycle can bear more risk in their portfolio of investments, as they can increase their labor to offset any losses they might suffer. Using a new survey we fielded in the American Life Panel (ALP), we examine how different measures of labor supply flexibility are related to measures of risk-taking in investments: individual participation in the stock market, and the percentage of an individual's financial wealth held in stocks. We find no evidence that flexibility over number of hours worked per week is related to investments in stocks. We find weak evidence that other flexibility measures--an individual's belief that they would be able to continue to work longer to make up for any negative wealth shocks, and the absence of factors that make it difficult to sustain a job into old age--may be related to greater risk-taking in investments. These results may indicate that flexibility at the extensive margin (ability to extend a career) may be more relevant to investment decision-making than flexibility at the intensive margin (ability to adjust hours). In the third paper, I describe the construction and characteristics of a unique dataset with which I lay the foundations for understanding pension system incentives and how they influence work and savings behavior over the lifecycle. Public pension systems across the developed world are in need of reform, but it is important to understand how the incentives in these systems affect behavior if we are to predict the consequences of different possible reforms. Previous literature has argued that public pensions displace private savings, but with elasticity of less than 1; this suggests that possible reductions in pension benefits through reforms would be partially (but not fully) offset by increases in private saving. Using new retrospective earnings history data for five European countries, in conjunction with linked survey data describing household wealth, I construct a dataset that captures the heterogeneous pension system incentives faced, and labor supply decisions made, at each point in the lifecycle for a large group of European men. My exploratory analysis of this dataset is consistent with the hypotheses that more generous income replacement by pension plans leads to lower private wealth accumulation, and greater reward within the pension system for continued work leads to later retirement. However, these statistical associations admit of plausible alternative explanations; the work documented in this paper cannot provide definitive answers on the incentive effects of pension systems, but provides the groundwork for significant extensions of research in this field, and eventually for detailed policy simulation of pension reform. (Abstract shortened by UMI.)
Keywords: Employment and Labor Force; Healthcare; Methodology; Net Worth and Assets; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Who Among the Elderly Owns Stocks? The Role of Cognitive Ability and Bequest Motive - Eun Jin Kim; Sherman D. Hanna; Chatterjee, Swarn; Lindamood, Suzanne (Journal of Family and Economic Issues, 2012)
Conventional advice is to reduce risky investments as one ages. Such a generalized focus on risk avoidance may be inappropriate for elderly with longer life spans and those with financial goals that extend beyond their lifetime. To better understand risky asset holdings among the elderly, we investigated the effect of cognitive ability and bequest motive on stock ownership and stock purchase. Using the 2004 wave of the Health and Retirement Study, we found that one-third of elderly households held stocks and 36 of those elderly stockowners had recently acquired stocks. The respondent's cognitive ability and bequest motive were strongly related to stock ownership. Among those who owned stock, a bequest motive was positively related to a recent purchase of stocks. PUBLICATION ABSTRACT
Copyright - Springer Science Business Media, LLC 2012 Language of summary - English Pages - 338-352 ProQuest ID - 1030719840 Last updated - 2012-08-02 Place of publication - New York Corporate institution author - Kim, Eun Jin; Hanna, Sherman D; Chatterjee, Swarn; Lindamood, Suzanne DOI - 2726553591; 70920932; 53465; JFEI; SPVLJFEI108343339295
Keywords: Health Conditions and Status; Healthcare; Net Worth and Assets; Retirement Planning and Satisfaction

Changes in retirement decisions: Determinants of plans and timing - Giuriceo, Katherine Dodge (Gerontology, 2011)
Purpose. This study examined dynamic factors in a worker's background, resources, jobs or health which influence their expectations about future decisions to work or retire at ages 62 or 65, as well as how these influences and expected timing change as the individual approaches retirement. Design and methods . Employing a conceptual framework based on Andersen's (1995) model of health care utilization, the first research question used Generalized Estimating Equations (GEE) to determine which predictors were associated with workers' expected retirement timing. The second question examined changes in expectations over time in response to changes in predictors, using a two-level approach modeled on Singer and Willett (2003). Utilizing the Core sample of the Health and Retirement Study (HRS); data on 5,989 individuals (48.3% female) were examined longitudinally across seven waves, 1992 and 2006. Results . For research question one, female gender was associated with a lower expectations to continue working at both early (62), and normal (65) retirement ages. Non-married status had a similar effect for 62 but not for age 65. Differences emerged among sub-groups with non-married females reporting greater plans to continue working at both retirement ages; non-married blacks however were less likely to report plans to continue working at age 65 only. Non-whites with poorer subjective health or health that limited work were less likely to expect to work at age 62, but there was no impact on plans for age 65. Changes were also important. Leaving married status was linked with changes in plans to work at 65 but not 62. Gaining employer sponsored benefits (pension and health coverage) increased likelihood of continued work at both ages. Implications . Findings confirmed that known predictors of retirement decisions are also associated with workers' expectations well before retirement age is reached. Andersen's model was useful for understanding the dynamic process leading up to retirement. Results also support the importance of employer sponsored benefits, such as pension and health insurance, on changes in plans as individuals approach retirement. Policy makers interested in prolonging work lives should look to modifiable factors (pensions and health insurance), which may impact retirement timing.
ISBN 9781124710396
Keywords: End of life decisions; Expectations; Methodology; Retirement Planning and Satisfaction

Cohort Based Analysis of Income Shocks Over the Life Cycle - Jeremy G. Moulton (University of California, Davis, 2011)
The following three chapters investigate the first job, retirement decisions, and bequests of birth cohorts born between 1908 and 1926. I employ cohort based natural experiments using the Great Depression and Social Security Amendments of 1972 and 1977 to estimate the effect of entering the labor market during a recession, choice of retirement age in response to a retirement benefit shock, and financial transfers with children when facing a late life income shock. The first chapter uses a regression discontinuity framework to show that less educated workers entering the labor market during the Great Depression experienced 7 to 10% lower earnings roughly ten years after the onset of the Great Depression, in 1940. These effects fade substantially ten more years later in the 1950 Census. More educated workers entering the labor market experienced no loss to earnings in 1940 and positive earnings in the 1950 census, but these results may be driven by the effects of World War II or a more favorable job market for educated laborers during the Great Depression. Using the same regression discontinuity framework, I also show that young workers did not significantly delay their entry into the labor market during the Great Depression by prolonging their stay in high school. The second chapter reinvestigates and helps explain the findings of Krueger and Pischke (1992), who find no significant response of retirees in response to the Social Security Notch (Amendments of 1972 and 1977). Using a hazard model and data from the AHEAD cohort of the Health and Retirement Study, we find that using a long-term incentive measures, of the form found in Coile and Gruber (2000), provides a better estimate of retirement decision making than single year accrual measures. We find that individuals respond to both the long-term incentive measure (decreases the hazard of retiring) and the present value of their Social Security wealth (increases hazard). However, using the exogenous variation caused by the Social Security Notch results in opposite signed effects for the incentive measure. We show that this odd result and the reason that Krueger and Pischke do not find a significant change in retirement is that the Social Security Notch is one experiment, but has two offsetting, but correlated treatments. The Social Security amendments increased both the incentive measure and Social Security wealth for the cohorts subject to the 1972 amendments (Pre-Notch cohort) and the opposite for those subject to the 1977 amendments (Notch cohort). We show that the lack of retirement response is not due to no response, but to large offsetting effects. The last chapter investigates intergenerational wealth transmission between fathers and children using the 1972 and 1977 Amendments to the Social Security Act. As shown in chapter 2, individuals did not change their retirement age in response to these amendments, so those affected by the 1972 amendments experienced increased growth in Social Security benefits while those subject to the 1977 amendments experienced a negative shock (the "Notch Generation"). Using the Health and Retirement Study, I find that sons with fathers born in the Notch Generation have significantly lower wealth levels than those with fathers born in surrounding cohorts, most notably the cohort born just prior. Further evidence suggests that the wealth difference is likely due to a higher probability of providing financial support to parents and a lower probability of receiving an inheritance and financial assistance from parents.
Keywords: Adult children; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction; Social Security

Conversations on death: Cost implications of end-of-life preparations - Cable, Heather M (Conversations on death: Cost implications of end-of-life preparations, 2011)
The end of a person's life is important. Sacred, even. But, more and more the end of life is also expensive--very expensive--for patients and for the taxpayer. According to the Dartmouth Atlas of Health Care, "patients with chronic illness in their last two years of life account for about 32% of total Medicare spending." As a result, there is a critical need to better understand effective solutions for reducing those costs. This paper focuses on the effect of living wills on total medical expenditures and utilization of heroic medical interventions at end-of-life. Using data pooled from the 2002-2008 exit surveys of the Health and Retirement Study, this paper uses logistic, regression and simulation models to evaluate the cost and care effects of three different types of living wills--those that call for comfort care only, those that call for limited care in certain situations, and those that call for receiving all care possible at end of life. The findings of this analysis indicate that patient preferences as expressed through living wills do, in fact, influence end-of-life medical expenditures as well as utilization of certain types of heroic end-of-life care. Of those patients who faced health care decisions in the final days of life, individuals who had living wills to limit care in some way had significantly lower total medical expenditures in the last two years of life, ranging from $2,730 (7%) (limited care or withheld treatments) to $8,285 (21%) (comfort care only) lower than their counterparts who did not have a living will. Conversely, those with living wills to receive all care possible had drastically ($24,171) (60%) higher end-of-life costs, as well as a 37 percent higher probability of utilizing life support, compared with those who had no living will.
ISBN 9781124597539
Keywords: Healthcare; Public Policy; Retirement Planning and Satisfaction

Debt and negative net worth among near-retirees - Brown, Susan M. E. (Family, Consumer and Human Development, 2011)
Going into retirement, near-retirees are looking at increased debt levels, which can offset any asset accumulations and reduce retirement income. By using data from the 2008 Health and Retirement Study (HRS), this study examines the debt and negative net worth of near-retirees. This study further investigates what factors are associated with the likelihood of holding consumer debt, holding mortgage debt, and holding home equity debt over holding no debt, and what factors are associated with the likelihood of holding negative net worth over holding a high level of net worth among near-retirees. The study sample includes 3,745 individuals between the ages of 51 and 64. The results of the multinomial logistic regression analysis indicate that, all else being equal, human capital factors such as education, physical health problems, and depression symptoms play a significant role in predicting the likelihood of holding debt and negative net worth. In particular, education is positively associated with the likelihood of holding consumer, mortgage, and home equity debt over holding no debt, while it is negatively associated with the likelihood of having negative net worth over having a high level of net worth. Among the socioeconomic characteristics that influence the likelihood of near-retirees holding debt and negative net worth are household income, working in the labor force, and race. In particular, household income positively influences the likelihood of holding mortgage debt over holding no mortgage debt as well as the likelihood of holding home equity debt over holding no home equity debt. However, household income negatively influences the likelihood of having negative net worth over having a higher level of net worth. The findings of this study could help financial educators, financial planners, and policymakers understand the differences in human capital and socioeconomic characteristics of near-retirees who hold some levels of debt over no debt and who hold no net worth or a lower level of net worth over a higher level of net worth. This study concludes that it is important for professionals, consumer educators, and financial planners to provide those who hold higher levels of debt and lower levels of net worth with financial literacy education; therefore, these individuals might be able to attain economic well-being in retirement.
ISBN 9781124618456
Keywords: Adult children; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Do Market Returns Influence Risk Tolerance? Evidence from Panel Data - Yao, R.; Angela L Curl (Journal of Family and Economic Issues, 2011)
This study used the 1992-2006 waves of the Health and Retirement Study (HRS) to investigate changes in risk tolerance levels over time in response to stock market returns. Findings indicate that risk tolerance tends to increase when market returns increase and decrease when market returns decrease. Individuals who change their risk tolerance in this manner are likely to invest in stocks when prices are high and sell when prices are low. Researchers, employers, financial educators and practitioners should help investors overcome the bias of overweighting recent news of market performance. PUBLICATION ABSTRACT
Keywords: Consumption and Savings; Other; Retirement Planning and Satisfaction; Risk Taking

Do Stronger Age Discrimination Laws Make Social Security Reforms More Effective? - David Neumark; Joanne Song (Michigan Retirement and Disability Research Center Working Paper, 2011)
Supply-side Social Security reforms to increase employment and delay benefit claiming among older individuals may be frustrated by age discrimination. We test for policy complementarities between supply-side Social Security reforms and demand-side efforts to deter age discrimination, specifically studying whether stronger state-level age discrimination protections enhanced the impact of the increases in the Social Security Full Retirement Age (FRA) that occurred in the past decade. The evidence indicates that, for older individuals who were caught by the increase in the FRA, benefit claiming reductions and employment increases were sharper in states with stronger age discrimination protections.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction; Social Security

Economic Measurement in the Health and Retirement Study - Steven F Venti (Forum for Health Economics and Policy, 2011)
The Health and Retirement Study (HRS) is widely use for research on the well-being of the elderly. This paper assesses the quality of economic and financial variables in the HRS. I find the coverage is comprehensive and the quality of the data is uniformly high. Thus the HRS has earned its position as the most widely used data source for research on retirement, saving adequacy, pension policy and a host of other aging-related topics. I identify two general areas that continue to merit special attention. The first is measurement error, particularly errors arising from item non-response and from inaccurate respondent reports of the ownership and level of assets. The second is the quality of the pension data. Where appropriate, I make suggestions for improving economic measures in the HRS.
Keywords: Methodology; Pensions; Retirement Planning and Satisfaction

The effect of late-life debt use on retirement decisions - Mann, Allison (Social Science Research, 2011)
This paper examines parallel shifts in late life debt use and retirement behaviors. After discussing the conceptual linkages between credit and labor markets, I use data from the 1992 to 2008 waves of the Health and Retirement Study to examine the temporal patterning of retirement and debt behaviors. I rely on the longitudinal structure of the data to estimate the effects of debt accumulation on retirement behaviors, using alternative specifications to identify treatment and control groups. The findings suggest that debt accumulation in later life has a significant effect on decisions to remain in the workforce in later years. PUBLICATION ABSTRACT
Keywords: Consumption and Savings; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

The Effects of Health Insurance and Self-Insurance on Retirement Behavior - Eric French; John Bailey Jones (Econometrica, 2011)
This paper provides an empirical analysis of the effects of employer-provided health insurance, Medicare, and Social Security on retirement behavior. Using data from the Health and Retirement Study, we estimate a dynamic programming model of retirement that accounts for both saving and uncertain medical expenses. Our results suggest that Medicare is important for understanding retirement behavior, and that uncertainty and saving are both important for understanding the labor supply responses to Medicare. Half the value placed by a typical worker on his employer-provided health insurance is the value of reduced medical expense risk. Raising the Medicare eligibility age from 65 to 67 leads individuals to work an additional 0.074 years over ages 60-69. In comparison, eliminating 2 years worth of Social Security benefits increases years of work by 0.076 years.
Keywords: Consumption and Savings; Medicare/Medicaid/Health Insurance; Other; Public Policy; Retirement Planning and Satisfaction

The Effects of the Financial Crisis on Actual and Anticipated Consumption - Michael D Hurd; Susann Rohwedder (Michigan Retirement and Disability Research Center Working Paper, 2011)
We studied how households adjust their spending in response to the financial crisis. Based on five waves of data from the Consumption and Activities Mail Survey, we quantified the reduction in total consumption and in specific categories of consumption in the older population at large and by stock ownership, both as a proxy for wealth and to test assumptions about whether stock ownership was associated with different responses. In particular, we compared consumption changes between 2007 and 2009 with consumption changes over prior years. We used panel data on anticipated changes in spending at retirement to quantify the effects of the financial crisis on well- being in retirement via a difference-in-differences approach.
Keywords: Consumption and Savings; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Essays in Labor Economics - McFall, Brooke Helppie (University of Michigan, 2011)
This dissertation is composed of two essays, both which use data from original survey projects to examine issues related to work choice. The first essay examines the labor supply effects of the wealth losses during the stock market crash of 2008 and 2009. A life-cycle model incorporating both consumption and retirement timing implies that exogenous wealth losses should delay optimal retirement timing. Using data from the Cognitive Economics Study and the Health and Retirement Study, this essay quantifies the wealth losses suffered by older Americans in terms of the additional length of time they would have to work to maintain the pre-crash consumption plan implied by their wealth holdings and expected retirement timing. Using these measures, Tobit regressions and a novel method for reducing the impact of error-ridden observations are used to examine the relationship between this measure of wealth loss and retirement planning. Several potential sources of heterogeneity in individuals' reactions to the crash are also examined. Results imply that wealth losses of 2008 and 2009 are associated with an increase in planned retirement age on the order of a few weeks to a few months for the average older American, but up to several months for some segments of the population. These results are consistent with results of recent studies and the life-cycle model, but stand in contrast to other examinations of wealth shocks on the general population of older Americans. The second essay is a product of the Job Seekers Study. The essay extends Mincer's seminal theory of family migration to allow couples to adjust to migration constraints by living apart, and examine the ways in which new PhD economists adjust to migration constraints imposed on them by their spouses or partners. Both the impact of migration constraints on job outcomes and the impact of job considerations on relationship outcomes are analyzed. The essay finds that migration constraints result in small costs in terms of job outcomes, relative to many existing studies, and that adjustment through living apart is common. These results imply that existing studies may overestimate the job impact of migration constraints.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Financial literacy and retirement planning in the United States - Annamaria Lusardi; Olivia S. Mitchell (Journal of Pension Economics and Finance, 2011)
We examine financial literacy in the US using the new National Financial Capability Study, wherein we demonstrate that financial literacy is particularly low among the young, women, and the less-educated. Moreover, Hispanics and African-Americans score the least well on financial literacy concepts. Interestingly, all groups rate themselves as rather well-informed about financial matters, notwithstanding their actual performance on the key literacy questions. Finally, we show that people who score higher on the financial literacy questions are much more likely to plan for retirement, which is likely to leave them better positioned for old age. Our results will inform those seeking to target financial literacy programmes to those in most need.
Keywords: Education; Financial literacy; Older Adults; Retirement Planning and Satisfaction

Financial Literacy: Implications for Retirement Security and the Financial Marketplace - Olivia S. Mitchell; Annamaria Lusardi (Pension Research Council Series, 2011)
As financial markets grow ever more complex and integrated, households must make increasingly sophisticated and all-too-often irreversible economic decisions. This is particularly evident in retirement decision-making. Traditional defined benefit pension schemes are being replaced with defined contribution pensions; employer and government judgment regarding how much to save and where to invest has been replaced by employees having to make these choices on their own (sometimes assisted by advisers); and retirees have become responsible for managing their own pension assets. This volume explores how financial literacy can enhance peoples’ ability to make informed economic choices. It proposes that financial literacy determines how well people make and execute saving, investing, borrowing, and planning decisions. It examines causality using controlled settings to disentangle whether financial literacy causes saving or vice versa, and demonstrates that financial education programs do indeed enhance financial decision-making and asset accumulation.
Keywords: Economics; Financial literacy; Older Adults; Retirement Planning and Satisfaction

Helping the Poorest Help Themselves? Encouraging Employment Past 65 in England and the USA - Lain, David (Journal of Social Policy, 2011)
In the context of population ageing and low retirement incomes, the UK government is encouraging delayed retirement. However, the OECD has argued that UK means-tested benefits disincentivise employment for the poorest, and Vickerstaff (2006b) has suggested managers have typically controlled opportunities to work beyond 65. In the US, contrastingly, benefits are meagre and difficult to access, and age discrimination legislation protects individuals from forced retirement. Would a US 'self-reliance' policy approach increase employment amongst the poorest over 65s in the UK and enhance or diminish their financial position? The evidence suggests that extending UK age discrimination legislation and restricting benefits would increase overall employment past 65, although not necessarily to US levels. Analysis of the English Longitudinal Study of Ageing and the US Health and Retirement Study finds the poorest over 65s were more likely to work in the USA than in England in 2002. However, within the USA, employment amongst the poorest was still low, especially compared with wealthier groups; logistic regression analysis primarily attributes this to lower levels of health and education. A US policy approach would therefore most likely damage the financial position of the poorest in the UK, as increased employment would not sufficiently compensate for lost benefits
Keywords: Cross-National; Demographics; Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

How Did the Recession of 2007-2009 Affect the Wealth and Retirement of the Near Retirement Age Population in the Health and Retirement Study? - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Michigan Retirement and Disability Research Center Working Paper, 2011)
This paper uses asset and labor market data from the Health and Retirement Study (HRS) to investigate how the recent Great Recession has affected the wealth and retirement of those in the population who were just approaching retirement age at the beginning of the recession, a potentially vulnerable segment of the working age population. The retirement wealth held by those ages 53 to 58 before the onset of the recession in 2006 declined by a relatively modest 2.8 percentage points by 2010. In more normal times, their wealth would have increased over these four years. Members of older cohorts accumulated an additional 5 percent of wealth over the same age span. To be sure, a part of that accumulation was the result of the upside of the housing bubble. The wealth holdings of poorer households were least affected by the recession. Relative losses are greatest for those who initially had the highest wealth when the recession began.The adverse labor market effects of the Great Recession are more modest. Although there is an increase in unemployment, that increase is not mirrored in the rate of flow out of full-time work or partial retirement. All told, the retirement behavior of the Early Boomer cohort looks similar, at least so far, to the behavior observed for members of older cohorts at comparable ages. Very few in the population nearing retirement age have experienced multiple adverse events. Although most of the loss in wealth is due to a fall in the net value of housing, because very few in this cohort have found their housing wealth under water, and housing is the one asset this cohort is not likely to cash in for another decade or two, there is time for their losses in housing wealth to recover.
Keywords: Demographics; Employment and Labor Force; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

How Do Subjective Mortality Beliefs Affect the Value of Social Security and the Optimal Claiming Age - Wei Sun; Anthony Webb (Center for Retirement Research at Boston College Working Papers, 2011)
Households that delay claiming Social Security are, in effect, making additional purchases of the Social Security annuity. Theoretical calculations show the delayed claiming is optimal, even for high mortality households. Yet most claim well before the theoretically optimal age. This paper investigates whether subjective mortality beliefs contribute to the prevalence of early claiming. The value of delay depends not only on life expectancy, but also on the degree of uncertainty surrounding the age of death. Using data from the Health and Retirement Study, we show that women approaching retirement understate their probabilities of surviving to age 75 by an average of 10 percentage points, whereas men's forecasts are, on average, correct. But both men and women exhibit greater confidence in their ability to forecast their age of death, relative to the predictions of life tables. But these subjective mortality beliefs have little effect on the value of Social Security or the optimal claim age, and cannot explain the prevalence of early claiming. We also find that self-assessed survival probabilities do not predict survival after controlling for health and socio-economic status, indicating a potential for medical underwriting to reduce adverse selection in the annuity market.
Copyright - Copyright Social Science Research Network Dec 2011 Language of summary - English ProQuest ID - 913272676 Last updated - 2012-01-02 Place of publication - Rochester Corporate institution author - Sun, Wei; Webb, Anthony DOI - 2551228411; 66534181; 79688; 10.2139/ssrn.1970312; 1970312
Keywords: Expectations; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction; Social Security

How Does Occupational Status Impact Bridge Job Prevalence - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn; Office of Productivity and Technology (Economic Working Paper, 2011)
Is bridge job prevalence reduced significantly if a change in occupation is required in addition to the hours and tenure requirements that typically define bridge job employment. Prior research has shown that the majority of older Americans with career employment do not exit the labor force directly from their careers. Rather, most career individuals take on a 'bridge job' later in life, that is, a job that follows full-time career (FTC) employment and precedes complete labor force withdrawal (i.e., retirement). One criticism of this finding is that bridge job prevalence may be overstated because the definition of a bridge job in the existing literature does not require a change in occupation. This paper investigates the extent to which bridge jobs involve a change in occupation or a switch to part-time status, both of which may signal retirement transitions as opposed to continued career employment, albeit with a different employer. We use the Health and Retirement Study (HRS), a nationally-representative longitudinal dataset of older Americans that began in 1992 as the basis for our analysis. We find that, among HRS respondents who were on a FTC job at the time of the first interview and who changed jobs in subsequent waves, 48 percent of the men and 40 percent of the women also changed occupations, using 2-digit occupation codes. Further, when hours worked are also considered, we find that more than three quarters of FTC respondents who changed jobs later in life had either a change in occupation or a switch from full-time to part-time status. Finally, an examination of those career workers who changed jobs but not occupations and who remained working full time reveals that, as a whole, they resemble those who took bridge jobs rather than those who remained on their FTC job. We conclude that the vast majority of career workers who changed jobs later in life did in fact do so as part of a retirement transition.
Product reproduced from digital image. Order this product from NTIS by: phone at 1-800-553-NTIS (U.S. customers); (703)605-6000 (other countries); fax at (703)605-6900; and email at orders ntis.gov. NTIS is located at 5301 Shawnee Road, Alexandria, VA, 22312, USA. NTIS Prices: PC A04/MF A04
Keywords: Employment and Labor Force; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

The implications of Alzheimer's Risk for Household Financial Decision Making: Essays on the acquisition of human capital - John Hsu (Department of Economics, 2011)
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Intrinsic Rewards of Work, Future Time Perspective, the Economy in the Future and Retirement Planning - Ting-Ying Yang; DeVaney, Sharon A. (The Journal of Consumer Affairs, 2011)
This study incorporated intrinsic rewards of work, future time perspective and perspective on the economy in the future to create a model for the psychological mechanism of planning for retirement. The data set included those who were not retired (N = 2,266) in the 1992 Health and Retirement Study. Confirmatory factor analyses and structural equation modeling were used. The analyses were conducted separately on the different types of retirement plans. The results suggest that human resource professionals should (1) encourage employees who perceive high intrinsic rewards of work to plan for their retirement, and (2) remind employees that retirement might be closer than they anticipate. PUBLICATION ABSTRACT
Keywords: Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

Modeling social participation as predictive of life satisfaction and social connectedness: Scale or index? - Zelenka, Anne T. (University of Denver, 2011)
Social participation in late adulthood through activities such as volunteering with charities, playing sports, and joining clubs can increase life satisfaction, directly by providing enjoyable engagement and indirectly by increasing a person's sense of social connectedness. When reported levels of different types of activities are used to measure social participation, conventional measure development procedures based on classical test theory lead to a proliferation of small participation subscales that don't show good reliability, don't have theoretical power, and don't match researchers' conceptions of the dimensions of participation. Based on the poor performance of conventional approaches, some researchers have suggested that social participation should be modeled as an index composed of its indicators rather than as a scale in which indicators reflect an underlying latent factor. Typical approaches in psychosocial research rely on reflective-indicator models, which correspond to scale development, rather than incorporating composite variables with causal indicators. The latter approach, where manifest indicators are specified as causing the unobserved construct, is sometimes known as formative measurement , since the construct of interest is formed by its indicators. This study compared a scale model of social participation based on reflective measurement to an index model based on formative measurement. Using a sample representative of community-dwelling U.S. adults over age 65 from the Health and Retirement Study's 2008 wave of data collection, two alternative measurement models of participation were constructed using sixteen items that recorded frequency of participation in different activities. Because patterns of participation differed for males and females, gender-specific models were developed. The scale models assigned participation items to subscales based on item intercorrelations. The index model assigned items to participation composites based on predictive associations with the outcomes of social connectedness and life satisfaction. The index construction process led to a unidimensional representation of participation, composed of six of the original sixteen participation activity items. The initial attempts to build a scale model led to structures with many small factors and poor predictive validity. Based on the findings of unidimensionality for the index model, a single-factor scale model was explored for female respondents only. Results showed that both index and scale approaches have the potential to produce participation models that are parsimonious, well-fitting, and externally valid even though conventional scale development rules-of-thumb and current conceptions of the domains of participation lead the researcher to non-parsimonious, poorly-fitting solutions lacking predictive capability. Participation measurement instrument developers often theorize the existence of three or more dimensions of participation. Whether they use conventional (reflective indicator) or more radical (formative indicator) models, they are advised, based on this study's results, to evaluate a single-dimensional structure among their candidate models.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Net Worth Accumulation by Different Quintiles of Older Adults Approaching Retirement Age and 10 Years Later - Martha N. Ozawa; Yeo, Yeong H. (Journal of Sociology and Social Welfare, 2011)
The shift in responsibility for income security from the government to individuals makes the accumulation of net worth a vital issue. We investigated the rate of net worth accumulation for people aged 51 to 61 in 1991 (N=7,544) and 61 to 71 in 2001 (N=5,711) using the RAND Health and Retirement Study. We found that the rate of net worth accumulation by the fifth (top) quintile was extremely high in 1991, and the distribution of net worth became more skewed in favor of the wealthy in 2001. Older adults in the first and second quintiles are unable to face the challenge of the shift in responsibility for income security from the government to individuals. Adapted from the source document.
Keywords: Demographics; Health Conditions and Status; Income; Net Worth and Assets; Retirement Planning and Satisfaction

Pensions in the Health and Retirement Study - John A. Turner (Industrial and Labor Relations Review, 2011)
Pensions in the Health and Retirement Study, by Alan L. Gustman, Thomas L. Steinmeier, and Nahid Tabatabai, is reviewed.
Keywords: Demographics; Other; Pensions; Public Policy; Retirement Planning and Satisfaction

A Rationale for Including a Brief Assessment of Hedonic Well-being in Large-scale Surveys - Arthur A. Stone (Forum for Health Economics and Policy, 2011)
Subjective well-being is comprised of both evaluative (life satisfaction) and hedonic (affect) components, and there has been a call to include both aspects of well-being in large-scale surveys. This paper presents a rationale for the feasibility of including a brief measure hedonic well-being based on the measurement of yesterday s affect and experience. It discusses issues of the distinctiveness of hedonic well-being from life satisfaction, the sensitivity of a single day s affect, the sample sizes required for detecting group differences, and the experiential content that could also be collected to extend the value of affective reports. I conclude that a brief assessment is feasible and, in conjunction with measures of evaluative well-being, could add to our understanding of well-being in populations.
Keywords: Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

Taking Early Retirement May Retire Memory, Too - Gina Kolata (New York Times, 2011)
While not everyone is convinced by the new analysis, published recently in The Journal of Economic Perspectives, a number of leading researchers say the study is, at least, a tantalizing bit of evidence for a hypothesis that is widely believed but surprisingly difficult to demonstrate. [...] they note, that could be because people whose memories and thinking skills are declining may be more likely to retire than people whose cognitive skills remain sharp. [...] research has failed to support the premise that mastering things like memory exercises, crossword puzzles and games like Sudoku carry over into real life, improving overall functioning. [This article references the 2010 JEP paper by Rohwedder and Willis which argues that "early retirement appears to have a significant negative impact on the cognitive ability of people in their early 60s".]
Keywords: Cross-National; Health Conditions and Status; Retirement Planning and Satisfaction

Is There Another Union Premium? The Effect Of Union Membership On Retirement Satisfaction - Neuman, Kevin (Industrial and Labor Relations Review, 2011)
Because the average American is spending more time in retirement it is important to understand how satisfied retirees are with their experience. Using data from the Health and Retirement Study the author tests for a positive union effect on retirement satisfaction. The author does not find evidence for a direct union premium since positive union effects disappear after controlling for retirement planning, finances, job characteristics, and duration. However, the author does find strong indirect union effects due predominantly to union members having greater defined benefit pension coverage and less forced retirement. These results suggest that declining unionization may not reduce overall retirement satisfaction directly; however, it may do so indirectly. In addition, retirement satisfaction appears to be adversely affected by negative work conditions such as stooping and job stress. General findings also show who in society has most difficulty adjusting to retirement. PUBLICATION ABSTRACT
Keywords: Employment and Labor Force; Other; Retirement Planning and Satisfaction

What Explains Changes in Retirement Plans during the Great Recession? - Gopi Shah Goda; John B. Shoven; Sita Nataraj Slavov (The American Economic Review, 2011)
We examine changes in subjective probabilities regarding retirement between the 2006 and 2008 waves of the Health and Retirement Study. Using a first-difference approach to eliminate individual heterogeneity, we find that the steep drop in asset prices in 2008 increased the reported probability of working at age 62 during the Great Recession. Increasing unemployment at least partly attenuated this effect, but subjective probabilities of working did not respond to changes in housing markets. Older workers' probabilities of working were more sensitive to fluctuations in the stock market, but less responsive to changes in labor market conditions.
Keywords: Employment and Labor Force; Housing; Methodology; Public Policy; Retirement Planning and Satisfaction

Accessibility of the residential environment: Its influence on the depressive symptoms of older adults - Guzzardo, Mariana T. (University of Connecticut, 2010)
As people age, a supportive and accessible environment becomes more salient in the face of declining functional capacity. Whereas past research supports a relationship between residential environment and well-being, few studies have focused on the specific relationship between the accessibility of the home and mental health. The purpose of the present study is to examine the influence of barrier-free/accessible features in the home on elderly individuals' depressive symptoms, when they experience difficulty with activities of daily living. The barrier-free/accessible features that are investigated include: ramps, railings, wheelchair modifications, grab bars, shower seats and call devices. This study uses data products distributed by the RAND Corporation, based on the 2006 wave of the Health and Retirement Study. The analytic procedures are divided into three parts. In the first place, descriptive analyses were conducted, including independent sample t -tests. These analyses served the purpose of examining differences between key groups within the sample (ethnic group comparisons, and comparisons between senior housing residents and non-senior housing residents). In the second place, hierarchical multiple regression analyses were conducted to examine the features of the home as predictors of depressive symptoms, after controlling for difficulty with ADLs, and various socio-demographic variables. In the third place, the main purpose of the present study was to test the influence of the residential environment on depressive symptoms through a structural regression (SR) model, using Structural Equation Modeling. The model contains functional impairment as a mediator, while age, income, education, gender, and living arrangement function as exogenous variables. Overall, results provide support for the hypothesized model. Findings suggest that accessible dimensions of the physical environment can contribute to psychological well-being by playing a compensatory or assistive role and meeting the individuals' functional needs.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Considering the impact of U.S. social policy retirement benefits on later life labor force participation - Ben Lennox Kail (Considering the impact of U.S. social policy retirement benefits on later life labor force participation, 2010)
As a life stage, retirement emerged out of the industrial revolution and the passage of the Social Security Act of 1935. Since the 1960s, however, several macrostructural changes have resulted in a much more varied landscape of later life labor force behavior. The research presented here extends the work of previous scholars on non-traditional paths to full labor force exit. Using data from the first eight waves of the Health and Retirement Study, the current research focuses on the role of retirement benefits from welfare policy and tax subsidized private retirement plans on transitions between labor force statuses in later life, using multinomial logistic regression in an Hierarchical Linear Modeling framework. Drawing on the hidden welfare state- and life course - perspectives yields several important findings. First, this study finds that welfare benefits allow individuals to reduce their work participation and fully exit the labor force, as well as to reduce the risk that they subsequently reverse their retirement. Because these benefits are nearly universal, they help decouple virtually all age eligible participants from work. Second, private benefits also help individuals to reduce their work, exit the labor force, and remain retired. However, because these benefits are limited to a select population they convey additional advantages to those beneficiaries. Third, the aforementioned macrostructural changes occur at different points within individuals' life courses and the results presented here suggest that this produces different patterns of labor force transitions across birth cohorts. Finally, using piecewise linear growth models, this study finds that, in addition to the actual welfare benefits individuals receive, becoming age eligible for public benefits also impacts later life labor force transitions. However, this influence is most noticeable among those who transition out of full time work, suggesting that public benefits are designed around a now parachronistic model of the life course.
ISBN 9781124709239
Keywords: Demographics; Employment and Labor Force; Event History/Life Cycle; Methodology; Public Policy; Retirement Planning and Satisfaction

Dentistry; Research conducted at University of Maryland has provided new information about dentistry - Anonymous (Health Insurance Law Weekly, 2010)
2010 APR 18 - ( http://www.newsrx.com NewsRx.com) -- In this recent study, researchers in the United States conducted a study To examine the convergence of an aging population and a decreased availability of dental care coverage using data from the Health and Retirement Study (HRS) (see also http://www.newsrx.com/library/topics/Dentistry.html Dentistry). We calculate national estimates of the number and characteristics of those persons age 51 years and above covered by dental insurance by labor force, retirement status, and source of coverage.
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Do Older Adults Anticipate Relocating?: The Relationship Between Housing Relocation Expectations and Falls - Stoeckel, Kimberly J.; Frank Porell (The Journal of Applied Gerontology, 2010)
The relationship between the occurrence of falls and the expectations older adults have about making future residential moves is examined in this research. Data from the 2002 Health and Retirement Study (HRS) are used to analyze self-reported probabilities of moving among a nationally representative sample of noninstitutionalized adults aged 65 and older. The results show that falls were predictive of anticipation of housing relocation as indicated by more than 50 reported probability of moving within the next 2 years. The results suggest that consideration of housing relocation is greater among older adults who experience tangible events indicative of a trajectory of deteriorating health. Reprinted by permission of Sage Publications Inc., copyright The Southern Gerontological Society.
Using Smart Source Parsing pp. Apr Sage Publications, Thousand Oaks CA
Keywords: Demographics; Health Conditions and Status; Housing; Methodology; Retirement Planning and Satisfaction

Does consumption buy happiness? Evidence from the United States - Thomas DeLeire; Ariel Kalil (International Review of Economics, 2010)
We examine the association between various components of consumption expenditure and happiness in the Health and Retirement Study (HRS), a nationally representative sample of older Americans. We find that only one component of consumption is positively related to happiness--leisure consumption. In contrast, consumption of durables, charity, personal care, food, health care, vehicles, and housing are not significantly associated with happiness. Second, we find that leisure consumption is associated with higher levels of happiness partially through its effect on social connectedness, as indexed by measures of loneliness and embeddedness in social networks. On one hand, these results counter the conventional wisdom that material goods can't buy happiness. One the other hand, they underscore the importance of social goods and social connectedness in the production of happiness.
Keywords: Consumption and Savings; Demographics; Retirement Planning and Satisfaction

Does Retirement Affect Cognitive Functioning? - Bonsang, Eric; Adam, Stéphane; Perelman, Sergio (Maastricht: METEOR, 2010)
This paper analyzes the effect of retirement on cognitive functioning using two large scale surveys. On the one hand the HRS, a longitudinal survey among individuals aged 50 living in the United States, allows us to control for individual heterogeneity and endogeneity of the retirement decision by using the eligibility age for Social Security as an instrument. On the other hand, a comparable international European survey, SHARE, allows us to identify the causal effect of retirement on cognitive functioning by using the cross-country differences in the age-pattern of retirement. The results highlight in both cases a significant negative, and quantitatively comparable, effect of retirement on cognitive functioning. Our results suggest that promoting labor force participation of older workers is not only desirable to insure the viability of retirement schemes, but it could also delay cognitive decline, and thus the occurrence of associated impairments at older age.
Keywords: Cross-National; Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Does Stock Market Performance Influence Retirement Expectations? - Gopi Shah Goda; John B. Shoven; Sita Nataraj Slavov (NBER Working Paper, 2010)
While media reports predicted substantial changes in labor supply behavior due to the sharp decline in the value of the stock market in October 2008, empirical evidence on the relationship between equity markets and retirement is mixed. We use panel data from the Health and Retirement Study to investigate the relationship between stock market performance and plans for retirement during 1998-2008, a period that includes the recent financial crisis, by exploiting within-year variation in the SandP 500 index across plausibly exogenous dates of interview. While we do detect a statistically significant negative relationship between the reported probability of working full-time at age 62 and the SandP 500 index in the most recent years of our study period, we do not find strong evidence that changes in equity markets influence changes in retirement plans over the period as a whole. We conclude that the higher probabilities of working reported in recent years were likely due to factors other than stock market performance, such as pessimism about economic security more generally.
Using Smart Source Parsing National Bureau of Economic Research, Inc
Keywords: Consumption and Savings; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

The Effect of Inheritance Receipt on Retirement - Brown, Jeffrey R.; Courtney Coile; Weisbenner, Scott J (Review of Economics and Statistics, 2010)
This paper provides new evidence on how wealth shocks influence retirement behavior. Economic theory generally posits that leisure is a normal good, yet it is difficult to obtain reliable empirical estimates of the wealth effect because wealth is correlated with numerous unobservable characteristics that affect labor supply. We use inheritance receipt as a wealth shock and find that it is associated with a significant increase in the probability of retirement, especially when the inheritance is unexpected. This evidence has important implications for how public policies, such as pension or tax reform, may influence retirement behavior through the wealth effect.
Keywords: Adult children; Employment and Labor Force; Net Worth and Assets; Other; Retirement Planning and Satisfaction

The Effect of the Risk of Out-of-Pocket Spending for Health Care on Economic Preparation for Retirement - Michael D Hurd; Susann Rohwedder (The University of Michigan, Michigan Retirement Research Center, 2010)
After retirement, the primary sources of uncertainty with respect to an individual s economic status are longevity, investment outcomes and out-of-pocket spending on health care. In previous work, we estimated economic preparation for retirement, taking into account the risk of living to an advanced old age and the concomitant risk of running out of resources. But while we accounted for the average level out-of-pocket spending for health care, we did not account for the risk of out-of-pocket spending. In this paper we augment our model for this omission. We find that the risk of out-of-pocket health care spending reduces economic preparation for retirement from about 72 of persons in the age range 65-69 to about 63 . However, this relatively modest reduction is quite unequally distributed: about 57 of single persons are adequately prepared when health care spending is not stochastic, but just 44 when it is. Among single women who are not high school graduates the percentage adequately prepared declines from 33 to 15 .
Keywords: Demographics; Healthcare; Retirement Planning and Satisfaction

The effects of childbearing patterns on the timing of retirement - Chung, Hsiao-Yin (Gerontology, 2010)
The effects of childbearing patterns on the timing of men's and women's retirement were examined. The data for this study come from the Health and Retirement Study, waves 1-7: 1992, 1994, 1996, 1998, 2000, 2002, and 2004. A proportional hazard model (Cox regression) was chosen for this study. Two measures of retirement were considered: labor force exit and self-defined retirement. The results indicated that men with dependent children are more likely to postpone the timing of labor force exit and their self-definition as retired. At the same time, the study indicated that the presence (or absence) and timing of early childbearing experience has a long-term effect on the timing of retirement in later life. In particular, for both men and women, childbearing factors associated with a greater family burden in early life (e.g., parenthood and early childbearing) are related to a later labor force exit. The number of children, however, only affects the timing of women's labor force exit.
Keywords: Adult children; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

The effects of disability on employment patterns among older workers - Hwang, Ju Hee (The effects of disability on employment patterns among older workers, 2010)
Given the substantial number of individuals with disabilities and the sheer rapid growth of U.S. aging population, research on labor transition among older people with disability is vital for improving quality of life for society in general, as well as people with disabilities. Nonetheless, there has been a lack of research on labor transition and older individuals with disabilities in the literature. To reduce and further eliminate labor transition among older people with disabilities, as well as to provide effective interventions and policies for eliminating, it is imperative to investigate the existence of labor transition of older workers and elucidate mechanisms in which labor transition occur. The purpose of this study was to investigate the prevalence of late onset disability among older workers, the consequences for their acquired disability on employment patterns, and the determining factors affecting later-life employment transitions. Given a lack of research employing a national data set for employment and older workers with disabilities, this study examined older people aged 50 and over and used the object measures for define a disability. This study was tested chi-square, ANOVA test, binary and multinomial logistic regression. As an ex post facto design, this study employed the Health and Retirement Study data. Of the total 10,890 age-eligible (age over 50) full time workers who reported thoroughly free of disability (healthy) at the time of baseline interview, the final sampling consisted of 1,096 older workers reported functional or mental disability two years later. 506 male (46.2%) and 590 female (53.8%) reported that they are experiencing disabilities. It is about 10.1% prevalence of an acquired disability among full time older workers. Surprisingly, the prevalence of mental disability was 7.3% and the prevalence of functional disability was 2.7% among older labor force participation. Findings for descriptive results show that about 62.4% workers still kept their full time job even though older workers experienced some types of disabilities. Older workers at older ages were much more likely to change their job to a par-time or quit their job than younger workers. Older workers with mental disability consistently have a better chance of being employed and sustaining their full time job than older workers with functional disability. The findings also confirm that older workers with high levels of education, those who are white, those are female and those in white collar occupations seem to more likely continue their full time job Chi-square tests, independent t-test, and ANOVA found that significant differences existed in age, the level of education, type of disability, self employed status, current occupation, industry, and financial factors (earnings, household net assets, and Social Security Retirement Income) between older individuals who kept their job and who quit their full time job. The binary logistic regression and multinomial logistic results support that gender, high level of education, mental disability, self employed status, white collar occupation and white collar related industry, and not depending on social security retirement pension were independently associated with employed older workers. Implications for rehabilitation counselor practice, education and future research are discussed.
ISBN: 9781124338187
Keywords: Disabilities; Employment and Labor Force; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

The Effects of Health Insurance and Self-Insurance on Retirement Behavior - John Bailey Jones; Eric French (2010)
This paper provides an empirical analysis of the effects of employer-provided health insurance, Medicare, and Social Security on retirement behavior. Using data from the Health and Retirement Study, we estimate a dynamic programming model of retirement that accounts for both saving and uncertain medical expenses. Our results suggest that Medicare is important for understanding retirement behavior, and that uncertainty and saving are both important for understanding the labor supply responses to Medicare. Half the value placed by a typical worker on his employer-provided health insurance is the value of reduced medical expense risk. Raising the Medicare eligibility age from 65 to 67 leads individuals to work an additional 0.074 years over ages 60-69. In comparison, eliminating two years worth of Social Security benefits increases years of work by 0.076 years.
Using Smart Source Parsing University at Albany, SUNY, Department of Economics, Discussion Papers
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction; Social Security

The Effects of the Economic Crisis on the Older Population - Michael D Hurd; Susann Rohwedder (University of Michigan Retirement and Disability Research Center Working Paper, 2010)
We study the effects of the 2007-2009 recession on the population age 55 and older. Households in and near retirement have suffered sizeable losses in assets as a result of the economic crisis. There are a number of ways in which households might respond: reduce spending and with that increase saving, work longer, and/or bequeath less. Using longitudinal data from the Health and Retirement Study and its supplemental surveys, we find that all of these adjustments have been important.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

Employment Patterns and Determinants Among Older Individuals with a History of Short-Duration Jobs - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (U.S. Bureau of Labor Statistics, Working Papers, 2010)
Many studies of labor force withdrawal patterns have focused on individuals who have had career jobs. This paper compares the demographic and economic characteristics of individuals who have never had a full-time career (FTC) job with those who have, and compares the timing and types of job switches that both groups make later in life. The comparison between non-FTC and FTC individuals is important because decisions by policymakers based on the existing retirement literature may have unintended consequences for individuals with only a series of short-duration jobs. We use a sample of respondents from the Health and Retirement Study (HRS) who have worked since age 50, and stratify respondents according to whether an individual has ever had a job that consists of 1,600 or more hours per year and lasts for at least ten years (i.e., a full-time career job). We find that individuals without FTC jobs are a heterogeneous group, representing individuals in many wage and occupational categories. Not surprisingly, we also find that individuals without FTC jobs are less likely than those with FTC jobs to be working in subsequent survey years. However, we find that the labor force withdrawal patterns of non-FTC individuals are similar to those of FTC individuals in many respects. In particular, individuals without FTC jobs change jobs later in life just as frequently as those with FTC jobs. Switching rates between wage-and-salary employment to self-employment and between white-collar and blue-collar jobs are largely similar by FTC status, as are reductions in wages later in life. Overall, the findings reveal that the work decisions later in life of individuals who have never had career employment are diverse, just as they are for individuals with career jobs.
Using Smart Source Parsing pp U.S. Bureau of Labor Statistics, Working Papers: 440
Keywords: Consumption and Savings; Employment and Labor Force; Net Worth and Assets; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Extending the working lives of older workers: The impact of Social Security policies and labor market - Xiaoyan Li (Extending the working lives of older workers: The impact of Social Security policies and labor market, 2010)
This dissertation addresses several issues related to public policies that encourage the extension of working lives of the elderly in the United States. It consists of three chapters. The first chapter and the second chapter of the dissertation evaluate the impacts of the increase in the Social Security Full Retirement Age (FRA) from age 65 (for those born before 1937) to age 66 (for those born between 1943 and 1954). As the FRA rises, the relative generosity of Social Security disability benefits in comparison to retirement benefits is rising, increasing the incentive for insured people to apply for disability benefits. The first chapter uses the Health and Retirement Study (HRS) to estimate this spillover effect. I find that an average four-month increase in the FRA modestly increases the two-year disability benefits application rate by 0.34 percentage points. The effect is greater (0.77 percentage points) among those with a work-limiting health problem. The increase in the FRA also creates an incentive for older workers to increase their labor supply. Using the Basic Monthly Current Population Survey 1994-2009, the second chapter estimates that the labor force participation rate of men aged 62-65 increased by 3.5-4.5 percentage points in response to a one-year increase in the FRA. The third chapter of the dissertation answers the question, "To what extent can the elderly readily find suitable jobs if they want or need to work?" This chapter shows that the employment transition rates are relatively low for older job searchers in the Health and Retirement Study: only half of older searchers successfully attain jobs. A negative age gradient in job attainment is estimated from a set of reduced-form econometric models, which although not conclusive, corroborates other evidence in the literature of statistical age discrimination in the labor market for older workers.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security

Gender Differences in Wealth at Retirement - Neelakantan, Urvi; Chang, Yunhee (The American Economic Review, 2010)
Recent economic trends, like the growing prevalence of defined contribution retirement plans, have made individuals increasingly responsible for their own financial security. Financial security greatly depends on the ability to accumulate adequate wealth (Edward Wolff 1998). Wealth can be a significant source of retirement income for individuals less and less able to rely on Social Security and employerprovided defined benefit pension plans. One concern in the current economic climate is the persistent gap in wealth between men and women. Several papers for example Lucie Schmidt and Purvi Sevak (2006) have found that the gap is significant even after controlling for individual characteristics. This paper contributes to the literature by studying the role of risk preferences in addition to other characteristics. Specifically, it addresses the following research question: controlling for other factors, do gender differences in risk preferences contribute to the gender wealth gap at retirement? The underlying premise is that women are more risk averse than men, which is supported by previous research (for example, Robert B. Barsky et al. 1997). A simple theoretical model of household decision-making illustrates that retirement wealth is a function of income earned over the lifetime and risk aversion. The model is empirically tested using data from the Health and Retirement Study (HRS).1 Results show that the gender gap in wealth persists even when risk preferences are added to the set of controls. Thus the unexplained gap remains a cause for concern.
Keywords: Consumption and Savings; Demographics; Retirement Planning and Satisfaction; Risk Taking

Happy Together: A Structural Model of Couples' Joint Retirement Choices - Maria Casanova (2010)
Evidence from different sources shows that a signicant proportion of spouses retire within less than a year from each other, independently of the age difference between them. The existing reduced- form analyses of couples' retirement suggest that this is partly due to complementarities in spouses' tastes for leisure, which are present when one or both partners enjoy retirement more if the other is retired as well. In order to accurately estimate the role of leisure complementarities, it is essential to appropriately control for incentives to joint retirement acting through the household budget con- straint. This paper presents a structural, dynamic model of older couples' saving and participation decisions which allows for the complementarities in spouses' leisure and where the nancial incentives and uncertainty facing spouses are carefully modeled. Couples are heterogeneous in household wealth and spouses' wages, pension claims, and health status. They face uncertainty in earnings, medical costs, and survival. The model parameters are estimated using a sample of older individuals from the Health and Retirement Study. Estimation results show that leisure complementarities are positive for both husband and wife and account for up to 8 percent of observed joint retirements. The social security spousal benefit is found to account for an extra 13 percent of them. These results imply that incentives for joint retirement play a crucial role in determining individual choices. Since these incentives cannot be captured in a model that takes one spouse's behavior as exogenous, this sug- gests that individual models of retirement are no longer an appropriate approximation of the average household's behavior, given the increasing number of working couples approaching retirement age.
Keywords: Retirement Planning and Satisfaction

Housing Price Volatility and Downsizing in Later Life - James Banks; Richard Blundell; Oldfield, Zoë; James P Smith (Research Findings in the Economics of Aging, 2010)
In this paper, we modeled several types of housing transitions of the elderly in two countries -- Britain and the United States. One important form of these transitions involves downsizing of housing consumption, the importance of which among older households is still debated. This downsizing takes multiple forms, including reductions in the number of rooms per dwelling and the value of the home. There is also evidence that this downsizing is greater when house price volatility is greater and that American households try to escape housing price volatility by moving to places that are experience significantly less housing price volatility. Our comparative evidence in suggests that there is less evidence of downsizing in Britain. Our results indicate that housing consumption appears to decline with age in the US, even after controlling for the other demographic and work transitions associated with age that would normally produce such a decline. No such fall in housing consumption is found in Britain, largely because British households are much more likely to stay in their original residence.
Keywords: Consumption and Savings; Cross-National; Demographics; Housing; Retirement Planning and Satisfaction

How Much Is Enough? The Distribution of Lifetime Health Care Costs - Anthony Webb; Natalia A. Zhivan (2010)
Estimates of the expected present value of lifetime out-of-pocket medical costs from age 65 onward are of limited value to households managing wealth decumulation in retirement. Their risk characteristics may differ from the average. They will also care about the whole probability distribution of health cost outcomes, and will want to update that probability distribution during the course of retirement. Using Health and Retirement Study data, we simulate health, mortality, and health cost histories of retired households. We show that the life expectancy and average health costs of our simulated households closely match published life tables and the findings of previous research. Using our simulated data, assuming a 3-percent real interest rate and including Medicare and private insurance premiums, we estimate that a typical household age 65 has a 5-percent risk of the present value of its lifetime health care costs exceeding 311,000, or 570,000 including the cost of long-term care. We find that relatively little resolution of uncertainty occurs with age, even for those who remain free of chronic disease.
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Human Capital Risk and Pension Outcomes - Olivia S. Mitchell; John A. Turner (Evaluating the Financial Performance of Pension Funds, 2010)
Keywords: Older Adults; Pensions; Retirement Planning and Satisfaction; Risk Factors

Inference of Signs of Interaction Effects in Simultaneous Games with Incomplete Information, Second Version - Áureo de Paula; Tang, Xun (Penn Institute for Economic Research Working Paper, 2010)
This paper studies the inference of interaction effects, i.e., the impacts of players' actions on each other's payoffs, in discrete simultaneous games with incomplete information. We propose an easily implementable test for the signs of state-dependent interaction effects that does not require parametric specifications of players' payoffs, the distributions of their private signals or the equilibrium selection mechanism. The test relies on the commonly invoked assumption that players' private signals are independent conditional on observed states. The procedure is valid in the presence of multiple equilibria, and, as a by-product of our approach, we propose a formal test for multiple equilibria in the data-generating process. We provide Monte Carlo evidence of the test's good performance infinite samples. We also implement the test to infer the direction of interaction effects in couples' joint retirement decisions using data from the Health and Retirement Study.
Using Smart Source Parsing pp Penn Institute for Economic Research, Department of Economics, University of Pennsylvania, PIER Working Paper Archive
Keywords: Methodology; Other; Retirement Planning and Satisfaction

The Influence of Retiree Health Benefits on Retirement Patterns - James Marton; Stephen A. Woodbury (Upjohn Institute Working Papers, 2010)
We estimate the effect of employer offers of retiree health benefits (RHBs) on the timing of retirement using a sample of Health and Retirement Study (HRS) men observed over a period of up to 12 years. We hypothesize that the effect of RHBs differs for workers of different ages--a hypothesis we can test now that the main HRS cohort has aged sufficiently. We apply three wellknown panel data estimators and find that, for men in their 50s, RHBs have little or no effect on retirement decisions; however, a substantial effect emerges for men in their early 60s. We use simulations to illustrate how RHBs alter retirement patterns.
Keywords: Consumption and Savings; Insurance; Public Policy; Retirement Planning and Satisfaction

The Influences on Bridge Employment Decisions - Pengcharoen, Chanjira; Kenneth S. Shultz (International Journal of Manpower, 2010)
Population aging, and changes in labor force participation among older adults, will have tremendous impacts on the aging workforce. Thus it is imperative that the factors that influence whether older workers will continue in their career employment, engage in bridge employment, or fully retire, should be understood better. This paper aims to focus on these issues. In the present study longitudinal data for 2,869 older workers from the Health and Retirement Study (HRS) data set in the USA were used to examine the influence of demographic (e.g., income), nonwork related factors (e.g., marital satisfaction), and work related factors (e.g., job involvement) on late-life employment decisions over a ten year period from 1992 to 2002. The results indicate a wide variety of factors impact employment decisions later in life. Specifically, it was found that work related factors of job involvement and schedule flexibility, as well as the nonwork related factors of certainty of retirement plans, attitudes toward retirement, and job seeking self-efficacy all distinguished the various employment statuses (e.g., completely retired, partly retirement, and not retired at all) of older workers over a ten year period.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Other; Retirement Planning and Satisfaction; Time Use; Women and Minorities

Joint retirement process of dual-worker couples: Expectations, experience, and depressive symptoms - Ho, Jeong-Hwa (The University of Wisconsin - Madison, 2010)
With the continuous increase in women's labor force participation, women now comprise about half of the labor force and the majority of couples are dual-worker couples. As a consequence, a growing number of couples have two retirements to coordinate at the end of their careers. Joint retirement happens when both spouses retire within a relatively short period of time and about twenty to forty percent of dual-worker couples retire jointly. It reflects the changing context of retirement and labor force participation in later life and has implications for individual well-being, academic research, and social policy regarding retirement. In this dissertation, I explore the joint retirement process by focusing on three phases: preretirement expectations, subsequent experience, and postretirement depressive symptoms. I examine how these phases are interconnected and to what degree characteristics of husbands and wives influence joint retirement. I use seven waves of panel data from the Health and Retirement Study (1992-2004). I find that about one in four dual-worker couples expect to retire jointly. Couples with higher preferences for shared leisure and couples receiving fewer intrinsic rewards from work are more likely to expect joint retirement. I find consistency between joint retirement expectations and subsequent experience. Couples in which both spouses expected joint retirement are over four times more likely to retire jointly compared to couples in which neither spouse expected to do so. When spouses had discordant expectations, joint retirement experience reflects husbands' and wives' expectations equally. Among couples in which both spouses expected to retire jointly, those who discussed retirement often are more likely to realize their expectations. I also find that joint retirement per se is not significantly related to postretirement depressive symptoms. Rather, the associations are contingent on previous expectations. Unlike findings of previous studies on consistency between expectations and subsequent experience, individuals who expected joint retirement are more likely to have restless sleep when they realized their expectations and retire jointly, compared to when they did not retire jointly. I speculate that poor health status and unrealistic expectations regarding retirement life may be reasons for this negative link. I conclude with discussion of the implications of this dissertation for research on retirement, social policy, and retirement education.
Keywords: Demographics; Employment and Labor Force; Expectations; Health Conditions and Status; Other; Retirement Planning and Satisfaction

A life-cycle analysis of retirement savings and portfolio choices: Optimal asset allocation and location with taxable and tax-deferred investment - Li, Zhe (Economics, 2010)
In this study, I analyze theoretically and empirically the optimal saving and investment decisions of the households in Defined Contribution (DC) pension accounts, and show that the pension characteristics play important roles in explaining the households' behavior. The first essay attempts to explain the observed asset allocation and location decisions for households making taxable and tax-deferred investment. I incorporate employer matching policies and other pension account characteristics into a life-cycle model of optimal intertemporal consumption and portfolio choice, which includes a taxable saving account and a tax-deferred retirement saving account. The model is estimated using data from the Surveys of Consumer Finances (1992 to 2007), and the structural parameters are recovered by the Method of Simulated Moments. After modeling the features of U.S. pension system, the predicted policy rules are able to explain the observed portfolio patterns of American households, who are more likely to hold equities in the tax-deferred pension account. The estimates and results show that employer matching policy induces higher proportion of total wealth held in the pension account, so investors tend to reduce equity holdings in the taxable account for precautionary saving purpose and boost equity investments in the tax-deferred account to maintain an optimal portfolio mix. I find that a 10 percentage point increase in the estimated employer matching rate makes investors reduce the average equity proportion in the taxable account by 22 percentage point and boost those holdings in the pension account by 10 percentage point. In contrast, since the employer stock match exposes the households to a riskier situation in the pension account than the cash match, it causes households voluntarily to hold less equity in that account, resulting in an average decrease of 4 percentage point in the equity ownership and 3 percentage point in the conditional equity proportion. Moreover, the policy experiment reveals that a deletion of Social Security taxes and payments makes the pension account the only source of retirement income, so households tend to put a higher proportion of savings in the tax-deferred account, and they are likely to invest conservatively and hold about 25 percent more of pension wealth in relatively safe assets. The second essay is about company stock investment in 401(k) plans. Previous studies on the determinants of company stock holdings focus on the past stock market performance of company stock, but ignore the characteristics of the retirement plans and individuals. In this study, using the data from Survey of Consumer Finances (SCF), I provide an empirical analysis of the factors that affect company stock holdings in 401(k) plans, by analyzing a broad list of company features, individual characteristics, and financial wealth information. My preferred estimates suggest that, different from general stocks which are sensitive to risk preference and total wealth, the decision of whether to hold company stock is more likely to be affected by the employer's characteristics and the availability of other investment opportunities. Individuals who work in larger companies and receive more employer matches in the retirement account are more likely to hold company stock in the retirement account, and they are less likely to hold company stocks when the wealth outside the pension account is large and they have other retirement accounts. In addition, I find that the company stock share in 401(k) account is decreasing with pension wealth and total net wealth, which indicates that less wealthy individuals are those who are more exposed to company stock risk. The third essay analyzes the impact of investment choice on savings in defined contribution pensions. The striking growth defined contribution (DC) pensions have vastly expanded the number of individuals with some discretion regarding their retirement savings. One of the factors that may affect saving decisions is investment choice: namely the ability of the participant to direct the investment of the assets in the pension account. In most studies, people who report that they have control over assets allocation in pension plans do not distinguish the assets between the participant contribution and the employer contribution, but it is common for the employer's contribution to be constrained-often to company stock. In this study, I use the Health and Retirement Study (HRS) to estimate the impacts of unconstrained and constrained investment choices on participant saving levels in DC Pensions. The estimates and results indicate that participants with investment choice contribute over 3 percentage points more of their earnings into the defined contribution plan than people without choice, and people constrained in their investment contribute about 3 percentage points less in their retirement saving account. In addition, I find that male and lower income participants tend to contribute more in a self-directed saving account.
Keywords: Consumption and Savings; Event History/Life Cycle; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Measuring How Risk Tradeoffs Adjust with Income - Mary F. Evans (Journal of Risk and Uncertainty, 2010)
Efforts to reconcile inconsistencies between theory and estimates of the income elasticity of the value of a statistical life (IEVSL) overlook important restrictions implied by a more complete description of the individual choice problem. We develop a more general model of the IEVSL that reconciles some of the observed discrepancies. Our framework describes how exogenous income shocks, such as unexpected medical expenditures, may affect labor supply decisions which in turn influence both the coefficient of relative risk aversion and the IEVSL. The presence of a consumption commitment, such as a home mortgage, also alters this labor supply adjustment. We use data from the Health and Retirement Study to explore the responsiveness of labor force exit decisions to spousal health shocks and the role of a home mortgage as a constraint on this response.
Journal Article
Keywords: Consumption and Savings; Employment and Labor Force; Income; Other; Retirement Planning and Satisfaction; Risk Taking; Time Use

Participation and Contributions in Tax-deferred Retirement Accounts: Evidence from Social Security Records - Honig, Marjorie; Irena Dushi (Workin, 2010)
Social Security Administration W-2 records contain employee annual tax-deferred contributions for 1990-2003 and sufficient information to calculate tax-deferred contributions for 1984-1989. We use this information to compare tax-deferred contribution profiles of three cohorts of respondents in the Health and Retirement Study to determine whether younger cohorts saved relatively more at the same stage of the life cycle than had older cohorts. We find that participation in tax-deferred retirement plans increased substantially for all cohorts from 1984 to 2003, and that respondents in more recent cohorts were more likely to participate in such plans than respondents of the same ages in the earliest cohort. Their contributions as a percent of earnings were not significantly larger than those of the earliest cohort, however. Despite the increased availability of these employer-provided plans throughout this period, participation rates and contribution amounts remained low among respondents in the lower half of the earnings distribution.
Keywords: Pensions; Retirement Planning and Satisfaction; Social Security

Pensions in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Harvard University Press, 2010)
Draws evidence from the National Institute on Aging's Health and Retirement Study to examine the pensions held by those approaching retirement age in the United States. Discusses theories explaining pensions; employment and retirement in the Health and Retirement Study; pension data in the Health and Retirement Study; pension plan participation in the Health and Retirement Study; pension plan type; imperfect knowledge of pension plan type; pension retirement ages; pension values; retirement incentives from defined benefit pensions; disposition of pensions upon leaving a job and pension incomes in retirement; and the changing role of pensions in total wealth.
Keywords: Employment and Labor Force; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Is private long-term care insurance affordable for older adults? - Kim, Nayoung (Economics, 2010)
Nationwide there are fewer than 7 million long-term care (LTC) insurance policies in force. Why do so few Americans buy private long-term care (LTC) insurance? Several theories have been offered as possible explanations, including the availability of Medicaid, misperceptions that Medicare or other policies cover LTC, beliefs that one's own risk of needing LTC services is small, or desires to simply rely on children and spouses for LTC. This study examines another possible explanation - that private LTC insurance is simply "unaffordable" for most older Americans, which may be why they don't buy it. This study begins by investigating the meaning of affordability in the context of private LTC insurance. I propose several definitions for affordability, drawing on concepts recently developed to gauge the affordability of acute-care health insurance and housing. Then using nationally representative data from the ongoing Health and Retirement Study (HRS) and the Rand HRS data the study examines the incidence of "unaffordability" of LTC insurance premiums among Americans over age 50, given each of our alternative definitions for it. I consider definitions for affordability, first, based on simple normative standards, such as whether remaining household income after paying for LTC insurance is above some (arbitrarily-set) threshold, and ratio definition, such as whether the ratio of premiums to income is less than some target amount, and more behavioral definitions of affordability, such as whether other adults with similar economic, demographic, and family circumstances are seen to purchase LTC insurance. In each case, the affordability definitions take into account the steep positive relationship between LTC insurance premiums and age-at-time-of-purchase. This analysis offers researchers and policymakers an operational framework for defining affordability, and for evaluating its relative importance as an explanation for non-purchase.
Keywords: Healthcare; Income; Insurance; Retirement Planning and Satisfaction

Protecting the Household Incomes of Older Workers with Significant Health-Related Work Limitations in an Era of Fiscal Responsibility - Jody Schimmel; David Stapleton (Michigan Retirement Research Center Working Paper, 2010)
Many proposals designed to reduce federal budget deficits include retirement policy reforms that would delay workers access to retirement benefits or reduce the value of benefits to those who retire early. Such reforms would have adverse consequences for the economic well-being of older workers with health-related work limitations. In this paper, we explore a set of policy options that take a work-support approach-an earned income tax credit (EITC), an employment services allowance, and a health insurance subsidydesigned to encourage and help workers continue to work if they can. To arrive at a population that might be eligible for such benefits, we first develop a straightforward model to predict the likelihood that a worker reporting a health-related work limitation would experience economic hardship as a result. The model bounds the target population by excluding those who are not expected to experience financial hardship from earnings loss due to a health-related work limitation. It also demonstrates an approach to eligibility determination that would discourage gaming and support rapid eligibility determination-critical for a program designed to extend employment and prevent financial hardship. Using conservative assumptions about program costs, our most expensive program would have a per capita cost of 14,600, or 11,300 if the health insurance subsidy is viewed as an ACA cost. This can be compared to estimated mean annual benefits of 14,855 in 2009 for Social Security Disability Insurance (SSDI) beneficiaries age 50 and older, plus 11,000 per year for Medicare after the 24-month waiting period. Because of its more favorable work incentives, a work-support program is likely to reduce hardship more than a program that preserves existing benefits for the same workers at comparable cost and is likely to be no more difficult to administer.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Public Policy; Retirement Planning and Satisfaction; Social Security

Retiree Health Insurance and Disengagement from a Career Job - Christina A. Robinson; Robert Clark (Journal of Labor Research, 2010)
Over the past two decades the prevalence of partial/phased retirements has increased dramatically, redefining retirement and the way in which retirement benefits are evaluated. Specifically the effect of retirement benefits on the transition away from a state of career employment has become the primary issue of interest. This study uses data obtained from the Health and Retirement Study (HRS) and the Rand HRS files, to examine the relationship between access to retiree health insurance (RHI) and the decision to leave one s career job. We employ a Cox Proportional Hazard Model to estimate how RHI affects the probability that an individual disengages from their career job, given they have not yet done so. Results indicate that those with access to RHI are 21 more likely to leave their career employer in all time periods than similar individuals without RHI. Several robustness tests including stratified estimation and propensity score matching are performed and no evidence of bias is detected.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

The Role of Re-entry in the Retirement Process - Michael D. Giandrea; Kevin E. Cahill; Joseph F. Quinn (Working Paper, 2010)
To what extent do older Americans re-enter the labor force after an initial exit and what drives these unretirement decisions? Retirement for most older Americans with full-time career jobs is not a one-time, permanent event. Labor force exit is more likely to be a process. Prior studies have found that between one half and two thirds of career workers take at least one other job before exiting from the labor force completely. The transitional nature of retirement may be even more pronounced when considering the impact of re-entry. This paper examines the extent to which older Americans with career jobs re-entered the labor force. The analysis is based on data from the Health and Retirement Study (HRS), an ongoing, longitudinal survey of older Americans that began in 1992. We examined the retirement patterns of a subset of 5,617 HRS respondents who were on a full-time career job at the time of the first interview. Logistic regression was used to explore determinants of re-entry among those who initially exited the labor force. We found that approximately 15 percent of older Americans with career jobs returned to the labor force after initially exiting. Respondents were more likely to re-enter if they were younger, were in better health, or had a defined-contribution pension plan. This research provides empirical evidence of how older Americans are utilizing bridge jobs as they transition from career employment, and that re-entry may be an important part of the work experience of older Americans.
Keywords: Consumption and Savings; Employment and Labor Force; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Self-reported neighborhood environment and risk of type 2 diabetes in the Health and Retirement Study and English Longitudinal Study of Ageing - Goldoftas, Barbara (Boston University, 2010)
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Social security claiming of the elderly in the United States - Peng, Yu-I (Social security claiming of the elderly in the United States, 2010)
This dissertation comprehensively studies the behavior of Social Security retirement benefit claiming of the elderly in the United States, using data from the 1992-2006 Health and Retirement Study (HRS) and the supplement "Prospective Social Security Wealth Measures of Pre-retirees". This dissertation begins by modeling the claiming behavior of Social Security retirement beneficiaries under a framework incorporating the incentives for married couples. For individuals who retire by age 62 (the earliest entitlement age), the results indicate that the expected amount of benefit is a strong predictor for the timing of claiming. However, life expectancy, consistent with previous studies, is not a critical determinant of the claiming decision alone, even after taking into account the dependent spouse's longevity expectation. The second chapter models the claiming behavior among individuals who have not retired by age 62 jointly with their retirement behavior. The results show a high correlation between the two decisions. By breaking down the sample, it is found that claiming is attached to retirement; after withdrawal from the labor force and with no labor income, retirees would rely on the Social Security benefits, and liquidity holding becomes a major factor explaining how soon retirees claim their benefits. However, for late-retiring workers, the Social Security retirement benefits do not give much retirement incentive. The third chapter of this dissertation brings in one of the most important Social Security mechanisms, the Social Security earnings test, and takes advantage of its recent reform, the abolishment of the test above the Normal Retirement Age (NRA) in year 2000, to analyze the role of the earnings test in the decisions of claiming and retirement. The earnings test is found to be a crucial factor that links the dates of them.
Keywords: Employment and Labor Force; Health Conditions and Status; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

The Social Security Early Retirement Benefit as Safety Net - John Bound; Timothy A Waidmann; Michigan Retirement Research Center (The University of Michigan, Michigan Retirement Research Center, 2010)
In this paper we used the Health and Retirement Study to examine the health and economic status of those who collect Social Security retirement benefits prior to the full retirement age. We used a propensity score reweighting method to estimate the fraction of early retirees who uses early retirement benefits as a safety net against deteriorating health and who might be induced to apply for disability benefits (SSDI) or retire without income replacement if the generosity or availability of early retirement benefits were reduced. We find that while the majority of early retirees would likely not qualify for disability benefits, approximately one in five have health characteristics similar to SSDI beneficiaries, and thus might not be able to replace losses in benefit income with labor income.
Keywords: Demographics; Disabilities; Retirement Planning and Satisfaction; Social Security

Social Security Reform: Raising the Retirement Ages Would Have Implications for Older Workers and SSA Disability Rolls - United States Governmental Office (Washington, DC, U.S. Government Accountability Office, 2010)
Question: What are the characteristics of those nearing retirement and how likely is it that they will be able to continue working should the retirement ages be raised? What policy options might help to reduce adverse effects on those who are unable to work longer? Finding: Using the NIA-funded Health and Retirement Study and citing a number of studies conducted by NIA-funded researchers, GAO found that raising the retirement ages would likely increase the number of workers applying for and receiving benefits through the Disability Insurance (DI) program. This increase would offset some of the savings implied by the retirement age increases, as well as increasing the DI caseload and administrative costs (which tend to be higher than retirement program costs). Waiting until later to receive benefits could also create financial hardship for some workers, namely those that are unable to continue working but do not qualify for DI or other governmental assistance programs. While policy options exist to mitigate the impact on affected workers, doing so will likely require expanding programs and increase benefit costs. Finding the balance between worker protections and costs will likely be challenging.
Keywords: Disabilities; Public Policy; Retirement Planning and Satisfaction

Spending Patterns in the Older Population - Michael D Hurd; Susann Rohwedder (Aging Consumer: Perspectives from Psychology and Economics, 2010)
This chapter deals with the concrete differences in consumption behavior across a person's life span. Although there is a prevasive belief that households reduce consumption at retirement, the interpretation that consumers adjust their spending after discovering they have fewer economic resources than they had anticipated prior to retirement is not wholly consistent with empirial evidence. The spending habits of older adults are determined by a variety of factors like age, marital status, and economic resources. Specifically, as the population ages, it will tend to spend less on transportation services, vacations, and food; and more on health care and charitable giving.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Three Essays on Cancer Survivorship and Labor Supply - Markowski, Michael P. (College of Health and Human Development, 2010)
These essays examine the effects of cancer on labor supply by cancer survivors in three situations: patients deciding whether to continue working during treatment, spouses deciding whether and how much to work in the years following treatment, and survivors deciding about the timing of retirement. These choices affect individual and societal welfare. Work matters to individual cancer survivors because it is a source of personal fulfillment, a measure of health and vitality, income, and employer-sponsored health insurance benefits. Work matters to society. The National Cancer Institute has estimated that cancer costs over $20 billion annually in work-loss days. Efforts to support and accommodate work by cancer survivors would reduce the indirect economic costs of cancer to society and would potentially improve the well-being of cancer survivors and their families. Although sixty percent of newly diagnosed cancer survivors decide to continue to work during treatment, little is known about the factors that are associated with that decision. Furthermore, spouses share in the cancer survivorship journey, yet the labor supply effect of cancer on spouses in working couples is unknown. With the incidence of cancer increasing with age, the labor supply decision of older cancer survivors increasingly becomes a decision about retirement. The studies use data from the Penn State Cancer Survivor Study (PSCSS) funded by the National Cancer Institute, and supplemented with data from the Health and Retirement Study (HRS), to produce estimates of the effects of cancer on work status and the usual hours of work per week for cancer survivors and spouses at difference stages of survivorship. Logistic regression methods were used to produce estimates of the effects of cancer on working or on complete retirement. Tobit models were used to estimate the effect of cancer on hours of work. The first study finds that the decision to work during treatment is mainly determined by clinical considerations, such as cancer type and stage, although job-related health insurance of survivors and spouses is associated with a greater likelihood of working through treatment. The second study finds that cancer has little long-term effect on the labor supply of the spouses of survivors, at least in older couples or where both partners were working at diagnosis, the situations that were the focus of this research. The third study finds that survivors of both genders who remain cancer-free postpone retirement compared to other adults with no cancer history, but female survivors with recurrences or new cancers retire sooner.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Three essays on the economics of household decision making - Bhatt, Vipul (Economics, 2010)
My research emphasizes the role of interrelated preferences in determining economic choices within a household. In this regard, I study both intergenerational interactions (between parents and children) and intragenerational interactions (between spouses). These linkages have important implications on individual economic behavior such as savings, labor supply, investment in human capital, and bequests which in turn affects aggregate savings and growth. Standard altruism models developed by Barro and Becker are based on an important assumption that parents and children have homogeneous discount factors, which precludes any role parents can play in influencing their child's time preferences. However, there is empirical evidence that parents attempt to shape their children's attitudes. The first essay of my dissertation, "Tough Love and Intergenerational Altruism" (based on this I also have a joint work with Masao Ogaki), proposes a framework to study the role of parents in shaping children's time preferences. The tough love altruism model modifies the standard altruism model in two ways. First, the child's discount factor is endogenously determined so that low consumption at young ages leads to a higher discount factor later in her life. Second, the parent evaluates the child's lifetime utility with a constant high discount factor. In contrast to the predictions of the standard model that transfers are independent of exogenous changes in the child's discount factor, the tough love altruism model predicts that transfers from the parent will fall when the child's discount factor falls. Thus, our model is more consistent with empirical evidence on parental punishments than the standard altruism model. The second essay, "Adolescent Substance Use and Intergenerational Transfers: Evidence from Micro Data," provides empirical evidence for the use of pecuniary incentives by the parent to influence child behavior. Using the first seven waves of the National Longitudinal Survey of Youth, 1997 (NLSY97), I measure the effect of child alcohol consumption on parental transfers. Owing to the plausible endogeneity of the child's alcohol use in the regression equation of transfers she receives from parents, I estimate this relationship using an instrumental variable which utilizes variation in the price of alcoholic beverages over time and across states as a source of exogenous variation. The main finding of the paper is that after accounting for the possible endogeneity of substance use, the incidence of alcohol consumption among youths significantly reduces the amount of parental transfers they receive. Given the robust evidence for a negative correlation between youth substance use and their discount factor in the economics and psychology literature, this result provides an empirical basis for the tough love model of intergenerational altruism. The existing literature on joint retirement suggests that married couples tend to coordinate their retirement decisions which seem to be largely explained by the complementarity in their preferences for leisure. However, the recent trend toward increased labor force participation of older married women may make synchronization of retirement decisions more difficult as more recent cohorts of women become more strongly attached to the labor force and build their own careers, a fact that has been overlooked in the literature. My third essay, "Cross-Cohort Differences in Joint Retirement: Evidence from the Health and Retirement Study," uses the Health and Retirement Study (HRS) data from 1992 through 2006 to document that the likelihood of a married couple jointly exiting the labor force (given that both were employed in the previous period) decreases across successive birth cohorts of wives. I then estimate a discrete choice multinomial model of labor force transition for married couples and find that, while economic factors have substantial power in explaining variation across married couples in retirement behavior, trends across cohorts in these factors do not contribute significantly towards explaining the observed cohort trend in joint retirement. This result suggests that non-economic factors, such as changes in social norms and attitudes towards work, are likely to be more important explanations for this observed trend. From a policy perspective, an implication of this finding is that the bias in the estimated effect of a policy aimed at influencing older workers' labor force behavior (caused by ignoring potential interactions in retirement decisions of spouses) can be mitigated if recent cohorts are less likely to retire together.
Dissertation/thesis number 3527814 ProQuest document ID 1081495581 ISBN 9781267622822
Keywords: Adult children; Health Conditions and Status; Retirement Planning and Satisfaction

Using the Health and Retirement Study to Analyze Housing Decisions, Housing Values, and Housing Prices - Hugo Benítez-Silva; Selçuk Eren; Frank Heiland; Jimenez-Martin, Sergi (Cityscape: A Journal of Policy Development and Research, 2010)
Few existing surveys provide detailed longitudinal information on households and their homes. This article introduces a data source, the Health and Retirement Study (HRS), which has this detailed information but has received little attention by housing researchers to date. The HRS is a rich longitudinal data set that provides information on house values, house prices, and detailed personal characteristics of those who own and sell their homes. The HRS is a nationally representative longitudinal survey that originally sampled 7,700 households headed by an individual aged 51 to 61 in the first interviews in 1992 and 1993. It now also samples additional cohorts of older Americans. Although the HRS is the data set of choice when analyzing the retirement behavior, savings, and health status of older Americans, given its wealth of demographic, health, and socioeconomic data, it has been rarely used to answer questions regarding the housing market. A seldom used section of the questionnaire provides detailed information about real estate transactions by households, however, enabling researchers to repeatedly observe both self-reported house values and the actual selling prices of properties sold since 1992 (originally bought in the past five decades). The article describes a number of important housing-related measures available in the HRS and illustrates the usefulness of these data by conducting a statistical analysis of the accuracy of self-reported home values. Specifically, we analyze the predictive power of self-reported housing wealth when estimating housing prices using the HRS data. The evidence shows a slight overestimation of housing values by older Americans.
Using Smart Source Parsing pp
Keywords: Consumption and Savings; Demographics; Housing; Income; Net Worth and Assets; Retirement Planning and Satisfaction

What the Stock Market Decline Means for the Financial Security and Retirement Choices of the Near-Retirement Population - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Journal of Economic Perspectives, 2010)
This paper investigates the effect of the current recession on the retirement age population. Data from the Health and Retirement Study suggest that those approaching retirement age (early boomers ages 53 to 58 in 2006) have only 15.2 percent of their wealth in stocks, held directly or in defined contribution plans or IRAs. Their vulnerability to a stock market decline is limited by the high value of their Social Security wealth, which represents over a quarter of the total household wealth of the early boomers. In addition, their defined contribution plans remain immature, so their defined benefit plans represent sixty five percent of their pension wealth. Simulations with a structural retirement model suggest the stock market decline will lead the early boomers to postpone their retirement by only 1.5 months on average. Health and Retirement Study data also show that those approaching retirement are not likely to be greatly or immediately affected by the decline in housing prices. We end with a discussion of important difficulties facing those who would use labor market policies to increase the employment of older workers.
Journal Article
Keywords: Consumption and Savings; Employment and Labor Force; Event History/Life Cycle; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Why Do the Elderly Save? The Role of Medical Expenses - Mariacristina De Nardi; Eric French; John Bailey Jones (The Journal of Political Economy, 2010)
This paper constructs a model of saving for retired single people that includes heterogeneity in medical expenses and life expectancies, and bequest motives. We estimate the model using Assets and Health Dynamics of the Oldest Old data and the method of simulated moments. Out-of-pocket medical expenses rise quickly with age and permanent income. The risk of living long and requiring expensive medical care is a key driver of saving for many higher-income elderly. Social insurance programs such as Medicaid rationalize the low asset holdings of the poorest but also benefit the rich by insuring them against high medical expenses at the ends of their lives.
Keywords: Consumption and Savings; Expectations; Healthcare; Other; Retirement Planning and Satisfaction

Women's alternative retirement transition options: Social Security retirement benefits and employment status - Gillen, Martie (Women's alternative retirement transition options: Social Security retirement benefits and employment status, 2010)
The purpose of this dissertation is to examine two common measures of retirement status: (1) receipt of Social Security retirement benefits and (2) employment status. A three manuscript format was used to report the effects of human capital characteristics (education, marital status, and health status), types of income sources (pension income, IRA/annuity income, investment asset income, and other income), and age on women's timing of Social Security retirement benefit receipt and employment status. Four waves of Health and Retirement Study (FIRS) data (2000, 2002, 2004, and 2006) were used in the analyses. Manuscript 1 used longitudinal data to investigate alternative retirement options based on timing of Social Security benefit receipt and employment status. A majority of women chose early receipt of benefits compared to normal or delayed receipt. A greater percentage of women who did not receive Social Security benefits were employed compared to those who received benefits. Among women employed full-time; a large percentage did not receive Social Security benefits while a large percentage of women employed part-time received benefits. Manuscript 2 used cross-sectional data to focus on timing of receipt of Social Security retirement benefits. Less than excellent health and receiving pension income increased the likelihood of early receipt. Not being married and receiving income from earnings and unspecified income sources reduced the likelihood of early receipt. Manuscript 3 used cross-sectional data to estimate the likelihood of being employed. Having more years of education and being divorced/separated increased the likelihood; while poor/fair health, older age, receipt of Social Security benefits, and pension income reduced the likelihood of being employed. Additionally, manuscript 3 estimated the likelihood of full and part-time employment for women receiving Social Security benefits. Overall, this dissertation updates current knowledge regarding the complex options of timing of receipt of Social Security retirement benefits and employment options.
Keywords: Adult children; Employment and Labor Force; Healthcare; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Work and Retirement: How and When Older Americans Leave the Labor Force - Joseph F. Quinn (2010)
A century-old trend toward earlier and earlier retirement among older American men came to a halt during the 1980s and then reversed. For older American women, a dramatic break from trend occurred at the same time. These changes coincided with significant changes in the retirement environment that altered the relative attractiveness of work and leisure late in life in favor of work. Since most of the environmental changes are permanent, we have entered new era, with workers leaving the labor force later than their predecessors, with many continuing to retire gradually, in stages, utilizing bridge jobs on the way out.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Work and Retirement Patterns for the G.I. Generation, Silent Generation, and Early Boomers: Thirty Years of Change - Richard W. Johnson; Barbara A Butrica; Corina D Mommaerts (Center for Retirement Research at Boston College Working Papers, 2010)
This study examines how the shifting choices and constraints facing older workers have changed work and retirement patterns over the past 30 years. Health improvements, declines in physical job demands, changes in Social Security rules, and the erosion in traditional defined benefit pension coverage and employer-sponsored retiree health insurance have altered work incentives at older ages. This paper compares labor force exits by older workers born 1913 to 1917 (part of the G.I. Generation), 1933 to 1937 (part of the Silent Generation), and 1943 to 1947 (part of the Baby Boom Generation). The analysis uses 16-year longitudinal panels from the Health and Retirement Study and decades-long administrative earnings records linked to respondents in the Survey of Income and Program Participation. The results show that early boomers worked longer than members of the Silent Generation, and that the pathways older workers follow out of the labor force have become more complex over time. The median retirement age for men was about one-half year higher in the 1943-47 cohort than in the 1933-37 cohort (62 vs. 61.5), but differences were more pronounced at older ages. By age 65, for example, 40 percent of early boomer men had not yet retired, compared with only 20 percent of Silent Generation men. Both male and female workers in the 1933-37 cohort were much less likely than their counterparts in the 1913-17 cohort to follow the traditional retirement path of exiting the labor force from full-time employment and never returning to work.
Using Smart Source Parsing pp Center for Retirement Research, Working Papers, Center for Retirement Research at Boston College
Keywords: Demographics; Employment and Labor Force; Pensions; Retirement Planning and Satisfaction

Work, retirement, and well-being: Does what you did for a living influence how you feel in retirement? Women's retirement and self-assessed well-being: An analysis of three measures of well-being among recent and long-term retirees relative to homemakers - Silver, Michelle Pannor (Public Policy Studies, 2010)
This dissertation contributes to the literature on retirement and subjective well-being by focusing on two key questions using data from the Health and Retirement Study: (1) Is retiring from a job that afforded greater opportunities to engage in autonomous, creative, and/or prestigious work linked with greater well-being in retirement? and (2) Are there differences in subjective measures of well-being for women who retire relative to women who are homemakers? Based on prior research comparing workers and retirees, one might expect retirees to report relatively poor well-being (e.g. Dave et al. 2006; Doshi et al. 2008). However, analyses of a sample of respondents who make the transition from working full-time to being fully retired between 1992 and 2006, suggest that retiring from a professional occupation is related to more favorable self-assessments of well-being. The second research question focuses on women's experiences by taking advantage of a unique comparison group which exists for women retiring at the early part of this century, namely homemakers or women who did not participate in the paid labor force. Analyses of female retirees who are compared to homemakers suggest that despite the major role change they experienced, participating in the paid labor force may have been a protective factor with regard to self-assessed well-being.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction; Women and Minorities

Are all Americans saving 'optimally' for retirement? - William G. Gale; John Karl Scholz; Ananth Seshadri (Michigan Retirement Research Center Research Paper, 2009)
Many people fear that Americans are preparing poorly for retirement. But developing rigorous evidence on this issue is difficult. In this paper we briefly discuss evidence on the adequacy of retirement wealth accumulation. We conclude that existing descriptive evidence does not seem consistent with dire assessments of poor financial preparation. We then extend the straightforward, but computationally complex dynamic programming approach used in our earlier work to assess the adequacy of retirement wealth preparation of Americans born before 1954. We find only 4 percent of HRS households have net worth below their optimal targets in 2004, though this percentage is somewhat higher for more recent HRS cohorts. While our work is preliminary, we find little evidence that Americans born before 1954 have prepared poorly for retirement.
Keywords: Consumption and Savings; Restricted data; Retirement Planning and Satisfaction

Bridge Jobs: A Comparison Across Cohorts - Michael D. Giandrea; Kevin E. Cahill; Joseph F. Quinn (Research on Aging, 2009)
Are today's retirees following in the footsteps of their older peers with respect to gradual retirement? Recent evidence from the Health and Retirement Study (HRS) suggests that most older Americans with full-time career jobs late in life moved to other jobs prior to complete labor force withdrawal. The authors explored the retirement patterns of two cohorts of individuals from the HRS. One group (the war babies) was born between 1942 and 1947 and therefore aged 59 to 64 years at the time of their fifth biennial HRS interviews in 2006. The others (the original HRS respondents) were aged 59 to 64 in 2000 and therefore 6 years older. The war babies have followed the gradual-retirement trends of their predecessors. Traditional one-step retirement appears to be fading as the effects of changes in the retirement environment continue to unfold.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Determinants and Consequences of Moving Decisions for Older Homeowners - Calvo, Esteban; Haverstick, Kelly; Natalia A. Zhivan (Center for Retirement Research at Boston College Working Papers, 2009)
The lore on whether older Americans move is mixed. While the familiar stereotype is that retirees flock to Florida or Arizona, prior studies have found that their home equity rises modestly over time, suggesting that they tend to stay put. This paper examines moving trends, determinants, and consequences using the original cohort of the Health and Retirement Study (HRS). We find that a full 30 percent of homeowners in the HRS cohort move over the 1992-2004 period, but most moves occur close to home. Overall, two types of movers emerge from the analysis those who affirmatively plan to move and those who react to changing circumstances. As proxies for these two types, this study uses the presence or absence of a negative shock, such as death of a spouse or entry into a nursing home. Our results show that the factors that help determine a move are similar for both groups, while the consequences of a move vary. Homeowners with shocks are more likely to discontinue homeownership and reduce net equity, supporting the hypothesis that households may view housing wealth as insurance against catastrophic events. Finally, while movers in both groups of homeowners experience improvements in psychological well-being, movers with shocks are impacted most by the shocks themselves.
Keywords: Demographics; Housing; Retirement Planning and Satisfaction

The Effect of Large Capital Gains or Losses on Retirement - Michael D Hurd; Reti, Monika; Susann Rohwedder (Developments in the economics of aging, 2009)
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

The effect of retirement on vigorous physical activity controlling for the socio-demographic variables of age, gender, education, income, race and perceived health status affect - Nekuda, Jayme D. (Human Sciences, 2009)
Health and Retirement Study data was used to examine the relationship between retirement and vigorous physical activity. The independent variables studied were vigorous physical activity in 1998 (T1) and retirement status in 2000 (T2). The dependent variable was vigorous physical activity in 2000 (T2). The entire sample consisted of 5,351 respondents who were in the workforce in 1998 (T1). In 2000 (T2), 4,449 reported still being in the workforce while 902 reported having retired between T1 and T2. The affect was controlled by the covariates of age, gender, education, income, race and perceived health status. These covariates together predicted approximately 16.5% to 22% of the variability in participation of vigorous physical activity. Participants in the entire sample consisted of 51.7% males, 48.3% females, average age of 59, average income of $80,558, and average years of education was 13.03. White/Caucasian individuals accounted for 82.4%, 13.5% were Black/African American and slightly over four percent reported being "Other". Those who retired between T1 and T2 consisted of 57.4% males, 42.6% females, average income of $56,828, and average years of education was 12.56. Individuals' perceived health status did not significantly change from T1 to T2 whether or not they retired. Examination found that the most significant indicator of participation in vigorous physical activity after retirement was an individual's participation in vigorous physical activity prior to retirement. There was no relationship however, between retirement status and participation in vigorous physical activity. Gender was significantly related to participation in vigorous physical activity, with men's participation being higher than women's. Perceived health status was also found to be significantly related to participation in vigorous physical activity. Those who perceived their health as excellent, very good or good were significantly more likely to participate in vigorous physical activity than those who reported their health as fair or poor. Education was negatively correlated to vigorous physical activity which contradicted the literature.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Financial Literacy and Financial Sophistication Among Older Americans - Annamaria Lusardi; Olivia S. Mitchell; Vilsa Curto (NBER Working Paper, 2009)
This paper analyzes new data on financial literacy and financial sophistication from the 2008 Health and Retirement Study. We show that financial literacy is lacking among older individuals and for the first time explore additional questions on financial sophistication which proves even scarcer. For this sample of older respondents over the age of 55, we find that people lack even a rudimentary understanding of stock and bond prices, risk diversification, portfolio choice, and investment fees. In view of the fact that individuals are increasingly required to take on responsibility for their own retirement security, this lack of knowledge has serious implications.
Keywords: Consumption and Savings; Net Worth and Assets; Retirement Planning and Satisfaction

Gradual Retirement, Sense of Control, and Retirees' Happiness - Calvo, Esteban; Haverstick, Kelly; Sass, Steven A. (Research on Aging, 2009)
The aim of this study was to explore the factors that affect an individual's happiness while transitioning into retirement. Recent studies have found that workers often view the idea of gradual retirement as a more attractive alternative than a cold turkey or abrupt retirement. However, there is very little evidence as to whether phasing or cold turkey makes for a happier retirement. Using longitudinal data from the Health and Retirement Study, the authors explored what shapes the change in happiness between the last wave of full employment and the first wave of full retirement. The results suggest that what matters is not the type of transition (gradual retirement or cold turkey) but whether people perceive the transition as chosen or forced.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

How Changes in Social Security Affect Retirement Trends - Alan L Gustman; Thomas L. Steinmeier (Research on Aging, 2009)
For married men, we find the conventional view of retirement trends that the long term trend to early retirement has been reversed -- is partially contradicted by recent data. Specifically, descriptive data collected from both the Census and the Health and Retirement Study (HRS) suggest that for those in their fifties, over the periods 1992 to 1998 and 1998 to 2004, the trend to early retirement reasserted itself and labor force participation fell. In contrast, for those in their sixties, there was an increase in work. Similarly, for those 65 and over, the amount of work increased. Simulations with a structural retirement model suggest that the recent acceleration of the trend to early retirement for those in their fifties is not the result of the change in Social Security rules. According to our model, changes in Social Security rules are expected to reduce the number of those in their early sixties who are working. This suggests that forces other than changing Social Security rules account for the observed increase in work by those in their early sixties, and that the effects of these forces are stronger than those suggested by the trends in descriptive data. Lastly, the analysis suggests that changing Social Security rules do help to explain the increase in work by those age 65 and older. The effects of these rule changes encourage workers to remain in their long term jobs for a longer time, encourage some to return from retirement to full time work, and encourage more partial retirement. Nevertheless, the changes in retirement induced by Social Security changes have been modest. Due to Social Security changes, the number of 65 year old married men at work increases by about two percentage points at ages 65 and 66, with slightly smaller changes at 67 to 69. Given the low basic labor force participation at 65 and 66, with 20 to 25 percent at full time work, and another 17 percent at part time work, the percentage increases in work due to Social Security changes are three or four times higher.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security

How Do Health Shocks Influence Retirement Decisions? - McGeary, Kerry Anne (Review of Economics of the Household, 2009)
The financial viability of the nation s Medicare and Social Security programs has come into question as older adult workers, in particular members of the baby-boomer generation, begin to voluntarily retire. Obviously, any deterioration in the health of older adults will inevitably increase pressure on the Medicare system. However, if older adults respond to changes in their health by reducing their labor supply, than this will also increase demand for the Social Security system. Using data on married and employed couples from the Health and Retirement Study (HRS), this paper determines how the labor supply of each member of a married couple is influenced by changes in the health, assets and medical expenditures of the other member of the couple. Therefore, adding to the extant literature as we determine how the labor supply of an individual responds to health shocks visited on their spouse. We find that the labor supply of both males and females is influenced by their own health shocks and health shocks suffered by their spouses.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

The Implications of Declining Retiree Health Insurance - Courtney Monk; Alicia H. Munnell (Center for Retirement Research at Boston College Working Papers, 2009)
A large number of retirees have employer-sponsored retiree health insurance (RHI). While RHI is a common source of supplemental coverage for Medicare beneficiaries, it is also the only affordable source of health insurance for many retirees under age 65 who have no access to Medicare. However, employers are scaling back their RHI benefits in response to rising health costs and changes in accounting rules, by either eliminating benefits which shifts costs to retirees, or tightening vesting requirements. Using data from the Health and Retirement Study, this paper examines the potential consequences of eliminating RHI for both pre-Medicare and Medicare-eligible retirees. For younger retirees the likely primary response is to work longer, and we find that number of workers age 55 to 64 would increase by 7 percent, as some of those who have their access to RHI eliminated would work rather than retire. Of those who still choose to retire, most lack any employer-sponsored health insurance option and would need to find an alternative source of coverage or go uninsured. For Medicare beneficiaries over 65, we estimate that about three quarters would replace RHI with another form of supplemental coverage. This shift would slightly reduce total spending and utilization for individuals who choose basic Medicare or a Medicare HMO as opposed to a Medigap plan, but health outcomes would probably be unaffected no matter which supplemental option is chosen. In short, a full elimination of RHI would primarily impact early retirees who must face the cost of much more expensive insurance or of financing illness without insurance. Policymakers may want to consider encouraging insurers to step in to provide more affordable plans for these early pre-Medicare retirees
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Integrating Retirement Models - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2009)
This paper advances the specification and estimation of models of retirement and saving in two earner families. The complications introduced by the interaction of retirement decisions by husbands and wives have led researchers to adopt a number of simplifications to increase the feasibility of estimating family retirement models. Our model relaxes these restrictions. It includes the extended choice set created when each spouse makes an independent retirement decision. It also includes the full range of complexity found in dynamic-stochastic models of retirement decision making, so far analyzed only in the context of single earner households. Retirement outcomes include full retirement, partial retirement and full-time work. Reverse flows from states of lesser to greater work are also included. The preference structure incorporates heterogeneity in time preference, varying taste parameters for full-time and part-time work, and the possibility of changes in preferences after retirement. The opportunity set reflects the full range of nonlinearities created by pensions and Social Security. Financial returns are stochastic. Exogenous shocks such as layoffs are also included. Estimation is based on data from the Health and Retirement Study. The solution method is based on backward induction. We show that this method is superior to a method based on a Nash equilibrium, providing plausible behavioral predictions when Nash equilibrium criteria fall silent. In contrast to some recent studies, the findings suggest the flow of wives into the labor force in the last few decades has probably reduced the amount of husbands work. The model also provides plausible responses to various policies. For example, we find that any effort to promote opportunities for partial retirement as a means to increase overall work is likely to be unsuccessful as any induced decline in full retirements is offset by a decrease in full-time work.
Keywords: Adult children; Methodology; Retirement Planning and Satisfaction

The mediating effects of the sense of control on the financial well-being of older adults - Karen A. Zurlo (The mediating effects of the sense of control on the financial well-being of older adults, 2009)
Statement of the problem. The financial well-being of the older adult population has improved over the past few decades, but the outlook for future generations is not positive. As government and employers become less accountable for the provision of retirement income, adults are required to take greater responsibility for their financial circumstances as they age, yet they often have neither the skills nor ability to exercise this control. By not exercising adequate control over their different aspects of their lives, adults may be exposed to financial risk in retirement. Methods. A cross-sectional, quantitative analysis using survey data from two components of the Health and Retirement Study (HRS), the HRS Rand Data files and the Psychosocial Leave-Behind Participant Lifestyle Questionnaire, was conducted. These surveys were administered in 2006 to a sample of 7,549 adults over the age of 50 and merged to conduct this analysis. Statistical analyses used multi-stage statistical modeling to test the mediating effects of the general sense of control and domain-specific levels of control, also known as control beliefs, on the relationship between the general attributes of older adults and their financial well-being. Financial well-being was measured as financial satisfaction and wealth. Results. The control beliefs of older adults significantly influence the size and magnitudes of the linkages between their demographic attributes and financial outcomes. Control beliefs boosted explained variance in financial satisfaction by over 70 percent and they increased explained variance in wealth by 4.5 percent. The mediation analyses were consistent with these results. Conclusion. Control beliefs are more strongly influential over older adults' sense of financial satisfaction than on their actual wealth levels. Accordingly, interventions that influence peoples' sense of control may enhance their felt well-being but will be less influential on levels of wealth. This study can be considered the first of its kind to use the psychological construct of sense of control as a mediating factor on the relationship between the attributes of older adults and self-assessed financial satisfaction as well as actual wealth outcomes. In this way we contribute to the newly developing research stream evaluating the determinants of self-reported happiness.
Keywords: Demographics; Methodology; Net Worth and Assets; Other; Retirement Planning and Satisfaction

Older Workers on the Move: Recareering in Later Life - Richard W. Johnson; Kawachi, Janette; Lewis, Eric K. (AARP's Public Policy Institute, 2009)
Recareering or career change is common at older ages. Workers who change careers typically move into jobs that pay less then their previous jobs and are less likely to offer pension and health benefits. On the positive side, new careers tend to offer more flexible employment arrangements, less stressful working conditions, and fewer managerial responsibilities. This report examines the extent and nature of career change by older workers and its consequences for later-life employment. Using data from the Health and Retirement Study (HRS), the analysis tracks a sample of workers ages 51 to 55 and employed full time in 1992 and computes the percentage who changed employers, occupations, or industries by 2006, when they were ages 65 to 69. In addition, the report measures the impact of personal and job characteristics on the likelihood that older workers switch employers and occupations. The report also examines how job characteristics such as wages, health insurance coverage, and pension coverage change when older workers move into new careers. Tabulations compare the new and old jobs in terms of occupation, industry, selfemployment, flexible work options, part-time work, stressful work conditions, managerial responsibilities, overall job satisfaction, and prestige scores that rank occupations in terms of social standing. Special attention is paid to the circumstances surrounding later-life job separations that influence career change. Older job changers who say they are retiring from their previous employers are especially likely to downshift into less demanding, more flexible new careers that pay less than their former positions. Laid-off workers and those who simply say they quit their former jobs are more likely than retirees to take new jobs in the same occupation. For this study, recareering involves a move to a new employer in a new occupation. The terms occupational change and career change or recareering are used interchangeably.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Preretirement Planning and Well-Being in Later Life: A Prospective Study - Jack H Noone; Christine Stephens; Fiona M. Alpass (Research on Aging, 2009)
Cross-sectional and retrospective research has identified a reliable relationship between preretirement planning and later-life well-being. Although it seems intuitive that retirement planning leads to more positive retirement outcomes, limited longitudinal analysis has confirmed the directionality of this relationship or clarified its complexities. The Health and Retirement Study, a prospective survey of American workers and retirees from 1992 to the present, can help illuminate this relationship. Data signifying the preretirement activities of employed individuals from the 1992 wave were compared with their postretirement ratings of retirement satisfaction and subjective physical and emotional health in 2004. An ordinal regression analysis indicated that those who had discussed retirement with their spouses and had retirement superannuation or savings plans in 1992 reported greater well-being in 2004 (controlling for health status, the reason for retirement, and income in 1992). These results confirm the importance of preretirement preparation and provide a rationale for developing more comprehensive, theory-driven measures of retirement planning.
Keywords: Methodology; Retirement Planning and Satisfaction

Retiree Health Benefits and the Decision to Retire - James Marton; Stephen A. Woodbury (Staff Working Papers, 2009)
We estimate the effect of employer offers of retiree health benefits (RHBs) on the timing of retirement using a sample of men observed over a period of up to 12 years in the Health and Retirement Study (HRS). Our main concern is that such estimates may be contaminated by unobserved heterogeneity - workers with a taste for early retirement sort into jobs offering RHBs. We attempt to address this concern by using a fixed-effects estimator, which yields substantially smaller estimates of the effect of RHB offers than estimators that do not attempt to control for unobservables. The findings suggest that an RHB offer increased the probability of retirement by 14 percent on average for men born between 1931 and 1941.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Retirement Decisions of Women and Men in Response to their Own and Spousal Health - Ilchuk, Serhii (The Pardee RAND Graduate School, 2009)
This dissertation studies the impact of individual and spousal health on the retirement decisions of both spouses in dual-earner families. The survival analysis techniques (Kaplan-Meier estimator, a Cox proportional hazards model, a Weibull specification) are used to analyze eight biennial waves (1992-2006) of the Health and Retirement Study (HRS), a nationally representative panel survey of the U.S. population over age 50. The modeling of retirement ages of both spouses and the time interval between their retirement dates provides a more accurate picture of the family retirement process than has been available in previous analyses. Of the various causes of early retirement, the onset of work disability has the biggest effect. The effect of functional disability is comparable, while major health events and chronic illnesses have smaller but statistically significant effects. The research findings also highlight the importance of correctly dating the exact timing of health deterioration to alleviate "justification bias" in empirical estimation of health effects. The estimates of the spousal health effects demonstrate that the onset of a husband's work disability can lead to an earlier age of retirement not only for the husband himself but also, through joint retirement, for his wife. This effect can be defined as a "joint early retirement" phenomenon. Husbands whose wives become ill also tend to retire at earlier ages. The "joint early retirement" phenomenon is more pronounced among families where the spouse remaining in the labor force is a low earner. The cost-of-illness estimates for indirect costs (productivity lost through an early retirement) of different health conditions are calculated at the individual and societal (adjusted for prevalence of conditions) levels. From a societal perspective, the most costly work disability conditions are those related to musculoskeletal and heart and circulatory conditions. At the individual level, the productivity losses are greatest from work disability related to heart and circulatory conditions and cancers and tumors. The total family productivity lost due to a husband's (a wife's) work disability is also estimated. The results of this dissertation have important implications for public policies related to labor force participation, Social Security reform, and health care.
Document number: RGSD-243
Keywords: Adult children; Health Conditions and Status; Retirement Planning and Satisfaction

Retirement Preparedness in Non-Married Women Near Retirement - Lee, Yoon G.; Rowley, Megan (Journal of Family and Consumer Sciences, 2009)
Using data from the 2004 Health and Retirement Study (HRS), the authors examined the savings and retirement preparedness of non-married women between the ages of 51 and 64. Approximately 68 of the non-married women did not meet one of the criteria for retirement preparedness (i.e., having investment assets greater than 25 of their net worth). Multivariate regression analyses show that all else being equal, divorced women held significantly lower levels of net worth and were less likely to meet the criterion for being financially prepared for retirement than their widowed counterparts. The findings suggest that women with less income, less education, who were Black, and in poor health had lower levels of net worth and were less likely to meet the criterion for being prepared for retirement.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction; Women and Minorities

Strange But True: Claim and Suspend Social Security - Alicia H. Munnell; Golub-Sass, Alex; Nadia S. Karamcheva (Center for Retirement Research at Boston College Briefs, 2009)
The brief’s key findings are: During the current economic crisis, many older workers are postponing retirement and some retirees are re-entering the labor force. Re-entrants age 66 and over can put their Social Security benefits “on hold” in exchange for higher benefits later. This “claim and suspend” strategy also offers greater flexibility to one-earner couples, allowing the higher earner to delay benefits while his spouse claims. The potential costs to Social Security are modest.
Keywords: Retirement Planning and Satisfaction; Social Security

Strange But True: Claim Social Security Now, Claim More Later - Alicia H. Munnell; Golub-Sass, Alex; Nadia S. Karamcheva (Center for Retirement Research at Boston College, 2009)
Keywords: Retirement Planning and Satisfaction; Social Security

Strange But True: Free Loan from Social Security - Alicia H. Munnell; Golub-Sass, Alex; Nadia S. Karamcheva (Center for Retirement Research at Boston College, 2009)
Keywords: Retirement Planning and Satisfaction; Social Security

Three Essays in Health Economics - Christina A. Robinson (Three Essays in Health Economics, 2009)
This essay examines topics in health economics. The first study uses data obtained from the Rand version of the Health and Retirement Study, to examine the relationship between retiree health insurance (RHI) and the decision to leave one's career job. This paper a Cox Proportional Hazard Model and estimates the probability that an individual disengages from their career job. Results indicate that access to RHI are significantly increases the probability of disengagement occurring. The second and third essays examine the relationship between Food Stamp Program (FSP) participation and obesity in women and children. There are two main bodies of literature that examine the effect of FSP participation on obesity, the first focuses on adults and the second on children. The literature focusing on adults finds that FSP participation is positively related to obesity in women, while no similar effect is found for children. This creates an interesting economic puzzle. The second chapter of this dissertation focuses on children and considers weight accumulation as dynamic process. To measure obesity, a child's BMI is compared to their medically ideal BMI; if FSP increases this deviation then FSP is found to increase childhood obesity. Results suggest that FSP participation does not significantly contribute to childhood obesity. The third essay considers the relationship between FSP participation and obesity in mothers. Three estimations are performed and evidence that mothers are not at an increased risk for obesity is found. I first consider a women's weight growth in the same framework employed in chapter 2 and find no significant relationship. Next, I consider how FSP participation affects the probability a mother becomes obese. Finally, I estimate the nutritional value of foods brought into FSP households controlling for the presence of children. Results from these estimations suggest that mothers are not at an increased risk for obesity due to FSP participation. Thus, it is not surprising that children who live in FSP households are not at an increased risk of obesity, and the puzzle is resolved.
Keywords: Health Conditions and Status; Income; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Unequal Giving: Monetary Gifts to Children Across Countries and Over Time - Julie M Zissimopoulos; James P Smith (RAND Working Paper, 2009)
Money parents give their adult children may be important for the financing of a child s education or a first home, relaxing binding credit constraints or responding to a transitory income shock. Financial transfers however, may extend economic disparities across generations if the wealthy transfer considerable resources to their children while middle class and poor households do not. In this paper, we first examine annual gifts of money from parents to adult children in the United States and ten Europe countries using the 2004 waves of the Health and Retirement Study (HRS) and Survey of Health, Ageing and Retirement in Europe (SHARE). Second, utilizing the long panel of the HRS, we study the long-run behavior of parental monetary giving to children across families and within a family. We found that in all countries, some parents gave money to children, many did not, the amount was low, about 500 Euros annually per child, and varied by parental socio-economic status and public social expenditures. In the short term parents in the U.S. gave money to a child to compensate for low earnings or satisfy an immediate need such as schooling. Over sixteen-years, parents gave an average of about 38,000 to all their children, five percent gave over 140,000 and gave persistently. With time, the amount of money children in the same family received became more equal and a child s level of education was one of the few remaining sources of differences in money given to children. Overall, the annual amount of money parents gave adult children in any country was not enough to affect the distribution of resources within or between families in the next generation although the timing of transfers for schooling or housing may have a significant impact on an individual child. Annual parental transfers for college age children in school in the U.S. were substantially higher than average transfers to all children. The effect of parental transfers for higher education on intergenerational mobility in the U.S. will depend in part upon whether this financing is essential in the schooling decision.
Keywords: Adult children; Cross-National; Demographics; Income; Retirement Planning and Satisfaction; SHARE

The Characteristics of Social Security Beneficiaries Who Claim Benefits at the Early Entitlement Age - Xiaoyan Li; Michael D Hurd; Loughran, David (AARP Public Policy Institute, 2008)
Keywords: Retirement Planning and Satisfaction; Social Security

Does the Rise in the Full Retirement Age Encourage Disability Benefits Applications? Evidence from the Health and Retirement Study - Xiaoyan Li; Nicole Maestas (Ann Arbor, University of Michigan, 2008)
As the Social Security full retirement age rises, the relative generosity of Social Security retirement benefits compared to disability benefits is declining, raising the incentive for insured people to apply for disability benefits. After controlling for other differences in observable characteristics, such as life-time earnings, we find that an average four month increase in the FRA slightly increases the two-year DI application rate by 0.04-0.30 percentage points. The effect is greater among those with a work limiting health problem (0.22-0.89 percentage points)
Keywords: Disabilities; Public Policy; Retirement Planning and Satisfaction; Social Security

The Effects of Retirement on Physical and Mental Health Outcomes - Dhaval, Dave; Rashad, Inas; Spasojevic, Jasmina (Southern Economic Journal, 2008)
While numerous studies have examined how health affects retirement, few have analyzed the impact in the reverse direction. Using the Health and Retirement Study (1992-2005), this paper estimates the effects of retirement on indicators of physical and mental health. To account for biases from unobserved selection and endogeneity, panel data methodologies are used, augmented by counterfactual and specification checks. Results indicate that complete retirement leads to a 5-14 increase in difficulties associated with mobility and daily activities, 4-6 increase in illnesses, and 6-9 decline in mental health (evaluated relative to the sample mean). The adverse health effects are mitigated if the individual is married, engages in physical activity, or continues to work part-time post-retirement. Evidence also suggests larger adverse health effects in the event of involuntary retirement. Retiring at a later age may lessen or postpone poor health outcomes for older adults, raise well-being, and reduce health care services utilization.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Family Care and Assisted Living: An Uncertain Future? - Douglas A. Wolf; Jenkins, Carol (The Assisted Living Residence: A Vision for the Future, 2008)
ProCite field 6 : In ProCite field 8 : eds
Keywords: Healthcare; Retirement Planning and Satisfaction

Health status and the labor force participation decisions of married couples - Lin, Peng (Health status and the labor force participation decisions of married couples, 2008)
This thesis examines the labor force participation decisions of married couples, and special attention is paid to a spouse's health conditions affecting their own and the spouse's labor force participation decision. I used the Health and Retirement Study survey data and estimated a seemingly unrelated bivariate probit model. A number of variables besides health condition were added: age, education level, and family unearned income. The results of this research paper support the findings from the relevant literature that the labor supply decisions of the husband and wife are related. The oldest age group is least likely to work. The younger the husband, the more likely it is that the husband will work. At the ages between 40 and 49, wives have the biggest probability to work. The higher the education level, the more likely it is that a spouse is going to work. The more total family unearned income, the less probable the spouse will go to work. Poor health has a negative effect on labor force participation and a positive effect for the spouse's labor force participation.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction; Women and Minorities

How Much Do State Economics and Other Characteristics Affect Retirement Behavior? - Alicia H. Munnell; Soto, Mauricio; Triest, Robert K.; Natalia A. Zhivan (Center for Retirement Research at Boston College Working Papers, 2008)
The labor force participation of men age 55-64 varies significantly among the various states of the Union. Little is known, however, about the reasons such variations exist. Using the Current Population Survey for the period 1977-2007, this paper demonstrates that the differences in the labor force participation of men age 55-64 are related to the labor market conditions, the nature of employment, and the employee characteristics in each state as well as a state pseudo replacement rate. These variables explain more than one-third of the total variation in labor force participation across states. Even controlling for state specific characteristics only cuts the explanatory power by half. To assess whether these relationships reflect different populations or unique aspects of the state economies, we turn to the Health and Retirement Study (HRS). We estimate equations for the probability of working and for the expected retirement for men in their late fifties and early sixties. We first estimate an equation predicting labor force participation using just the state-level variables taken from the CPS, then estimate an equation using both the CPS state-level variables and demographic and economic information for each individual taken from the HRS. The results show that while the state-level variables explain very little variation in an individual s probability of working or expected retirement age, most state-level variables have a statistically significant effect on such behavior both before and after the inclusion of the HRS information.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Involuntary Retirements: Prevalence, Causes, and Impacts - Lachance, Marie-Eve; Seligman, Jason S. (2008)
This paper examines the prevalence, causes, and impacts of involuntary retirement using data from the Health and Retirement Study (HRS), wherein 30 percent of retirees experience involuntary retirement. We find that factors motivating voluntary retirement (aging, pensions, Social Security, savings, and preferences) are much weaker determinants of involuntary retirement, whereas poor health and job loss are very significant determinants for this group. Our results indicate that involuntary retirees are at much greater risk of falling into poverty and account for the great majority of reports of retirement dissatisfaction. We suggest policymakers consider social insurance reform with the fundamental differences between voluntary and involuntary retirement in mind.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

A Micro-Level Analysis of Recent Increases in Labor Force Participation Among Older Workers - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Center for Retirement Research at Boston College Working Papers, 2008)
Aggregate data reveal a sizable increase in labor force participation rates since 2000 among American workers on the cusp of retirement, reverting back to levels for older men not seen since the 1970s. While these aggregate numbers are useful in that they document overall trends, they do not elucidate the reasons behind workers decisions. The Health and Retirement Study (HRS), a nationally-representative, longitudinal survey of older Americans that spans 1992 to 2004, provides micro-level data regarding these retirement trends. Moreover, the HRS contains detailed information about the types of jobs older Americans are taking (e.g., full-time versus part-time, self-employed versus wage-and-salary, low-paying versus high-paying, blue collar versus white collar). This study capitalizes on the richness of the HRS data and explores labor force determinants and outcomes of older Americans, with an emphasis on retirees' choices in recent years. We present a cross-sectional and longitudinal description of the financial, health, and employment situation of older Americans. We then explore retirement determinants using multinomial logistic regression to model gradual retirement and logistic and OLS regression to model the work-leisure (whether to work) and hours intensity (how much to work) decisions of older workers. Evidence suggests that the majority of older Americans retire gradually, in stages, and that younger retirees continue to respond to financial incentives just as their predecessors did. In addition, the retirement decisions of younger and middle-aged retirees appear similar in the face of macro-level changes in the early part of this decade.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Out-of-Pocket Medical Expenses and Retirement Security - Kathleen McGarry; Jonathan S Skinner (2008)
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Planning and Financial Literacy: How do women fare? - Annamaria Lusardi; Olivia S. Mitchell (NBER Working Paper, 2008)
Many older US households have done little or no planning for retirement, and there is a substantial population that seems to undersave for retirement. Of particular concern is the relative position of older women, who are more vulnerable to old-age poverty due to their longer longevity. This paper uses data from a special module we devised on planning and financial literacy in the 2004 Health and Retirement Study. It shows that women display much lower levels of financial literacy than the older population as a whole. In addition, women who are less financially literate are also less likely to plan for retirement and be successful planners. These findings have important implications for policy and for programs aimed at fostering financial security at older ages.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

Quit Your Job and Get Healthier? The Effect of Retirement on Health - Neuman, Kevin (Journal of Labor Research, 2008)
Although the health effect of retirement has important policy implications, few economists have researched the topic. This paper utilizes longitudinal data from the Health and Retirement Study and instruments retirement status using exogenous variation in public and private pensions. Subjective health change models indicate retirement preserves the health of both men and women, although insignificant results for objective health change models suggest the preservation may be more perceived than real. The same pattern of results is found using continuous measures of annual hours. At the very least, the results give strong evidence against the anecdotal idea that retirement harms health.
Keywords: Healthcare; Retirement Planning and Satisfaction

Retirement and Consumption in a Life Cycle Model - David M. Blau (Journal of Labor Economics, 2008)
Consumption expenditure declines sharply at the time of retirement for many households, but the majority maintain a smooth consumption path. A simple life cycle model with uncertainty about the time of retirement can account for this pattern. A richer version of the model is calibrated to data from the Health and Retirement Study (HRS). The median change in consumption expenditure at retirement generated by the model is zero, while the mean is negative, matching the HRS data. However, the magnitude of the drop in consumption among households that experience a decline is too small in the model compared to the data.
Keywords: Consumption and Savings; Event History/Life Cycle; Retirement Planning and Satisfaction

Retirement and the Demand for Health - Raquel Fonseca; Pierre-Carl Michaud; Galama, Titus; Arie Kapteyn (RAND, 2008)
This paper investigates the effect of allowing for endogeneous retirement in a life-cycle health production model with uncertainty. In particular, we study responses to changes in health insurance over the life-cycle and how retirement affects the price elasticity of the demand for health.
Keywords: Event History/Life Cycle; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Is Retirement Being Remade? Developments in Labor Market Patterns at Older Ages - Sewin Chan; Ann H. Stevens (Recalibrating Retirement Spending and Saving, 2008)
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

The Retirement Consumption Puzzle: Actual Spending Change in Panel Data - Michael D Hurd; Susann Rohwedder (NBER Working Paper, 2008)
The simple one-good model of life-cycle consumption requires that consumption be continuous over retirement; yet prior research based on partial measures of consumption or on synthetic panels indicates that spending drops at retirement, a result that has been called the retirement-consumption puzzle. Using panel data on total spending, nondurable spending and food spending, we find that spending declines at small rates over retirement, at rates that could be explained by mechanisms such as the cessation of work-related expenses, unexpected retirement due to a health shock or by the substitution of time for spending. In the low-wealth population where spending did decline at higher rates, the main explanation for the decline appears to be a high rate of early retirement due to poor health. We conclude that at the population level there is no retirement consumption puzzle in our data, and that in subpopulations where there were substantial declines, conventional economic theory can provide the main explanation.
Keywords: Event History/Life Cycle; Health Conditions and Status; Retirement Planning and Satisfaction

Retirement Transitions Among Married Couples - Angela L Curl; Aloen L. Townsend (Journal of Workplace Behavioral Health, 2008)
Retirement is often viewed as an event when someone completely withdraws from paid employment. The purpose of the present study was to examine the patterns of retirement transitions evidenced in married couples in the Health and Retirement Study over an 8-year period (1992 to 2000). The sample consisted of White and Black married couples (N = 1,118) where both spouses were working and at least one spouse was aged 51 to 61 at baseline. A variety of complex retirement patterns were found. Husbands were more likely than wives to show a linear pattern (i.e., a transition directly from work to complete retirement). Transitions were related within couples. Policy and practice implications are discussed.
Keywords: Adult children; Retirement Planning and Satisfaction

The Role of Retiree Health Insurance in the Employment Behavior of Older Men - David M. Blau; Gilleskie, Donna B. (International Economic Review, 2008)
We model the employment and medical care decisions of older men who face health risk. The budget constraint incorporates detailed characteristics of health insurance as well as Social Security and private pensions. A man whose health insurance is tied to continued employment with his current employer faces the risk of large medical expenditures in the event of an adverse health shock if he retires before becoming eligible for Medicare at age 65. A man whose employer provides retiree health insurance or who has access to other health insurance not tied to his employment decision (e.g., from his wife) can retire before age 65 without consequences for his health insurance coverage. We use data from the Health and Retirement Survey to estimate the parameters of the model using structural methods. Simulations based on the estimates imply that changes in health insurance, including access and restrictions to retiree health insurance and Medicare have a modest impact on employment behavior among older males.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

The Sacred Enterprise: Religion and attitudes toward work and retirement in the United States - Ebel, Donald J. (The Sacred Enterprise: Religion and attitudes toward work and retirement in the United States, 2008)
Weberian theory suggests that ascetic forms of Protestantism provided the ingredients required for the birth of capitalism in the West. This same theory links doctrinal and behavioral aspects of these religious groups to improved economic outcomes. In 1961, Gerhard Lenski tested these theories against individual attitudes, and a relationship was identified that supported Weber's theories. Since Lenski's study was conducted, dramatic religious and economic changes have unfolded in the United States that may indicate that a process of secularization has ensued. This study follows Lenski's example in testing Weber's theoretical construct using updated methods and data unavailable in 1961. Using data from Wave 1 (1992) of the Health and Retirement Study, this study tests the effect of religious affiliation upon economic attitudes as defined by the age of desired retirement and attitudes toward work. The sample is restricted to men active in the workforce in 1992. The multi-method design follows two stages. First, historical comparative analysis is used to identify trends and transitions in religion and the economy within the United States across the Twentieth Century. The second stage is comprised of two analyses--multi-level random coefficient analysis for the study of the effects of religion upon retirement attitudes, and logistic regression for the study of the effects of religion upon work attitudes. The qualitative and quantitative components of this study are used to inform one another, and to allow the statistical findings to be accurately placed within their historical context. The study finds that religion has little to no influence upon attitudes toward retirement. Findings in the analysis of religion and work indicate a weak relationship between religion and work attitudes that is mediated by the presence of other factors such as health status, age and the level of anticipated Social Security benefits. In both analyses, level of commitment indicates a suppressive effect. Ultimately, changes in the religious and economic experience of Americans, the social institution of retirement, and in population structures have led to a process of secularization which restricted religion's influence upon economic attitudes as of 1992 for working men in the United States.
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

What Effect Do Time Constraints Have on the Age of Retirement? - Friedberg, Leora; Wei Sun; Anthony Webb (Center for Retirement Research at Boston College Working Papers, 2008)
Work affects both the time available for non-market activities and the times at which those activities are performed and therefore work-induced constraints on time use may influence retirement decisions. We analyze these effects by combining new data from the American Time Use Survey with information on retirement in the Health and Retirement Study. We find that the propensity to engage in three types of non-work activities household production, leisure, and tertiary activities (eating, sleeping, grooming) are substantially altered by work. Moreover, the ways in which the timing of these activities are distorted differ across ten different job types (industry-occupation combinations) that we examine in the ATUS. We use the resulting measures of time distortions as control variables in multinomial logit retirement models that we estimate in the HRS. Older workers in jobs with greater distortions to the quantity and timing of leisure activities have an increased propensity to leave those jobs, either for new jobs or for retirement. On the other hand, workers in jobs with greater distortions to household production have a reduced propensity to leave their jobs, and distortions to tertiary activities raise the propensity to take new jobs but reduce the propensity to retire.
Keywords: Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

When Should Married Men Claim Social Security Benefits? - Sass, Steven A.; Wei Sun; Anthony Webb (Center for Retirement Research at Boston College Briefs, 2008)
Most married men claim Social Security benefits at age 62 or 63, well short of the age that maximizes the expected present value of the average household s benefits. That many married men leave money on the table is surprising. It is also problematic. It results in much lower benefits for surviving spouses and the low incomes of elderly widows are a major social problem. If married men delayed claiming Social Security benefits, retirement income security would significantly improve. This brief focuses on the potential gains from delayed claiming and the factors that may influence claiming behavior. It then considers possible policy responses.
Keywords: Adult children; Public Policy; Retirement Planning and Satisfaction; Social Security

Working longer: The solution to the retirement income challenge - Alicia H. Munnell; Sass, Steven A. (Brookings Institution Press, 2008)
Investigates the prospects for moving the average retirement age to 66 from 63. Examines companies' incentives to employ older workers and what government can do to promote continued participation in the workforce. Considers the challenge of ensuring a secure retirement for low-wage workers and those unable to continue to work --Provided by publisher.
Includes bibliographical references (p. 179-200) and index.
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Are 401(k) Saving Rates Changing? Cohort/Period Evidence from the Health and Retirement Study - Irena Dushi; Honig, Marjorie (Michigan Retirement and Disability Research Center Working Paper, 2007)
This research examines the determinants of eligibility and participation in 401(k) plans using two cross-sections of data from the Health and Retirement Study. Our sample consists of workers ages 51-56 representing two cohorts: the original HRS cohort born 1931-41, first interviewed in 1992, and the Early Baby Boomer (EBB) cohort born 1948-53, interviewed in 2004. Participation in 401(k) pensions in the EBB cohort is nearly 50 percent greater than that of the earlier cohort. This substantial growth in 401(k) plan participation over a relatively brief period may reflect intrinsic differences in tastes between the two cohorts, changes over this period in the external environment regarding retirement saving, or the joint effects of both influences.
Keywords: Pensions; Retirement Planning and Satisfaction

Burnout and the Retirement Decision - Nicole Maestas; Xiaoyan Li (Retirement Research Center, 2007)
We introduce the process of psychological burnout and recovery as an explanation for the phenomenon known as unretirement. We illustrate theoretically how predictable time variation in burnout could generate retirement and subsequent re-entry in a standard retirement model. We apply this model to the longitudinal Health and Retirement Study, presenting a novel measure of burnout, the Burnout EX3 Index. The index is correlated with different types of work stressors, and its time profile discriminates among different types of retirees. For example, prior to retirement, burnout rises steeply for future unretirees then falls rapidly after retirement; whereas burnout among future partial retirees is low and changes little over time. Using a series of econometric models derived from our theoretical model, we show that as burnout rises, retirement becomes more probable, and as burnout recedes following retirement, re-entry becomes more probable. While access to public and private pension benefits increases the likelihood of retirement for all retirees, pension accruals are least important for those who will later unretire, suggesting that unretirees are more willing to trade future gains in pension wealth for leisure than other retirees. Indeed, for this group, the effect of burnout dominates that of the net return to work.
Keywords: Employment and Labor Force; Healthcare; Retirement Planning and Satisfaction

Cross-Cohort Differences in Health on the Verge of Retirement - Beth J Soldo; Olivia S. Mitchell; Tfaily, Rania; John McCabe (Redefining Retirement: How Will Boomers Fare?, 2007)
Baby Boomers have left a unique imprint on US culture and society in the last 60 years, and it might be anticipated that they will also put their own stamp on retirement, the last phase of the life cycle. Yet because Boomers have not all fully retired, we cannot yet judge how they will fare as retirees. Instead, we focus on how this group compares with prior groups on the verge of retirement, that is, at ages 51-56. Accordingly, this chapter evaluates the stock of health which Early Boomers bring to retirement and compare these to the circumstances of two prior cohorts at the same point in their life cycles. Using three sets of responses from the Health and Retirement Study, we find some interesting patterns. Overall, the raw evidence indicates that Boomers on the verge of retirement are in poorer health their counterparts 12 years ago. Using a summary health index designed for this study, we find that those born 1948 to 1953 share health risks with the War Baby cohort. This suggests that most of the health decline instead began before the late 1940's. A more complex set of health conclusions emerges from the specific self-reported health measures. Boomers indicate they have relatively more difficulty with a range of everyday physical tasks, but they also report having more pain, more chronic conditions, more drinking and psychiatric problems, than their HRS earlier counterparts. This trend portends poorly for the future health of Boomers as they age and incur increasing costs associated with health care and medications. Using our health index, only those at the 75th percentile or higher are likely to be characterized as having good or better health.
ProCite field 6 : In ProCite field 8 : eds
Keywords: Health Conditions and Status; Other; Retirement Planning and Satisfaction

Dear Graduate, Please Keep The Change - Darlin, Damon (New York Times, 2007)
There may be another compelling reason to save and that is that while many aspects of retirement savings are predictable, the big unknowable is health care costs. ''If you believe in the logic of the life cycle model, then once you get used to peanut butter, all else follows,'' said Jonathan Skinner, a economics professor at Dartmouth College who has studied retirement issues and recently wrote a paper titled ''Are You Sure You're Saving Enough for Retirement?'' for the National Bureau of Economic Research. ''That's the assumption that I am questioning: Do people want to be stuck in peanut butter in retirement?'' [Skinner is referencing projections of increased out-of-pocket medical expenses that are based on Health and Retirement Study data.]
Keywords: Consumption and Savings; Event History/Life Cycle; Retirement Planning and Satisfaction

Do the Sick Retire Early? Chronic illness, asset accumulation and early retirement - Miah, M. Solaiman; Wilcox-Gök, Virginia (Applied Economics, 2007)
Our objective is to determine how chronic illness affects asset accumulation and retirement. Previous studies have found that poor health leads to early retirement, but those studies failed to look at the indirect impact of chronic illness on retirement. Using data from the Health and Retirement Study, we define an illness as chronic if the individual reports having asthma, cancer, heart disease, stroke or diabetes for four or more years. We first estimate how a chronic illness influences asset accumulation. We then estimate how asset accumulation and current poor health influence retirement. We observe that the vast majority of the chronically ill population do not report their general health to be poor nor do they report functional limitations in activities of daily living. Nevertheless, our results indicate that chronic illness leads these people to accumulate fewer assets during their working years and consequently retire later. Neither researchers nor policymakers discussing the many critical issues surrounding illness and retirement have addressed this issue.
Keywords: Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

The Effect of Retirement Incentives on Retirement Behavior: Evidence from the Self-Employed in the United States and England - Julie M Zissimopoulos; Nicole Maestas; Lynn A Karoly (Michigan Retirement Research Center Working Paper, 2007)
In this paper, we examine how public and private pension and health insurance systems affect the retirement transitions. In many countries, public and private pension eligibility, as well as access to health insurance varies between self-employed and wage and salary workers, and these differences are likely to cause differential retirement patterns both within and across countries. We use the variation in these institutional features within and across the United States and England to analyze retirement patterns. Based on longitudinal data from the Health and Retirement Study (HRS) in the United States and the English Longitudinal Survey of Ageing (ELSA) we find that the higher labor force exit rate of wage and salary workers compared to self-employed workers is due to defined benefit pension incentives created by the public and private pension systems. Higher rates of labor force exit at ages 55 and older in England compared to the United States are due in part to the availability of publicly provided health insurance.
Keywords: Cross-National; Medicare/Medicaid/Health Insurance; Pensions; Retirement Planning and Satisfaction

Effect of Retirement on Eating Out and Weight Change: An Analysis of Gender Differences - Chung, Sukyung; Barry M Popkin; Marisa E Domino; Sally C. Stearns (Obesity, 2007)
OBJECTIVES: The objectives were to understand how the retirement decisions of older Americans influence household food consumption patterns by gender and, in turn, to examine the impact of the change in food consumption on weight. RESEARCH METHODS AND PROCEDURES: This study used five waves of the Health and Retirement Study (1992 to 2002; n=28,117). Participants were 50 to 71 years old during the study period. We used longitudinal regression analyses controlling for health events, spousal factors, socioeconomic factors, and individual fixed effects over time. RESULTS: Retirement of the individual and of his/her spouse reduced the individual's monthly spending on eating out by 10 and 7 on average, respectively, but did not change household spending on food at home. The wife's, but not the husband's, retirement decreased the spouse's spending on eating out by 13/mo. Spending on eating out was a significant but weak (0.003BMI/ ) predictor of weight gain. DISCUSSION: The decrease in spending on eating out after retirement, particularly women's, suggests that people eat out less when they have more time for food preparation at home. However, increases in other risks of weight gain with retirement, such as physical inactivity, could counteract the effects of eating out less.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Effects of Retirement on Health among Men and Women in the Health and Retirement Study - Fondow, Meghan Dee Miller (Effects of Retirement on Health among Men and Women in the Health and Retirement Study, 2007)
The myth of retirement and health states that health declines following retirement. Previous studies examining the veracity of this myth offer contradictory findings and varied methodologies. Several studies have found support for the myth, but others have found that health may actually improve in retirement. Also, it has been suggested that retirement may affect health of men and women in different ways. The purpose of the current study was to clarify and extend previous findings regarding the relationship between retirement and health among men and women using data from the Health and Retirement Study. The study was conducted in two phases. For the first phase, cross-sectional data were analyzed with working and retired participants matched on age, sex, race, and education. In the second phase, a longitudinal matched sample was utilized that included working participants, half of whom had retired by four year follow up. Sex, marital status, and income were examined as potential moderators. Results indicated that retired participants in both samples reported more functional health impairment and more symptoms of depression. However, the effect appeared to be evident primarily among people who had been forced to retire. There was no difference between voluntary retirees and working participants on functional health impairment, and voluntary retirees actually reported fewer symptoms of depression than working participants. Overall, this study provides support for the myth of retirement and health, but only among people forced to retire.
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Future Social Security Entitlements and the Retirement Decision - Courtney Coile; Gruber, Jonathan (Review of Economics and Statistics, 2007)
A critical question for Social Security policy is how program incentives affect retirement behavior. We use the Health and Retirement Survey (HRS) to examine the impact of Social Security incentives on male retirement. We implement forward-looking models whereby individuals consider the incentives to work in all future years. We find that forwardlooking incentive measures for Social Security are significant determinants of retirement. We also find that private pension incentives have roughly similar effects. Our findings suggest that Social Security policies that increase the incentives to work at older ages can significantly reduce the labor force exit rate of older workers.
Keywords: Employment and Labor Force; Methodology; Public Policy; Retirement Planning and Satisfaction; Social Security

A Gradual Exit May Not Make for a Happier Retirement - Calvo, Esteban; Haverstick, Kelly; Sass, Steven A. (Center for Retirement Research at Boston College Briefs, 2007)
Workers often say they want to retire gradually. As retirement is a sharp break with life as they know it, it’s not surprising that many prefer to negotiate the transition a step at a time. Many policymakers also view gradual retirement favorably. They see it as a way to extend careers, shorten retirements, and thereby improve retirement income security. Expanding opportunities for gradual or “phased” retirement has thus gained a prominent place on the policy agenda. Workers who say they want to retire gradually, however, are clearly not basing their preference on personal experience. These workers have not retired both ways, concluding that retiring in stages is better. To shed light on this issue, this brief summarizes a new study comparing individuals who retired gradually with those who retired “cold turkey” and asks which are happier in retirement. The study uses happiness as the yardstick because it measures realized quality of life; other criteria — such as income, wealth, social status, or health — measure potential quality of life. Greater happiness in retirement is also what workers seem to expect if they exit the labor force gradually…
Keywords: Retirement Planning and Satisfaction

Growing Older in America: The Health and Retirement Study (US Department of Health and Human Services, 2007)
Growing Older in America: The Health and Retirement Study describes the breadth and depth of the HRS to help familiarize a broad range of researchers; policymakers; media; and organizations concerned with health, economics, and aging with this data resource. Published in 2007, this colorful data book describes the HRS's development and features and offers a snapshot of research findings based on analyses of the Study's data. Sections of the report look at older adults health, work and retirement, income and wealth, and family characteristics and intergenerational transfers. More than 65 figures and tables illustrate the text.
Keywords: Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Health Insurance Patterns Nearing Retirement - Helen G Levy (Redefining Retirement: How Will Boomers Fare?, 2007)
ProCite field 6 : In ProCite field 8 : eds
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Hours Flexibility and Retirement - Kerwin K. Charles; Decicca, Philip (Economic Inquiry, 2007)
Data from the Health and Retirement Study indicate that hours constraints are a common feature of jobs held by workers nearing retirement. We present a simple model that predicts that workers who are not free to lower their usual hours of work should be more likely than their unconstrained counterparts to retire by some future date. Our estimates, which are robust to various specifications, support this prediction. The amount by which being hours constrained is estimated to raise retirement probabilities is nearly as large as the effect of being in relatively poor health, suggesting an economically significant effect.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Housing Wealth and Retirement Timing - Martin P. Farnham; Purvi Sevak (The University of Michigan, Michigan Retirement Research Center, 2007)
We use data from the Health and Retirement Study (HRS) and the Office of Housing Enterprise Oversight to measure the effect of changes in housing wealth on retirement timing. Using cross-MSA variation in house-price movements to identify wealth effects on retirement timing, we find evidence that such wealth effects are present. According to some specifications the rate of transition into retirement increases in the presence of positive housing wealth shocks. In addition, we use data on expected age of retirement to measure the impact of housing wealth shocks on expectations about retirement timing. Using renters as a control for heterogeneity in local amenities and using individual fixed effects to control for unobserved individual heterogeneity, we find that a 10 increase in housing wealth is associated with a reduction in expected retirement age of between 3.5 and 5 months.
Keywords: Housing; Retirement Planning and Satisfaction

The Impact of Retirement on Trajectories of Physical Health of Married Couples - Angela L Curl (Applied Social Sciences, 2007)
Retirement's impact on health in married couples is important due to increasing life expectancy and the retirement of Baby Boomers. There is mixed evidence about retirement's effects, if any, on physical health. In addition, there is a lack of research that examines the effect of one spouse's retirement on the other spouse's health. Secondary analysis was conducted using longitudinal data from the Health and Retirement Study (HRS), which was designed to obtain information about health and economic status from pre- to post-retirement. The sample consisted of 1,666 non-Hispanic married couples (176 Black couples and 1490 White couples) where both spouses participated in HRS from 1992 to 2000 and at least one spouse was age 51-61 at baseline. Political economy, social stratification, and interdependence theories provided the conceptual framework. Multilevel modeling was used to analyze spouses' short-term and long-term changes in health after retirement. Health was measured using four separate indicators (number of disease diagnoses, lower body difficulties, self-rated health, mortality). Retirement was operationalized two ways: self-defined retirement and labor force status (working, retirement, unemployed, disabled). Other predictors were demographics, health-related control variables and household characteristics. Husbands experienced an increase in their number of disease diagnoses and their risk of having at least one lower body difficulty (e.g., difficulty walking up a flight of stairs) during the first wave of their retirement, but fewer disease diagnoses long-term (i.e., up to 8 years post-retirement), compared to non-retired husbands. Wives experienced worse self-rated health during the first wave of their own retirement. Wives' retirement had a short-term positive impact on the self-rated health of husbands, but husbands' retirement did not affect wives' health. The health of certain individuals was more negatively affected by retirement than others due to their social stratification characteristics (race, education, income, wealth, age). Health disadvantage was predicted by both higher and lower social status (depending on gender, health outcome, retirement measure, and length of time since retirement). Findings of this study are important for social workers helping married couples through retirement transitions, for furthering empirical knowledge and research methodology, and for their implications for social justice and policy reform. Indexing (document details)
Keywords: Adult children; Health Conditions and Status; Retirement Planning and Satisfaction

Life-Cycle Models: Lifetime Earnings and the Timing of Retirement - John Laitner; Daniel S. Silverman (Michigan Retirement and Disability Research Center Publication, 2007)
After dropping for a century, the average retirement age for U.S. males seems to have leveled off in recent decades. An important question is whether as future improvements in technology cause wages to rise, desired retirement ages will resume their downward trend, or not. This paper attempts to use HRS panel data to test how relatively high (or low) earnings affect male retirement ages. Our goal is to use cross sectional earning differences to help anticipate likely time series developments in coming decades. Our preliminary regression results show that higher earnings do lead to somewhat earlier retirement. Unless additional analysis changes the parameter estimates, the implication is that the downward trend in male retirement ages will ultimately return.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Preparing for the Future: Latinos' Financial Literacy and Retirement Planning - Wei Sun; Gia Barboza; Karen Richman (The Business Journal of Hispanic Research, 2007)
Over the past three decades, the burden of responsibility for retirement savings has shifted from employer to employee. Saving for retirement has changed from an insured, employer-provided benefit to an uninsured employee-provided deduction from a paycheck. When retirement planning and investment decision-making is largely relegated to individuals, financial literacy is essential. Financial illiteracy, however, is widespread throughout the population and is of particular concern for Latinos. Closing the gap between what American workers generally and Latino workers, in particular, need to know to prepare for retirement and their current level ofp reparation is an urgent need. This paper disaggregates ethnic differences between Latinos, both foreign and US born, and non-Latino Blacks and Whites in the analysis of core and supplemental data from the 2004 Health and Retirement Study (HRS). While other analyses of data from the survey deal with aggregates, this study explains how individual characteristics among ethnic groups affect financial literacy.
Keywords: Financial literacy; Older Adults; Retirement Planning and Satisfaction; Women and Minorities

Projecting Behavioral Responses to the Next Generation of Retirement Policies - Alan L Gustman; Thomas L. Steinmeier (Michigan Retirement and Disability Research Center Publication, 2007)
This paper examines retirement and related behavioral responses to policies that on average are actuarially neutral. Many conventional models predict that actuarially neutral policies will not affect retirement behavior. In contrast, our model allows those with high time preference rates to find that the promise of an actuarially fair increase in future rewards does not balance the loss from foregone current benefits. Using data from the Health and Retirement Study, we find that from age 62 through full retirement age, the earnings test reduces full-time work by married men by about four percentage points, or by about ten percent of married men at full-time work. Abolishing the requirements on many jobs that an individual work full-time or not at all, what we term a minimum hours constraint on employment, would induce more than twice as many people to enter partial retirement as would leave full-time work, so that total full-time equivalent (FTE) employment would increase, although by a modest amount. If all benefits from personal accounts could be taken as a lump sum, the fraction not retired at age 62 would fall by about 5 percentage points compared to a system where there is mandatory annuitization of benefits.
Keywords: Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Decisions: Federal Policies Offer Mixed Signals about When to Retire - United States Governmental Office (Washington, DC, U.S. Government Accountability Office, 2007)
Question: We need to understand the (interacting and sometimes contradictory) incentives in Social Security, Medicare, and pension laws and how workers respond to them in order to address the demographic challenges facing the nation. Finding: Using the NIA-funded Health and Retirement Study, GAO found that Federal policies offer mixed incentives. The availability of social security at age 62 provides an incentive to retire early, while the increase in the full retirement age and elimination of the earnings test encourages continued work. Medicare provides a strong incentive for those without health insurance to stay working until age 65 but this also is an encouragement to retire earlier than the full retirement age. Tax policy also encourages earlier retirement. In addition, workers retirement depends strongly on retiree health insurance and pension plan availability. Recommendation: Consider changes to law, programs, and policies that support retirement security and provide incentives to encourage work at older ages.
Keywords: Medicare/Medicaid/Health Insurance; Pensions; Public Policy; Retirement Planning and Satisfaction

The Social Security Earnings Test and Work Incentives - Hugo Benítez-Silva; Frank Heiland (Journal of Policy Analysis and Management, 2007)
The labor supply and benefit claiming incentives provided by the early retirement rules of the Social Security Old Age benefits program are of growing importance as the Normal Retirement Age (NRA) increases to 67, the labor force participation of Older Americans rises, and a variety of reforms to the Social Security system are considered. Any reform needs to take into account the effects and rationale of the Social Security Earnings Test and the Actuarial Adjustment Factor, which are likely to be widely misunderstood due to the relatively little attention paid by policymakers and researchers to the fact that Americans are willing to work while receiving benefits. We describe these incentives and emphasize that individuals who claim benefits before the NRA but continue to work, or return to the labor force, can reduce the early retirement penalty by suspending the collection of monthly benefits if they earn above the Earnings Test limit. We then argue that the Earnings Test can be distortionary and is costly to administer, and that these characteristics are inflated by the lack of information given to Older Americans regarding the consequences of working while receiving retirement benefits. We present results from statistical models of labor force exit behavior using data from the Health and Retirement Study showing the relevance of these incentives, and investigate the importance of informational asymmetries among beneficiaries regarding benefit withholding using a dynamic life-cycle model of labor supply and benefit claiming. We then use the latter framework to compare the behavioral and welfare implications of a removal of the Earnings Test to the policy of providing more information regarding the Earnings Test and the adjustment of the rate of benefit pay to Older Americans. 2007 by the Association for Public Policy Analysis and Management.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security

Some Chronically Ill Adults Wait for Medicare to Arrive - Gina Kolata (New York Times, 2007)
"When uninsured adults with common chronic illnesses became eligible for Medicare, they saw doctors and were hospitalized more often and reported greater medical expenses than people who had had insurance." This article references results of a reseach study led by Dr. John Z. Ananian, published in the New England Journal of Medicine, that used data from the Health and Retirement Study. "Dr. Ayanian and his colleagues focused on 5,158 [of 9,760 adults aged 51 to 61 in 1992] ... who survived to age 65 by 2004 and who either had private insurance or no insurance at all before receiving Medicare."
Keywords: Health Conditions and Status; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Subjective Survival Probabilities in the Health and Retirement Study: Systematic Biases and Predictive Validity - Todd E. Elder (Michigan Retirement Research Center Research Paper, 2007)
Recent research has demonstrated that retirement planning and well-being are closely tied to probabilistic forecasts about future events. Using longitudinal data from the Health and Retirement Study, I show that individuals subjective survival forecasts exhibit systematic biases relative to life table data. In particular, many respondents fail to account for increases in yearly mortality rates with age, both longitudinally and in crosssection. Additionally, successive cohorts of the near elderly do not appear to revise survival forecasts to match increases in longevity. Forecasting bias may merely be due to the framing of questions designed to elicit expectations, but real biases may result in suboptimal savings rates and timing of retirement. Cross-sectional variation in subjective survival forecasts also appears to reflect differences in cognitive ability across respondents, suggesting that subjective information is more relevant for some individuals than others. Despite these shortcomings, subjective mortality probabilities predict actual mortality and portfolio choice, and they contain information not found in selfreported health status or objective measures of health limitations.
Keywords: Expectations; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Three Essays in Public Economics - Kim, Matthew (Three Essays in Public Economics, 2007)
This dissertation consists of three essays in public economics. The first essay is theoretical and examines higher education. The second and third essays are empirical and examine charitable behavior and tax subsidies. The first essay presents a stylized theoretical model of competition among need-blind colleges and universities that implement early decision admissions. Under need-blind admissions, an applicant's financial aid status cannot affect their likelihood of admission. In the model, a need-blind school can use early decision admissions as a screening mechanism to indirectly identify a student's ability-to-pay, while superficially maintaining a need-blind policy. As a result, in equilibrium, non-financial aid students are more likely to be admitted than financial aid students of comparable quality. The second essay examines the relationship between charitable giving and religious attendance. Using data from the Independent Sector Survey of Giving and Volunteering, I estimate a tax price elasticity for religious attendance of 0.4, which implies that charitable giving and religious attendance are complements. I resolve the difference between my estimate and a recent estimate by Gruber (2004) that implies that charitable giving and religious attendance are substitutes. While Gruber imputes itemization status, an important factor in calculating tax incentives, I use survey-reported itemization status. This imputation creates a large amount of non-classical measurement error. I show that the measurement error is responsible for the disparate results: if I also impute itemization status, I obtain similar results as Gruber. The third essay presents new results regarding the charitable behavior of retired and nearly-retired individuals. I estimate a simultaneous equation model of charitable giving, volunteering, and labor supply derived from a quadratic utility function. By explicitly modeling these joint decisions, I account for potential substitutability and complementarity among the choice variables. I estimate the model by maximum likelihood using a sample of single individuals from the Health and Retirement Study. The parameter estimates imply price and income elasticities that are similar to, though somewhat smaller than, previous estimates. The parameter estimates are also used to simulate the effects of various policy changes to the Social Security system.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

What Happens to Health Benefits After Retirement? - Richard W. Johnson (Boston College, Center for Retirement Research at Boston College, 2007)
Because most workers receive health benefits from their employers, retirement often disrupts health insurance coverage. Some employers offer health insurance to retirees, but many firms are cutting retiree health benefits by passing more costs to retirees or eliminating benefits altogether. Few alternatives exist. Private nongroup coverage is generally quite expensive, and few people in their 50s and early 60s qualify for publicly financed benefits. Many workers who cannot obtain retiree benefits from their own employers or their spouses employers delay retirement to age 65, when Medicare coverage begins. This brief examines the availability and cost of health insurance coverage at ages 55 to 64 and changes in coverage after retirement. Today most workers with employer health benefits retain their coverage when they retire early, although their required premium contributions have increased sharply over the past ten years. In the future, however, steady declines in the share of younger workers with access to retiree health benefits may jeopardize income security for the next generations of retirees.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

What Makes Retirees Happier: A Gradual or 'Cold Turkey' Retirement? - Calvo, Esteban; Haverstick, Kelly; Sass, Steven A. (Chestnut Hill, MA, Center for Retirement Research at Boston College, 2007)
This study explores the factors that affect an individual s happiness while transitioning into retirement. Recent studies highlight gradual retirement as an attractive option to older workers as they approach full retirement. However, it is not clear whether phasing or cold turkey makes for a happier retirement. Using longitudinal data from the Health and Retirement Study, this study explores what shapes the change in happiness between the last wave of full employment and the first wave of full retirement. Results suggest that what really matters is not the type of transition (gradual retirement or cold turkey), but whether people perceive the transition as chosen or forced.
Keywords: Retirement Planning and Satisfaction

Why Do Boomers Plan to Work Longer? - Mermin, Gordon B.T.; Richard W. Johnson; Daniel P. Murphy (The Journals of Gerongology, Series B: Psychological Sciences and Social Sciences, 2007)
OBJECTIVE: Recent changes in retirement trends and patterns have raised questions about the likely retirement behavior of baby boomers, the large cohort born between 1946 and 1964. This study examined recent changes in retirement expectations and the factors that drove them. METHODS: Using data from the Health and Retirement Study, the analysis compared self-reported probabilities of working full time past ages 62 and 65 among workers aged 51 to 56 in 1992 and 2004. The study modeled retirement expectations for both generations and used the estimated regression coefficients to identify the forces that accounted for generational differences. RESULTS: Between 1992 and 2004, the mean self-reported probability of working full time past age 65 among workers aged 51 to 56 increased from 27 to 33 . Lower rates of retiree health insurance offers from employers, higher levels of educational attainment, and lower rates of defined benefit pension coverage accounted for most of the growth. DISCUSSION: Given the continued erosion in employer-sponsored retiree health benefits and defined benefit pension plans, boomers will likely remain at work longer than members of the previous generation. Lengthier careers will likely promote economic growth, increase government revenue, and improve individual financial security at older ages.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Ageing and Well-Being: Consumption and Time Use of Elderly Americans - Gortz, Mette (Ageing and Well-Being: Consumption and Time Use of Elderly Americans, 2006)
This paper studies patterns of consumption, household production and leisure for the elderly American population. The main objective of the paper is to study how incorporating the value of time spent in household production and leisure affects economic well-being. Based on the 2003 Consumption and Mail Activities Survey (CAMS) from the Health and Retirement Study (HRS), we find that the level of expenditure is lower for non-retired people, while levels of housework and leisure are higher. We also see that expenditure are decreasing with age, while leisure is increasing with age for both groups. Inequality in expenditure is higher for the group of retired households as compared to the group of non-retired households. However, while the elderly and retired seem to be less well off in terms of consumption goods bought in the market, they are generally "richer" in terms of time for household production or leisure. Broadening our concept of economic well-being to include first the value of household production and secondly the value of leisure reduces our measure of economic inequality among the elderly.
Keywords: Consumption and Savings; Demographics; Net Worth and Assets; Retirement Planning and Satisfaction

Baby Boom Generation: Retirement of Baby Boomers is Unlikely to Precipitate Dramatic Decline in Market Returns, but Broader Risks Threaten Retirement Security - United States Governmental Office (U.S. Government Accountability Office, 2006)
The first wave of baby boomers(born between 1946 and 1964) will become eligible for Social Security early retirement benefits in 2008. In addition to concerns about how the boomers' retirement will strain the nation's retirement and health systems, concerns also have been raised about the possibility for boomers to sell off large amounts of financial assets in retirement, with relatively fewer younger U.S. workers available to purchase these assets. Some have suggested that such a sell-off could precipitate a market "meltdown," a sharp and sudden decline in asset prices, or reduce long-term rates of return. In view of such concerns, we have examined (1) whether the retirement of the baby boomers is likely to precipitate a dramatic drop in financial asset prices; (2) what researchers and financial industry participants expect the effect of the boomer retirement to have on financial markets; and (3) what role rates of return will play in providing retirement income in the future. We have prepared this report under the Comptroller General's authority to conduct evaluations on his own initiative as part of the continued effort to assist Congress in addressing these issues. Our analysis of national survey and other data suggests that retiring boomers are not likely to sell financial assets in such a way as to cause a sharp and sudden decline in financial asset prices. A large majority of boomers have few financial assets to sell. The small minority who own most assets held by this generation will likely need to sell few assets in retirement. Also, most current retirees spend down their assets slowly, with many continuing to accumulate assets. If boomers behave the same way, a rapid and large sell off of financial assets appears unlikely. Other factors that may reduce the odds of a sharp and sudden drop in asset prices include the increase in life expectancy that will spread asset sales over a longer period and the expectation of many boomers to work past traditional retirement ages. A wide range of academic studies have predicted that the boomers' retirement will have a small negative effect, if any, on rates of return on assets. Similarly, financial industry representatives did not expect the boomers' retirement to have a big impact on the financial markets, in part because of the globalization of the markets. Our statistical analysis shows that macroeconomic and financial factors, such as dividends and industrial production, explained much more of the variation in stock returns from 1948 to 2004 than did shifts in the U.S. population's age structure, suggesting that demographics may have a small effect on stock returns relative to the broader economy. While the boomers' retirement is not likely to cause a sharp and sudden decline in asset prices, the retirement security of boomers and others will likely depend more on individual savings and returns on such savings. This is due, in part, to the decline in traditional pensions that provide guaranteed retirement income and the rise in account-based defined contribution plans. Also, fiscal uncertainties surrounding Social Security and rising health care costs will ultimately place more personal responsibility for retirement saving on individuals. Given the need for individuals to save and manage their savings, financial literacy will play an important role in helping boomers and future generations achieve a secure retirement.
Keywords: Demographics; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Diverse Pathways in Retirement Transitions: Influences of Family, Work, Wealth, and Health - Peters, Cheryl L. (Diverse Pathways in Retirement Transitions: Influences of Family, Work, Wealth, and Health, 2006)
Shaped by life course and feminist perspectives, this study investigated the influence of finances, human capital, health, family situations, and work factors on two different retirement transitions among married and partnered men and women. Because women and men arrive at retirement under different life circumstances, logistic regression analyses were conducted separately by gender. Respondents were drawn from Waves 1–4 of the biennial, longitudinal Health and Retirement Survey (HRS) and included individuals who retired between Waves 1 and 2 (1992–1994), Waves 2 and 3 (1994–1996), and Waves 3 and 4 (1996–1998). Retirees (n = 1,275) transitioned from the labor force at Time 1 to either a partial or complete retirement at Time 2. Results indicated that, relative to partially retired men, completely retired men had higher earnings at their job, worked for larger companies, were more likely labor union members, were covered in pension plans, started pension incomes at Time 2, had health insurance that continued in retirement, likely covered partners in their health plan, were older, were in poorer health, and had provided 400+ hours of care to a grandchild in the last year. Relative to completely retired men, partially retired men had more wealth, were more likely receiving health insurance coverage from their partners' health plan, had partners who were working for pay at Time 2, had fewer years at their last job, retired earlier than planned, and perceived their last jobs as important. Relative to partially retired women, completely retired women were more likely covered in pension plans, had health insurance that continued in retirement, were more likely labor union members, were White, were older, were in poorer health, and had grandchildren in the home at the time of retirement. Relative to completely retired women, partially retired women had partners who were working for pay at Time 2, retired earlier than planned, and were providing financial support to another individual. Results suggest that partial retirement is a possible solution for workers trying to negotiate a labor force exit while keeping financial and health benefits. Implications and future directions were explored.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction; Women and Minorities

A Dynamic Model of Retirement and Social Security Reform Expectations: A Solution to the New Early Retirement Puzzle - Hugo Benítez-Silva; Debra S. Dwyer; Sanderson, Warren C. (Michigan Retirement Research Center Research Paper, 2006)
The need for Social Security Reform in the next years is hardly a matter of debate. Therefore, the widespread believe among Americans that Social Security will not be able to pay benefits in the long run at the level that was anticipated, does not come as a surprise. The government acknowledges the situation, and predicts that substantial benefits cuts will be necessary, yet no legislation has been passed to tackle the problem. Researchers, however, have rarely modeled the uncertainty over Social Security reform and benefit levels, and how they affect claiming behavior and retirement. The purpose of this paper is to assess the extent to which these perceptions of future cuts might explain the puzzle of earlier take-up despite bigger penalties to doing so in the presence of increasing longevity. By introducing a small amount of uncertainty (based on self-reported responses to questions regarding expectations over future cuts) of a relatively small cut (compared with what the government reports as necessary to solve the crisis) in a dynamic life-cycle model of retirement, we are able to match the claiming behavior observed in the data, without relying on heterogeneous preferences. Our results support the hypothesis that expectations over future benefits are affecting current behavior. We find that a mis-specified dynamic retirement model would erroneously predict that an increase in the NRA would delay claiming behavior and increase labor supply at older ages. Once the appropriate earnings test incentives are modeled, and we account for the probability of reforms to the system, an increase in the NRA has little effect on claiming behavior, and it can even increase the proportion of individuals claiming before the NRA.
Keywords: Expectations; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction; Social Security

The Effect of Subjective Survival Probabilities on Retirement and Wealth in the United States - David E Bloom; Canning, David; Moore, Michael; Song, Younghwan (NBER Working Paper, 2006)
We explore the proposition that expected longevity affects retirement decisions and accumulated wealth using micro data drawn from the Health and Retirement Study for the United States. We use data on a person's subjective probability of survival to age 75 as a proxy for their prospective lifespan. In order to control for the presence of measurement error and focal points in responses, as well as reverse causality, we instrument subjective survival probabilities using information on current age, or age at death, of the respondent's parents. Our estimates indicate that increased subjective probabilities of survival result in increased household wealth among couples, with no effect on the length of the working life. These findings are consistent with the view that retirement decisions are driven by institutional constraints and incentives and that a longer expected lifespan leads to increased wealth accumulation.
Keywords: Expectations; Net Worth and Assets; Retirement Planning and Satisfaction

The Effects of Defined Contribution Plans on the Retirement Decision - Hong, Wonku (Risk Management and Insurance, 2006)
This study examines the effects of pensions on the retirement decision, focusing on the differences between defined benefit (DB) plans and defined contribution (DC) plans. I find that DC plans have different effects on the accumulation of retirement wealth, the incentives for retirement and the risk of retirement benefits than DB plans. Thereby, DC plans have different effects from DB plans on the decision to retire. This paper is the first empirical study to investigate the effect of longevity risk in pension plans on retirement. It is an important addition to the literature on retirement behavior since longevity risk will become more important as individuals have longer life expectancies and bear more longevity risk due to increasing likelihood of coverage by DC plans or Social Security personal accounts. Previous research has found that DB plans have an age-incentive effect on retirement. That is, the structure of DB plans may induce individuals to retire at a specific age. By contrast, the structure of DC plans does not have age-incentive effects. Thereby, individuals with DC plans may retire either earlier or later on average than individuals with DB plans because of the absence of age-related incentives in DC plans. To shed further light on these issues, this study introduces risk factors, and particularly longevity risk, to an option value model of the retirement decision. Longevity risk is important to DC participants since DC plans usually offer a lump-sum benefit at retirement. Since payouts are not guaranteed over life expectancy, retirees with DC plans bear a greater risk of outliving their resources, i.e., longevity risk. The additional risks in DC plans may make workers save more, and retire later. This paper extends a standard intertemporal model of consumption and retirement by incorporating risk factors for different pension types into the retirement decision problem. Comparative statics from the optimal solution show that increases in risk factors (i.e. longevity risk) during retirement induce workers with DC plans to retire later than workers with defined benefit (DB) plans. This study then tests the predictions of this model empirically, using the data from the Health and Retirement Study (HRS). Empirical results confirm the predictions of the theoretical model. First, workers with DC plans expect to retire later than workers with DB plans. Next, increase in pension option value, measured as the difference between the maximum pension value and the pension value of 1992, decreases the probability of retirement, thereby increasing the expected retirement wage. By contrast, greater pension wealth increases the probability of retirement, reducing the expected retirement age. Considering that pension wealth in DC plans is about half of pension wealth in DB plans, it is reasonable to conclude that workers with DC plans retire later than workers with DB plans. Finally, longevity risk, as measured by the Annuity Equivalent Wealth (AEW), decreases probability of retirement, increasing the expected retirement age.
Keywords: Pensions; Retirement Planning and Satisfaction

Financial Literacy and Retirement Preparedness: Evidence and Implications for Financial Education Programs - Annamaria Lusardi; Olivia S. Mitchell (Michigan Retirement Research Center Publication, 2006)
Economists are beginning to investigate the causes and consequences of financial illiteracy to better understand why retirement planning is lacking and why so many households arrive close to retirement with little or no wealth. Our review reveals that many households are unfamiliar with even the most basic economic concepts needed to make saving and investment decisions. Such financial illiteracy is widespread: the young and older people in the United States and other countries appear woefully under-informed about basic financial computations, with serious implications for saving, retirement planning, mortgages, and other decisions. In response, governments and several nonprofit organizations have undertaken initiatives to enhance financial literacy. The experience of other countries, including a saving campaign in Japan as well as the Swedish pension privatization program, offers insights into possible roles for financial literacy and saving programs.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Heterogeneity in Preferences and Productivity: Implications for Retirement - Gortz, Mette (University of Copenhagen, Dept. of Economics, 2006)
This paper discusses the determinants of the retirement decision and the implications of retirement on economic well-being. The main contribution of the paper is to formulate the role of individual heterogeneity explicitly. We argue that individual heterogeneity in 1) productivity of market work versus housework, 2) preferences for leisure compared to consumption, and 3) marginal utility of wealth, is correlated with the retirement decision. Based on US consumption and time use data for 2001 and 2003 from the Consumptions and Activities Mail Survey (CAMS), we study the patterns of individual choices of expenditure, household production and leisure for people in and around retirement. The unobserved individual heterogeneity factor is isolated by comparing cross-sectional evidence and panel data estimates of the effects of retirement on consumption and time allocation. Based on cross-section data, we can identify a difference in consumption due to retirement status, but when the panel nature of the data is exploited, the effect of retirement on consumption is small and insignificant. Moreover, the analyses point at a large positive effect of retirement on household production. Our results therefore contribute to the discussion of the so-called retirement-consumption puzzle. Many analyses of the retirement-consumption drop assume that the retirement decision is exogenous. However, the individual decision on when to retire may depend on expected changes in consumption and time allocation. This suggests that the retirement decision is endogenous. To test this, we apply an instrumental variables method in the treatment effects tradition.
Keywords: Consumption and Savings; Net Worth and Assets; Retirement Planning and Satisfaction

How Did the Elimination of the Earnings Test Above the Normal Retirement Age Affect Retirement Expectations? - Pierre-Carl Michaud; Arthur H.O. vanSoest (The University of Michigan, Michigan Retirement Research Center, 2006)
This study examines the effect of the 2000 repeal of the earnings test above the normal retirement age on retirement expectations of workers aged 51 to 61 their probabilities to work past age 62 and 65 as well as the age at which they expect to start claiming old age social security benefits. We use administrative records linked to the HRS to create variables that accurately reflect the change in financial incentives. For men, we find results in line with theoretical predictions on the probability to work after age 65. For example, men whose marginal wage rate increased when the earnings test was repealed, showed the largest increase in the probability to work full-time past normal retirement age. For women, we do not find significant results, possibly due to omitting spouse benefits and their interaction with the earnings test. We also do not find significant evidence of effects of the repeal of the earnings test on the probability to work past age 62 or the expected claiming age. On the other hand, for those reaching the normal retirement age, deviations between the age at which Social Security benefits are actually claimed and the previously reported expected age are more negative in 2000 than in 1998, suggesting that the repeal has increased claiming immediately after reaching normal retirement age. Since our calculations show that the tax introduced by the earnings test was small when accounting for actuarial benefit adjustments and differential mortality, our results suggest that although workers form expectations in a way consistent with forward-looking behavior, they misperceive the complicated rules of the earnings test.
Keywords: Retirement Planning and Satisfaction; Social Security

The Impact of Health Insurance Availability on Retirement Decision Reversals - Joshua Congdon-Hohman (The University of Michigan, Michigan Retirement Research Center, 2006)
This paper uses the longitudinal aspect of the Health and Retirement Survey to explore the characteristics associated with reversals in retirement (referred to here as unretirement ). Through the use of survival time analysis, this paper show that health insurance plays a significant role in unretirement decisions. This role is underestimated when a static probit analysis is used alone. The results hold up for a number of different retirement identifiers that are based both on self-reports of retirement and actual work levels. The results are also robust to various definitions of retirement prompted by the difficult question of how to classify partial retirements. The importance of health insurance provision in a retiree s decision also remains significant when other shocks and the prospect of planned unretirement are introduced.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Inherit the Wind; There's Little Else Left - Porter, Eduardo (New York Times, 2006)
The latest numbers confirm that a vast majority of baby boomers cannot count on an inheritance to help them out of their jam. Even as the total pile of wealth passed down the generations has increased sharply, the inheritance received by a typical American has declined. The shift can be explained in part by demographics changes, but also by the changing nature of old age (life expectancy has increased) and retirement financing (rather, the lack of it). [The article quotes a paper by Hurd and Smith, based on the Health and Retirement Study]
Keywords: Adult children; Consumption and Savings; Demographics; Net Worth and Assets; Retirement Planning and Satisfaction

Men With Health Insurance and the Women Who Love Them: the Effect of a Husband's Retirement on His Wife's Health Insurance Coverage - Jody Schimmel (The University of Michigan, Michigan Retirement Research Center, 2006)
Health insurance coverage in the years prior to retirement is particularly important because it protects the household from the financial risks of uninsurance as well as the health consequences of delaying care while uninsured. While results from the retirement job lock literature show that those who would lack coverage after retirement continue to work to maintain benefits, little work has explored the types of health insurance choices made by couples after retirement. It may be difficult for a married man to coordinate continuous coverage for a younger wife whose primary source of coverage has been from the husband, and thus households may pay more for non-group coverage or be exposed to the risks of uninsurance. This paper studies a panel of married couples from the 1992-2004 waves of the Health and Retirement Study (HRS) to study the types of health insurance decisions households make around the time of retirement. Results indicate that households seem to do well at avoiding uninsurance at the time of retirement, but may make high cost choices in order to insure the wife. Men switch into Medicare or coverage from their wife at retirement if they lose their own coverage, but a large fraction of women take-up privately purchased coverage. In fact, the transition from husband s coverage to privately purchased coverage is twice as large in periods when the husband retires than otherwise. Transitions to uninsurance are lower in periods of retirement than at other times, suggesting that men continue to work if either spouse would lose coverage. Though less risky, insurance purchased in the non-group market is expensive relative to employer-sponsored coverage. Thus, married households may need to increase savings to pay for health insurance that bridges the gap until the wife can claim Medicare at age 65.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

A New National Retirement Risk Index - Alicia H. Munnell; Anthony Webb; Delorme, Luke (Center for Retirement Research at Boston College, 2006)
Americans weaned on post-war affluence have come to expect an extended period of leisure at the end of their work life. And, indeed, the majority of today s retirees are able to afford a decent retirement. However, this group is living in a golden age that will fade as Baby Boomers and Generation Xers reach traditional retirement ages in the coming decades. This gloomy prediction reflects the trend towards longer retirements and likely declines in retirement incomes relative to pre-retirement earnings known as replacement rates. Because many Americans appear unaware of these disquieting trends, the Center for Retirement Research at Boston College has developed the National Retirement Risk Index. The Index measures the share of working-age households who are at risk of being unable to maintain their pre-retirement standard of living in retirement.
Keywords: Methodology; Public Policy; Retirement Planning and Satisfaction

Probabilistic Thinking and Early Social Security Claiming - Delavande, Adeline; Michael M. Perry; Robert J. Willis (The University of Michigan, Michigan Retirement Research Center, 2006)
This study analyzes the extent to which an individual.s survival expectations influence his or her decision to claim social security benefits at an early age. We find that subjective survival probabilities capture meaningful behavioral responses to incentives for early Social Security claiming when they are purged of measurement error using risk factors as instruments. Among people who are still working at age 62, those who expect to live longer are likely to delay claiming of Social Security benefits to a degree that is both statistically and economically significant.
Keywords: Methodology; Retirement Planning and Satisfaction; Social Security

The Role of Conventional Retirement Age in Retirement Decisions - Charles Brown (The University of Michigan, Michigan Retirement Research Center, 2006)
Existing research on retirement behavior tends to ignore conventional or focal or usual retirement ages in the model and estimation, and then ask whether a model which takes no direct account of such conventions can account for the observed spikes in the retirement hazard at age 62 and 65. This paper, in contrast, focuses on a direct measure of usual retirement age, based on a question that has been included in each wave of the Health and Retirement Study HRS). Using actual survey responses has several advantages: it identifies respondents who say that there is no usual retirement age for workers like them; it distinguishes between those who regard 62 and those who regard 65 as the relevant age; and it identifies the not insignificant number of workers for whom the usual age is neither 62 nor 65. There is little evidence that workers regard 63, the age at which COBRA coverage could provide a bridge to Medicare eligibility, as conventional, or that those affected by the increase in the age of eligibility for full retirement benefits under Social Security have adopted 66 or 67 as a focal retirement age. Following Wave I HRS respondents for six additional waves (12 years) so that their actual retirement can be observed shows that the actual retirement hazard is substantially higher at (and around) the age that workers identified in Wave I as the usual retirement age for workers like them. This is true even when we control for actual age at each wave, and for baseline values of earnings, wealth, health, and marital status. The finding that workers are more likely to retire at a particular age if they regard that age as the usual retirement age for workers like them suggests that the direct measures of the usual age may be useful in more formal models of the retirement process. In a world where some workers understand the incentives they face and respond appropriately, but others are poorly informed and overwhelmed by the choices they face, the usual retirement age may be a starting point for modeling the behavior of the latter group of workers.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Social Security Replacement Rates for Alternative Earnings Benchmarks - Olivia S. Mitchell; John W R Phillips (Benefits Quarterly, 2006)
Social Security reform proposals are often presented in terms of their differential impacts on hypothetical or example workers. This article explores how different benchmarks produce different replacement rate outcomes. The authors use the Health and Retirement Study (HRS) from the University of Michigan to evaluate how Social Security benefit replacement rates differ for actual versus hypothetical earner profiles, and examine whether these findings are sensitive to alternative definitions of replacement rates. They conclude that more precise analyses of possible distributional patterns from Social Security reform proposals would follow if benefit estimates were derived from actual earnings profiles, rather than hypothetical scaled patterns.
Keywords: Retirement Planning and Satisfaction; Social Security

Three Essays on Elderly Migration and Local Fiscal Policy - Woo, Seokjin (Three Essays on Elderly Migration and Local Fiscal Policy, 2006)
The first essay develops a retirement migration model using a nested logit (NL) specification. The dichotomous nest structure is constructed based on States' average temperature; Sunbelt nest and Non-sunbelt nest. The estimation results from the census 2000 reveal two interesting facts. First, the Multinomial-logit model and the NL retirement migration model agree on which state tax policy is an important determinant of interstate migration of retirees in terms of the magnitude and statistical significance of the coefficient. Second, the migration patterns predicted by the MNL-based model tend to be under-estimated, compared to the NL retirement migration model. Second essay develops a retirement migration model based on the random coefficient specification to investigate the effect of individual heterogeneity on migration decisions of retirees. The estimation results from the census 2000 reveal three interesting facts regarding the effect of individual heterogeneity on migration decisions. First, income and housing value of retirees interact negatively with income tax and property tax, respectively. Second, warm winter interacts positively with health condition and education level, and negatively with home ownership. Third, retirees are heterogeneous regarding the degree to which they appreciate warm winter. Third essay develops a stochastic dynamic programming discrete choice model which explains the sequence of migration and retirement decisions of older workers in the United States. The structural parameters of the model are estimated using the panel data from the Health and Retirement Study for the households whose heads worked in 1992. This paper contributes to the elderly migration literature in the following three aspects. First, it examines the migration decisions of older workers approaching retirement, an age group whose migration behavior has rarely been investigated. Second, including retirement decision in the model allows me to investigate the interaction between retirement and migration decisions. Third, this is the first study which estimates a stochastic dynamic programming discrete choice model for elderly migration. I find that the differentials in local fiscal policy across U.S. states affect the decision of where-to-move conditioning on moving, but does not affect the decision of whether-to-move to any significant extent.
Keywords: Demographics; Public Policy; Retirement Planning and Satisfaction

A Three-Part Study on the Relationship Between Retirement Planning and Health - Linda Christine Albert (A Three-Part Study on the Relationship Between Retirement Planning and Health, 2006)
Researchers consistently conclude that finances and health are the two most significant factors associated with retirement decision-making and a successful retirement experience. Retirement planning is one mechanism by which individuals prepare for the retirement transition; however, retirement planning routinely emphasizes financial concerns, often to the exclusion of health or other significant aspects of retirement. Retirement planning is an increasingly relevant topic at a time when the population is aging, company-sponsored pensions and retiree benefits have diminished significantly, and reform is being sought for the long-standing social programs that have provided support for generations of older Americans. From a financial perspective, few would question the positive benefits associated with retirement planning; however, preparing for a healthy retirement is equally important. If a relationship between retirement planning and health status were to be established, Americans might find increased public and private support for individual retirement planning efforts, particularly among more vulnerable populations such as minorities and women. This dissertation explores the notion that engagement in retirement planning is associated with health status through three studies. Utilizing data from the Health and Retirement Study (HRS), the first article explores prevalence of plans for retirement among worker and retiree respondents, and compares health and other key characteristics associated with planning among the two sub-samples. The second and third articles focus on time order relationships between health status and retirement planning, with article two addressing the question of whether onset of poor health precedes planning for retirement and article three examining health status of planners versus non-planners, over time, to determine whether those who engage in retirement planning are more likely to realize better health outcomes. A brief review of the health, retirement, and retirement planning literature provides the theoretical framework for these research questions and related hypotheses. This dissertation consists of five chapters. Chapter 1 is an introduction to the retirement planning and health literature, Chapters 2-4 describe the series of three studies conducted, and Chapter 5 discusses the overall conclusions as well as future directions for research.
Keywords: Health Conditions and Status; Healthcare; Public Policy; Retirement Planning and Satisfaction

Veterans and Functional Status Transitions in Older Americans - Xian Li; Engel, Charles C.; Han Kang; Armstrong, David W. (Military Medicine, 2006)
Objectives: This research examines the relationship of veteran status with functional status transitions in older Americans. Methods: Data for this study come from the Survey of Asset and Health Dynamics among the Oldest Old. We use a structural multinomial logit model to decompose the effect of older veterans into the direct effect and the indirect effects via physical health conditions and mental disorders on functional status transitions. Results: Although there is no distinct association among those functionally independent at baseline, veteran status significantly impacts age-dependent transitions from functional dependence to other statuses. At age 85, the excess mortality and the lower level of functional resolution among functionally dependent veterans are considerable. Conclusions: Physical health is more important than mental health in transmitting the effect of veteran status on functional status transitions in functionally dependent persons.
Keywords: Older Adults; Retirement Planning and Satisfaction; Transitions; Veterans

Are DC Plans Tools for Learning? Pension Design, Financial Education, and Portfolio Choice for Older Workers - Seligman, Jason S.; Bose, Rana (University of Georgia, 2005)
This work considers the potential for Defined Contribution (DC) pension plans to educate and affect better overall asset management though participation. We engage six waves of the Health and Retirement Survey to investigate whether household exposure to active management or participation in plan sponsored financial education impact portfolio allocations and wealth. We consider outcomes both within and outside of the worker s DC plan, allow for simultaneous allocation decisions via multivariate probit specifications, and construct a synthetic counterfactual via propensity score matching to test our results. We find repeated evidence that both of the plan features we test improve asset allocations and financial outcomes.
Keywords: Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Are Traditional Retirements a Thing of the Past? New Evidence on Retirement Patterns and Bridge Jobs - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Washington, DC, U.S. Department of Labor, Bureau of Labor Statistics, 2005)
Purpose: This paper investigates whether permanent, one-time retirements are coming to an end just as the trend towards earlier and earlier retirements did nearly 20 years ago. We explore how common bridge jobs are among today s retirees, and how uncommon traditional retirements have become. Methods: Using data from the Health and Retirement Study (HRS), we explore the work histories and retirement patterns of a cohort of retirees aged 51 to 61 in 1992 over a ten-year time period in both a cross-sectional and longitudinal context. Bridge job determinants are examined using bivariate comparisons and a multinomial logistic regression model of the bridge job decision. Results: We find that one-half to two-thirds of the HRS respondents with full-time career jobs take on bridge jobs before exiting the labor force completely. We also find that bridge job behavior is most common among younger respondents, respondents without defined-benefit pension plans, and respondents at the lower- and upper-end of the wage distribution. Implications: The evidence suggests that changes in the retirement income landscape since the 1980s appear to be taking root. Going forward, traditional retirements will be the exception rather than the rule.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Changes in Consumption and Activities in Retirement - Michael D Hurd; Susann Rohwedder (The University of Michigan, Michigan Retirement Research Center, 2005)
The simple one-good model of life-cycle consumption requires consumption smoothing. According to previous results based on partial spending and on synthetic panels, British and U.S. households apparently reduce consumption at retirement. The reduction cannot be explained by the simple one-good life-cycle model, so it has been referred to as the retirement-consumption puzzle. An interpretation is that at retirement individuals discover they have fewer economic resources than they had anticipated prior to retirement, and as a consequence reduce consumption. This interpretation challenges the life-cycle model where consumers are assumed to be forward looking. Using panel data on anticipated consumption changes at retirement and on recollected consumption changes following retirement, we find that the median recollected change in spending at retirement is zero and that the recollections are broadly consistent with anticipations. Based on a measure of total spending in true panel we find that the actual mean and median changes are slightly positive. Therefore, we find no retirement-consumption puzzle.
Keywords: Consumption and Savings; Event History/Life Cycle; Retirement Planning and Satisfaction

Changes in Wealth for Americans Reaching or Just Past Normal Retirement Age - Copeland, Craig (Employee Benefit Research Institute, EBRI Issue Brief No. 277, 2005)
This Issue Brief provides a first step in determining how retirees now starting to retire those first to be affected by the shift to lump-sum payments and 401(k) asset accumulation.are managing their wealth. Americans born from 1931 1941 are the focus of this study, since these Americans ranged in age from 51 61 in 1992 (at the beginning of the study period) and had reached age 61 71 by 2002 (the end of the study period). These Americans have been affected by fundamental changes in the employment-based retirement plan market, as fewer people are covered by defined benefit pension plans and more people are covered by defined contribution plans, principally the 401(k) plan. This shift has led to tremendous growth in IRA assets, as workers used these tax-favored savings vehicles to roll over their defined contribution and/or defined benefit assets upon job change or retirement.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Discussion of James Poterba, Joshua Rauh, Steven Venti and David Wise, Utility Evaluation of Risk in Retirement Savings Accounts - Robert J. Willis (Analyses in the Economics of Aging, 2005)
Keywords: Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction; Risk Taking

Estimating Life-Cycle Parameters from Consumption Behavior at Retirement - John Laitner; Daniel S. Silverman (The University of Michigan, Michigan Retirement Research Center, 2005)
Using pseudo-panel data, we estimate the structural parameters of a life cycle consumption model with discrete labor supply choice. A focus of our analysis is the abrupt drop in consumption upon retirement for a typical household. The literature sometimes refers to the drop, which in the U.S. Consumer Expenditure Survey we estimate to be approximately 16 , as the retirement consumption puzzle. Although a downward step in consumption at retirement contradicts predictions from life cycle models with additively separable consumption and leisure, or with continuous work-hour options, a consumption jump is consistent with a setup having nonseparable preferences over consumption and leisure and requiring discrete work choices. This paper specifies a life cycle model with these latter two elements, and it uses the empirical magnitude of the drop in consumption at retirement to provide an advantageous method of identifying structural parameters most importantly, the intertemporal elasticity of substitution.
Keywords: Consumption and Savings; Event History/Life Cycle; Retirement Planning and Satisfaction

Financial Literacy and Planning: Implications for Retirement Well-Being - Annamaria Lusardi; Olivia S. Mitchell (The University of Michigan, Michigan Retirement Research Center, 2005)
Only a minority of American households feels confident about retirement saving adequacy, and little is known about why people fail to plan for retirement, and whether planning and information costs might affect retirement saving patterns. To better understand these issues, we devised and fielded a purpose-built module on planning and financial literacy for the 2004 Health and Retirement Study (HRS). This module measures how workers make their saving decisions, how they collect the information for making these decisions, and whether they possess the financial literacy needed to make these decisions. Our analysis shows that financial illiteracy is widespread among older Americans: only half of the age 50 respondents could correctly answer two simple questions regarding interest compounding and inflation, and only one-third correctly answered these two questions and a question about risk diversification. Women, minorities, and those without a college degree were particularly at risk of displaying low financial knowledge. We also evaluate whether people tried to figure out how much they need to save for retirement, whether they devised a plan, and whether they succeeded at the plan. In fact, these calculations prove to be difficult: fewer than one-third of our age 50 respondents ever tried to devise a retirement plan, and only two-thirds of those who tried actually claim to have succeeded. Overall, fewer than one-fifth of the respondents believed they engaged in successful retirement planning. We also find that financial knowledge and planning are clearly interrelated: those who displayed financial knowledge were more likely to plan and to succeed in their planning. Moreover, those who did plan were more likely to rely on formal methods such as retirement calculators, retirement seminars, and financial experts, and less likely to rely on family/relatives or co-workers.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Older Workers: Labor Can Help Employers and Employees Plan Better for the Future - United States Governmental Office (GAO Report, 2005)
Demographic changes pose serious challenges for employers, the economy, and older Americans. As the baby boomers near traditional retirement ages, the loss of experienced workers could have adverse effects on productivity and economic growth. Also, many older Americans face less-secure retirements due to rising health care costs, pension coverage changes, and fiscal pressures on the nation's retirement programs. Due to the growing importance of workers aged 55 or older, GAO examined: (1) areas of the labor market affected by the aging of the workforce; (2) factors that influence the timing of retirement; and (3) what employers are doing to hire and retain older workers. All areas of the labor market are likely to be affected by the aging of the workforce. Like workers in general, a majority of older workers are employed in professional, management, service, office and administrative support, and sales occupations. However, employers in every occupation face the likelihood that a greater percentage of their workforce will be nearing retirement age. Potential skill gaps from impending retirements and a slowdown in the growth of the labor supply may make older workers a resource of growing importance. Focus group participants without a college degree cited health, finances, and layoffs most often as factors constraining the timing of their retirement and work decisions. Participants without such constraints, most often cited lifestyle and work perceptions as the factors driving their decisions. Also, despite survey findings showing that many older workers wish to gradually reduce their hours, overall, focus group participants indicated they either were not aware of options for continued work after retirement or that their current or former employer did nothing to retain them. Many saw barriers to future employment, including their own limited skills and perceived age bias. While some employers are making an effort to hire and retain older workers, such as offering flexible work arrangements, most have not yet made these efforts a priority. We found some examples of programs targeted toward older workers, and many employers express a willingness to initiate practices to retain older workers. However, most surveyed employers do not implement these practices widely. In addition, only about one-third of participants in a roundtable discussion of employers concerned about the aging workforce indicated that they provided a specific plan or program to recruit or retain older workers. Employers cite a number of barriers to offering more opportunities, such as federal pension regulations.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

Retirement and Marital Decision-Making: Effects on Retirement Satisfaction - Maximiliane E Szinovacz; Adam Davey (Journal of Marriage and the Family, 2005)
This study explores how partner s employment and preretirement decision-making structures affect retirement satisfaction, using pooled data from Waves 1 to 4 of the Health and Retirement Surveys. Based on resource theory, the analyses indicate that retired husbands are least satisfied if their wives remain employed and had more say in decisions prior to the husband s retirement. Retired wives are least satisfied if their husbands remain employed and had more say in decisions prior to the wife s retirement. These results suggest that retirement transitions undermine married retirees satisfaction if they enhance the other partner s influence in the relationship. More research should address linkages between work and family realms during transitions such as retirement and explore the negotiation processes surrounding such transitions.
Keywords: Adult children; End of life decisions; Retirement Planning and Satisfaction

Retirement and the Evolution of Pension Structure - Friedberg, Leora; Anthony Webb (Journal of Human Resources, 2005)
Defined benefit pension plans have become considerably less common since the early 1980s, while defined contribution plans have spread. Previous research showed that defined benefit plans, with sharp incentives encouraging retirement after a certain point, contributed to the striking decline in American retirement ages. In this paper we find that the absence of age-related incentives in defined contribution plans leads workers to retire almost two years later on average, compared to workers with defined benefit plans. Thus, the evolution of pension structure can help explain recent increases in the typical retirement age, after decades of decline.
Keywords: Pensions; Retirement Planning and Satisfaction

Saving Shortfalls and Delayed Retirement - Au, Andrew; Olivia S. Mitchell; John W R Phillips (University of Michigan Retirement Research Center Working Paper, 2005)
Prior research has suggested that many older Americans have not saved enough to maintain consumption levels in old age. One way older persons might respond to inadequate savings would be to extend their worklives by delaying retirement. This paper examines evidence on this matter using the Health and Retirement Study, a nationally representative panel survey of people age 51-61 in 1992 followed for several years in a panel. We use the data to project household retirement assets and to determine how much more saving would be needed to preserve post-retirement consumption levels. Our research then examines the links between derived saving shortfall measures and delayed retirement patterns. Among nonmarried persons, there is evidence that larger shortfalls do produce delayed retirement, though the effect is not quantitatively large. For married couples, pre-retirement wealth shortfalls do not appear to be significantly associated with delayed retirement. Evidently couples have other means of handling saving shortfalls.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

The Selection of Partial or Full Retirement by Older Workers - Kim, Haejeong; DeVaney, Sharon A. (Journal of Family and Economic Issues, 2005)
The study investigated whether older workers chose partial or full retirement instead of full-time work. Partial or full retirement status was modeled as a combination of self-reported retirement status and change in number of hours worked. The results of multinomial logistic regression using data from the first and fifth waves of the Health and Retirement Study collected in 1992 and 2000 showed that age and gender had similar effects on the likelihood of partial and full retirement. Full retirement was also influenced by investment assets, pensions, employee health insurance, and poor health. The likelihood of partial retirement was also influenced by self-employment, chronic health conditions, and education. Workers who seek partial retirement need working conditions that allow them to make this choice.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Utility Evaluation of Risk in Retirement Saving Accounts - James M. Poterba; Joshua Rauh; Steven F Venti; David A Wise (Analyses in the Economics of Aging, 2005)
The shift from defined benefit to defined contribution plans in the United States has drawn new attention to the effect of participants' asset allocation decisions on their financial resources for retirement. This paper develops a stochastic simulation algorithm to evaluate the effect of holding a broadly diversified portfolio of common stocks, or a portfolio of index bonds, on the distribution of 401(k) account balances at retirement. We compare the alternative distributions of retirement wealth both by showing the empirical distribution of potential wealth values, and by computing the expected utility of these outcomes under standard assumptions about the structure of household preferences. Our analysis highlights the critical role of other sources of wealth, such as Social Security, defined benefit pension annuities, and saving outside retirement plans in determining the expected utility cost of holding equities in the retirement account. Our findings also demonstrate the importance of the equity premium in affecting investors' utility from different retirement asset allocations. Viewed from the beginning of a working career, and given the historical pattern of returns on stocks and bonds, a household that does not have extremely high risk aversion would achieve a higher expected utility by holding a portfolio of stocks rather than bonds.
RDA ProCite field 6 : In ProCite field 8 : ed
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

What Makes Retirees Happy? - Bender, Keith A.; Natalia A. Jivan (Center for Retirement Research at Boston College Briefs, 2005)
Economic well-being in retirement has been of increasing interest for economic researchers. The policy implications are large. As the baby boom generation nears retirement, understanding the factors that determine economic well-being enables policymakers to evaluate and possibly reform present retirement institutions, such as public and private pension programs. Of particular interest in this field has been the focus on retirement income adequacy, that is, the financial resources retirees need to be above some minimal level…
Keywords: Retirement Planning and Satisfaction

Bulls, Bears and Retirement Behavior - Courtney Coile; Phillip B. Levine (NBER Working Paper, 2004)
The historic boom and bust in the stock market over the past decade had the potential to significantly alter the retirement behavior of older workers. Previous research examining the impact of wealth shocks on labor supply supports the plausibility of this hypothesis. In this paper, we examine the relationship between stock market performance and retirement behavior using the Health and Retirement Study (HRS), Current Population Survey (CPS), and Survey of Consumer Finances (SCF). We first present a descriptive analysis of the wealth holdings of older households and simulate the labor supply response among stockholders necessary to generate observed patterns in retirement. We show that few households have substantial stock holdings and that they would have to be extremely responsive to market fluctuations to explain observed labor force patterns. We then exploit the unique pattern of boom and bust along with variation in stock exposure to generate a double quasi-experiment, comparing the retirement and labor force re-entry patterns over time of those more and less exposed to the market. Any difference in behavior that emerged during the boom should have reversed itself during the bust. We find no evidence that changes in the stock market drive aggregate trends in labor supply.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Can I Retire? Benchmarks to Consider in Making the Retirement Decision - Karen E. Lahey; Kim, Doseong; Newman, Melinada L. (Journal of Financial Planning, 2004)
The decision to retire is a significant life-cycle event for a financial planner's client(s). To aid financial planners and their clients in this process, we analyze a longitudinal database of individuals who have retired or are near retirement. We summarize the findings and provide both financial and nonfinancial benchmarks that clients can use in arriving at their own retirement decision. Among the variables examined, we find that age, health, a spouse's retirement status, and mortgage debt are the factors that most significantly influence the decision to retire. We also illustrate differences found between those who decide to retire and those who do not by providing eight benchmark scenarios. The first four scenarios compare retired and nonretired married couples based on their reported health status, while the second set of comparisons is based on the ownership of business assets.
Keywords: Retirement Planning and Satisfaction

A Collective Retirement Model: Identification and estimation in the presence of externalities - Pierre-Carl Michaud; Vermeulen, Frederic (Labour Economics, 2004)
We study the labor supply dynamics of elderly couples by means of a structural collective model. The model allows for general externalities with respect to spouses' leisure. Preferences and the intrahousehold bargaining process are identified by using panel data with couples and individuals who turned into widow(er)hood in the covered period. The model does not only look at the extensive margin (working versus being retired), but also at the intensive margin (how many hours are worked) and the claiming decision for social security benefits. We apply the model to American households coming from the first five waves of the Health and Retirement Study. We also provide model simulations for two widely discussed reform proposals; more specifically the abolition of the earnings test and the elimination of the spouse benefit. The model simulations reveal only small changes in labor supply of elderly couples.
Keywords: Retirement Planning and Satisfaction

Crime and Early Retirement Among Older Americans - Daniel S. Silverman; Olivia S. Mitchell (Pension Research Council Working Paper, 2004)
This paper investigates the relationship between local crime rates and the retirement decisions of older Americans. We do so by linking data from the Health and Retirement Study with measures of local crime patterns taken from the Federal Bureau of Investigation s Unified Crime Reports. If we condition on crime rates alone, there is either a weakly positive or no relationship between local crime patterns and older men s propensity to retire early. But unobservable factors associated with early retirement may be correlated with residence in higher-crime rate cities, so next we condition on both the expectation for the crime rate and deviations from average crime levels. We find a positive and statistically significant association between early retirement and expectations for murder rates, and a positive but, on average, imprecisely estimated positive association between early retirement and unexpected increases in crime. The effect of unanticipated increases in crime is greatest, and significant for those in poor health. In this latter group, men are 14 percent more likely to retire early given a standard deviation increase in unexpected murder rates. These findings are consistent with a pattern of more early retirement among those who live in higher crime areas, and earlier retirement among those in poor health when crime levels rise above anticipated levels.
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Do Spouses Coordinate Their Retirement Decisions? - Richard W. Johnson (Center for Retirement Research at Boston College, 2004)
The movement of married women into the labor market is transforming retirement behavior. A generation ago, when few married women spent many years in the labor force, it was relatively simple for spouses to coordinate their retirement decisions. Couples typically focused on the generosity of the husbands retirement benefits and the impact of his retirement decision on future benefits. Today, however, retirement decisions are more difficult to coordinate, because many women have accumulated substantial retirement benefits in their own names. As a result, many couples now need to consider how the decision to stop work will affect income and retirement benefits for both spouses. The evidence suggests that couples like to retire together and, since husbands tend to be older than their wives, the increased labor force participation of women may lead to later retirement of men. This brief examines retirement behavior and measures the extent to which husbands and wives appear to coordinate their retirement decisions.
Keywords: Adult children; Retirement Planning and Satisfaction

The Effect of Social Security on Retirement in the United States - Courtney Coile; Gruber, Jonathan (Social Security Programs and Retirement Around the World, 2004)
ProCite field 6 : In ProCite field 8 : eds.
Keywords: Methodology; Retirement Planning and Satisfaction

The Effects of Health Insurance and Self-Insurance on Retirement Behavior - Eric French; John Bailey Jones (Center for Retirement Research at Boston College Working Papers, 2004)
Using the first estimable dynamic programming model of retirement behavior that accounts for both savings and uncertain medical expenses, we assess the importance of employer-provided health insurance and Medicare in determining retirement behavior. Including both of these features allows us to determine whether workers value employer- provided health insurance because the subsidy contained in the insurance lowers their average medical expenses, or because health insurance also reduces their medical expense risk. Using data from the Health and Retirement Study, we find that the reduction in expected medical expenses explains about 60 of a typical individual s valuation of health insurance, with the reduction in volatility explaining the remaining 40 . We find that for workers whose insurance is tied to their job, shifting the Medicare eligibility age to 67 will significantly delay retirement. However, we find that the plan to shift the Social Security normal retirement age to 67 will cause an even larger delay.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Financial Education and Saving - Annamaria Lusardi (Pension Design and Structure: New Lessons from Behavioral Economics, 2004)
In this paper, I examine the financial situation of older households. In addition, I examine whether employers' initiatives to reduce planning costs via retirement seminars have an effect on workers' saving. Using data from the Health and Retirement Study, I first show that many families arrive close to retirement with little or no wealth. Portfolios are also rather simple, and many families, particularly those with low education, hold little or no high-return assets. I further show that seminars foster saving. This is particularly the case for those with low education and those who save little. By offering financial education, both financial and total net worth increase sharply, particularly for families at the bottom of the wealth distribution and those with low education. Retirement seminars also increase total wealth (inclusive of pension and Social Security) for both high and low education families. Taken together, this evidence suggests that retirement seminars can foster wealth accumulation and bolster financial security in retirement.
RDA 1998-002 ProCite field 6 : In ProCite field 8 : eds.
Keywords: Education; Net Worth and Assets; Retirement Planning and Satisfaction

The Health Effects of Retirement: A Theoretical and Empirical Investigation - Neuman, Kevin (University of Notre Dame, 2004)
This study strives to answer the question of how retirement affects health. Assessing how retirement affects health leads to better estimates of health care costs and a better understanding of the retirement decision. The study develops a model of health investment where individuals maximize lifetime utility derived from consumption goods, leisure and healthy time and produce health using leisure and medical goods. Solving the model generates an equilibrium condition for health investment. Assuming that healthy time is a normal good, the model predicts that retirement will increase health investment and thus health for retirees in the next period relative to workers. The empirical test uses a sample of older adults from the longitudinal Health and Retirement Study. To account for the endogeneity of the retirement decision the study employs an instrumental variable model exploiting exogenous variation in Social Security and private pension benefits. The study also improves on previous work by estimating a model where health change in one period is regressed on previous period retirement status allowing the health stock time to adjust to changes in investment behavior. Using subjective health measures, the study finds that retirement decreases the probability of a good health change for men by over 8%, but increases the probability for women by 15%. The difference between sexes persists using a sample of women who worked a significant number of years in their lifetime, and is not due to the particular set of instruments used. Retirement also preserves health for both sexes, reducing the probability of a health decline by 2.5% for men and 3.5% for women. Comparing the subjective results to objective measures reduces concerns about reporting bias for the negative effects for men although the results cannot rule out role bias in the positive results for women. The results recommend leaving the Social Security early entitlement age untouched, or extending Medicare and disability coverage to those in poor health who are forced to work by entitlement age increases, potentially allowing individuals to enter retirement in better health, reducing health care costs.
Keywords: Consumption and Savings; Disabilities; Health Conditions and Status; Public Policy; Retirement Planning and Satisfaction; Social Security

How Alternative Definitions of Retirement and Social Class Shape Conclusions about the Retired Population - Araiza, Isabel (How Alternative Definitions of Retirement and Social Class Shape Conclusions about the Retired Population, 2004)
The conceptualization and operationalization of retirement remains a challenge in retirement research. Those studies which have examined multiple conceptualizations of retirement often limit the investigation to two, three, or four definitions of retirement. These studies also produce contradictory results with respect to the degree of overlap among various definitions of retirement. Moreover, in the investigation of the relationship between predictor variables and the probability of retirement, push and pull factors (such as pension receipt and health) are often the focal point of the inquiry. While most studies include in their analysis a class measure as a control variable for the model, seldom is the relationship between social class and the probability of retirement the focal point of the investigation. This study employs data from the 1998 wave of the Health and Retirement Study to perform an extensive analysis of seven operationalizations of retirement and five operationalizations of social class to evaluate how the use of alternative definitions of retirement and social class shape conclusions drawn about the composition of the retired population. Analyses are performed for the entire sample selected for this study, as well as for Non-Hispanic White, Hispanic, and Non-Hispanic Black subgroups. The results of the analyses indicate that different operationalizations of retirement affect the characterization the retired population; moreover the use of different operationalizations of social class influences the perceptions of the socio-economic condition of the retired population. Despite socio-economic achievements, the findings suggest that initial inequalities associated with ascriptive traits like race and gender continue to constrain women and minorities' life course trajectories. While it is not possible to conduct a comprehensive examination of operationalizations of retirement in gerontological literature, this study includes operationalizations of retirement that acknowledge retirement as an event, an identity, and a process.
Keywords: Demographics; Healthcare; Methodology; Retirement Planning and Satisfaction; Women and Minorities

How Do Pensions Affect Expected and Actual Retirement Ages - Alicia H. Munnell; Triest, Robert K.; Natalia A. Jivan (Center for Retirement Research at Boston College Working Papers, 2004)
This paper uses the first six waves of the Health and Retirement Study to investigate the impact of pensions on expected retirement age, on the probability of being retired in each wave given employment in the previous wave, and on the probability of retiring earlier than planned. Pension coverage per se and the type of pension are important in each case. Pension wealth reduces the expected retirement age by 0.6 year, and the incentives in defined benefit plans lower the expected age by another 1.1 years. Pension wealth increases the probability of retiring in a given wave, and pension accruals reduce the probability. Other characteristics of defined benefit plans, as measured by the pension dummy, further raise the probability of being retired. Finally, with regard to the probability of retiring earlier than planned, a change in defined contribution wealth increases the probability, but pension coverage per se reduces it. That is, those with pensions tend to be more accurate planners than those without.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Individual Financial Decisions in Retirement Plans: The Role of Participant Direction - Papke, Leslie E. (Journal of Public Economics, 2004)
Workers with individual retirement saving accounts often make decisions about contribution rates and asset allocation that affect ultimate retirement income. This paper presents econometric evidence from two data sets on the role that participant investment choice plays in asset allocation, contributions, and account balances. My preferred estimates indicate that participants with investment choice are 36 percent more likely to make an annual contribution. These participants are estimated to invest 13 percentage points more in stocks, contribute between one and three percentage points more of salary, and have at least 9000 more in their account than comparable participants without investment choice.
Keywords: Retirement Planning and Satisfaction

A Longitudinal Look at the Predictors of Four Types of Retirement - Weymouth, Penny L. (A Longitudinal Look at the Predictors of Four Types of Retirement, 2004)
The general purpose of the study was to further the understanding of the retirement process. More specifically, the study investigated several personal and work-related predictors of individual retirement status that have received relatively little past examination. By gaining a better understanding of the retirement process, policy makers and organizational leaders can use this knowledge to make informed decisions affecting older workers, their organizations, and society in general. Public release data of the Health and Retirement Study (HRS)--a recent, large, representative, national panel study that focuses on the health, retirement, and aging of persons born between the years of 1931 and 1941--were analyzed. In-home, face-to-face interviews were conducted in 1992, with follow-up interviews conducted every two years by phone. From survey years 1992 through 2000, samples of working individuals over the age of 50 were used to examine nine hypotheses and four different operationalizations of retirement. The hypotheses involved the following predictor variables: gender, partner status, characteristics of one's partner (i.e., retirement status and health), number of dependents, obsolescence of job skills, "demanding" job characteristics, perceived age-related discrimination, work and retirement attitudes, and flexibility of organizational policies regarding older workers. Event history analysis using logistic regression was used to predict the dichotomous criterion variables, while linear mixed model analysis for repeated measures was used to predict the continuous dependent variable. After statistically controlling variables such as age, health, and finances, results indicated that gender, partner's retirement status, work and retirement attitudes, and organizational flexibility were each predictors of at least one type of retirement. In addition, the statistical interaction of gender with partner status predicted retirement defined in several ways. The study expanded what is known about retirement predictors by examining actual versus intended retirement behavior and increased the generalizability of past research by utilizing national panel data. The study also highlighted the importance of clearly defining retirement measures and explored the complete versus partial retirement typology. It was suggested that flexible work options may improve work and retirement attitudes by making the transition into retirement a gradual process, and may keep older employees in the work force longer.
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Minimum Hours Constraints, Job Requirements and Retirement - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2004)
A structural retirement model estimated with data from the Health and Retirement Study is used to simulate the effects of policies firms might adopt to improve employment conditions for older workers and thereby encourage delayed retirement. Firm policies that effectively abolished minimum hours constraints would strongly increase the number partially retired, while reducing full time work and full retirement, resulting in only a small net increase in full time equivalent employment. Reducing physical and mental requirements of jobs would have much weaker effects on retirement than was suggested by work with the 1970s Retirement History Study. Reducing informal pressures to retire, increasing employer accommodations to health problems, and reducing the prevalence of layoffs and retirement windows would have only small effects on retirement outcomes.
ProCite field 3 : Unlisted; Unlisted
Keywords: Consumption and Savings; Disabilities; Employment and Labor Force; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Part-time Labor Markets for Older Workers - Chen, Jennjou (Part-time Labor Markets for Older Workers, 2004)
This dissertation examines the part-time job markets for older workers, particularly for individuals who utilize part-time jobs as a bridge between their career jobs and full retirement. The retirement decision of older workers is an important policy issue provoking significant public attention. Before the 1978 Amendments to the Age Discrimination in Employment Act (ADEA), many workers either chose to retire or were forced to retire at age 65. Today, mandatory retirement is prohibited in the United States, and older employees have the option to stay in the labor force as long as they wish. Perhaps because of this fact, an increasing number of American older workers choose to work part-time, and use part-time jobs as a transition to their full retirement. Interestingly, however, part-time work often involves moving to a new employer instead of remaining with an original full-time employer. This dissertation tries to examine why this happens. This dissertation begins by examining patterns of transition among older workers from career jobs to full retirement, and then compares the individual and firm characteristics of older workers who take different paths toward retirement. Five waves of the Health and Retirement Study (HRS) from 1992 to 2000 are employed. The HRS data shows that part-time inside and part-time outside older workers are different in many ways: gender, race, pension characteristics, firm size, industry, and occupation. These results demonstrate that working inside part-time and outside part-time are different phenomena. This dissertation also studies the wage differences between part-time inside and part-time outside workers. Various wage equations for part-time inside and part-time outside jobs are estimated. Furthermore, using polychotomous choice models, this dissertation employs several selectivity correction techniques to address the endogenous choice and selection bias problems. Observed wages and potential wage offers are compared in order to explain older workers' part-time job choices.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Personal Accounts and Family Retirement - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2004)
This paper constructs a model of retirement and saving by two earner couples. The model includes three dimensions of behavior: the joint determination of retirement and saving; heterogeneity in time preference; and the interdependence of retirement decisions of husbands and wives. Estimation is based on panel data from the Health and Retirement Study covering the period 1992 to 2000. When husbands postpone their retirement so they can retire together with their typically younger wives, the spike in retirement at age 62 is smeared to later ages. Thus retirements differ between one and two earner families. We find both an asymmetry in which husbands prefer their wife to be retired before they retire, and a clear distaste of many husbands to retiring when their wives are in poor health, while the wives are willing to stay at home with sickly husbands. We simulate a system of personal Social Security accounts based on a 10.6 percent contribution rate over the lifetime. One version allows individuals to make lump sum withdrawals at retirement instead of annuitizing. This program would increase the retirement rates of husbands at age 62 by about 15 percentage points compared to the current system. Adding a lump sum option, by itself, would increase retirements at 62 by about 6 percentage points.
Keywords: Public Policy; Retirement Planning and Satisfaction; Social Security

Retirement Transitions: The role of shocks to household resources - Kim, Sora (Retirement Transitions: The role of shocks to household resources, 2004)
The role of shocks to household resources in affecting retirement transitions among older employees was analyzed using data from the Health and Retirement Study (HRS). The transitions of reverse retirement and partial retirement were of particular interest. The objectives of the study were: 1) To explore how shocks, or unexpected changes to financial and human resources, affect retirement transitions, and 2) To explore the relative importance of shocks in making retirement transitions. The study sample consisted of 2,514 HRS respondents, born between 1926 and 1938, who changed employment status between 1998 and 2000 or between 2000 and 2002. A multinomial Logit model was used in order to make comparisons among the four retirement transition groups. The empirical model included institutional variables and demographic and environmental control variables. The results suggest that just as the paths to retirement are diverse and complex, so are their determinants. Shocks to financial resources had the largest effects on reverse retirement transitions. Shocks to human resources, including family structure and health, affected all retirement transitions. Institutional variables had the largest marginal effects on partial retirement. As expected, positive shocks to assets decreased the odds of reverse retirement, and negative income shocks had larger marginal effects on retirement transitions than positive income shocks. However, positive asset shocks had larger marginal effects on retirement transitions than negative asset shocks. The partial retirement group was distinguished from the reverse retirement group in terms of financial shock impacts; for members of the partial retirement group, rather than shocks to resources, institutional supports were key determinants. Fewer significant effects on the odds of partial retirement over traditional retirement were found, and the effects were smaller than those for reverse retirement and retirement from part-time employment in terms of their magnitudes. The loss of human resources was important across the transition groups, with greater impact of shock to marital status on women's labor force transitions compared to men's. To reduce shocks to household resources under uncertainty, retirement education should encompass information on asset allocation and financial risk. These topics may help workers more effectively plan for retirement.
Keywords: Health Conditions and Status; Healthcare; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Savings and Retirement in the New Millennium - Anthony Webb (Economics, 2004)
The typical pension plan has changed dramatically in the past twenty-five years. There has been a large increase in the coverage of defined contribution (DC) plans, in which the pension is generally paid in unannuitized form, and where the amount of the pension depends on investment returns and the amount contributed. There has been a corresponding decline in the coverage of defined benefit (DB) plans in which the pension is some function of salary and years of service. DC plans place greater responsibility on the individual to make adequate provision for his retirement. They also lack many of the age related incentives of DB plans that have been shown to influence retirement. The first chapter, "The Effect of 401(k) Eligibility on Household Asset Holdings: New Evidence from the Health and Retirement Study", examines the question of whether contributions to 401(k) plans, the most common type of DC plan, have merely displaced other non pension savings, or whether they represent additional saving that would not otherwise have been made. A comparison of the savings of participants with those of non-participants would likely produce biased estimates, as participants probably have a stronger unobserved taste for savings than non-participants. I therefore follow previous practice in comparing eligible with ineligible households. Eligibility is, however correlated with DB plan membership, which may also affect savings behavior. I therefore restrict my analysis to households that are also members of DB plans, a relatively homogenous group. Previous researchers use asset balances imputed from donor households of a different pension type, leading to further potential bias. I therefore re-impute missing data, including eligibility among my covariates. Using the Health and Retirement Study, a panel dataset, I find no evidence of any displacement of other savings in either financial assets or home equity by 401(k) contributions. If anything, eligible households save more in other financial assets, a finding that I attribute to the financial education often associated with the introduction of DC plans. In my second chapter, co-authored with Professor Friedberg, I use data from the same dataset to show that retirement patterns have changed as DC plans have spread. We estimate that the financial incentives in DB plans lead people to retire almost two years earlier on average, and that the decline in DB plan coverage over the period 1983 to 1995 has increased average retirement age by two to four months. In my third chapter, I examine whether the observed failure of the elderly to dissave is a result of concerns about end-of-life expenditure. Using data from the Asset and Health Dynamics among the Oldest Old (AHEAD) dataset, I show that married couples save more if they expect to enter long-term care, but that single women do not. I attribute the difference in behavior between the two groups to a desire on the part of couples to make adequate provision for the surviving spouse.
Keywords: Pensions; Retirement Planning and Satisfaction

Social Security, Pensions and Retirement Behaviour Within the Family - Alan L Gustman; Thomas L. Steinmeier (Journal of Applied Econometrics, 2004)
This paper estimates a structural model of family retirement using US data from the Health and Retirement Study (HRS). It provides further insight into household retirement decision making and the reasons for interdependence in the retirement decisions of each spouse. Improvements in HRS data and matched employer provided pension histories allow more precise identification of key parameters governing interdependent behaviour within the household. In an earlier study we found that interdependence was due to preferences rather than coordination of retirement incentives in the budget, and in particular that it is not a correlation in preferences, but the appearance of the spouse's retirement status in the husband's and wife's utility function that is largely responsible for coordination of retirement between spouses. We now find that a measure of how much each spouse values being able to spend time in retirement with the other accounts for a good portion of that apparent interdependence. For the wife, the husband's retirement status influences her retirement decision only if she values spending time in retirement with her husband. For husbands, the effect of having the wife already retired on his retirement decision is roughly doubled if he enjoys spending time in retirement with his wife, but there is some effect even if he does not. This is consistent with our earlier findings that the husband is more influenced by having a retired spouse than the wife is. The increase in the extent of the dependence of the wife's labour supply on the husband's retirement from our past work probably is traceable to better measurement of the opportunity set facing the husband in HRS data. Once estimated, we use the model to investigate the labour supply effects of alternative social security policies, examining the effect of dividing credit for earnings evenly between spouses, or of basing social security benefits on the amounts accumulated in private accounts. Both policies change the relative importance of spouse and survivor social security benefits within the household and both raise the relative reward to work later in the life cycle. The incentives created are modest, and retirement responds accordingly. Nevertheless, at some ages, such as 65, there may be as much as a 6 increase in the old age work force under privatized accounts. Copyright 2004 John Wiley and Sons, Ltd.
RDA 1996-005; HRS 1992
Keywords: Adult children; Pensions; Retirement Planning and Satisfaction; Social Security

Annuities and Retirement Satisfaction - Panis, Constantijn (RAND Unrestricted Draft, 2003)
This paper analyzes pre-retirement expectations and post-retirement satisfaction, in particular their association with the degree to which retirees financial resources are in the form of annuities. Using the 1992-2000 Health and Retirement Study (HRS), we find that most retirees are very satisfied with their overall situation, but the degree of satisfaction varies substantially with retirees characteristics. In particular, people in better health and with more financial resources tend to be more satisfied. Holding constant the present value of retirement resources and other factors, we find that retirees who can finance more of their consumption in retirement from pension annuities (vs. Social Security benefits and accumulated savings) are more satisfied. Retirees with lifelong annuities also tend to maintain their level of satisfaction during retirement, whereas those without tend to become less satisfied over time. We find the very same patterns with alternative depression-related measures of well-being in retirement. The findings have important implications for the well-being of future American retirees, who are increasingly reliant on DC pension plans rather than traditional DB.
Keywords: Expectations; Net Worth and Assets; Retirement Planning and Satisfaction; Social Security

Baby Boomers' Retirement Prospects: An Overview - United States Congressional Office (A CBO Study, 2003)
Having enjoyed historically high incomes over their working years, baby boomers (people born from 1946 to 1964) make up one of the most prosperous generations in U.S. history. In the past 15 years, however, their finances have become a source of concern in policy circles and in the press as doubts have arisen about whether boomers are accumulating enough wealth to maintain their current or expected standards of living after they retire.1 One worry is that low saving by boomers could hurt the economy by limiting the growth of investment, productivity, and wages. Such curbs on economic activity could compound the budgetary pressures that the federal government will face as increasing numbers of boomers become eligible for benefits from Social Security and Medicare.
Keywords: Demographics; Public Policy; Retirement Planning and Satisfaction; Social Security

Can Unexpected Retirement Explain the Retirement-Consumption Puzzle? Evidence from Subjective Retirement Expectations - Melvin Stephens Jr.; Steven Haider (Center for Retirement Research at Boston College Working Papers, 2003)
Previous research finds a systematic fall in consumption at retirement, even when these retirements are expected, which implies households do not behave as predicted by the lifecycle/ permanent income hypothesis. However, the worker s expected date of retirement is typically predicted using an instrument - age - that we show to be correlated with unexpected retirements and will therefore lead to biased estimates. In this paper, we use an alternative instrument for expected retirement: workers own subjective beliefs of their expected retirement dates. We find that subjective retirement expectations provide strong predictive power for subsequent retirements above and beyond the impact of age on retirement probabilities. We still find, however, that consumption falls for workers who retire when expected although the estimated impact is 50 percent smaller when using retirement expectations as an instrument instead of age.
Keywords: Consumption and Savings; Expectations; Retirement Planning and Satisfaction

Do Pensions Impede Phased Retirement? - Even, William; David A. Macpherson (IZA DP, 2003)
Many workers reveal a preference for a gradual reduction in work hours as they approach retirement (“phased retirement”), rather than a sudden change from full-time work to full-time retirement. Pension regulations may impede phased retirement without a switch of employers by prohibiting access to pension assets. This study uses Health and Retirement Survey data to investigate the extent to which a gradual reduction in work hours is made difficult by pensions, particularly defined benefit plans. The study also explores other possible impediments to phased retirement.
Keywords: Pensions; Retirement Planning and Satisfaction

Does the Current Climate Discourage Seasoned Pros? - Greene, Kelly (Wall Street Journal, 2003)
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

The Effects of Health Events on the Economic Status of Married Couples - Stephen Wu (The Journal of Human Resources, 2003)
This paper uses measures of exogenous health shocks to identify the different channels through which changes in health conditions affect income, wealth, and consumption behavior. The results indicate that serious health conditions have strong effects on household wealth, but that the effects for women are larger and more significant than the effects for men. The source of the asymmetry arises from the fact that general living expenses increase when wives become seriously ill, while for husbands, health shocks do not affect these expenditures.
Keywords: Adult children; Employment and Labor Force; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Employers Use of Early Retirement Incentives, 1992-2000 - Nielson, Norma L.; Chan, David K.W. (Calgary, AB, University of Calgary, Haskayne School of Business, 2003)
This paper examines data from the Health and Retirement Study relating to the use of early retirement incentives by employers. Those early retirement offers tend to occur around age 59 and are found with varying frequencies in different occupations and professions. Cash bonuses were the most common type of early retirement incentive offered with enhanced pension benefits being the second most popular. Statistical examination of five waves of data spanning the period 1992-2000 reveals demographic and workplace factors that explain portions of the variance. Both age and salary exhibit nonlinear relationships, with the likelihood of an early retirement offer first increasing and then decreasing with both variables. Employer offers of special early retirement incentives peak at age 59 and at salaries between 60,000 and 100,000 respectively. Characteristics related to a greater likelihood of receiving an early retirement incentive are male gender, union membership, longer tenure with a firm, greater labor market experience, less reliance on physical labor in one s job, and participation in a defined benefit pension plan. However, a substantial proportion of the variation across industries and occupations remains unexplained.
Keywords: Retirement Planning and Satisfaction

Fiscal Effects of Social Security Reform in the United States - Courtney Coile; Gruber, Jonathan (Center for Retirement Research at Boston College Working Papers, 2003)
Social Security is the largest social insurance program in the U.S., and has been shown to be a major determinant of the labor supply decisions of older workers. As such, reforming the Social Security system can have two fiscal impacts: a mechanical effect through changing the rules on benefits entitlements or taxation, and a behavioral effect through individual responses to these changes in benefits or taxes. We build a simulation model that computes these effects for major reforms to the system, building on estimated retirement responses to changing net Social Security entitlements. We then estimate the fiscal impact of reform for the 1931-1941 cohort of workers represented by the Health and Retirement Survey. We find that raising the early and normal retirement age by three years would reduce net costs for this cohort by roughly 30 , and that moving to a much higher benefit level would raise net costs by roughly 55 . Importantly, we find that in both cases the behavioral impacts on net costs are relatively small, at most one-third, and generally less than one-fifth of the total. The reason for these small effects is that the U.S. Social Security system is roughly actuarially fair, so that delaying or inducing retirement has relatively little impact on system balances; most of the effects that do arise are due to changes in general income and consumption taxes.
RDA
Keywords: Public Policy; Retirement Planning and Satisfaction; Social Security

Health Insurance Costs and Early Retirement Decisions - Richard W. Johnson; Davidoff, Amy J.; Perese, Kevin (Industrial and Labor Relations Review, 2003)
The loss of health insurance may be an important component of the cost of retirement, especially for workers without retiree health insurance coverage. The authors find that insurance costs significantly reduce retirement rates for full-time wage and salary workers ages 51 to 61. Simulations suggest that a 1,000 increase in the net present value of health insurance premium costs reduces the probability of early retirement by 1.17 percentage points for men and by 0.24 percentage points for women, corresponding to elasticities of -0.22 and -0.24, respectively. The authors' models predict that expanding the Medicare program to cover those aged 62-64 would increase retirement rates for workers with employer-sponsored coverage who lack retiree benefits, if the government subsidizes their coverage. However, the impact would be small, increasing overall retirement rates by only 7 .
RDA 1998-006
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Household Income, Asset Allocation, and the Retirement Decision - Karen E. Lahey; Kim, Doseong; Newman, Melinada L. (Financial Services Review, 2003)
Keywords: Income; Net Worth and Assets; Retirement Planning and Satisfaction

How Do Cash Balance Plans Affect the Pension Landscape? - Kevin E. Cahill; Soto, Mauricio (Boston College, Center for Retirement Research, 2003)
Keywords: Pensions; Retirement Planning and Satisfaction

How Do Negative Events Shape the Subsequent Work-Family Life Course? The case of involuntary versus voluntary retirement - Dentinger, Emma (How Do Negative Events Shape the Subsequent Work-Family Life Course? The case of involuntary versus voluntary retirement, 2003)
This dissertation examines whether it matters that someone retires voluntarily or involuntarily. Specifically, I investigate three possibilities for life after retirement: subsequent reemployment, divorce, ad major health problems (heart attacks and death). The question I address is: does knowing whether or not one retires voluntarily or involuntarily (due to health problems or downsizing, for example) aid in predicting any of those outcomes after retirement? Do these processes operate differently for various subgroups, such as by race and gender? To do this, I employ Cox event history techniques using the University of Michigan's 1992 - 1998 Health and Retirement Study (HRS). I find that men and women in their 50s, 60s and 70s who are forced to retire for job-related reasons between 1992 and 1998 are more likely to engage in post-retirement employment compared to those who voluntarily retire, adapting to this unexpected transition by re-engaging in the work role. In contrast, men and women who retire for health reasons during this time are less likely to engage in post-retirement employment (for women this is dependent on having a pension) and more likely to experience cumulative health disadvantage. However, men who retire involuntarily for health-related reasons (for their own health or a family member's) are also less likely to divorce post-retirement than are men who are voluntary retirees. Spousal influences, measured by marital status in the combined models and spousal characteristics among the married sample, appear to be significant factors in various ways. For example, women who are divorced, separated or widowed prior to retirement are more likely to re-engage in the work role, reflecting their generally weaker economic positions. Married and partnered men are more likely than single men to re-engage in paid work. I find no confirmation for the prediction that women's family circumstances, such as having a child living at home, are more consequential for their post-retirement experiences than men's family circumstances on their own experiences. Life post-retirement for both men, and women is affected by family influences about equally, albeit in different ways.
Keywords: Adult children; Health Conditions and Status; Retirement Planning and Satisfaction

How Has the Shift to 401(k)s Affected the Retirement Age? - Alicia H. Munnell; Kevin E. Cahill; Natalia A. Jivan (Boston College, Center for Retirement Research, 2003)
Keywords: Pensions; Retirement Planning and Satisfaction

The Impact of Technological Change on Older Workers: Evidence from Data on Computer Use - Friedberg, Leora (Industrial and Labor Relations Review, 2003)
New technologies like computers alter skill requirements. This paper explores two related effects of the spread of computers on older workers, using data from the Current Population Survey and the Health and Retirement Study. One conclusion is that impending retirement, rather than age alone, explains why older workers used computers less than prime-age workers did. A second conclusion is that computer users retired later than non-users. Although this pattern may arise because workers planning later retirement decided to acquire computer skills, the empirical analysis suggests that the causation also went in the other direction, with computer users choosing to delay retirement. It will be important to understand these effects as the baby boom cohort nears retirement, while technologies continue to change rapidly.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Investment Choice in Defined Contribution Plans: the Effects of Retirement Education on Asset Allocation - Leslie A. Muller (Benefits Quarterly, 2003)
The article presents a summary of the research titled "Investment Choice in Defined Contribution Plans: The Effects of Retirement Education on Asset Allocation." Pension plan sponsors and policy makers both have recently become concerned as to whether participants have the financial knowledge to choose how their pension assets are invested. The article provides evidence of the effect of retirement classes on asset allocation in self-directed defined contribution plans.
Keywords: Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Joint Labor Supply Dynamics of Older Couples - Pierre-Carl Michaud (IZA DP, 2003)
This paper studies the labour force participation dynamics of older couples in the United States. Longitudinal data from the five available waves of the Health and Retirement Study (HRS) is used to investigate if the dynamics introduced by considering both spouses behavior provide additional information in trying to fit observed participation sequences. The paper uses a bivariate dynamic binary choice model with unobserved heterogeneity and serial correlation to disentangle the many sources of dynamics and correlation in a couple s decision making. First, strong true state-dependence is found and results in a bunching of participation and non-participation sequences. Cross-spouse state-dependence is also found which points to indirect effects of social security and pension incentives through complementarity in leisure. Second, the Spouse Allowance program is found to have predicted effects on participation of the couple and these effects are statistically significant. A simulation exercise presents evidence that the elimination of the spouse allowance can raise participation of wives at age 62 by more than the decrease in participation of husbands at age 65.
Keywords: Adult children; Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Measuring the Optimal Income Replacement Rate: A Panel Data Analysis - An, Chong-Bum; Jeon, Seung-Hoon (Sungkyunkwan University, Korea; Dept. of Economics, 2003)
In order to analyze welfare of retirees, this paper investigates the optimal income replace rate and analyzes how retirement decision affects the post- and pre-retirement consumption. The data analysis using the HRS shows that consumption decreased after retirement for both early and late retirement groups. The post- and pre-retirement consumption ratio (CRATIO) is computed to be 0.922, which implies that the optimal income replacement rate for all retirees is 92.2 . We investigate the interdependence of the decisions on when to retire and how much to consume after retirement (or CRATIO) by using the switching regression model, which tests the hypothesis that early retirement and short labor period induces the low post-retirement income and low post-retirement consumption. The empirical results from the switching regression model show that early retirement decision may affect the post-retirement consumption. After deciding to retire early, retirees would have consumed less than they actually have. The estimation results that used CRATIO as a dependent variables are similar to the results that used post-retirement consumption as a dependent variable.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

Option Value Estimation with HRS Data - Andrew A. Samwick; David A Wise (Labor Markets and Firm Benefit Policies in Japan and the United States, 2003)
We estimate the effect of financial incentives to delay retirement on the probability of retirement in the Health and Retirement Study. We find statistically significant effects of both pension wealth and pension incentives on the probability of retirement. The effects are more robust when retirement is defined only as a job separation rather than a complete transition out of the labor force. We also investigate possible interactions between the effects of health, wealth, and health insurance on retirement.
RDA 1997-011 ProCite field 8 : eds.
Keywords: Public Policy; Retirement Planning and Satisfaction

Partners in Marriage: An analysis of husbands' and wives' retirement behavior - Pienta, Amy M. (Journal of Applied Gerontology, 2003)
The goal of this analysis is to compare the retirement behavior of husbands and wives. Hypotheses are offered to describe two sets of factors associated with retirement of husbands and wives. These are included in the usual modes of retirement hypothesis and the new modes of retirement hypothesis. Using data from the 1992 Health and Retirement Survey, multinomial models are estimated to assess whether various personal, spousal, and familial factors are related to retirement status. Results indicate that in addition to personal characteristics, wives' retirement status is related to familial factors, economic resources, and spouses' personal characteristics supporting the new modes of retirement hypothesis. Husbands differ mainly in that familial and spousal attributes have more limited relationships with retirement behavior thereby supporting the usual modes of retirement hypothesis.
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Perspectives from the President’s Commission on Social Security Reform - John F. Cogan; Olivia S. Mitchell (Journal of Economic Perspectives, 2003)
Social Security faces a severe financial problem. In about 15 years, the program will begin to experience permanent annual cash deficits, when annual benefit payments will exceed the amount collected in payroll tax revenues. By 2041, according to the Social Security Trustees 2002 Report, the Social Security trust fund is projected to be insolvent, meaning that the program will be legally unable to pay scheduled benefits. One way of expressing the financial shortfall is to compute the present value of the difference between system outlays and revenues over a 75-year horizon, which is currently equal to a permanent and immediate tax rate increase of 1.86 percent of payroll, or equivalent to $3.2 trillion in present value. If the policy of pay-as-you-go financing is continued for the next 25 years, a 50 percent payroll tax increase will be required at that time to pay scheduled benefits.
Keywords: Older Adults; Retirement Planning and Satisfaction; Social Security; Taxes

Planning and Saving for Retirement - Annamaria Lusardi (Dartmouth College, Dept. of Economics, 2003)
There are vast differences in wealth holdings, even among households in similar age groups. In addition, a large percentage of U.S. households arrive close to retirement with little or no wealth. While many explanations can be found to rationalize these facts, approximately thirty percent of households whose head is close to retirement have done little or no planning for retirement. Planning is shaped by the experience of other individuals: individuals learn to plan for retirement from older siblings. They also learn from the experience of old parents. In particular, unpleasant events, such as financial difficulties and health shocks at the end of life, provide incentives toward planning. In addition, planning affects wealth levels as well as portfolio choice. Individuals who plan are more likely to hold large amounts of wealth and to invest their wealth holdings in high return assets, such as stocks. Thus, planning plays an important role in explaining the saving behavior of many households.
RDA 1998-002
Keywords: Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Private Pensions: Participants Need Information on Risks They Face in Managing Pension Assets at and during Retirement - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 2003)
Question: Individuals face increasing responsibility for ensuring the sufficiency of their retirement savings, a result of the continuing trend toward pension plans with individual accounts and longer life expectancies. Finding: Using the NIA-funded Health and Retirement Study, GAO found that while plan sponsors provide timely information about payout options (e.g., lump-sum versus annuity) and that many plans offer both lump-sum and annuity options, there is little discussion regarding the relative risks of the available options, as well as the risk of outliving one s savings. While many retirees received annuities (60 percent), a large proportion that had the option of annuitizing chose instead to receive a lump-sum distribution. Recommendation: More effort is needed to increase public awareness of the risks associated with various options for pension distributions and the implications of choosing one option versus another for the likelihood of outliving one s retirement savings.
Keywords: Consumption and Savings; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Reasons for Job Change and the Disposition of Pre retirement Lump Sum Pension Distributions - Gary V. Engelhardt (Economics Letters, 2003)
Estimates from logit models on a sample of 890 individuals from the 1992 Health and Retirement Study (HRS) eligible to receive a pre retirement lump sum pension distribution suggest that pension assets may have been used to buffer economic shocks upon job change.
ProCite field 3 : Center for Policy Research, Syracuse U
Keywords: Employment and Labor Force; Pensions; Public Policy; Retirement Planning and Satisfaction

Retirement Incentives and Couples' Retirement Decisions - Courtney Coile (NBER Working Paper, 2003)
The typical family in the US is now a dual-earner couple, yet there are relatively few studies that examine the retirement decision in a household framework, particularly outside the context of a structural model. This paper explores how husbands and wives retirement behavior is influenced by their own financial incentives from Social Security and private pensions and by spillover effects from their spouses incentives. Spillover effects are possible due to income effects and complementarity of leisure; if significant, their omission will bias estimates of the effect of changing Social Security policy on retirement. I estimate reduced-form retirement models and find that men and women are similarly responsive to their own incentives: an increase of 1,000 in the return to additional work is associated with a reduction of 0.9 of baseline retirement for men and 1.3 of baseline retirement for women. I find that men are very responsive to their wives financial incentives but that women are not responsive to their husbands incentives and present evidence to suggest that this may be due to asymmetric complementarities of leisure. Policy simulations indicate that estimates of the effect of a policy change on the probability of men working at age 65 are biased by 13 to 20 if spillover effects are omitted.
Keywords: Adult children; Retirement Planning and Satisfaction

Retirement Income Data: Improvements Could Better Support Analysis of Future Retirees' Prospects - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 2003)
Future demographic trends include a doubling of the nation's retiree population and only modest labor force growth, leading to concerns about retirement income adequacy for future generations. Credible projections of the effects of policy proposals on federal spending and future retirees' income are necessary. Because adequate data is critical to the analysis of retirement income and wealth, GAO was asked to identify data improvements that experts say are a priority for the study of retirement income and wealth, as well as factors limiting efforts to obtain the needed information. Experts consulted by GAO cited priorities for improving retirement data that fit into two broad categories: (1) obtaining better data from employers on employee benefits and (2) obtaining better data by linking more individual and household surveys with administrative data (such as employer records, and Social Security earnings history records). Information from employers, such as documents describing the features of their pension plans, would enable analysts to forecast future retirement income of pension holders, based on the specific features of their pension plans and the likely distribution of pension income and wealth for different segments of the population. Linking individual and household surveys with administrative data creates new information, such as the demographic characteristics of employees whose pensions are affected by the formulas that employers use to calculate contributions or pension payments. Analysts attribute the shortcomings in retirement income data primarily to fragmentation of the responsibility for data collection and analysis, the burden of data collection on respondents, and confidentiality considerations that restrict access to these data. Fragmentation of responsibility occurs, in their view, because no single agency has a statutory mandate to collect or to analyze all the data needed to support a more comprehensive study of retirement income and wealth. With regard to respondent burden, some information on pension plans is no longer collected, in part, out of concern that it was an unnecessary burden on the firms having to submit it. Finally, certain kinds of data needed to make projections are not widely available to all analysts because of the confidentiality laws that authorize their collection.
Keywords: Methodology; Pensions; Retirement Planning and Satisfaction

The Retirement-Consumption Puzzle: Anticipated and Actual Declines in Spending at Retirement - Michael D Hurd; Susann Rohwedder (NBER Working Paper, 2003)
The simple one-good model of life-cycle consumption requires consumption smoothing. However, British and U.S. households apparently reduce consumption at retirement and the reduction cannot be explained by the life-cycle model. An interpretation is that retirees are surprised by the inadequacy of resources. This interpretation challenges the life-cycle model where consumers are forward looking. However, data on anticipated consumption changes at retirement and on realized consumption changes following retirement show that the reductions are fully anticipated. Apparently the decline is due to the cessation of work-related expenses and the substitution of home production for market-purchased goods and services.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

Risk Ratings that Do Not Measure Probabilities - Viscusi, W.K.; Jahn K. Hakes (Journal of Risk Research, 2003)
Survey questions regarding assessed survival chances are an often-used example of a risk rating scale for eliciting a probability assessment. The responses to such questions do exhibit several properties of probabilities, but differ in some key respects, resulting in relationships which are not only inconsistent with accurate beliefs, but also in which precision is sacrificed for ease of use. The Health and Retirement Study, for example, uses a 0 to 10 scale to measure self-assessed survival probabilities to a particular age. Transformation of these responses for use as a probability results in some patterns that are consistent with a model of imperfect information, or a monotonic transformation of imperfectly perceived risks, but more subtle analysis reveals inconsistencies with either of these theories, suggesting the scale is inappropriate for use as a probability measure. The age-related effects for female respondents are the most salient results that are inconsistent with use of the survey's response scale as representing a probability.
Keywords: Expectations; Health Conditions and Status; Retirement Planning and Satisfaction

The Role of Social Context in the Relationship Between Health and Retirement - Tay K. McNamara (The Role of Social Context in the Relationship Between Health and Retirement, 2003)
While many studies have evaluated the effects of health on the retirement decision, these studies have typically paid less attention to the multi-level nature of the context within which individuals and couples make retirement decisions. Using data from waves 1 (1992) through 5 (2000) of the Health and Retirement Study, the present study addresses the multi-level nature of social context and its effects on the relationship between health and retirement. In three linked subanalyses, particular attention was paid to how three core concepts of life course theory (i.e., the social clock, the interdependence of family and work trajectories, and the role of institutions in shaping inequalities) might help to clarify the relationship between health, retirement, and social context. The results of this study indicate that social context, as embodied by internalized norms, social groups, and institutional structures, moderates the relationship between retirement and poor health. More specifically, the analysis of the social clock (micro-level context) indicates that internalized expectations about the correct time to retire influence whether a nonworking person considers themselves retired. Workers in poor health are disproportionately likely to consider themselves "unretired", nonworking but not retired. The analysis of the interdependence of work and family (meso-level context) found that couples jointly evaluated the husbands' and wives' health statuses when making reverse retirement decisions, but not necessarily when making retirement decisions. The analysis of the role of institutions in shaping inequalities focused on the effects of employer policies beneficial to workers in poor health. The effects of two types of policies, employer flexibility in number of hours worked and employer provided health insurance, were examined. While it is not feasible for one study to address all aspects of social context, the present study highlights the relationship between health and retirement on several levels.
Keywords: Adult children; Event History/Life Cycle; Health Conditions and Status; Retirement Planning and Satisfaction

Saving, Wealth and Retirement: Evidence from the Health and Retirement Study - Khitatrakun, Surachai (Saving, Wealth and Retirement: Evidence from the Health and Retirement Study, 2003)
This dissertation examines household saving and retirement decisions using data from the 1992 to 2000 Health and Retirement Study (HRS). After a brief introduction, the second chapter examines the relationship between children and household net worth around the time of retirement. Restricting the sample to first-time married couples and controlling for many factors including lifetime earnings and unearned income, I find that households with more children generally have less net worth than households with fewer, but the difference is small. Moreover, there is no strong evidence that the difference is a result of the adverse effect of college financial aid rules on savings. In addition, there is little evidence that children affect parents' subjective assessments of retirement security. These findings are consistent with the basic principle of the life-cycle framework where parents plan optimally for their retirement consumption. The third chapter examines how wealth changes affect retirement decisions. I focus on the differences between self-reported expected retirement dates in one survey and either the actual or expected retirement dates in the next survey for the same individuals, and relate these to changes in household net worth. Moreover, I recognize that institutional constraints could deter individuals from adjusting their retirement dates to accommodate unanticipated events, such as wealth shocks. I find that the relationship between wealth changes and retirement is generally significant in the expected direction, and more pronounced for the respondents unlikely to face binding institutional constraints. The fourth chapter examines whether Americans are preparing adequately for retirement. My coauthors and I construct a life-cycle model that incorporates detailed HRS data on family structure and age of retirement and allows for uncertainties in earnings, social security benefits, and defined benefit pension receipts. Then, we solve every household's life-cycle problem and, using data on the household's entire history of earnings realizations, derive optimal wealth at given ages. The model explains over 70 percent of the variation in wealth for married households, and over 80 percent for never-married single households. Comparing the derived optimal wealth targets with the observed amount of net worth, we find little evidence that HRS households have under-saved.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

A Structural Model of the Effect of Retiree Health Insurance on Early Retirement - Tunceli, Kaan (A Structural Model of the Effect of Retiree Health Insurance on Early Retirement, 2003)
This study contributes to the existing literature by pursuing two complementary goals: (1) To estimate the effect of planning to retire early on access to employer provided retiree health insurance (ERHI); and (2) to produce a consistent estimate of the effect of ERHI on the probability of early retirement, allowing for the possibility that access to retiree health insurance is an endogenous variable. The empirical analysis uses the data from the first five Waves of the Health and Retirement Study (HRS), which were conducted every other year from 1.992 to 2000. The analysis focuses on men who were less than 65 in 2000, full-time workers, and had insurance as active workers in 1996. The retirement model is specified with three sequential equations: Planning to retire early in 1992, access to retiree health insurance in 1996, and retirement between 1996 and 2000. Not only demographic and socioeconomic characteristics of men, but also those of spouses to estimate the structural retirement model are included in all three equations. Alternative estimation techniques are used including univariate probit, bivariate probit, and trivariate probit models. The results vary significantly across estimation techniques. Planning to retire early encourages access to ERHI in the bivariate and trivariate models, while it does not in the univariate model. The effect of access to ERHI on early retirement is positive and significant in all three models. However, the effect is larger for bivariate and trivariate models compared to the univariate model. The trivariate model provides evidence that correlations between error terms across the structural equations are significant. The correlation between errors in the access equation and the retirement equation is negative. Therefore, it is likely that previous literature underestimated the effect of access to retiree health insurance on early retirement. One important implication for public policy is that policy initiatives such as a Medicare buy-in or health insurance tax credits that increase access to retiree health insurance are likely to have large effects on retirement decisions. In other words, the unintended effects on labor force participation of policies that increase access to retiree health insurance might be greater than previous research has suggested.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Wealth Effects and the Consumption of Leisure: Retirement Decisions During the Stock Market Boom of the 1990s - Coronado, Julia L.; Maria Perozek (FEDS Working Papers, 2003)
It is well accepted that households increase consumption of goods and services in response to an unexpected increase in wealth. Consensus estimates of this wealth effect are in the range of 3 to 5 cents of additional consumption spending in the long run for each additional dollar of wealth. Economic theory also suggests that consumption of leisure, like consumption of goods and services, should increase with positive shocks to wealth. In this paper, we ask whether the run-up in equity prices during the 1990s led older workers to retire earlier than they had previously planned. We identify the effect by exploiting unique data on retirement expectations from the Health and Retirement Survey. Our econometric results suggest that respondents who held corporate equity immediately prior to the bull market of the 1990s retired, on average, 7 months earlier than other respondents.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

What People Don't Know About Their Pensions and Social Security: An Analysis Using Linked Data from the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (Public Policies and Private Pensions, 2003)
Pension plan descriptions from respondents to the 1992 Health and Retirement Study are compared with descriptions obtained from their employers. Earnings histories reported by respondents are compared with earnings histories from the Social Security Administration. The probability of linking employer pension data, which is two thirds for current jobs, and of obtaining permission to link an earnings history, which is over 70 percent, are not well explained by respondent characteristics. Half of respondents with linked pension data correctly identify plan type, and fewer than half identify, within one year, dates of eligibility for early and normal retirement benefits. Benefit reduction rates are essentially not reported. Respondents do better in reporting pension values, but the unexplained variation is still considerable. In contrast, respondent reported values together with other observables, account for 80 percent of the variation in pension values and 75 percent of the variation in covered earnings measured from linked records. Thus prospects are good for imputing plan values, but not for imputing the location or size of early retirement incentives. Our findings raise questions about how well respondents understand complex pension and Social Security rules.
RDA 1996-005ProCite field[8]: eds.
Keywords: Consumption and Savings; Employment and Labor Force; Income; Pensions; Retirement Planning and Satisfaction; Social Security

What You Don't Know Can't Help You: Knowledge and Retirement Decision Making - Sewin Chan; Ann H. Stevens (Cambridge, Mass., National Bureau of Economic Research, 2003)
This paper examines the relationship between pension incentives, individuals knowledge about those incentives, and the retirement decision. Combining detailed self- and employer-reported data on private pensions, we construct measures of the accuracy of individuals self-reports of their pensions. We show that the minority of well-informed individuals display dramatically larger responses to financial incentives than indicated by average estimates. These results suggest that there is substantial heterogeneity in responsiveness to pension incentives across the population. Finally, we estimate a joint model of information acquisition and retirement decision-making. These results confirm the substantial differences in behavior between informed and uninformed segments of the population.
Boston College, Center for Retirement Research, and the Social Security Administration
Keywords: Education; Pensions; Retirement Planning and Satisfaction

Couple Retirement Patterns and Retirement Age: A Comparison of Austria and the United States - Maximiliane E Szinovacz (International Journal of Sociology and Social Policy, 2002)
Keywords: Methodology; Retirement Planning and Satisfaction

Delays in Claiming Social Security Benefits - Courtney Coile; Diamond, Peter; Gruber, Jonathan; Jousten, Alain (Journal of Public Economics, 2002)
This paper focuses on Social Security benefit claiming behavior, a take-up decision that has been ignored in the previous literature. Using financial calculations and simulations based on an expected utility maximization model, we show that delaying benefit claim for a period of time after retirement is optimal in a wide variety of cases and that gains from delay may be significant. We find that approximately 10 of men retiring before their 62nd birthday delay claiming for at least one year after eligibility. We estimate hazard and probit models using data from the New Beneficiary Data System to test four cross-sectional predictions. While the data suggest that too few men delay, we find that the pattern of delays by early retirees is generally consistent with the hypotheses generated by our theoretical model.
Keywords: Retirement Planning and Satisfaction; Social Security

Do Retiree Health Benefits Cause Early Retirement? - Linsenmeier, David M. (Princeton University, 2002)
I examine whether the availability of early retiree health benefits increases the likelihood of early retirement. Although there is a positive association between the availability of retiree health benefits and early retirement, this association could be driven by other factors that are correlated with retiree health benefits and affect retirement decisions. I build a simple model to show that individuals in poor health and with poor outside insurance options value retiree health benefits more. I then use variation in health status and outside insurance options to examine, within a difference-in-differences framework, whether the estimated correlation between retiree health benefits and early retirement reflects demand for health insurance. My results indicate that the effect of retiree health benefits is not statistically significantly larger for those in poor health, but that it is larger for those who lack insurance from other sources, particularly from their spouses. I conclude that retiree health benefits do increase the hazard of early retirement and that demand for health insurance among the near-elderly is not closely tied to health status.
Robert Wood Johnson Foundation and to Princeton s Industrial Relations Section
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

The Effects of Changing Social Security Administation's Early Entitlement Age and the Normal Retirement Age - Panis, Constantijn; Michael D Hurd; Loughran, David; Julie M Zissimopoulos; Steven Haider; Patricia A St Clair (Social Security Administration: Labor & Population Program, 2002)
The Old-Age and Survivors Insurance (OASI) program is projected to be unable to meet its obligations by approximately the year 2041. Many proposals that aim to restore solvency include provisions to accelerate the already legislated increase of the normal retirement age (NRA) or to increase it beyond the current target of 67 years; some proposals also suggest raising the early entitlement age (EEA) beyond 62 years. This document sheds light on the implications of EEA and/or NRA increases on the solvency of the OASI and DI programs. It does not discuss private accounts. The report starts with a characterization of workers who claim benefits at age 62 and a discussion of retirement planning. We then estimate formal models of retirement and DI application and simulate the financial consequences of EEA and/or NRA increases and other policy proposals. We conclude with an assessment of likely responses of employers to changes in Social Security policy. Most analyses in this report are based on the Health and Retirement Study (HRS), a survey of individuals in their 50s and 60s with very extensive information about work, financial resources including Social security and private pensions, and health.
RDA 2000-010
Keywords: Methodology; Retirement Planning and Satisfaction; Test

Experiencing Transitional Events in the Pre-Retirement Years - Morgan, Allan (University of Massachusetts Boston, The Gerontology Institute, 2002)
Keywords: Retirement Planning and Satisfaction

Explaining Why So Many Households Do Not Save - Annamaria Lusardi (Dartmouth College, Dept. of Economics, 2002)
There are vast differences in wealth holdings, even among households in similar age groups. In addition, a large percentage of U.S. households arrive close to retirement with little or no wealth. While many explanations can be found to rationalize these facts, approximately thirty percent of households whose head is close to retirement have done little or no planning for retirement. Planning is shaped by the experience of other individuals: individuals learn to plan for retirement from older siblings. They also learn from the experience of old parents. In particular, unpleasant events, such as financial difficulties and health shocks at the end of life, provide incentives toward planning. In addition, planning affects wealth levels as well as portfolio choice. Individuals who plan are more likely to hold large amounts of wealth and to invest their wealth holdings in high return assets, such as stocks. Thus, planning plays an important role in explaining the saving behavior of many households.
RDA 1998-002
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

How Does Job Loss Affect the Timing of Retirement? - Sewin Chan; Ann H. Stevens (National Bureau of Economic Research, 2002)
We use the Health and Retirement Study to examine the effects of job loss on factors affecting retirement incentives, including earnings, assets and pensions. We then estimate models of the retirement decision, which take into account the incentive to retire and any additional effects of displacement that are not captured by retirement incentives. There are substantial effects of displacement on retirement incentives as the result of changes to both earnings and pensions. Displacement significantly increases the probability of retirement, but only a small fraction of the displacement-induced changes in retirement behavior and labor force participation are the result of workers responding to these altered retirement incentives.
National Science Foundation Grants 9905275 and 9907824.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

The Influence of Pensions on Behavior: How Much Do We Really Know? - Alan L Gustman; Thomas L. Steinmeier (TIAA-CREF Research Dialog, 2002)
Economists have developed models to explain the impact of pensions and Social Security on various outcomes, such as retirement, worker turnover, and saving. However, some recent research has raised questions about these conventional models. This issue of Research Dialogue summarizes findings from our ongoing research on pensions and Social Security. Using data from the new longitudinal Health and Retirement Study that reports both the respondents' own knowledge about their pensions and the actual provisions of their pension plans, our research emphasizes how well the conventional model does in describing behavior, answers some of the questions raised by others, and raises some new questions. We also discuss the implications of our findings for researchers and policy makers.
Keywords: Pensions; Retirement Planning and Satisfaction

Money Matters: Beyond the Nest Egg - Greene, Kelly (The Wall Street Journal, 2002)
Keywords: Retirement Planning and Satisfaction

Older Workers and their Selection of Partial and Full Retirement: Evidence from Health and Retirement Study - Kim, Haejeong (Older Workers and their Selection of Partial and Full Retirement: Evidence from Health and Retirement Study, 2002)
The purpose was to investigate older workers' retirement transitions by examining factors associated with partial retirement and full retirement during a four-year period. The study used data from three waves of the Health and Retirement Study. The sample consisted of 3,268 primary respondents who were working full time in Wave 1. A conceptual model was developed based on the life-cycle retirement model, the lifecycle income hypothesis, disengagement theory, activity theory, continuity theory, lifecourse perspectives, role theory, and the findings of previous research on retirement behavior. Binary logit regression and multinomial logit regression analyses were employed for model estimation. Major findings from the multinomial logit using baseline predictors to examine partial and full retirement in Wave 3 are 1) unearned income, Individual Retirement Account and Keogh plans positively impact the likelihood of partial retirement versus full-time work, while the ownership of defined benefit plans and the ownership of defined contribution plans negatively impact partial retirement versus full-time work; 2) the number of chronic conditions positively impact the likelihood of partial retirement; 3) perceived age discrimination, age, male, and a college degree are positively associated with the likelihood of partial retirement; 4) the expected age of Social Security benefit receipt is negatively related to the likelihood of full retirement versus full time work, while the ownership of defined benefit plans, the ownership of both defined benefit and defined contribution plans, the ownership of IRA and Keogh plans, the ownership of health insurance after retirement are positively related to the likelihood of full retirement; 5) excellent and good health, and the meaning of work is more important are negatively associated with the likelihood of full retirement; and 6) age is positively associated with the likelihood of full retirement. The conflicting effects of pension plans on partial retirement and full retirement show that pension are a stimulus to encourage working although part-time, while pension plans are important as retirement incentives for the full retirement decision. Theoretical, empirical, and practical implications are presented based on the findings.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Passed over for promotion because of age: An empirical analysis of the consequences - Adams, Scott J. (Journal of Labor Research, 2002)
I test whether older individuals who report that their firms favor younger workers in promotion decisions are harmed by this often-cited discriminatory practice. Using the Health and Retirement Study, I determine whether such workers are more likely to experience lower wage growth, to separate from their employer, or to retire early, in comparison with workers with similar demographic and job characteristics. The evidence is consistent with lower wage growth and a greater likelihood of early retirement. Much of the effect, however, is likely to stem from a high correlation between delayed-payment contracts and promotion practices.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Planning; Ready to Quit, but Deep in Debt - Altman, Daniel (New York Times on the Web, 2002)
Keywords: Retirement Planning and Satisfaction

Preparing for Retirement: The Importance of Planning Costs - Annamaria Lusardi (National Tax Association Proceedings, 2002)
RDA 1998-002
Keywords: Retirement Planning and Satisfaction

Retirement and the Stock Market Bubble - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2002)
This paper specifies and estimates a structural dynamic stochastic model of the way individuals make retirement and saving choices in an uncertain world, and applies that model to analyze the effects of the stock market bubble on retirement behavior. The model includes individual variation both in retirement preferences and in time preferences. Estimates are based on information covering the period 1992 through 2000 from the Health and Retirement Study (HRS), a panel survey of retirement age respondents and their spouses. The extraordinary returns in the stock market in the late 1990's, which more than doubled stock prices and unexpectedly increased the value of a mixed portfolio by nearly 60 percent, increased retirement for the HRS sample of workers by over 3 percentage points by the turn of the century and would have decreased the average retirement age by about a quarter of a year if it had not been interrupted. The subsequent decline in the market, which very nearly wiped out the gains that had been made during the preceding surge, effectively neutralized the effect of the preceding stock market gains on retirement. The effects of the bubble were to increase retirement as long as the bubble continued, but any continuing effects of the bubble after its end will probably be minimal.
RDA
Keywords: Consumption and Savings; Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Planning and Health Outcomes in the Health and Retirement Study - L.M. Albert; Sandra L Reynolds (Southwest Journal on Aging, 2002)
Keywords: Healthcare; Retirement Planning and Satisfaction

Review of: Forecasting Retirement Needs and Retirement Wealth - Michael A. Curme (Journal of Economic Literature, 2002)
ProCite field 3 : Miami U
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

Self-defined Retirement Status and Engagement in Paid Work Among Older Working-age Women: Comparison Between Childless Women and Mothers - Namkee G Choi (Sociological Inquiry, 2002)
From changes in retirement laws and incentives many people, including working women, can decide when to retire based on their own preferences and needs. Family structure and familial roles are a major issue of when people will decide to retire, especially if considering women. Differences between women without children and those with children that are no longer living at home, and the likelihood of retirement among people of the two groups, is assessed. The author, also considers those women that take part in bridge jobs as a path to retirement. Detailed demographic findings comparing and contrasting those women with children living at home, those women with children not living at home, and those women who are childless, are given. Analyses of the data showed that women with children living at home were the least likely to claim retirement. Over the 2 years of data studied none of the three groups showed a change in their work status. The author feels that retirement is becoming a symbol of status, rather than a symbol that one has served in the workforce for many years and is now withdrawn
Keywords: Adult children; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

Undepressing Findings About Retirement - Morin, Richard; Deane, Claudia (Washington Post, 2002)
Keywords: Retirement Planning and Satisfaction

Wealth and the Timing of Retirement - Khitatrakun, Surachai (University of Wisconsin-Madison, Economics Department, 2002)
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Wealth Shocks and Retirement Timing and Other Essays - Purvi Sevak (Wealth Shocks and Retirement Timing and Other Essays, 2002)
This dissertation contains essays on two groups of individuals whose economic well being and behavior have received considerable attention in recent years: retirees and single mothers at risk of welfare receipt. Chapter 1 “Wealth Shocks and Retirement Timing: Evidence from the Nineties,” uses the 1992 to 1998 waves of the Health and Retirement Study (HRS) to find that exogenous increases in wealth lead to earlier retirement. Panel data on wealth and saving are used to estimate an elasticity of retirement flows between 1996 and 1998 with respect to wealth of 0.39 and 0.50 for men. Difference-in-differences regressions of retirement rates of individuals whose pension wealth depends on the stock market—individuals with defined contribution (DC) plans, to those whose pension wealth is not directly affected by the market—individuals with defined benefit (DB) pension plans, are also estimated. Consistent with wealth effects, significant increases in retirement rates are found among workers with DC plans. Chapter 2, “Local Fiscal Policy And Retiree Migration,” uses the 1992 to 2000 waves of HRS and town-level fiscal data from the Census of Governments, to examine whether moves by households near retirement age are motivated by local fiscal policy. The data show some evidence that movers lower their fiscal burden. Households that move across states the first time after their children have reached adulthood reduce their property tax liability by an average of $115. However, there is a great deal of heterogeneity across different types of movers. It is clear that while fiscal policy may factor into the move decision, it is just one of many variables upon which location choice by retirees is based. Chapter 3, “AFDC, SSI, And Welfare Reform Aggressiveness: Caseload Reductions Vs. Caseload Shifting,” uses pooled cross-sectional data from the 1986 to 1996 Current Population Survey (CPS) to examine whether reforms to the AFDC program that have made receipt of cash benefits more difficult for single mothers affected caseloads of the SSI program. Variation in state welfare reform over time shows that female-headed households in states pursuing welfare reform were 21.6 percent more likely to receive SSI.
Keywords: Demographics; Net Worth and Assets; Public Policy; Retirement Planning and Satisfaction

Wealth Shocks and Retirement Timing: Evidence from the Nineties - Purvi Sevak (Michigan Retirement Research Center Research Working Paper, 2002)
This paper explores whether the timing of retirement responds to unexpected changes in wealth. The period of the 1990s allows a unique examination of this question because of the large and unexpected capital gains realized by many households. Using the 1992 through 1998 waves of the Health and Retirement Study, and two different identification strategies, I find evidence consistent with the theoretical expectations of wealth effects for men. Using panel data on savings and wealth I estimate the elasticity of observed retirement flows between 1996 and 1998 with respect to wealth is between 0.39 and 0.50 for men.
Paper based on Chapter 1 of Purvi Sevak's Dissertation
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Who Expects to Continue Working After Age 62? The retirement plans of couples - Pienta, Amy M.; Mark D Hayward (The Journals of Gerontology: Social Sciences, 2002)
OBJECTIVES: This study examines the individual, spousal, and household characteristics associated with the retirement expectations of husbands and wives. METHODS: Using data from the 1992 Health and Retirement Study, subjective probabilities of working full-time after reaching age 62 and age 65 are used to measure retirement expectations. The retirement expectations of husbands and wives are modeled simultaneously using a joint-generalized least-squares approach. RESULTS: Within a marriage, retirement expectations are shaped by individual, spousal, and household characteristics. We observe some gender differences in cross-spousal influence with wives' retirement expectations being more influenced by husbands' resources and constraints than vice versa. Nonetheless, individual and household factors associated with retirement expectations are widely shared by husbands and wives. DISCUSSION: Husbands and wives both respond to individual and joint constraints and opportunities when planning for retirement. Findings support that there is considerable overlap in retirement planning of husbands and wives during early parts of the retirement decision-making process. However, inequity in cross-spousal influences is a defining characteristic of retirement decision making. Implications for both policy makers and practitioners are briefly discussed.
Keywords: Adult children; Demographics; Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction; Risk Taking

Workers Who Take Early Social Security Retirement Benefits - Julie M Zissimopoulos; Panis, Constantijn; Michael D Hurd (Washington, DC, RAND Labor and Population Program; Prepared for the Social Security Administration, 2002)
The objectives of this analysis are to shed light on the differences between workers who take early Social Security retirement benefits and those that postpone claiming, and to identify the types of individuals that would be particularly vulnerable to an increase in the Early Entitlement Age (EEA) above its current level of age 62. Generally speaking, we find workers who accept early retirement benefits are less likely to be college educated, less likely to be in management positions or to be professionals and more likely to have left the labor force before age 62. There are no large differences in financial wealth between Takers and Postponers, except for in pension wealth. Takers are much less likely to be covered by a pension plan and have lower pension wealth than Postponers. Moreover, while quite healthy on average, Takers are more likely to be in poorer health than workers who postpone benefits. This difference is particularly important for understanding the impact of raising the EEA. Individuals with a limited ability to continue working past age 62 due to health problems may experience substantial welfare losses in case of an increase in the EEA. Among a particularly vulnerable group of Takers, those in poor health and without pension entitlement, we find that more than half have a physically demanding job. These workers are particularly likely to apply for DI benefits in case of an increase of the EEA, which would add to rather than reduce total Social Security outlays.
RDA 2000-010
Keywords: Retirement Planning and Satisfaction; Social Security

Worklife Determinants of Retirement Income Differentials Between Men and Women - Phillip B. Levine; Olivia S. Mitchell; John W R Phillips (Innovations in Financing Retirement, 2002)
Women enter retirement having spent fewer years in market, earned less over their lifetimes, and work in different jobs than men of the same age. This study examines whether these differences in work life experiences help explain why many women end with lower level of retirement income in old age. We use Health and Retirement Study (HRS), which provide information on labor market histories along with the ability to predict retirement income from employer pensions, social security benefits, and investment returns. We document differences in anticipated retirement income by sex that exist largely between non-married men and women. Multivariate models show that 85 percent of this retirement income gap can be attributed to differences in lifetime labor market earnings, years worked, and occupational segregation by sex. Our results suggest that as women's work life experiences become more congruent with men's over time, the gap in retirement income between men and women may shrink.
RDA ProCite field 6 : In ProCite field 8 : eds.
Keywords: Income; Methodology; Retirement Planning and Satisfaction; Women and Minorities

Access to wealth among older workers in the 1990s and how it is distributed: Data from the Health and Retirement Study - R.V. Burkhauser; Robert R. Weathers II (Assets for the Poor: The Benefits of Spreading Asset Ownership, 2001)
Older American laborers' access to financial assets is investigated. Data from the Health and Retirement Study are analyzed to determine whether older workers had access to wealth and how financial assets were distributed among older working Americans. Three categories of wealth for older working Americans are identified: home equity, social security compensation, and employer pensions. Several findings regarding (1) the connection between wealth distribution, poverty, and income; (2) the occupational and racial characteristics of wealth deciles; (3) discrepancies in the asset holdings across wealth deciles; (4) changes in the wealth accumulation of older working Americans between 1992 and 1996; and (5) changes in income mobility over the same period. Several methodological recommendations for future research on wealth distribution are offered, eg, taking the size of one's household into consideration since the head of household may not have access to all of the household's wealth. 17 Tables, 1 Figure, 1 Appendix. J. W. Parker
RDA ProCite field 8 : eds.
Keywords: Demographics; Income; Net Worth and Assets; Retirement Planning and Satisfaction

Breast Cancer Survival, Work, and Earnings - Cathy J. Bradley; Bednarek, Heather; David Neumark (NBER Working Paper, 2001)
Relying on data from the Health and Retirement Study, we examine differences between breast cancer survivors and a non-cancer control group in employment, hours worked, wages, and earnings. Overall, breast cancer has a negative impact on the decision to work. However, among survivors who work, hours of work and, correspondingly, annual earnings are higher compared to women in the non-cancer control group. These findings suggest that while breast cancer has a negative effect on women's employment, breast cancer may not be debilitating for those who remain in the work force. We explore numerous possible biases underlying our estimates especially selection based on information in the Health and Retirement Study, and examine related evidence from supplemental data sources.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Medicare/Medicaid/Health Insurance; Methodology; Other; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Can Americans Maintain Pre-Retirement Consumption Standards in Retirement? - John Karl Scholz (University of Wisconsin-Madison, 2001)
Keywords: Consumption and Savings; Income; Retirement Planning and Satisfaction

Choice, Chance, and Wealth Dispersion at Retirement - Steven F Venti; David A Wise (Aging Issues in the United States and Japan, 2001)
RDA 1999-002 ProCite field 8 : eds.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Couples Approaching Retirement: The Organization of Pension Behavior within the Family - Kim Shuey (Couples Approaching Retirement: The Organization of Pension Behavior within the Family, 2001)
In this analysis I used Wave 1 of the Health and Retirement Study to explore how the utilization of pension opportunities intersects with family context. I examined how decisions about retirement savings are shaped by family structure and family dynamics. Structural explanations of pension opportunities take non-market factors such as family responsibilities into account only to the extent that they shape location in the labor market. However, like other decisions related to household resources and savings, many decisions regarding employer pensions occur within the context of the family and it is likely that they are influenced by the resources and behavior of other family members. This research is an initial attempt to incorporate spouse characteristics and household dynamics into explanations of pension behavior. The analyses show the importance of considering the interdependence of decision making among couple members when conducting analyses of financial behavior and pension participation. Results suggest that women, at least this cohort of women, are more influenced by their spouses than are men. Working women tended to coordinate pension decisions with their husbands in a manner that was consistent with or complimentary to the behavior of their husbands. This points to the importance of attending to the influence of the spouse on individual behavior, as well as gender differences in this influence, and the way in which power dynamics within the household filter the translation of individual preferences into individual behavior. The analyses also demonstrate the necessity of accounting for differences in individual preferences and "states of mind" in pension research, since preferences for planning and risk influenced pension participation. In addition, the analyses indicate that there are substantive reasons for making an analytic distinction between primary and supplemental participation. Results also show that the potential selection effects involved in modeling pension participation did not bias the estimates. Although the theoretical reasons for performing these corrections remain, little was gained analytically. In contrast, the analyses demonstrated the importance of acknowledging and correcting for the non-independence of observations when examining individual-level behavior with a sample that contains both members of a couple.
Keywords: Adult children; Demographics; End of life decisions; Pensions; Retirement Planning and Satisfaction

Does Retirement Education Teach Individuals to Save Pension Distributions? - Leslie A. Muller (Social Security Bulletin, 2001)
Keywords: Pensions; Retirement Planning and Satisfaction

Eddies in the Stream: The Prevalence of Uncertain Plans for Retirement - David J Ekerdt; Kyle J Hackney; Karl Kosloski; S. DeViney (The Journals of Gerontology: Social Sciences, 2001)
OBJECTIVE: This study examined an assumption of retirement theory that typifies older workers as preretirees who are planfully engaged in paths toward retirement. METHODS: Using survey responses among workers in the 1992 and 1994 waves of the Health and Retirement Study, we described the prevalence of nonsubstantive answers to questions about the expected form and timing of retirement (e.g., don't know, haven't thought about it ). We tested explanations for this uncertainty as an artifact of the survey process, but also as an outcome of the opportunity structure for retirement planning. RESULTS: Survey procedure did generate some of these noncommittal responses. Depending on question type, approximately 10 to 40 of workers did not state when or how they would retire, and such responses were less prevalent across age and time. In addition, categorical uncertainty about form and timing was theoretically predictable in a framework that supposed that workers less subject to a socially attended life--at work or away--would be more undecided about the future. DISCUSSION: Uncertainty is an authentic, meaningful stance toward retirement that theory and research design should not ignore. Just as actual transitions to retirement can be ambiguous or blurred, the expectation of retirement, as well, can be untidy.
Keywords: Demographics; Employment and Labor Force; End of life decisions; Health Conditions and Status; Healthcare; Methodology; Other; Retirement Planning and Satisfaction; Time Use

The Effect of Health on Employment Transitions of Older Men - David M. Blau; Gilleskie, Donna B. (Worker Wellbing in a Changing Labor Market, 2001)
ProCite field 6 : In ProCite field 8 : ed.
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

The Effects of Education on Retirement: A Continuity Perspective - Boeri, Miriam Williams (Southwest Journal on Aging, 2001)
Keywords: Demographics; Retirement Planning and Satisfaction

Elderly Labor Supply: Work or Play? - Steven Haider; Loughran, David (Boston College, 2001)
As the labor force has begun to retire at earlier ages and the population of the U.S. continues to age, people over the age of 65 that are still working have become a very important part of the economy. This study creates many questions that will allow the researchers to find out why some people over the age of 65 continue to work. Those elderly people that work past normal retirement age, somewhat surprisingly, are the ones that are most educated, wealthiest, and healthiest. At the same time these elder workers receive less compensation than younger workers and less compensation then they had in the past. Health was found to be the deciding factor in whether or not these elderly people stay in the workforce.
Keywords: Employment and Labor Force; Health Conditions and Status; Other; Retirement Planning and Satisfaction

Health Insurance on the Way to Medicare: Is Special Government assistance warranted? - Pamela F. Short; Dennis G. Shea; M. Paige Powell (The Commonwealth Fund, Publication 457, 2001)
The survey analyses described in this report are intended to help policymakers understand better the health insurance problems that confront Americans who are approaching age 65 and Medicare eligibility. A clear understanding of these problems is crucial to deciding whether or not to proceed with incremental coverage reforms for older, pre-Medicare adults. We had four specific research objectives: 1. To learn about the transitions in health insurance coverage experienced by older adults prior to age 65, especially as they relate to changes in employment and health; 2. To look at how well a policy allowing people to buy in to the Medicare program at age 62 (as proposed by former President Clinton and others) would compensate for the loss of employer-based insurance; 3. To see if there are compelling arguments, in addition to early retirement and the loss of employer coverage, to target older Americans in particular for coverage expansions; 4. To explore the empirical justification for targeting people age 62 and older, rather than setting eligibility for a buy-in at some other age. More generally, we wanted to produce a compendium of relevant statistics that would be useful to policy analysts and others who are considering coverage reforms for older Americans.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

How Do Couples Decide to Retire? - Courtney Coile (NBER, 2001)
Keywords: Adult children; Retirement Planning and Satisfaction

How Effective is Redistribution Under the Social Security Benefit Formula? - Alan L Gustman; Thomas L. Steinmeier (Journal of Public Economics, 2001)
In this study, data from the Health and Retirement Study linked to the Social Security Administration is used in order to analyze wealth redistribution by way of Social Security. This redistribution seems to go from the upper earners to the lower earners. More specifically, the wealth is being redistributed from men to women and, when looking at the household context, from primary earners to secondary earners. The study also illustrates wealth redistribution when specific factors are taken into account and show how much of an effect different variables have on the redistribution of wealth. From their analysis the authors conclude that privatizing the Social Security system would have no effect on redistribution of wealth.
RDA 1996-005
Keywords: Consumption and Savings; Income; Retirement Planning and Satisfaction; Social Security

Impact of Displacement on Older Workers - Steven Haider (Santa Monica, CA, RAND Corp, 2001)
We examine the impact of job displacement on older workers. Whereas previous studies focus on the earnings losses associated with displacement, we examine compensation losses more generally. Using the Health and Retirement Study, we measure the impact of a job loss on earnings, pension wealth, and health insurance. When pension and health insurance losses are incorporated to measure the overall impact of a displacement, the estimated total compensation loss increases by nearly 100 percent relative to the standard analysis that only examines earnings losses.
Keywords: Employment and Labor Force; Health Conditions and Status; Income; Insurance; Other; Retirement Planning and Satisfaction

The Impact of Involuntary Job Loss on Subsequent Alcohol Consumption by Older Workers: Findings from the Health and Retirement Survey - William T Gallo; Elizabeth H Bradley; Michele J. Siegel; Stanislav V Kasl (The Journals of Gerontology: Social Sciences, 2001)
OBJECTIVE: To estimate the effect of involuntary job loss on subsequent alcohol consumption by older workers in the United States. METHODS: Using longitudinal data from the 1992 and 1994 waves of the Health and Retirement Survey, the authors estimated multivariate models to assess the impact of involuntary job loss on subsequent alcohol use. Two outcomes were investigated: reported daily alcohol consumption and onset of drinking. The analysis sample included 207 workers who experienced involuntary job loss between survey dates and a comparison group of 2,866 continuously employed workers. RESULTS: After baseline alcohol consumption and a variety of socioeconomic and illness-related covariates were controlled, involuntary job loss was not associated (p .05) with number of daily drinks consumed at follow-up. However, among those who did not consume alcohol at baseline, individuals who suffered involuntary job loss were twice as likely as continuously employed individuals to start drinking by follow-up (OR = 2.01; CI = 1.06-3.80). The majority of those who began drinking at follow-up reported drinking less than 1 drink per day. DISCUSSION: The findings provide evidence of a significant relationship between job loss and subsequent alcohol use among baseline nondrinkers. However, the magnitude of the changes in drinking was quite modest.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Methodology; Other; Retirement Planning and Satisfaction; Risk Taking

Imperfect Knowledge, Retirement and Saving - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2001)
RDA 1996-005
Keywords: Pensions; Retirement Planning and Satisfaction

Income and Wealth Differentials of Late Middle-aged United States-born and Foreign-born Households in the United States: Implications for immigrant Social Security and retirement income - Rojanawon, Wichian (Boston College, 2001)
This study examines the economic resources and retirement outlook of older foreign-born individuals and their families in the United States. Past research indicates that immigrants experience some disadvantages compared to the U.S.-Born in the labor market due to migration and adjustment to a new culture as well as difficulty with the english language. Through the political economy and life course perspectives, stressing the importance of an individual's early experiences with the labor force, it is predicted that certain disadvantages will have an impact on retirement prospects as well as issues associated with old age. Nevertheless, there is a scarcity of research on the economic status of aging immigrants in the immigrant and retirement research, including the current research and discussion on social security reform. Research questions and hypotheses are addressed by using the Wave 1 of the Health and Retirement Study (HRS) and the HRS restricted data files. Findings from this study suggest that as a group, immigrants are likely to have low social security wealth and their income, assets and investment profiles are less than those of native-born counterparts are. Immigrants are also less likely to have employer-sponsored pensions and stock investment. If they do own stocks, the value of their holdings is likely to be much less. Recommendations for addressing policy, practice, and research efforts are presented with the goal of improving the economic conditions of aging immigrants who are at risk of poverty in old age.
Keywords: Demographics; Healthcare; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

Job Loss and Employment Patterns of Older Workers - Sewin Chan; Ann H. Stevens (Journal of Labor Economics, 2001)
This article uses data from the Health and Retirement Study to examine the employment patterns of workers aged 50 and above who have experienced an involuntary job loss. Hazard Models for returning to work and for exiting post displacement employment are estimated and used to examine work patterns for 10 years following a job loss. Our findings show that a job loss results in large and lasting effects on future employment probabilities. Four years after job losses at age 55, the employment rate of displaced workers remains 20 percentage points below the employment rate of similar nondisplaced workers.
ProCite field 3 : Rutgers U; Yale U
Keywords: Consumption and Savings; Employment and Labor Force; Retirement Planning and Satisfaction

Labor, Love and Leisure: Complementarity and the Timing of Retirement by Working Couples - Nicole Maestas (University of California, Berkeley (Dept. of Economics), 2001)
This paper develops and estimates a simple structural model for the joint determination of husband and wife retirement timing. I combine a standard lifecycle model with cooperative bargaining between spouses. Husbands and wives are assumed to have distince preferences between consumption and leisure, and to potentially value leisure more (or less) if their spouse is also retired. The model illustrates two mechanisms through which spouses' retirement decisions are interrelated: leisure complementarity and unequal decision-making power. The model is estimated using data for couples in the Health and Retirement Study who are both working at the start of the survey. The empirical results suggest that couples with greater leisure complementarity tend to retire together, or within a few years of each other. This effect is enhanced with the wife has greater decision-making power within the household. Relative to individualistic modles that ignore leisure complementarity and bargaining issues, the model provides a much better description of the actual distribution of joint retirement dates in the data.
RDA 2000-008
Keywords: Retirement Planning and Satisfaction

Medicare and Retirement Decisions - Richard W. Johnson (The Urban Institute, 2001)
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Modeling Retirement Behavior: A Test of the Option-Value Model Using the Health and Retirement Study - Harris, Amy Rehder (Congressional Budget Office, 2001)
This study outlines a latent variable model for consistently estimating the effects of health and other characteristics on the labor force transitions of older, working-aged adults. This model deals explicitly with both the potential endogeneity of global self-reported health measures and with the measurement error inherent in quantifying health status. We estimate the model using the longitudinal Health and Retirement Study and evaluate its properties by testing its underlying assumptions. We intend our results to inform work that uses the kinds of latent variable models we have been using in our own research as well as other research using the health variables available on the HRS.
RDA 1998-003
Keywords: Pensions; Retirement Planning and Satisfaction; Social Security

Planning for Retirement: The Accuracy of Expected Retirement Dates and the Role of Health Shocks - Debra S. Dwyer (Center for Retirement Research at Boston College Working Papers, 2001)
This paper illustrates the effect that unexpected health changes could have on a person s retirement decision and future. It is believed by the researchers that retirement age is something that a person decides over the course of their life by thinking of many factors that could influence their welfare in retirement. An economic model is designed in order to understand possible effects of different factors and health shocks on retirement age. Various policies and retirement plans are examined along with in-depth econometric and strategic models. Health prevailed as a key predictor in ones retirement decision. The occurrence of a shock in ones health normally forces the worker to retire sooner than had been anticipated. Net worth, social security, and pension plans are all important in making the initial retirement plan, but have little effect on the outcomes based on the plan.
Keywords: Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Products Of Clean Living - Williams, Marjorie (Washington Post, 2001)
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

Retiree Health Insurance and Labor Force Behavior of Older Men in the 1990s - David M. Blau; Gilleskie, Donna B. (Review of Economics and Statistics, 2001)
In this study the authors use behavioral and empirical models, along with data from Wave 1 (1992) and Wave 2 (1994) of the Health and Retirement Study, to gain an understanding of how changes in health insurance policies effect a persons decision to retire or continue working. It is hypothesized that older men who have employer-provided health insurance along with employer-provided retiree health insurance (EPRHI) are more likely to retire, as well as less likely to reenter the labor force or change jobs, than a similar person without EPRHI. From their models the author s observe that one s own EPRHI and one s spouses EPRHI are correlated with lower job changing, but not significantly. Older men and those with poor health are less affected by EPRHI than their younger or healthier counterparts. Also, EPRHI is associated with low labor force exit and higher labor force entrance, but not significantly.
Keywords: Employment and Labor Force; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Retirement and Wealth - Alan L Gustman; Thomas L. Steinmeier (Social Security Bulletin, 2001)
This article analyzes the relationship between retirement and wealth. Using data from the first four waves of the longitudinal Health and Retirement Study—a cohort of individuals born from 1931 to 1941—we estimate reducedform retirement and wealth equations. Our results show that those who retire earlier do not necessarily save more and that even if one’s primary interest is in the relationship between Social Security policy and the decision to retire, it is important to incorporate saving behavior and other key decisions into the analysis.
RDA 1996-005; Revision of NBER WP 8229
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

The Retirement Decision of Working Married Couples: A test of some competing hypotheses - Wang, Jianxin (State University of New York at Stony Brook, 2001)
This dissertation investigates the retirement decision of married couples. Using the longitudinal Health and Retirement Study (hrs), i test how well the stackelberg model of joint decision-making fit the data. I test several hypotheses regarding leadership role in the household. I also use sub-samples defined by cluster analysis to allow for heterogeneity in decision-making.
Keywords: Adult children; Employment and Labor Force; Other; Retirement Planning and Satisfaction

Retirement Incentives and Expectations - Sewin Chan; Ann H. Stevens (NBER Working Paper, 2001)
This paper investigates the relationship between expectations concerning retirement and incentives for retirement provided by employer-sponsored pension plans and Social Security. Measures of pension wealth and broader measures including earnings, Social Security, and assets are significantly related to individuals' expectations to continue work in their 60s. Results show that individuals strongly consider these incentives when planning for retirement. However, the degree to which these incentives affect behavior varies greatly between OLS and fixed-effects estimation strategies.
Keywords: Employment and Labor Force; Expectations; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Planning - Loughran, David; Panis, Constantijn (Washington, DC, RAND Labor and Population Program; Prepared for the Social Security Administration, 2001)
This report is concerned with two issues. First, it describes when individuals near retirement age plan to retire, and documents how their characteristics differ by planned retirement age. Second, it evaluates how accurately these individuals predict the timing of their retirement, and documents how good planners differ from poor planners. Consistent with earlier studies of retirement expectations, we demonstrate that retirement expectations in the HRS are closely correlated with many of the standard determinants of actual retirement. Broadly speaking, workers who expect to retire before age 62 tend to be wealthy and have generous pensions. Private pension incentives play an important role in determining retirement expectations. Individuals with private pensions are disproportionately represented among individuals expecting to retire early and, conditional on having a private pension, access to early pension benefits greatly increases the odds of planning an early retirement. Private pension wealth declines considerably with expected retirement age further suggesting that individuals are responsive to private pension plan incentives. There is little correlation between Social Security wealth and expected retirement age. There is strong evidence that spouses coordinate their retirement plans. The simple correlation between the expected retirement ages of husbands and wives is 0.43. Perhaps somewhat surprisingly, though, only 14 percent of couples expect the husband and wife to retire in the same year. In 50 percent of cases, husbands report that they expect to retire after their wives retire.
RDA 2000-010 Panis
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Retiring Together or Working Alone: The Impact of Spousal Employment and Disability on Retirement Decisions. - Richard W. Johnson; Melissa Favreault (Center for Retirement Research at Boston College Working Papers, 2001)
It is commonly the case that spouses retire at the same time as one another, however, this study examines the effect of one persons decision to retire, because of injury, on their spouses work decisions. Understanding the effects of injury related retirement on the work status of the spouse is of great importance to policy makers. This article focuses on retirement decisions and how they are influenced by spousal health and employment status. Mathematical models and interpretations are made in order to analyze the data. They noticed that a vast majority of women that worked for pay did so when their husband was also employed. When the husband retired voluntarily women were slightly less likely to stay employed. Differences in spousal employment, especially between classes, was greatest when the husband was under 62 and therefore not able to receive Social Security. Men were less likely to work if their wife was not working. If the husband retired involuntarily the wife was more likely then not to return to the workforce or continue to work.
RDA 1998-006
Keywords: Adult children; Retirement Planning and Satisfaction

Reversing Decades-Long Trend, Americans Retiring Later in Life - Walsh, Mary Williams (New York Times on the Web, 2001)
Keywords: Retirement Planning and Satisfaction

The Role of Micro-level Panel Data in Policy Research - R.V. Burkhauser; Smeeding, Timothy M. (Schmollers Jahrbuch: Zeitschrift fur Wirtschafts und Sozialwissenschaften/Journal of Applied Social Science Studies, 2001)
This paper focuses on the value of longitudinal micro-level data for policy centered research on behavioral and economic well-being. It provides examples of policy questions that can best be answered using such data and shows how they have been answered using data from four ongoing longitudinal panels--the BHPS (British Household Panel Study), the GSOEP (German Socio-Economic Panel), the HRS (Health and Retirement Study) and the PSID (Panel Study of Income Dynamics). Finally, it suggests a set of policy issues that can be considered using these data or from a national or a cross-national perspective.
ProCite field 3 : Cornell U; Syracuse U
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Methodology; Public Policy; Retirement Planning and Satisfaction

Should a Lump-Sum Payment Replace Social Security's Delayed Retirement Credit? - Orszag, Peter R. (Center for Retirement Research at Boston College Briefs, 2001)
Transforming Social Security’s delayed retirement credit into a lump-sum payment rather than an increased monthly payment would likely encourage more workers to defer retirement and benefit claiming. The idea is thus worthy of further exploration. Several important design issues, however, must be addressed before policymakers give serious consideration to the reform. The most problematic aspect of the proposal is that implementing a lump-sum payment system for individuals older than the normal retirement age may create political pressure to extend this approach to those who are younger than the normal retirement age. Such an extension would risk a significant increase in elderly poverty rates relative to the current Social Security system…
Keywords: Retirement Planning and Satisfaction; Social Security

Social Security Incentives for Retirement - Courtney Coile; Gruber, Jonathan (Themes in the Economics of Aging, 2001)
The 'tax effect' is one of the effects used to explain the rapid decline in the labor force participation of older men over age 62. This paper provides a thorough investigation of this 'tax effect' by studying it along four different dimensions. Using HRS data, the impact of SS retirement incentives are considered and the distribution of the incentives across the population is assessed. The paper then examines the role of private pensions and the importance of considering retirement incentives in the next year vs. considering incentives for all possible years.
ProCite field 8 : ed.
Keywords: Demographics; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

Two Essays Related to Labor Market Behavior: Demand for publicly provided job training programs in Illinois and Poor health, asset accumulation, and early retirement behavior - Miah, Mohammad Solaiman (Northern Illinois University, 2001)
Essay 1. This essay examines the determinants of the demand for public job training programs in Illinois. My first objective is to determine which personal characteristics influence support for an increase in spending on publicly provided job training programs for the unemployed across various income groups in Illinois. In particular, I empirically test for a u- shaped relationship between income and the demand for publicly-provided job training. My second objective is to examine the role of local economic conditions in determining the demand for job training programs. I use data from the 1995 Illinois policy survey supplemented with county- and regional-level data (including the unemployment rate, manufacturing employment, population density, and poverty rate). I do not find a u-shaped relationship between income and the demand for job training. However, I find that regional economic conditions, particularly the unemployment rate, the poverty rate, and population density, significantly influence the demand for job training programs in Illinois. In contrast, I find county-level economic conditions are not very influential. Essay 2. The purpose of this essay is to examine the impact of chronic health conditions on asset accumulation and retirement. Compared to a healthy worker, a person with a chronic health condition throughout his or her working life may have had reduced labor force participation and may have built a smaller portfolio of assets. Because this individual will have lower asset income than a healthy person, he or she will be less likely to retire, other things equal. Thus, chronic poor health may lead to opposing effects on the labor supply of the elderly. In my empirical analysis, I use data on adults aged 51-61 from the Health and Retirement Study (HRS) to study asset accumulation and retirement behavior of the chronically ill. I find that for 90% of individuals with chronic health problems, asset accumulation is sufficiently reduced to delay retirement. The needs of this group have not been addressed by researchers or policy makers discussing critical issues surrounding poor health and retirement.
Keywords: Education; Employment and Labor Force; Health Conditions and Status; Income; Net Worth and Assets; Other; Retirement Planning and Satisfaction

When Do You Retire? Here Are 6 Answers - Berger, Leslie (New York Times on the Web, 2001)
Keywords: Retirement Planning and Satisfaction

Why Some Workers Remain in the Labor Force Beyond the Typical Age of Retirement - Williamson, John B.; Tay K. McNamara (Boston College CRR Working Paper, 2001)
This study explored the ways in which race, gender, and age moderated the effects of several determinants of labor force participation among people ages 60 to 80. The role of race, gender, and age in moderating the effect of various factors on labor force participation was examined using the 1998 Health and Retirement Study (HRS) data. Binomial logistic regression models were used to evaluate the interaction between race, gender, age and other determinants of labor force participation. The effects of various factors on labor force participation differed by gender, race, and age. The negative effects of low education and poor health, respectively, were stronger for women and blacks. Also, the positive effect of low nonwage income was weaker for older workers, probably due partly to poorer health. Our findings suggest that different types of policies would help to encourage labor force participation among different groups. Because lack of access to employment may deter continued work among subgroups such as blacks and women with low education, job training or job search programs might provide incentives for employment in these groups. Additionally, employer flexibility regarding part-time work and work demands might make continued work attractive for more older workers.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Will the Aid You Need Be There for You? - Hughes, Mona (Orlando Sentinel, 2001)
Keywords: Healthcare; Retirement Planning and Satisfaction

A Benefit of One's Own: Older Women's Entitlement to Social Security Retirement - Phillip B. Levine; Olivia S. Mitchell; John W R Phillips (Social Security Bulletin, 2000)
Using data from the Health and Retirement Study (HRS) and linked administrative records, we explore differences in old-age benefits between men and women attributable to differences in length of work life and pay. We find that most women are fully insured for Social Security purposes, but those who are not would have to work substantially more to become eligible. Among those who are eligible, additional work would translate into only slightly higher benefits.
RDA 1996-006 ProCite field 3 : Wellesley College; U PA; US Social Security Administration
Keywords: Consumption and Savings; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction; Social Security; Women and Minorities

The Best of Both Worlds - Kunde, Diana (Chicago Tribune, 2000)
Keywords: Retirement Planning and Satisfaction

Consequences of Health Events: Economics and Behavioral Outcomes in the Health and Retirement Study - Tracy Falba (Consequences of Health Events: Economics and Behavioral Outcomes in the Health and Retirement Study, 2000)
ProCite field[9]:
Keywords: Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

'Decade of Behavior' project launched - American Psychological Society (University Record, 2000)
Keywords: Retirement Planning and Satisfaction

Does Mental Health Affect Transitions out of the Labor Force in Older Workers? - Linda A. Wray (American Sociological Association, 2000)
This paper extends earlier studies on health and work by examining how mental health affects transitions out of paid work in the years prior to the traditional Social Security retirement ages. Specifically, I investigate how mental health is linked to transitions to early retirement or other unemployed state in 1996 for middle-age adults who were currently working in 1992 and, in particular, whether deficits in mental health affect those transitions. To answer those questions, I use data from the first three waves of the Health and Retirement Study, a panel study of a nationally representative sample of Americans age 51-61 in 1992. Results of logistic regression analyses indicated that mental health had a strong and significant influence on the move from paid work to unemployment in three ways, net of other documented health, job, and socioeconomic correlates of work status: (1) Above-average self-assessed mental health predicted the transition from current worker to retiree. (2) Above -average mental health played a protective role in keeping workers in the work force rather than being laid off, on sick leave, or otherwise unemployed. (3) Increased CES-D depressive symptoms between 1992 and 1994 predicted exits from paid employment and into other unemployment by 1996. The results also indicate that mental health was an even more important predictor of transitions out of paid work among middle-age workers than were physical health and functioning.
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Early Retirement Windows - Charles Brown (Forecasting Retirement Needs and Retirement Wealth, 2000)
ProCite field 8 : eds
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Employer Provided Pension Data in the NLS Mature Women's Survey and in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (Research in Labor Economics, 2000)
RDA 1996-005
Keywords: Consumption and Savings; Employment and Labor Force; Income; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Forecasting Retirement Needs and Retirement Wealth - Olivia S. Mitchell; P. Brett Hammond; Anna M. Rappaport (University of Pennsylvania Press, 2000)
Thirteen papers draw on data from the Health and Retirement Study and from other sources to explore people's preparation for and the financial challenges of retirement in the United States. Papers discuss new paths to retirement; how prepared Americans are for retirement; projected retirement wealth and saving adequacy; individual savings and investment choices associated with 401(k) plans; factors explaining retirement savings shortfalls; women's economic well -being at the end of their work lives and the factors that appear to be associated with the poorer economic status of older women relative to older men; the prospects for widow poverty; minorities facing retirement; early retirement windows; the relationship between people's expectations about their retirement, their realizations of retirement, and the role of health shocks in this process; planning for health care needs in retirement; the evaluation of pension entitlements; social security earnings and projected benefits. Mitchell is at the Wharton School, University of Pennsylvania. Hammond is with the Teachers Insurance Annuity Association-College Retirement Equities Fund (TIAA -CREF). Rappaport is at William M. Mercer, Inc. Index.
RDA 1996-002 ProCite field 8 : eds.
Keywords: Consumption and Savings; Health Conditions and Status; Healthcare; Pensions; Retirement Planning and Satisfaction; Women and Minorities

Forecasting Retirement Needs and Retirement Wealth (Book Review) - Hardcastle, Peter; Pryor, Bob (The Actuary, 2000)
Keywords: Retirement Planning and Satisfaction

A Framework for Analyzing and Managing Retirement Risks - Olivia S. Mitchell; Zvi Bodie (University of Pennsylvania, 2000)
This paper provides an overview of new approaches and products to help people assess and meet their old-age security goals. We first examine retirement planning models and conclude that many do not yet incorporate key types of uncertainty deemed essential to economists and finance experts, including cross-asset correlations. Many financial planners also fall short of using the full range of tools of risk management – hedging, insurance, and diversification – to guide those making retirement plans. Turning to innovation, we examine several financial products that appear to offer new opportunities to protect against old-age risk. These products include inflation-linked annuities, survivor bonds, long-term care insurance, and reverse annuity mortgages. Some of the innovations arise from bundling existing insurance products. We also suggest that the arrival of new products to market that could protect retirement income have been slowed by market failures and institutional rigidities as well as information barriers; these have limited international diversification in investments, among other outcomes. There remains a profoundly important role for additional economic and financial research to better inform stakeholders on the costs and benefits of developing innovative products for retirement security
Keywords: Retirement Planning and Satisfaction

The Future of Age Integration in Unemployment - John C Henretta (The Gerontologist, 2000)
This article discusses the direction and implications of current and possible future trends in workplace age integration. The study used HRS respondents' attitudes towards work as a way of examining the possible supply of older workers. Overall, there are a number of underlying trends that will combine in the near future that will likely result in an increase of older persons remaining in the work force for longer. The shifting population age composition and the high education and ability levels of the cohorts born around 1950 are some of the trends that contribute to the increased demand for older workers. Other trends, such as changes in Social Security eligibility ages, the shift to DC pension plans, and the improving health of older cohorts, contribute to the increase in the supply of older workers. HRS data indicate that an overwhelming majority, 77 of men and 71 of women, say that they would like to continue some paid work when they retire. Evidence also suggests that since job flexibility among this cohort is limited, that either significant job changing from pre-retirement to postretirement jobs will be required, or significant job redesign must occur.
Keywords: Adult children; Demographics; Employment and Labor Force; Methodology; Other; Retirement Planning and Satisfaction; Social Security

Health Consequences of Marriage for the Retirement Years - Pienta, Amy M.; Mark D Hayward; Kristi Rahrig Jenkins (Journal of Family Issues, 2000)
Over the last few decades there has been an increasing trend toward divorce, postponed marriage, never marrying, and cohabitation. It is also known that marriage increases ones health, mainly because of the ability to gain from the help of a spouse or other relatives that transfer finances and time to the married person. How will changes in marriage trends effect the health of people as they reach retirement ages? What aspects of health are linked to marriage? Married persons from this data were the least likely to be afflicted by any of the diseases or limitations studied. Widowed and divorced persons were found to have the worst overall health of any two groups. However, cohabiting people were not much better off then the widowed or divorced persons. The authors also break down the data further and compare genders and races. Exiting marriage, surprisingly, was worse then never having been married.
Keywords: Adult children; Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

The Height of Success - Behar, Darren; Chapman, James (Daily Mail, 2000)
Keywords: Retirement Planning and Satisfaction

Heterogeneity in the Retirement Process: Patterns and Determinants of Labor Force Withdrawal Among Individuals with Low-Wage and Short-Duration Jobs - Kevin E. Cahill (Heterogeneity in the Retirement Process: Patterns and Determinants of Labor Force Withdrawal Among Individuals with Low-Wage and Short-Duration Jobs, 2000)
While the retirement patterns of full-time career individuals have been closely examined in the retirement literature, much less is known about the retirement behavior of low-wage individuals and those with non- traditional work histories. Knowledge of how these groups retire is crucial in evaluating the impact of pro-work policies on older americans. The first paper of this dissertation presents a two- period theoretical model of retirement with borrowing constraints in which individuals optimize lifetime utility subject to a budget constraint by choosing the intensity of work in and the duration of period one (the working period), and the level of consumption in both periods. The model predicts that individuals with binding borrowing constraints are more likely to exit the labor force early and work full time just before complete labor force withdrawal. The two empirical papers use a nationally representative sample of 12,652 older americans who are participating in the Health and Retirement Study. The first paper focuses on individuals in the bottom 20% of a year-specific, gender-specific wage distribution (low-wage); the second focuses on individuals who have not held a job lasting at least 10 years and consisting of 1600 or more hours per year (non-full-time career). Descriptive statistics show that low-wage individuals and non-full-time career individuals differ from others with respect to health status, race, marital status, wealth, and health insurance and pension coverage. Differences also exist regarding bridge job activity and the consequences of job transitions later in life. An empirical model of retirement yields three notable findings. First, key incentive variables remain significant when examining retirement determinants of both groups. Second, low-wage individuals appear less responsive to many retirement incentives. Third, the marginal impacts of key incentive variables are not significantly altered by the exclusion of non-full-time career individuals. This research suggests that decisions concerning pro-work policies should be made in light of possible heterogeneity in the retirement processes between these two groups and the rest of the population.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

How Effective is Redistribution Under the Social Security Benefit Formula? - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 2000)
This paper uses earnings histories obtained from the Social Security Administration and linked to the survey responses for participants in the Health and Retirement Study to investigate redistribution under the current social security benefit formula. When individuals are arrayed by indexed lifetime earnings, benefits are significantly redistributed from those with high lifetime earnings to those with low lifetime earnings. However, much of this apparent redistribution is from men to women, and when examined at the level of the family, from primary to secondary earners. When families are arrayed according the total lifetime earnings, and spouse and survivor benefits are taken into account, the extent of redistribution from families with high lifetime earnings to families with low lifetime earnings is roughly halved. When families are arrayed by their earnings potential, i.e., earnings during years when both spouses are engaged in substantial work, there is very little redistribution from families with high to low earnings capacity. Accordingly, at least for families on the verge of retirement day, introducing a system that ignored issues of redistribution would have no major effect on the distribution of social security benefits net of taxes among families with different earnings capacities.
Keywords: Consumption and Savings; Income; Retirement Planning and Satisfaction; Social Security

How Much Should Americans Be Saving for Retirement? - Bernheim, B. Douglas; Forni, Lorenzo; Gokhale, Jagadeesh; Laurence J. Kotlikoff (American Economic Review, 2000)
Deciding if HRS households are saving too much or too little cannot be determined from the data alone. However, by applying the ESPlanner to the data, the rate at which American households should be saving as they approach retirement can be determined. Households that are currently saving under the assumption that Social Security benefits will be paid in full are saving far too little. For all households besides the poorest ones in the sample, median recommended saving rates are fairly high because of the risk of major cuts in Social Security benefits.
Keywords: Demographics; Net Worth and Assets; Retirement Planning and Satisfaction

The Impact of 401(k) Plans on Retirement - Friedberg, Leora; Anthony Webb (University of California, San Diego, 2000)
In 1993 38.9 million people were covered by a 401(k) plan, up from 7.1 million in 1983. The rapid growth of 401(k) and other defined contribution pension plans may alter retirement patterns of older workers. Previous research showed that the spread of defined benefit plans, with sharp age-related incentives first discouraging and later encouraging retirement, contributed to the early retirement trend of past decades. Defined contribution plans differ along several dimensions, especially in their smooth rate of pension wealth accrual. We use data from the Health and Retirement Study to show that retirement patterns have begun to change as defined contribution plans have spread. Our estimates indicate that the financial incentives in defined benefit pensions lead people to retire almost two years earlier on average, compared to people with defined contribution plans.
ProCite field 8 : U VA and NBER; U CA, San Diego
Keywords: Employment and Labor Force; Pensions; Retirement Planning and Satisfaction

Micro Determinants of Labor Force Status Among Older Americans - Hugo Benítez-Silva (SUNY-Stony Brook, 2000)
This paper uses the first three waves of the Health and Retirement Survey (HRS) to investigate the determinants of labor force status among older Americans. Using transitions at two-year intervals we find that after being retired or unemployed, those who are actively searching for a job have a higher probability of returning to work. We also find that being in good physical and mental health measured by objective and subjective variables increases the chances of becoming employed, as does having worked in the last twelve months. Those who are receiving disability payments are less likely to make this transition. If we focus on those who are married, we find a preference for joint leisure through the influence of the labor force status, health and age of the respondent s partner on the transition decisions. We investigate transitions in and out of employment and self-employment, and for subsamples of males and females. Using monthly employment dummies for the period 1989-97, we analyze monthly, quarterly, semi-annual and annual transitions and find that most of our conclusions are independent of the periodicity but that the effects of the variables vary across specifications.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Minorities Face Retirement: Worklife Disparities Repeated? - Honig, Marjorie (Forecasting Retirement Needs and Retirement Wealth, 2000)
ProCite field[3]: CUNYProCite field[6]: InProCite field[8]: eds.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction; Women and Minorities

Modeling the Effect of Health on Retirement - John Bound; Michael Schoenbaum; Todd R. Stinebrickner; Timothy A Waidmann (National Bureau of Economic Research, 2000)
RDA 2000-007
Keywords: Health Conditions and Status; Retirement Planning and Satisfaction

New Paths to Retirement - Joseph F. Quinn (Forecasting Retirement Needs and Retirement Wealth, 2000)
ProCite field 8 : eds.
Keywords: Consumption and Savings; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

The Normative Anticipation of Retirement by Older Workers - David J Ekerdt; Karl Kosloski; Stanley DeViney (Research on Aging, 2000)
The scope of explanation for retirement behavior could be greatly enlarged by acknowledging workers' extended engagement with the question before the event - its givenness in their future and their course of action toward it. Evidence for such extended involvement is provided by survey responses of 2,575 male and 2,346 female US workers ages 51-61 in the 1992 Health and Retirement Study who saw themselves being within 15 years of retiring. To the extent that workers foresaw less time left at work, they reported more frequent thinking and talking about retirement. This pattern was quite general. The consideration given to retirement was, as expected, more frequent in circumstances that might orient workers toward the future. However, even absent these circumstances, subjective proximity still predicted the topicality of retirement. Widely held, albeit individual, timetables for retirement demonstrate its embeddedness in the subjective life course of older workers. 2 Tables, 1 Figure, 41 References. Adapted from the source document
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Patterns of Dissaving in Retirement - Steven Haider; Michael D Hurd; Reardon, Elaine; Williamson, Stephanie (AARP Public Policy Institute, 2000)
Abstract: Examined patterns of dissaving among households with at least one older adult. Data were obtained from the Social Security Administration's New Beneficiary Data System (NBDS) on older adults (mainly those aged 62-65) who received Social Security benefits for the first time in 1980-1981 and who were interviewed in 1982 and 1991. Data were also obtained from the 1993 and 1995 waves of the National Institute on Aging's Asset and Health Dynamics Among the Oldest Old (AHEAD) survey of adults aged 70 and older. Multivariate analyses indicated that changes in wealth were fairly flat in the 1980s (based on NBDS data), with mean wealth growing just under one percent per year for the 9 years of the sample period, while median wealth declined by about one-quarter of a percentage point per year. The AHEAD data from the 1990s suggest that most adults aged 70 and older enjoyed wealth increases, which in large part were due to the dramatic rise in stock prices over the 2 years of the survey period. Overall, there was increasing wealth inequality, with less well off households dissaving more rapidly than better off households. Households in which health declined between the waves studied were more likely to dissave. Savings patterns of households with and without children were fairly similar. Two appendixes provide information on the study methodology and additional data tables
Keywords: Consumption and Savings; Net Worth and Assets; Retirement Planning and Satisfaction

Pension Wealth at Midlife: Comparing Self-Reports with Provider Data - Richard W. Johnson; Sambamoorthi, Usha; Crystal, Stephen (Review of Income and Wealth, 2000)
This paper evaluates the accuracy of estimates of pension wealth based on self-reports by comparing them to estimates based on provider data. Using data from the Health and Retirement Study, we found that few workers are well informed about their future pension benefits. Self-reports were often incomplete and typically varied widely from those based on information from providers. In defined benefit (DB) plans, discrepancies were greatest for workers who had limited education, earned low wages, and did not expect to retire soon. Differences in median pension wealth were smaller at the aggregate level than the individual level, because individual differences tended to offset each other when aggregated. Provider data appear better than self-reports for DB plans, but not for defined contribution (DC) plans. Where both are available, the best method of computing pension wealth may be to estimate DB wealth from provider data and to estimate DC wealth from self -reports.
ProCite field 3 : Urban Institute; Rutgers U; Rutgers U
Keywords: Employment and Labor Force; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Prospects for Widow Poverty - David R Weir; Robert J. Willis (Forecasting retirement needs and retirement wealth., 2000)
ProCite field[8]: eds.
Keywords: Consumption and Savings; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Retirement Expectations and Realizations: The Role of Health Shocks and Economic Factors - Debra S. Dwyer; Hu, Jianting (Forecasting Retirement Needs and Retirement Wealth, 2000)
This chapter explores the relationship between peoples' expectations about retirement, their realizations of retirement, and the role of health shocks in this process. We look at how accurately people predict retirement and we examine the determinants of changes in retirement expectations. Expectations are made under uncertainty about future health, labor force status, household characteristics, and economic variables; therefore plans must frequently be updated with new information. While many factors influence the decision to retire, we are specifically interested in the role of health shocks in peoples' decisions to alter their plans to retire. Research to date has recognized the importance of understanding the relationship between health and retirement; however, until now, information about health, work, and economic well-being was difficult to obtain in a single survey. The Health and Retirement Study (HRS) is the first national survey to combine comprehensive data on all of these areas. Nevertheless much of the early HRS research has used only the first wave of data, at which time many in the cohort were too young to retire. In this chapter we use new information on this group of people from wave 2, enabling us to observe this cohort moving into retirement. In what follows we first offer a brief discussion of the literature, and then discuss empirical models, data used in the analysis, results and conclusions.
ProCite field 8 : eds.
Keywords: Expectations; Health Conditions and Status; Retirement Planning and Satisfaction

Retirement Outcomes in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (Social Security Bulletin, 2000)
This study examines retirement outcomes in the first four waves of the 1992 -98 Health and Retirement Study (HRS). The article compares outcomes under alternative definitions of retirement, describes differences in outcomes among demographic groups, compares retirement dynamics based on self-reported retirement status, and compares retirement flows in the 1990s and 1970s and between cohorts of the HRS. Among other findings, measured retirement is seen to differ, sometimes substantially, with the definition of retirement used and among the various groups analyzed.
ProCite field 3 : Dartmouth College; TX Tech U
Keywords: Consumption and Savings; Demographics; Retirement Planning and Satisfaction; Social Security

Retiring with a Difference - Kunde, Diana (London Free Press, 2000)
Keywords: Retirement Planning and Satisfaction

Saver Behavior and 401(k) Retirement Wealth - James M. Poterba; Steven F Venti; David A Wise (American Economic Review, 2000)
Contributions to 401(k) plans are now the most important form of retirement saving. Since 401(k) plans were introduced in the early 1980's, they have expanded rapidly and continuously. By 1998, roughly half of all households were eligible to participate in 401(k) plans, and more than 36 million workers made contributions to these employer-provided saving plans. In 1995, the last year for which the U.S. Department of Labor has released definitive data, 401(k) contribu- tions amounted to $87.4 billion, or 55 percent of all contributions to employer-sponsored pension plans. The level of contributions, and their share of all pension contributions, is probably signifi- cantly higher today. The spread of 401(k) plans is the most important indicator of the move to personal retirement saving. In 1980, almost 92 percent of pension-plan contributions were to tradi- tional employer-provided plans, and about 64 percent of these contributions were to conventional defined-benefit plans. Today, almost 60 percent of contributions are to personal retirement accounts, including 401(k), IRA, and Keogh plans. Including employer- provided, non-40 1 (k) defined-contribution plans, over 76 percent of contributions are to plans that are controlled in large measure by individuals. These individuals make partici- pation, contribution, asset-allocation, and withdrawal decisions. In this paper, we describe the likely impor- tance of 401(k) assets for future older Ameri- cans and the effect of investment decisions on asset accumulation. We also examine the extent to which retirement assets may be affected by several decisions: preretirement withdrawals, management fees and expenses, contribution rates, and early retirement. Our analysis focuses on 401(k) saving, but applies more broadly to other forms of individual retirement saving.
RDA 1999-002
Keywords: Consumption and Savings; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Scaling the Semantics of Satisfaction - Hazelrigg, Lawrence E.; Melissa A. Hardy (Social Indicators Research, 2000)
Self-assessed satisfaction is typically measured on an ordinal scale of verbal categories. Here, data from the 1992 Wave 1 of the US Health and Retirement Study (N = 12,654 respondents) are used to investigate whether the boundaries that persons implicitly set between contiguous categories are uniformly set across persons and/or across domains of satisfaction, or are variably sensitive to status characteristics and/or to domain. Analysis demonstrates systematic variations and sensitivities in the semantics of satisfaction. This semantic elasticity affects other estimates in models of self-assessed satisfaction. 3 Tables, 3 Figures, 43 References. Adapted from the source document
Keywords: Methodology; Retirement Planning and Satisfaction

Social Security and Retirement - Courtney Coile; Gruber, Jonathan (NBER Working Paper, 2000)
A critical question for Social Security policy is how program incentives affect retirement behavior. We use the wealth of new data available through the Health and Retirement Survey (HRS) to examine the impact of Social Security incentives on male retirement. We implement forward-looking models of retirement whereby individuals consider not just the incentives to work in the next year but in all future years as well. We find that such forward looking incentive measures for Social Security are significant determinants of retirement decisions. Our findings suggest that Social Security policies which increase the incentives to work at older ages can significantly reduce the exit rate of older workers from the labor force.
Keywords: Retirement Planning and Satisfaction; Social Security

Social Security Benefits of Immigrants and U.S. Born - Alan L Gustman; Thomas L. Steinmeier (Issues in the Economics of Immigration, 2000)
Immigrants realize higher Social Security benefits per year worked in the U.S. then U.S. born, even when earnings are identical in all years the immigrant has been in the U.S. The benefit formula favors those with low lifetime covered earnings, and the years prior to immigration are treated as years of zero earnings. If instead earnings were averaged only over years of residence in the U.S., and benefits were prorated based on the share of a 35 or 40 year base period spent in residence, immigrants would receive the same return on their social security taxes as U.S. born. For a sample from the Health and Retirement Study, a group born between 1931 and 1941, prorating reduces immigrants' social security benefits by 7 to 15 percent. For immigrants who entered in the 1980's, the reductions would be over 30 percent. Prorating would reduce the present value of benefit payments to immigrants born from 1932 to 1941 by 7.5 billion to 15 billion. Most immigrants will still pay slightly more in taxes than they will receive in benefits. Taxes received from immigrants who subsequently emigrate without collecting benefits tip the balance in favor of including immigrants.
RDA 1996-005 ProCite field 8 : ed.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Studies on the Relationship Between the Elderly and Public Policies - Harris, Amy Lenae (Studies on the Relationship Between the Elderly and Public Policies, 2000)
A number of important demographic phenomena--rising life expectancy, the post-war baby boom, and the subsequent baby bust--will have dramatic effects on the age distribution of the U.S. population well into the next century. In particular, the American population is aging. This dissertation looks at the relationships between two very different public policies and the aging population. The first relationship is a possible intergenerational conflict over public education spending at the local level. Previous research by Poterba (1997) shows a negative effect from aging on public education spending at the state level. Using school district data, the second chapter shows that at the local level the elderly also have a negative and statistically significant effect on per-pupil education spending; however, the district-level results are much smaller than previous state-level results. Several pieces of evidence are then presented to bolster my results which indicate that the elderly are much less likely to support increased spending at the state level than at the local level. The second relationship is the interaction between elderly retirement behavior and the largest federal public spending program, Social Security. To project the aging population's future claims for Social Security benefits, it is crucial to have a reliable model of retirement behavior which incorporates the incentives of the Social Security system. A promising model of retirement is the Stock and Wise (1990a) option-value model. Their structural retirement model predicts retirement behavior based on the forward-looking incentives created by social security and pensions. However, they estimated their model using an unrepresentative sample of 1,500 salesmen working for one large firm. The third chapter tests whether the Stock and Wise option-value model can be applied to a more representative sample of males from the Health and Retirement Study. When the option-value model is applied to the HRS sample, the model fails to yield economically meaningful parameters. My results suggest that additional work is needed to accurately model and project future retirement behavior of the growing elderly population.
Keywords: Demographics; Employment and Labor Force; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

The trend is to retire gradually - Kunde, Diana (Ottawa Citizen, 2000)
Keywords: Retirement Planning and Satisfaction

Women on the Verge of Retirement: Predictors of Retiree Well-Being - Phillip B. Levine; Olivia S. Mitchell; James Moore (Forecasting Retirement Needs and Retirement Wealth, 2000)
RDA 1996-002; Revision of Pension Research Council Working Paper 97-2 ProCite field 6 : In ProCite field 8 : eds.
Keywords: Retirement Planning and Satisfaction; Women and Minorities

The Adequacy of Household Saving - Engen, Eric M.; William G. Gale; Cori E. Uccello (Brookings Papers on Economic Activity, 1999)
This paper shows that, in a life-cycle simulation model in which people save for retirement and due to uncertain future earnings and lifespan, there will be a distribution of optimal wealth-earnings ratios, even among observationally equivalent households. Therefore even low levels of wealth can be consistent with optimization. Using HRS and SCF data, we find that more than half of married households where the husband works full-time have wealth -earnings ratios exceeding the optimal median simulated ratio for households with the same characteristics. The model understates accumulation among households with high wealth-earnings ratios. Both results suggest accumulation is adequate for most such households. However, there is evidence of undersaving at the 5th and the 25th percentiles. We also reconcile most previous studies that have been interpreted as showing inadequate household saving with our results.
RDA 1998-006
Keywords: Adult children; Consumption and Savings; Event History/Life Cycle; Income; Net Worth and Assets; Retirement Planning and Satisfaction

An Analysis of Retirement Expectations: Evidence from the US Health and Retirement Survey - Forni, Lorenzo (Bank of Italy, Public Finance Division Research Department, 1999)
Are people rational in making their retirement plans? Do they follow the prescriptions of life cycle theory in their decision of when to retire? This paper tackle these questions using data on expected and actual retirement age drawn from the 1992 and 1994 waves of the Health and Retirement Study.
Keywords: Event History/Life Cycle; Expectations; Retirement Planning and Satisfaction

Effect of Pensions on Saving: Analysis with Data from the Health and Retirement Study: A Comment - Rust, John (Carnegie Rochester Conference Series on Public Policy, 1999)
Keywords: Consumption and Savings; Employment and Labor Force; Income; Pensions; Retirement Planning and Satisfaction; Social Security

Employer Provided Pension Data in the NLS Mature Women's Survey and in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (National Bureau of Economics Research, 1999)
We compute pension wealth from employer provided pension plan descriptions matched to respondent surveys to the National Longitudinal Survey of Mature Women (NLS-MW) and the Health and Retirement Study (HRS). These calculations provide detailed information on the level and distribution of pension wealth and a variety of incentives from pensions. Differences between the pensions of men and women are largely explained by differences in earnings. However, there also are differences in the shapes of the pension accrual profiles of defined benefit plans that are likely to reflect tenure of women. Pension coverage is lower in the NLS-MW than in the HRS. As a result, wealth is lower in the NLS-MW than in the HRS. But the difference in coverage is not due to the effects of pension matching. Pension values for covered respondents are similar between the NLS-MW and HRS surveys. Systematic differences between the surveys in the rate at which pensions were matched do not have a major effect on findings as to the levels and distributions of pension wealth between the surveys.
Keywords: Consumption and Savings; Employment and Labor Force; Income; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Examining the Links Between Retirement and Health Insurance: Implications for Medicare Eligibility - Super Jones, Nora (1999)
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Housing America's Elderly Population - Shafer, Robert (Cambridge, MA, Harvard University, 1999)
Abstract: Examined the housing choices of older adults. Data were obtained from the Assets and Health Dynamics Among the Oldest-Old (AHEAD) survey on 8,222 adults aged 70 and older in 1993 and 6,047 housing units. It was found that 74.9 percent of older adults lived in conventional housing, 10 percent lived in shared housing, 6.6 percent in age-segregated housing, 5.5 percent in supported housing, and 2.9 percent in assisted living facilities. While geographic location and income had little effect on housing choices, educational attainment and net worth had significant influences. Older adults with higher educational attainment and higher net worth were more likely to favor conventional housing. While specific medical ailments had little effect on housing choice, the need for assistance with activities of daily living had a meaningful relationship with the decision.
Keywords: Housing; Retirement Planning and Satisfaction

The Importance of Accommodation on the Timing of Male Disability Insurance Application - R.V. Burkhauser; Butler, J.S.; Kim, Yang-Woo; Robert R. Weathers II (Journal of Human Resources, 1999)
Using data from the 1978 Survey of Disability and Work and the 1992 Health and Retirement Study, we test the importance of accommodation and other policy variables on the timing of application for Social Security Disability Insurance benefits following the onset of a work-limiting condition. We correct for choice-based sampling in the Survey of Disability and Work by extending the Manski and Lerman (1977) correction to the likelihood function of our continuous time hazard model, we find that this correction significantly affects the results. Similar findings emerge from these two data sets. Accommodation significantly reduces the speed of application and more generous benefits increase the speed of applying for SSDI.
RDA
Keywords: Disabilities; Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Influences on the Bridge Employment Decision Among Older USA Workers - Weckerle, Joelle R.; Kenneth S. Shultz (Journal of Occupational and Organizational Psychology, 1999)
This study examines four organizational and personal variables (voluntariness of retirement, organizational flexibility, pre-retirement planning, and anticipated financial rewards) to determine their influence on the retirement decisions of older workers. The retirement decisions being studied are: considering early retirement, continuing to work, or obtaining bridge employment either in the same job or a different job. Results indicate that anticipated financial reward, job flexibility, and voluntariness of retirement are all significant predictors that distinguish older workers in the four retirement decision groups. The implications of these findings for both workers and employers are discussed as well as some of the benefits of utilizing bridge employment as an option when considering early retirement decisions.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Information, Expectations, and Savings for Retirement - Annamaria Lusardi (Behavioral Dimensions of Retirement Economics, 1999)
RDA 1998-002ProCite field[3]: U ChicagoProCite field[8]: ed.
Keywords: Consumption and Savings; Event History/Life Cycle; Retirement Planning and Satisfaction

Job Loss and Retirement Behavior of Older Men - Sewin Chan; Ann H. Stevens (NBER Working Paper, 1999)
This paper uses data from the Health and Retirement Study to examine the employment and retirement behavior of men aged fifty and above who have experienced an involuntary job loss. Hazard models for returning to work and for exiting post-displacement employment are estimated and used to examine work patterns for ten years following a job loss. The findings show that a job loss results in large and lasting effects on future employment probabilities, and that these effects vary with the age of the worker. Displaced workers in their fifties are estimated to have a three in four chance of returning to work within two years after a job loss, whereas for a 62-year-old job loser, the probability is less than a third. Once re-employed, men 50 and above face significantly higher probabilities of exiting the workforce than do workers who have not experienced a recent job loss; however, the direction of this effect gradually reverses over time. The net outcome of these entry and exit rates is a substantial gap between the employment rates of men who have and have not lost jobs, that lasts at least seven years.
ProCite field 8 : Rutgers U; Yale U and NBER
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Lifetime Earnings, Saving Choices, and Wealth at Retirement - Steven F Venti; David A Wise (Wealth, work, and health: Innovations in measurement in the social sciences: Essays in honor of F. Thomas Juster, 1999)
RDA 1999-002 WiseProCite field[8]: eds
Keywords: Consumption and Savings; Event History/Life Cycle; Methodology; Net Worth and Assets; Retirement Planning and Satisfaction

Linkages with Data from Social Security Administrative Records in the Health And Retirement Study - Olson, Janice A. (Social Security Bulletin, 1999)
Keywords: Consumption and Savings; Disabilities; Health Conditions and Status; Retirement Planning and Satisfaction; Social Security

New Developments in the Economic Analysis of Retirement - Lumsdaine, Robin L.; Olivia S. Mitchell (Handbook of labor economics. Volume 3C, 1999)
ProCite field[3]: Brown U; U PAProCite field[8]: eds.
Keywords: Consumption and Savings; Employment and Labor Force; Pensions; Retirement Planning and Satisfaction; Social Security

Pension Type and Retirement Wealth - Blank, Emily C. (Industrial Relations, 1999)
Throughout the 1980s and 1990s there has been a gradual shift from defined-benefit pensions, where an individual obtains a specified amount of retirement income, to defined-contribution pensions, where only the annual contribution by the employer is specified. In this article the author hypothesizes that defined-contribution plans have a greater probability than defined-benefit plans of leaving a retired person with inadequate expected retirement income. Wave 1 (1992) of the Health and Retirement Study is used for the data that is input into the author s retirement wealth equation where retirement wealth is positive and a function of job tenure, age, sex, race, investment portfolio, and whether or not the individual was born in the U.S. The analysis gives some support for defined-benefit pensions being more affective, however this is true only for those still working. At the same time, so long as there is a cautious mix of stocks and bonds, the data clearly indicates that defined-contribution plans are beneficial to retired individuals. Also recognized by this study is that those people with the highest educations collect the most retirement benefits, keeping earnings constant.
Keywords: Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Perspectives on the household saving rate - William G. Gale; Sabelhaus, J.; Hall, R. E. (Brookings Papers on Economic Activity, 1999)
IN SEPTEMBER AND OCTOBER 1998, the personal saving rate as measured in the national income and product accounts (NIPAs) dipped below zero for the first time since the Great Depression. For the entire year, personal saving totaled just 0.5 percent of personal disposable income, the lowest rate since 1933. And in the advance estimate for the first quarter of 1999, the personal saving rate fell to –0.5 percent. These results are just the latest steps in the decline of the NIPA personal saving rate, which, after averaging 7.6 percent in the 1960s, 8.2 percent in the 1970s, 6.7 percent in the 1980s, and 4.8 percent in 1990–94, fell to 3.0 percent in 1996 and 2.2 percent in 1997. Although both academic publications and the popular press have repeatedly warned of a saving crisis over the last twenty years, the virtual disappearance of personal saving since 1998 has brought the issue back into the limelight.
Keywords: Restricted data; Retirement Planning and Satisfaction; Saving

Prospects for Social Security Reform - Olivia S. Mitchell; Myers, Robert; Young, Howard (Pension Research Council Publications, 1999)
Keywords: Older Adults; Retirement Planning and Satisfaction; Social Security

Retirees into golden years - Kunde, Diana (Dallas Morning News, 1999)
Keywords: Retirement Planning and Satisfaction

Retirement Patterns and Employee Benefits: Do Benefits Matter? - Fronstin, Paul (The Gerontologist, 1999)
This article investigates the impact of postretirement employee benefits on the likelihood that workers expect to retire before age 62 and age 65. Using data from the 1992 Health and Retirement Study, probit regression models were estimated to explore the effect of pension plans and retiree health insurance on the expectation of early retirement. With respect to pension plans, the effects of both the type of pension plan and the expected benefits from those plans are explored. Similar effects were explored for retiree health benefits. The results indicate that postretirement pension benefits and the availability of retiree health benefits have a significant influence on workers' retirement age expectations.
Keywords: Employment and Labor Force; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

Social Security, Pensions, and the Retirement Decisions of Individuals and Couples - Courtney Coile (Social Security, Pensions, and the Retirement Decisions of Individuals and Couples, 1999)
This thesis presents three empirical studies of Social Security, private pensions, and retirement decisions. Chapter 2 is a study of the retirement decisions of women and couples. Motivated by the fact that the typical household is a dual-worker family, this chapter addresses three issues. The first is the effect of retirement incentives from Social Security and pensions on women's retirement behavior. The second is the spillover effects of incentives on the retirement behavior of spouses. The third is the joint retirement decision-making of couples. Using the Health and Retirement Study (HRS), the retirement incentives from Social Security and pensions are calculated and reduced form models of the impact of each spouse's incentives on their own and spouse's retirement decisions are estimated, as well as two-stage models using incentives as instruments for retirement behavior. The principal findings are that women are as responsive to their own retirement incentives as men and that women's incentives have large spillover effects on men's behavior, while men's incentives do not. The latter result is attributed to asymmetric complementarities of leisure. Chapter 3, joint with Jonathan Gruber, examines the retirement decisions of men. This chapter also uses the HRS to compute retirement incentives and aims to overcome a lack of attention in previous work to dynamic incentives, to the separate effect of Social Security and pensions, to the identification of retirement impacts, and to data deficiencies. Forward-looking incentive measures are found to be more important in explaining behavior and policy simulations suggest that incentive effects may be large. Chapter 4, joint with Peter Diamond, Jonathan Gruber, and Alain Jousten, examines Social Security benefit claiming behavior. The key findings are that delays are optimal in a wide variety of cases, that a non-trivial share of early retirees delays at least one year, and that delays are consistent with cross-sectional predictions.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Social Security Reform: Implications of Raising the Retirement Age - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 1999)
Question: How might increases to the Social Security retirement age affect the solvency of the Old-Age Survivors Insurance, Disability Insurance, and Supplemental Security Income programs? Finding: Raising the Social Security early or full eligibility retirement ages could improve the OASDI balance sheet by reducing benefits paid out and increasing payroll taxes collected as well as contribute to economic growth as workers staying in the labor force for longer. However, this could lead to higher unemployment at younger ages and increases in applications for DI and SSI (among those who for health reasons are not able to stay in the labor force longer). Some portions of the population (e.g., less-healthy older workers and those in blue-collar occupations) may encounter difficulties remaining in the labor force. Recommendation: There is a need for greater understanding through further research on how to prevent effects of any changes from falling disproportionately on already-vulnerable populations.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction; Social Security

The Tail Ends: Hedging against old age and other natural catastrophes - James Moore (The Tail Ends: Hedging against old age and other natural catastrophes, 1999)
This dissertation is comprised of two essays examining two different topics that can be grouped under the rubric of risk management. The first examines estimation uncertainty and its implications for risk transfer at the corporate level and the price of that risk transfer. The second explores whether households are adequately preparing for the risks they face as they age. The past few years have seen the development and growth of traded securities with payoffs tied to natural and industrial disasters. Pricing the insurance features imbedded in these securities is difficult and imprecise. This lack of pricing precision translates to greater required return premiums to holders of these securities. The first essay explores the nature of pricing uncertainty for a number of datasets, security designs, and loss distributions using both jackknife and bootstrap techniques. The economic impact of pricing uncertainty is then briefly explored given comparisons of prices from secondary market trading to more common issues with similar risk characteristics and predictions from theoretical models. Using the Health and Retirement Study, the second essay explores asset holdings among a nationally representative sample of people on the verge of retirement. We assess how much more people would need to save in order to preserve consumption levels after retirement. We find that the median older household has current wealth of approximately $325,000 including pensions, social security, housing, and other financial wealth, an amount projected to grow to $380,000 by retirement at age 62. Nevertheless, our model suggests that this median household will still need to save 16% of annual earnings to preserve pre-retirement consumption. Delaying retirement to age 65, reduces required additional saving to 7% of earnings per year. These summary statistics conceals extraordinary heterogeneity in both assets and saving needs in the older population. Older high wealth households have 45 times more assets than the poorest decile and this disparity increases with age. There are also large differences in saving targets, ranging from 38% of annual earnings for those in the lowest wealth decile to negative rates for the wealthiest decile.
Keywords: Consumption and Savings; Healthcare; Other; Retirement Planning and Satisfaction; Risk Taking

This time, the concept of career change is personal - Kunde, Diana (Dallas Morning News, 1999)
Keywords: Retirement Planning and Satisfaction

Wealth Accumulation in the Health and Retirement Study: The Importance of Including Pension Wealth - Cori E. Uccello; Perese, Kevin (The Urban Institute, 1999)
RDA 1998-006
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Wealth, Work, and Health: Innovations in Measurement in the Social Sciences: Essays in honor of F. Thomas Juster - James P Smith; Robert J. Willis (University of Michigan Press, 1999)
Twelve papers, presented at a December 1996 conference at the Institute for Social Research (ISR), celebrating the career of F. Thomas Juster and his retirement from the University of Michigan and the ISR, focus on survey measurement and analysis of survey data in the social sciences. Papers discuss the several cultures of research on subjective expectations; measuring investment in young children with time diaries; the unfolding bracket method in the measurement of expenditures and wealth; lifetime earnings, saving choices, and wealth at retirement; inheritances and bequests; pension and social security wealth in the Health and Retirement Study; the size distribution of wealth in the United States as measured by recent household surveys; a cross -national comparison of health, work, and economic well-being of older workers aged fifty-one to sixty-one using the U.S. and Dutch data sets; labor market transitions and whether subjective probabilities of working have predictive power for actual retirement; the impact of education and heart attack on smoking cessation among middle-aged adults; the association of influenza vaccine receipt with health and economic expectations among elders; and co -residence between married adult children and their elderly unmarried mothers. Contributors include economists. Smith is at the RAND Corporation. Willis is at the University of Michigan and the Institute for Social Research. No index.
ProCite field 8 : eds.
Keywords: Consumption and Savings; Health Conditions and Status; Income; Methodology; Retirement Planning and Satisfaction

401(k) Plans and future patterns of retirement saving - James M. Poterba; Steven F Venti; David A Wise (American Economic Review, 1998)
This paper summarizes current participation and contribution patterns in 401(k) plans and projects 401(k) balances at retirement age for workers currently between the ages of 30 and 40. The various factors that will influence future 401(k) balances are discussed. The projections based on HRS data suggest that 401(k) plans are likely to play a significant role in providing for the retirement income of future retirees.
RDA 1999-002
Keywords: Employment and Labor Force; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction

An Analysis of the Choice to Cash-Out, Maintain, or Annuitize Pension Rights at Job Change or Retirement - Michael D Hurd; Lee A. Lillard; Panis, Constantijn (RAND, 1998)
Keywords: Pensions; Retirement Planning and Satisfaction

Anchoring Effects in the HRS: Experimental and Nonexperimental Evidence - Michael D Hurd (The National Bureau of Economic Research, 1998)
The Health and Retirement Study (HRS) and a number of other major household surveys use unfolding brackets to reduce item nonresponse. However, the initial entry point into a bracketing sequence is likely to act as an anchor or point of reference to the respondent. For example, when the initial entry point is high the distribution will be shifted to the right, leading one to believe that holdings of the particular asset are greater than they truly are. This paper analyzes some experimental data on housing value from HRS wave 3 for anchoring effects. The paper also compares the distributions of assets in HRS waves 1 and 2 for evidence about any anchoring effects that may have been caused by changes in the entry points between the waves. Both the experimental data on housing values and the nonexperimental data from HRS waves 1 and 2 on assets show anchoring effects.
ProCite field 8 : RAND Corporation and NBER
Keywords: Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Boomers May Go Bust - Russell, Cherly (American Demographics, 1998)
Keywords: Retirement Planning and Satisfaction

Can Americans Afford to Retire? New Evidence on Retirement Saving Adequacy - Olivia S. Mitchell; James Moore (Journal of Risk and Insurance, 1998)
This paper looks at the recent research regarding retirement wealth accumulation and decumulation and assesses whether Americans are doing a reasonable job of preparing for retirement, and spending down while in the retirement phase.
RDA 1996-002; HRS 1992
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Caring for Children and the Retirement Decision - Lumsdaine, Robin L. (Brown University Dept. of Economics, 1998)
Keywords: Adult children; Healthcare; Retirement Planning and Satisfaction

The Cause of Wealth Dispersion at Retirement: Choice or Chance? - Steven F Venti; David A Wise (American Economic Review, 1998)
RDA 1999-002 ProCite field 3 : Dartmouth College; NBER
Keywords: Income; Net Worth and Assets; Retirement Planning and Satisfaction

Effects of Pensions on Savings: Analysis with Data from the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier (NBER Working Paper, 1998)
This paper examines the composition and distribution of total wealth for a cohort of 51- to 61-year olds from the Health and Retirement Study (HRS), and the role of pensions in forming retirement wealth. Pension coverage is widespread, covering two-thirds of households and accounting for one-quarter of accumulated wealth. Social security benefits account for another quarter of total wealth. As calculated from earnings records, the present discounted value of social security benefits is less than the present value of taxes paid. Earlier than many expected, social security is already a poor investment on average for this cohort on the verge of retirement. When pensions and social security are included, wealth accumulated by the HRS population to date is substantial. At their expected retirement date, using only the wealth accumulated by their mid-fifties, the HRS household with median replacement rate could finance a fixed, nominal two-thirds joint and survivor annuity replacing 79 percent of last earnings, and a real annuity replacing 52 percent of last earnings. Replacement rates for median earners are higher. Additional savings made over the seven years remaining until retirement will raise those replacement rates by about a fifth. When measured against a standard of adequacy based on average yearly earnings over the worklife, with adjustments made for the absence of preretirement savings, children, taxes, work-related expenses and other factors, these replacement rates appear adequate. Lifetime earnings are measured for each individual in the HRS from social security earnings records augmented by self-reported earnings histories. When pensions and social security are counted in total wealth, the ratio of wealth to lifetime earnings declines from very high levels in the bottom ten percent of the earnings distribution, remains at roughly 40 percent from the 25th through 95th percentile of the lifetime earnings distribution, and then falls to 32 percent for those in the top five percent of the earnings distribution. This result is consistent with the predictions of a simple, stripped-down life-cycle model. Also consistent is a finding that the ratio of wealth to lifetime earnings is no higher for those with pensions than for those without pensions. However, heterogeneity is quite important. Real estate and business wealth are a larger share of total wealth for those without pensions, reflecting the importance of self-employment in wealth accumulation. Multivariate regressions relating total wealth to pension coverage and pension value, which standardize for sources of heterogeneity, suggest that pensions cause very limited displacement of other wealth, if any. Pensions add to total wealth by at least half the value of the pension, and in most estimates by a good deal more. These findings are not consistent with a simple life-cycle explanation for savings. They also raise questions about whether pensions are fundamentally a tax avoidance device, allowing substitution of pension for nonpension savings.
RDA 1996-005 ProCite field 8 : Dartmouth College and NBER; TX Tech U
Keywords: Adult children; Consumption and Savings; Employment and Labor Force; Income; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Household Wealth of the Elderly under Alternative Imputation Procedures - Hoynes, Hilary; Michael D Hurd; Chand, Harish (Inquiries in the economics of aging, 1998)
Although many reach retirement with few resources except housing equity and a claim to social security and Medicare, financial wealth, nonetheless, makes an important contribution to the economic status of many of the elderly. Most of our up-to-date information about the wealth of the elderly is based on the Survey of Income and Program Participation (SIPP), which sometimes adds an asset module to its core survey. As in many surveys of assets, the rate of missing data on individual asset items is high, about 30 to 40 percent among those with the asset. This raises the issue of the reliability of SIPP wealth measures because respondents who refuse or are unable to give a value to an asset item may not be representative of the population. Indeed, in the Health and Retirement Survey (HRS) it is clear that asset data are not missing at random. Through the use of bracketing methods, which we will discuss below, the HRS was able to reduce the rate of missing asset data substantially, and the data that were added in this way increased mean wealth in the HRS by about 40 percent (Smith 1995). Furthermore, because the additional data increased the mean so much, they undoubtedly increased measures of wealth inequality.
ProCite field[3]: U CA, Berkeley and NBER; SUNY, Stony Brook, RAND, and NBER; U CA, Berkeley
Keywords: Consumption and Savings; Demographics; Income; Net Worth and Assets; Retirement Planning and Satisfaction

The Influence of Push and Pull Factors on Voluntary and Involuntary Early Retirees' Retirement Decision and Adjustment - Kenneth S. Shultz; Morton, Kelly R.; Weckerle, Joelle R. (Journal of Vocational Behavior, 1998)
This paper examines early retirees' decisions to retire, as well as their postretirement adjustment, in terms of both push (negative considerations: e.g., poor health) and pull (positive considerations: e.g., leisure interests) factors. Results confirm the hypothesis that both negative push and positive pull factors differentially influenced those retirees who voluntarily retired and those forced to retire. After retirement, the negative push factors became the more salient differentiators; those forced to retire appeared to have generally lower self ratings of physical and emotional health and lower satisfaction rates. In addition, the findings suggest that the way an individual views their retirement decision is related to their postretirement experience: those who viewed their retirement decision as voluntary reported higher satisfaction and health levels during retirement than those who viewed their retirement as involuntary.
Keywords: Adult children; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

Married Women's Retirement Expectations: Do Pensions and Social Security Matter? - Honig, Marjorie (American Economic Review, 1998)
ProCite field 3 : Hunter College and Graduate School, CUNY
Keywords: Methodology; Pensions; Retirement Planning and Satisfaction; Social Security; Women and Minorities

The Microeconomics of the Retirement Decision in the United States - Joseph F. Quinn; R.V. Burkhauser; Kevin E. Cahill; Robert R. Weathers II (1998)
Keywords: Methodology; Retirement Planning and Satisfaction

Moving the Nest: A Look at the Effects of Family and Work Status Change in Later Mid-Life - Regina M. Bures (University of Chicago - Population Research Center, 1998)
Using data from the first two Waves of the Health and Retirement Survey (HRS), this research examines the relationship between migration, family change, and work status change in later mid-life. The results suggest that both family and work status change have significant effects on mobility in later mid-life. The findings for work status change appear consistent with theories of labor force migration: Individuals who worked full-time at both waves were significantly less likely to move long distances than nearly every other group. Departure from the labor force increased the likelihood that an individual experienced a move, either locally and interstate. Changes in the number of adult children resident in a household are found to have strong and significant effects on mobility in later mid-life. Adult children returning home are positively associated with both local and interstate moves. Children leaving home have an even greater impact on mobility. A previously unreported finding is that adult children leaving home have a significant positive effect on long-distance mobility. These findings extend the migration literature by seeking to explain mobility and migration in the context of family and work change over the life course.
Keywords: Adult children; Demographics; Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Partners in Marriage: An Analysis of Family Effects and the Likelihood of Retirement - Pienta, Amy M. (Penn State University Population Research Institute, 1998)
Keywords: Adult children; Retirement Planning and Satisfaction

Reasons for Retirement: Antecedents and Consequences - Stetz, Thomas Andrew (Reasons for Retirement: Antecedents and Consequences, 1998)
Data from the first wave of the Health and Retirement Study (HRS) were analyzed to determine the underlying structure of the reasons for retirement and to determine if the reasons for retirement were related to subsequent retirement adjustment. The results suggested three types of reasons for retirement, work reasons, personal reasons, and family reasons. The results also showed that retirement because of poor health was the only reason for retirement that was related to the physical and emotional well-being of subsequent retirement.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

Retiree Health Benefits and Retirement Behavior: Implications for Health Policy - Lynn A Karoly; Jeannette Rogowski (Washington, DC, U.S. Dept. of Labor, 1998)
Keywords: Healthcare; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Social Security Reform: Raising Retirement Ages Improves Program Solvency but May Cause Hardship for Some - United States General Accounting Office (U.S. General Accounting Office, 1998)
Question: Evaluate the proposals before Congress to reform and improve the solvency of the Social Security system. Finding: Using the NIA-funded Health and Retirement Study, GAO found that raising the Social Security retirement ages could improve long-term solvency for the program by increasing revenues and reducing benefits, but it is unclear whether employers will be willing to retain or hire older workers. Older blue-collar workers may be adversely affected because they are at risk for certain health problems that limit their ability to continue working.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

Symposium on Work, Retirement and Wealth: Current Data and Future Needs: An International Perspective - R.V. Burkhauser; Robert Clark; Richard M. Suzman (Australasian Journal on Ageing, 1998)
Discusses a cross-national symposium on elderly work, retirement, and wealth that drew on the US Health and Retirement Study and Panel Study of Income Dynamics, the Netherlands Household Panel Study, the German Socioeconomic Panel, and several East and Southeast Asian datasets.
Keywords: Demographics; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

Why There Are Differences in Retirement Income by Race in America - Hill, Tomeka (Watson Wyatt Worldwide, 1998)
Keywords: Income; Retirement Planning and Satisfaction

Applications to the US Disability Program: A Semiparametric Approach - Riphahn, Regina T.; Kreider, Brent (1997)
This study investigates the determinants of applications for U.S. disability benefits between 1986 and 1993 using a semiparametric discrete factor procedure. Approximating a dynamic optimization model, the estimation carefully accounts for a variety of potential biases that were not addressed in previous studies. Our results indicate vast differences in the responses of men and women to variations in policy measures. Past labor earnings and fringe benefits as well as benefit eligibility and benefit amounts clearly affect application behavior.
ProCite field 8 : U Munich; U VA
Keywords: Disabilities; Retirement Planning and Satisfaction; Social Security

Building Better Retirement Income Models - Bone, Christopher M.; Olivia S. Mitchell (North American Actuarial Journal, 1997)
There is a strong and immediate need to collect more data and to construct better retirement income policy models. In the very near future, changes must be made to the U.S. retirement policy. These changes and the policy itself will only be effective if it is based on strong retirement models. The article describes recent efforts and developments that may interest those concerned with retirement issues. The HRS is praised for its ability to obtain the necessary information on older workers that has for so long been missing from the field of retirement research.
Keywords: Methodology; Retirement Planning and Satisfaction

The Effect of Health on Employment Transitions of Older Men - David M. Blau; Gilleskie, Donna B.; Slusher, Chuck (Chapel Hill, NC, UNC-Chapel Hill, Department of Economics, 1997)
Keywords: Employment and Labor Force; Health Conditions and Status; Retirement Planning and Satisfaction

Gender Privilege in Retirement Planning and Saving - Scott, Megan Mary (Gender Privilege in Retirement Planning and Saving, 1997)
This dissertation combines qualitative and quantitative methods to explore how husbands and wives divide and share retirement planning and saving. The qualitative analysis focuses primarily on testing hypotheses about how class, marital power and gender enactments influence the division of saving and financial planning activities over the lifecourse. Interviews with retired couples and ethnographic data from financial planning seminars comprise the qualitative portion of the thesis. The quantitative sections are based on a secondary analysis of data about 2451 working couples from the 1992 wave of the Health and Retirement Study which tested these hypotheses. The qualitative findings suggest that wives' savings activities--to 'stretch' household resources, like domestic labor--are undervalued. In contrast, husbands' activities--to grow and monitor accumulated reserves--are valued, often eclipsing the labor of other household members. Upon retirement, these male activities become even more salient as they replace male 'breadwinning.' Additionally, in many middle class households, the husband's earnings contribute to 'primary retirement reserves' while wives' earnings are earmarked for 'secondary savings.' The quantitative analysis indicates that balance of marital power (as resource theory suggests) influences which spouse will handle family finances, particularly for black couples. However, wives relatively lower levels of retirement planning and disadvantaged knowledge of discretionary savings reserves can not be explained by the balance of relative earnings
Keywords: Adult children; Consumption and Savings; Healthcare; Retirement Planning and Satisfaction; Women and Minorities

Health Insurance and Retirement Behavior: Evidence from the Health and Retirement Study - Lynn A Karoly; Jeannette Rogowski (RAND, 1997)
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

On the Measurement of Expectations, Uncertainty, and Preferences - Juster, F. Thomas (The Journals of Gerontology: Social Sciences, 1997)
Keywords: Demographics; Employment and Labor Force; Expectations; Healthcare; Retirement Planning and Satisfaction

New Evidence on the Money's Worth of Individual Annuities - Olivia S. Mitchell; James M. Poterba; Mark J. Warshawsky (NBER Working Paper Series, 1997)
This paper presents new information on the expected present discounted value of payouts on individual life annuities. The annuity we examine is the single premium immediate life annuity, an insurance product that pays out a nominal level sum as long as the covered person lives, in exchange for an initial lump-sum premium. This annuity offers protection against the risk of someone outliving his saving, given uncertainty about longevity. For reasonable estimates of behavioral parameters, we calculate that individual annuities are currently priced so that retirees without bequest motives should find these policies of substantial value in configuring their portfolios to smooth retirement consumption. We also find that the expected present discounted value of payouts, relative to the initial cost of the annuity, has increased over the last decade. These findings bear on the policy debate regarding the role of individual choice and self-reliance in retirement planning.
Keywords: Annuitization; Economics; Retirement Planning and Satisfaction

Pension and Social Security Wealth in the Health and Retirement Study - Alan L Gustman; Olivia S. Mitchell; Andrew A. Samwick; Thomas L. Steinmeier (National Bureau of Economic Research, 1997)
Together, pensions, social security and health insurance account for half of the wealth held by all households in the Health and Retirement Study (HRS), for 60 percent of total wealth of HRS households who are in the 45th to 55th wealth percentiles, and even for 48 percent of wealth for those in the 90th to 95th wealth percentiles. The HRS surveys households aged 51 to 61 in 1992, and obtains pension plan descriptions from respondents' employers. Pension accrual profiles, income and wealth distributions by type, wealth-income ratios and accrued wealth by pension status are also explored.
ProCite field 8 : Dartmouth College and NBER
Keywords: Consumption and Savings; Income; Medicare/Medicaid/Health Insurance; Methodology; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Preference Parameters and Behavioral Heterogeneity: An Experimental Approach in the HRS - Barsky, Robert; Miles S Kimball; Juster, F. Thomas; Matthew D. Shapiro (Quarterly Journal of Economics, 1997)
This paper reports measures of preference parameters relating to risk tolerance, time preference, and intertemporal substitution. These measures are based on survey responses to hypothetical situations constructed using an economic theorist's concept of the underlying parameters. The individual measures of preference parameters display heterogeneity. Estimated risk tolerance and the elasticity of intertemporal substitution are essentially uncorrelated across individuals. Measured risk tolerance is positively related to risky behaviors, including smoking, drinking, failing to have insurance, and holding stocks rather than Treasury bills. These relationships are both statistically and quantitatively significant, although measured risk tolerance explains only a small fraction of the variation of the studied behaviors.
Keywords: End of life decisions; Health Conditions and Status; Retirement Planning and Satisfaction

Profile of Older Americans: Report One - M. Kristen Peek (Tampa, FL, The Florida Policy Exchange Center on Aging, University of South Florida, 1997)
Keywords: Demographics; Retirement Planning and Satisfaction

Projected Retirement Wealth and Savings Adequacy in the Health and Retirement Study - James Moore; Olivia S. Mitchell (National Bureau of Economic Research, 1997)
Low saving rates raise questions about Americans' ability to maintain consumption levels in old age. Using the Health and Retirement Study, this paper explores asset holdings among a nationally representative sample of people on the verge of retirement. The authors assess how much more people would need to save in order to preserve consumption levels after retirement. They find that the median older household has current wealth of approximately 325,000 including pensions, social security, housing, and other financial wealth, an amount projected to grow to about 380,000 by retirement at age 62. Nevertheless, their model suggests that this median household will still need to save 16 of annual earnings to preserve pre-retirement consumption. For retirement at age 65, assets are expected to be 420,000 and required additional saving totals 7 of earnings per year. These summary statistics conceal extraordinary heterogeneity in both assets and saving needs in the older population.
RDA ProCite field 8 : Wharton School; Wharton School and NBER
Keywords: Consumption and Savings; Health Conditions and Status; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Retirement Trends and Patterns in the 1990s: The End of an Era? - Joseph F. Quinn (The Public Policy and Aging Report, 1997)
This article documents the dramatic change in retirement trends of the mid-1980's, mentions some of the contributing factors that may have lead to the change, and discusses some preliminary research on the nature of retirement patterns in the 1990's. Results show that both older men and women are working much more now than the pre-1985 retirement trends would have predicted. HRS data emphasizes that retirement patterns in America are varied and confirms the importance of gradual retirement, especially bridge jobs, to the retirement process of the 1990s.
Keywords: Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

The Role of Bridge Jobs in the Retirement Patterns of Older Americans - Joseph F. Quinn (Social Policy and the Labour Market, 1997)
ProCite field 8 : eds.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Social Security Reform: Implications for Women s Retirement Income - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 1997)
Question: evaluate (1) why women s benefits are lower than men s under the current Social Security system, (2) the possible differential effects on women of the new privatization reform proposals, and (3) what can be done to minimize the possibly negative effect on women of certain elements of the Social Security reform proposals. Finding: Using the NIA-funded Health and Retirement Study, as well as citing some research conducted by NIA-funded grantees, GAO noted that women s Social Security benefits are often lower than men s due to lower wages and fewer years in the workforce. Some of the proposals to reform Social Security by shifting responsibility of saving for retirement to individuals via accounts funded as a proportion of their salary could make the difference between men s and women s benefits worse. For example, greater risk aversion among women could lead to lower investment returns; further, women could face substantially lower benefits (and hence a lower likelihood of retirement income adequacy) if annuitization formulae take their longer life expectancy into account. Recommendation: Improve information about investment objectives and financial planning to reduce differences in investment strategy and improve retirees ability to manage their assets. Consider mandatory annuitization to reduce the possibility of individuals outliving their savings. Use unisex lifetables to ensure those with comparable savings at retirement have comparable monthly benefits.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Socioeconomic Status and Racial and Ethnic Differences in Functional Status Associated with Chronic Diseases - Raynard Kington; James P Smith (American Journal of Public Health, 1997)
OBJECTIVES: This study examined the relationships between wealth and income and selected racial and ethnic differences in health. METHODS: Cross-sectional data on a national sample of 9744 men and women aged 51 through 61 from the 1992 Health and Retirement Survey were analyzed to examine the association between socioeconomic status and racial and ethnic differences in functional status among those with hypertension, diabetes, a heart condition, and arthritis. RESULTS: Compared with Whites, African Americans report higher rates of hypertension, diabetes, and arthritis, while Hispanics report higher rates of hypertension and diabetes and a lower rate of heart conditions. Accounting for differences in education, income, and wealth had little effect on these prevalence differences. In general, among those with chronic diseases, African Americans and Hispanics reported worse function than Whites. This disadvantage was eliminated in every case by controlling for socioeconomic status. CONCLUSIONS: While socioeconomic status, including wealth, accounts for much of the difference in functional status associated with these chronic diseases. It plays a relatively small role in explaining differences in the prevalence of chronic disease, possibly reflecting different causal pathways.
Keywords: Demographics; Health Conditions and Status; Income; Methodology; Other; Retirement Planning and Satisfaction; Women and Minorities

Changes Over Time in Subjective Retirement Probabilities - Honig, Marjorie (University of Michigan, 1996)
Reliable forecasts of future retirement patterns are of obvious importance in formulating public policy. The predictive value of workers' expectations regarding retirement depends, however, on whether expectations are reliable indicators of future retirement, conditional on the information available at the time that expectations are formed. Using workers' responses in the U.S. Health and Retirement Survey about the chances of working after age 62, this paper provides some tentative answers to two important questions regarding retirement expectations: Does there appear to be a high random component to expectations regarding future retirement and, if not, does the same behavioral model that generates retirement realizations seem to generate retirement expectations as well? Findings on changes in reported expectations between Waves 1 and 2 of the HRS suggest that expectations may well provide useful information about future retirement.
Keywords: Expectations; Retirement Planning and Satisfaction

Income and Wealth of Older American Households: Modeling Issues for Public Policy Analysis - Alan L Gustman; Juster, F. Thomas (Assessing Knowledge of Retirement Behavior, 1996)
This paper evaluates the extent to which current knowledge of retirement, savings, pension and related behavior is sufficient for determining the effects of major policy initiatives on the incomes and wealth of the aged population of the United States. Data are presented from two new surveys, the Health and Retirement Study and the Asset and Health Dynamics Among the Oldest Old Survey, describing the distributions of the major components of income and wealth to be explained by these behavioral models. The data suggest that the amount of wealth had by the older population has been severely understated in earlier surveys. Disagreements and inconsistencies in models of savings indicate that there is no agreed upon behavioral model upon which to base policy analysis. Similar problems characterize the pension literature. Most strikingly, central features of these three major branches of behavioral analysis are mutually inconsistent. Although there are important linkages among the behaviors determining retirement, savings and pension outcomes, research in each area ignores or misspecifies the related behavior from other areas. Consequently, significant advances are required before we can confidently predict the effects of contemplated changes in policies on income and wealth in retirement.
ProCite field 6 : In ProCite field 8 : eds.
Keywords: Consumption and Savings; Pensions; Retirement Planning and Satisfaction

Profiling Plans for Retirement - David J Ekerdt; Stanley DeViney; Karl Kosloski (The Journals of Gerontology: Series B, 1996)
Actual decision making for retirement is largely inaccessible to investigation, yet research can focus on plans as a window into the preretirement process. This article proposes a construct that profiles five generic types of retirement plans, including plans to retire completely, change jobs, never retire, and uncertainty about retirement. The heuristic value of the construct lies in its recognition of the heterogeneity of retirement intentions. The five plan types were operationalized among workers aged 51-61 in the 1992 Health and Retirement Study. Convergent validity was demonstrated by comparisons to analogous survey questions. Construct validity was shown by predictable relationships between intentions and elements of workers' opportunity structure. The retirement-plans construct can serve as the foundation for a taxonomy of specific retirement plans (e.g., about timing, employment), to organize research on stability and change in retirement intentions, and characterize the path dependence of eventual retirement behavior.
Keywords: Adult children; Demographics; Employment and Labor Force; End of life decisions; Health Conditions and Status; Methodology; Other; Retirement Planning and Satisfaction

The Role of Bridge Jobs in the Retirement Transition: Gender, Race and Ethnicity - Joseph F. Quinn; Kozy, M. (The Gerontologist, 1996)
This paper uses the first wave of HRS data to describe the retirement patterns of the 1990s and to investigate whether these patterns differ by race and ethnicity. Results demonstrate that retirement patterns are varied, even within narrowly defined age groups. Many Americans, probably more in the future, are choosing to retire gradually and are turning to bridge jobs as a transitional stage between a career job and complete labor force withdrawal. There are in fact differences in how people leave the labor force by race and ethnicity, although they do not fall into an obvious pattern. This wave of data shows that Hispanic men are more likely than both white and black men to be on or have last worked on a bridge job. Among women, blacks are least likely to have last worked on a bridge job. Further research on these results is planned for when the future waves of HRS data become available.
Keywords: Employment and Labor Force; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

Stability and Change in Plans for Retirement - David J Ekerdt; Stanley DeViney; Karl Kosloski (University of Michigan, 1996)
Health and Retirement Study panel data make it possible to investigate workers' prior decision making for retirement far in advance of the event. Using a multinomial construct that profiles general types of retirement plans, we found relative persistence of workers' intentions to retire completely, but relative instability of intentions to pursue more complex paths to retirement (e.g., partial retirement, successive jobs). Considering also the continued prevalence of large proportions with vague plans for retirement, these results show a cohort with a common expectation of retirement but quite unsettled as to how and when it will come about.
Keywords: Retirement Planning and Satisfaction

Older Union and Nonunion Workers and their Jobs in the Health and Retirement Survey - Alan L Gustman; Olivia S. Mitchell; Thomas L. Steinmeier (Proceedings: Industrial Relations Research Association, 1995)
This paper compares a variety of factors associated with retirement between those who are covered by a union on their job and those who are not. Despite the well-publicized decline in union coverage and the elimination of opportunities in the union sector, union members approaching retirement age seem to be enjoying the same benefits they would have when unions were stronger. Union membership among this cohort is still 25 for men and almost 20 for women. Results show that these union members have much higher coverage by pensions and health insurance than non-members. These pension plans are likely to be defined benefit plans and therefore are more likely to encourage early retirement, making these holders more likely to expect to retire earlier.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

An Overview of the Health and Retirement Study - Juster, F. Thomas; Richard M. Suzman (Journal of Human Resources, 1995)
This paper examines the scientific, public policy, and organizational background out of which the Health and Retirement Study emerged. It describes the evolution of the major parameters of the survey and the unique planning structure designed to ensure that the substantive insights of the research community were fully reflected in the content of the database, highlights key survey innovations contained in the HRS, and provides a preliminary assessment of the quality of the data as reflected by sample size, sample composition, response rate, and survey content. The paper also describes the several types of administrative data that are expected to be added to the HRS data: earnings and benefits from Social Security files, and health insurance and pension data from the employers of survey respondents.
ProCite field 3 : National Institute on Aging; National Institute on Aging
Keywords: Demographics; Healthcare; Methodology; Retirement Planning and Satisfaction

Retirement Measures in the Health and Retirement Survey - Alan L Gustman; Olivia S. Mitchell; Thomas L. Steinmeier (The Journal of Human Resources, 1995)
The HRS offers researchers the opportunity to explore a vast amount of detailed information that will help to answer outstanding questions about retirement. The survey provides new information, based on better measures than have ever been available before, that could help evaluate current programs and improve future policy design. The following areas of the HRS are praised for providing excellent data that will help researchers answer outstanding questions: labor, economic status, health status, family, and disability plan participation. Unique features such as administrative records on earnings and SS benefits and employer-provided data on pensions and health insurance are also described.
Keywords: Demographics; Retirement Planning and Satisfaction

How Does Pension Coverage Affect Household Saving. Final Report - Sabelhaus, J. (Washington, DC, Urban Institute, 1994)
This paper analyzes the extent to which substitution between pension coverage and household-level saving occurs at the micro level. Data from the beta release of the Health and Retirement Study (HRS) which covered people age 51 to 61 in 1992 is used. The results are mixed. Although there appears to be some substitution between household saving and pension coverage in the top half of the income distribution, the level differences in accumulated wealth seem to fall short of complete offset. Evidence that household wealth accumulation does not vary significantly by type of pension coverage is also found. The paper explores various explanations for why the pension offset is missing or incomplete.
Keywords: Adult children; Consumption and Savings; Employment and Labor Force; Income; Methodology; Pensions; Retirement Planning and Satisfaction

People patterns: Living longer means working a little longer - Otten, Alan L. (Wall Street Journal, 1994)
More than 9,800 men and women in their 50s and 2,800 of their spouses have taken part in a continuing Health and Retirement Study conducted by the University of Michigan's Institute for Social Research on behalf of the National Institute on Aging. One set of questions asked workers just how long they believed they would continue working. Of those who had given the matter some thought, 16% of the men and 18% of the women anticipated retiring fully before age 62; 52% of women and 48% of men assumed they would quit work by 65.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Many in 50s Face Hard Years - Snider, Mike (USA Today, 1993)
Keywords: Retirement Planning and Satisfaction

Prospective Retirement Migration - Myers, George C.; Clara G. Muschkin (University of Michigan, 1993)
Linkages between retirement and residential mobility are examined prospectively, using measures of retirement migration expectations included in the first wave of the Health and Retirement Survey. Variations in individuals' decisions to move at the time of planned retirement are analyzed as a function of current social and demographic characteristics, the accumulation of ties to the community of current residence, and the gradual development of ties to potential place of destination. Place ties, home ownership, and income are found to be the strongest predictors of intentions to move at retirement. These findings confirm the view that decisions regarding retirement migration involve both factors that are distinctive for elderly mobility, as well as those derived from more general models of migration.
Keywords: Demographics; Retirement Planning and Satisfaction

The Subjective Probabilities of Retirement of White, Black, and Hispanic Married Women - Honig, Marjorie (University of Michigan, 1993)
Analyses by race and ethnicity of several important dimensions of labor market behavior have been constrained in the past by limited samples of black and especially of Hispanic populations in nationally representative data sets. This paper uses a partial sample from the new Health and Retirement Survey, and provides the first comparative picture of the current labor force status, accumulated labor force experience, and pension and health insurance coverage of pre-retirement non-Hispanic white, non-Hispanic black, and Hispanic married women, as well as the first insights into the factors influencing retirement decisions of black and Hispanic married women. A model of the subjective probability that married women currently working full-time will continue to work full-time after age 62 is estimated for each population. The analysis focuses on the extent to which married women, in forming retirement expectations, take account of their own economic opportunities as well as factors related to the value of their time to the family. The results provide evidence that important aspects of current compensation such as health and disability insurance, as well as expected deferred compensation in the form of pension and Social Security benefits, are significant determinants of the likelihood of continued work for each of the three populations.
Keywords: Expectations; Retirement Planning and Satisfaction; Women and Minorities